Nitrogen to protein conversion factors for the tropical spiny rock lobster (Panulirus ornatus), tiger prawn (Penaeus monodon), and brine shrimp (Artemia salina) - Adam Yeap; Basseer Codabaccus; David S. Nichols; Chris G. Carter (Aquaculture, 2027)

A stochastic agent-based model for naive CD8+ T cell recirculation dynamics in mice - Nagat Elrefaei; David A. Christian; Thomas A. Adams (Journal of Theoretical Biology, 2026)

One flock, four lactations: A longitudinal study of intramammary infections in meat-sheep production system - David W.I. McBean; Nuno Silva; Kathryn J. Allan; Xinyi Huang; Adam D. Hayward; Keith T. Ballingall (Small Ruminant Research, 2026)

Pronounced drought and wet periods during the Maya Terminal Classic period reconstructed using stalagmite calcium isotopes - Daniel H. James; Harold J. Bradbury; Stacy A. Carolin; Sebastian F.M. Breitenbach; Hai Cheng; Ian J. Orland; Jason H. Curtis; Adam Hartland; Christina Gallup; Ola Kwiecien; Andrew J. Mason; Gideon M. Henderson; et al. (Earth and Planetary Science Letters, 2026)

Targeting cellular senescence mitigates chemotherapy-induced bone loss in young and aged mice - David J. Izquierdo; Enrique Blancarte-Hernandez; Charles A. Schurman; Birgit Schilling; Anna Woloszyk; Leonardo Aguilar; Adam Salmon; Vaida Glatt (GeroScience, 2026)

North American crayfish: A quest for the biggest catch - Caitlin C. Bloomer; Susan B. Adams; Zanethia C. Barnett; Zackary A. Graham; Emmy M. Delekta; David M. Hayes; Zachary J. Loughman; Hugh MacIntosh; M. Worth Pugh; Karen Reed; Nathaniel F. Shoobs; Christopher A. Taylor; et al. (Ecology, 2026)

Geomechanical modeling and slip and dilation tendency analysis track stress evolution during geothermal energy extraction - Kevin J. Smart; David A. Ferrill; Adam J. Cawood (Journal of Structural Geology, 2026)

A search for hydroacoustic signals from bolides - Peter Brown; Luke McFadden; David McCormack; Mareike Adams; Denis Vida (Icarus, 2026)

Insights on the heterogeneity of thermal transfer in the chalk aquifer using fibre-optic distributed temperature sensing - Katerina Kyrkou; Joseph Kelly; Adam Booth; Fleur Loveridge; David Boon; Edward Hough; Lawrence Scott; Matthew Jackson; Adrian Butler; Daniel Perez; Athena Chalari (Geothermics, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Differential response of the copepods Calanus glacialis and Pseudocalanus spp. to recent warming in the Chukchi Sea - Adam H. Spear; David G. Kimmel; Alexei I. Pinchuk; James T. Thorson (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Correction to: Genetic structure in a previously extirpated population of gray wolves following reintroduction and natural recolonization - Heather R. Clendenin; David E. Ausband; Jennifer R. Adams; Paul A. Hohenlohe; Lisette P. Waits (Conservation Genetics, 2026)

Assessing differences among elasmobranch nurseries to aid conservation based on a genomics framework - Dominic G. Swift; Amanda M. Barker; William B. Driggers; Bryan S. Frazier; Douglas H. Adams; James J. Gelsleichter; Dana M. Bethea; Bethany M. Deacy; David S. Portnoy (Conservation Biology, 2026)
Elasmobranch nurseries often differ in environmental conditions, demographics, and use patterns. These differences affect the distribution of genetic variation among nurseries. However, conservation and management strategies often fail to account for such differences because they are difficult to characterize. We assessed differences in connectivity, genetic variation, and numbers of breeders among scalloped hammerheads ( Sphyrna lewini ) sampled in five nurseries in the western North Atlantic Ocean. We used a reduced‐representation genomic approach to genotype 472 young of the year and small juveniles at 8,334 loci containing single‐nucleotide polymorphisms. We inferred full‐ and half‐sibling relationships and used mitochondrial genome haplotypes to differentiate between maternally and paternally related half‐siblings. Among 45 sibling pairs detected, 91% were from the same nurseries and only four pairs were sampled in different nurseries, indicating strong site fidelity. Weak but significant genetic heterogeneity was detected among nurseries based on analysis of molecular variance (0.02% variation, F ST 0.00018, 95% confidence interval 0.00008–0.00028). We quantified standing genetic variation and estimated the contemporary effective population size for each nursery, and although some differences were observed, they were not statistically significant. Our results suggested that female scalloped hammerheads consistently used specific nurseries and that connectivity (via males or females straying between nurseries) facilitated the dispersal of genetic variation, which may enhance population resilience to environmental change. The genomics framework we applied is broadly applicable to conservation‐based assessments of elasmobranch nurseries and essential habitats of other highly mobile species and provides a powerful tool for addressing conservation challenges.

Lessons learned from the “spot the alien” citizen science campaign (2022–2025) in Maltese waters and the second record of Cephalopholis hemistiktos in the Mediterranean - Alan Deidun; Laura Prieto Gomez; Adam Gauci; Audrey Zammit; David Fernando Ramirez Montano; Maria Corsini-Foka; Bruno Zava; Alessio Marrone (Frontiers in Marine Science, 2026)
Introduction Citizen science is increasingly recognised as a valuable approach for monitoring marine non-indigenous species (NIS), range-expanding species (RES), and cryptogenic taxa. This study evaluates the outcomes of the Spot the Alien campaign in Maltese waters between 2022 and 2025. Methods A total of 441 expert-validated records of 30 NIS, RES and cryptogenic species were analysed to assess temporal and spatial reporting patterns, species richness, habitat and observation-method associations, reporting hotspots, and the influence of outreach activities. Results Reporting effort and species richness increased throughout the study, with 2025 yielding the highest number of records. Species accumulation and rarefaction analyses indicated that the campaign documented a substantial proportion of the detectable target fauna. Reporting patterns varied significantly among seasons, habitats, and observer groups, highlighting the influence of both ecological factors and reporting behaviour. The campaign also produced the second Mediterranean record of the Indo-Pacific grouper Cephalopholis hemistiktos. Discussion The Spot the Alien campaign demonstrates that expert-validated citizen science can provide reliable, cost-effective support for the surveillance of marine bioinvasions. The findings highlight the importance of sustained public engagement, rigorous validation, and long-term monitoring to improve early detection and inform future citizen-science initiatives.

Use of edible insect (Rhynchophorus phoenicis) larvae in Chin-chin: effect on nutritional, minerals, antioxidant, antinutrient and sensory properties - Dorcas Olasimbo Owolabi; Kayode Olayele Karigidi; Taiwo Busayomi Adams; Oluwatomiwa David Kolade; Emmanuel Sina AKintimehin (International Journal of Tropical Insect Science, 2026)

Primary hyperparathyroidism and renal secondary hyperparathyroidism in a rabbit (Oryctolagus cuniculus) presenting with a mineralized biliary cyst - Marina Liles; David Sanchez-Migallon Guzman; Adam Moreno; Nicole Mikoni; Peter Delisser; Melissa Chromik; Anna Vincek; Krista Keller (Journal of Exotic Pet Medicine, 2026)

Photoperiod induces sex-specific immune priming in Pyrrhocoris apterus - Adam Bajgar; Gabriela Krejčová; Vlastimil Smýkal; David Doležel (Insect Biochemistry and Molecular Biology, 2026)

What triggered the catastrophic 15 January 2022 Hunga eruption? - Jie Wu; Shane J. Cronin; Marco Brenna; Joali Paredes-Mariño; Sung-Hyun Park; Mila Huebsch; Alessio Pontesilli; Chris Firth; David Adams; Teresa Ubide; Kyle Hamilton; Alice MacDonald; et al. (Earth and Planetary Science Letters, 2026)

A cautionary tale of disequilibria in microlite-melt evolution driven by fast crystallization kinetics: Implications for modeling volcanic processes - Jie Wu; Alessio Pontesilli; Marco Brenna; Shane J. Cronin; Sung-Hyun Park; Joali Paredes-Mariño; Kyle Hamilton; Marta Ribó; David Adams; Mila Huebsch (Earth and Planetary Science Letters, 2026)

The evolution of stone flaking technology at Leang Panninge (South Sulawesi, Indonesia) from the Late Pleistocene to the ‘Toalean’ technocomplex - Suryatman; Akin Duli; David McGahan; Andi Muh. Saiful; Basran Burhan; Ratno Sardi; Zubair Mas’ud; Fardi Ali Syahdar; Muh. Alif; Muhammad Nur; Aisyah Arung Qalam; Iwan Sumantri; et al. (Archaeological and Anthropological Sciences, 2026)

Mineral Stabilization Slows Losses of Peatland Carbon Following Long‐Term Drainage for Agriculture - Katy J. Faulkner; Katerina Georgiou; David A. Coomes; Philippa Ascough; Anna Basford; Rodney G. O. Burton; Romy Copley; Emma Keerberg; Alanie Lapina; Kimber Moreland; Christopher Evans; Ross Morrison; et al. (Global Change Biology, 2026)
Cultivated peatlands are a major CO 2 emission source, but the processes that regulate the decomposition of drained peat are debated, especially as drained peat becomes increasingly shallow. Many cultivated peatlands are underlain by a mineral soil layer. Surface subsidence, oxidation and tillage reduce the peat thickness, which intermixes peat with minerals as peat is lost. A key question is whether this mixing can reduce emissions by making soil organic carbon (SOC) more stable by transforming particulate organic carbon (POC)—which dominates the carbon stock in deep drained peatlands and is readily accessible to microbial decomposers—into mineral‐associated organic carbon (MAOC), which is less accessible to decomposers. To explore this question, we surveyed ten sites across the East Anglian Fens in England, a once extensive (~3900 km 2 ) peatland landscape that has been drained for cultivation since the mid‐seventeenth century. We used variation in cultivation to establish a peat loss gradient to evaluate how topsoil SOC (0–40 cm) and its forms change as peat is lost. As the peat was lost, the soils became rich in minerals (rising from 46% to 88% silt+clay content), resulting in an initial 11‐fold rise in newly‐formed MAOC, but a monotonic decline and near‐total loss of POC. POC turnover times were 3158 ± 62 years, indicative of peat, and POC was always older than MAOC; consequently, microbially‐processed peat along with gradual contributions of recently fixed carbon were sources of MAOC. A four‐month laboratory incubation showed that the MAOC:POC ratio was negatively correlated with respiration. We conclude that long‐term carbon retention via MAOC formation has the potential to reduce carbon loss from degraded, mineral‐mixed peatlands. However, because this MAOC pool is itself vulnerable to loss under continued agricultural drainage, this mechanism is expected to slow rather than halt long‐term soil carbon loss from drained peatlands.

Skeletal muscle microvascular and respiratory responses to exercise in healthy and T2D adults: agreement and reproducibility study of NIRS technologies - Adam A. Luco; Martin Gram; Inge Ramakers; Terence Ryan; Osvaldo Enriquez; James Faulkner; Lee Stoner; David S. Rowlands (European Journal of Applied Physiology, 2026)
Introduction Continuous wave (CW) near-infrared spectroscopy (NIRS) is widely used in skeletal muscle tissue hemodynamic and respiratory research utilizing fixed light scattering assumptions. Purpose Compare reproducibility and technical characteristics of CW-NIRS against frequency-domain (FD)-NIRS, which allows for intra-individual scattering correction. Methods Muscle blood flow (mBF) and oxygen uptake ( $${\text{m}\dot{\text{V}}\text{O}}_{2}$$ ) (using rapid-occlusions), and perfusion were assessed with NIRS in 10 healthy (ND) and 10 type-2 diabetic (T2D) men at rest and during knee extensions at 5% and 15% of maximal voluntary contraction (MVC) on three occasions within 10 days. Results In both groups, exercise responses for mBF and $${\text{m}\dot{\text{V}}\text{O}}_{2}$$ were not substantially different between technology with moderate-high between-day reproducibility (ICC range 0.72–0.98). However, compared to FD-NIRS, CW-NIRS perfusion substantially higher at rest (21 uM; 90%CI 29–13), 5%MVC (18 uM; 27–9) and 15%MVC (17 uM; 26–8) in T2D, but not ND. Standardized typical errors during exercise were small-moderate: e.g., 15%MVC mBF, CW-NIRS (ND 0.45; T2D 0.49), FD-NIRS (0.35; 0.49); mV̇O 2 , CW-NIRS (0.24; 0.26), FD-NIRS (0.45; 0.32); perfusion CW-NIRS (0.25; 0.25) and FD-NIRS (0.25; 0.23); and, not different between groups and technology. Conclusion Both NIRS technologies are reproducible. CW-NIRS assumptions work for muscle blood flow and oxygen use at rest and during exercise. FD-NIRS might be better at detecting changes in perfusion during exercise, especially in older or clinical groups. However, FD-NIRS is more expensive and complex, making it less practical.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Sustainable phosphorus capture with PZsorb: Reducing pollution and enabling circular nutrient management - Mariam Darestani; Bijan P. Markhali; Adam Farahani; Matheus C. Duarte; Atefeh Ahmadbeigi; Deshveen Chandran; Ricky-John Spencer; David E.J. Garman; Pooja Kaur Chaggar; Kazem Javan (Journal of Water Process Engineering, 2026)

Fault and fracture response to Neogene extension in the western Delaware Basin, Texas - David A. Ferrill; Adam J. Cawood; Kevin J. Smart; Daniel J. Lehrmann; Bethany Rysak Bryce; Mark A. Evans; Lisa D. Stockli; Daniel F. Stockli (Journal of Structural Geology, 2026)

CO2 capture by adsorption: Research progress and technology demonstration - Ronny Pini; Camille Petit; David Danaci; Reza Haghpanah; Mauro Luberti; Ana Mafalda Ribeiro; Sai Gokul Subraveti; Adam Ward (International Journal of Greenhouse Gas Control, 2026)

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Direct Versus Indirect Bypass in Early-Stage Moyamoya (Suzuki I-III): A Propensity Score-Weighted Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Victor Gabriel El-Hajj; Michael Rizzuto; Matthews Lan; Pious Patel; Michael Baldassari; Arbaz Momin; Yazan Shamli Oghli; Marissa Tucci; Joseph Schaefer; et al. (Translational Stroke Research, 2026)

Creation and Effectiveness of a HeadSmart-Based Primary Provider Education Tool for Timely Pediatric CNS Tumor Diagnosis - William Daley; Daniel Pacheco; Claire F. Miller; David Walker; Adam L. Green (Journal of Cancer Education, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Advancing soil health with biochar - Effects on soil microbial activity and diversity - Adam El-Aradi; Agnieszka A. Nowak; Tala Kasim; David J. Webb; Daniel J. Nowakowski (Science of The Total Environment, 2026)

PFAS released from the metals recovery process of the lithium-ion battery black mass - Phong H.N. Vo; Christian Vogel; Simon M. Clark; David P. Bishop; Morten Droas; Ewa Partyka-Jankowska; Michael W. Förster; Christian Adam; Vladimir Strezov; Hong T.M. Nguyen (Journal of Hazardous Materials, 2026)

Proximal measurements of microwave reflectance using GNSS-IR track semi-arid grassland vegetation dynamics during greening and browning phases - Charles J. Devine; Russell L. Scott; Joel A. Biederman; Jinyang Du; David J.P. Moore; Andrew F. Feldman; Jessicca S. Guo; David K. Adams; William K. Smith (Agricultural and Forest Meteorology, 2026)

Building trust in the integration of artificial intelligence into chemical risk assessment: findings from the 2024 ECETOC workshop - Timothy W. Gant; Alistair Boxall; Daniel Burgwinkel; Maryam Zare Jeddi; Ivo Djidrovski; Steffi Friedrichs; Barry Hardy; Thomas Hartung; Daniela Holland; Andreas Karwath; Anne Kienhuis; Nicole Kleinstreuer; et al. (Archives of Toxicology, 2026)
Artificial Intelligence (AI) is increasingly influencing chemical risk assessment, enabling faster, more comprehensive, and potentially more ethical assessments. The application of AI in chemical risk assessment refers to both generative and predictive algorithms encompassing machine learning, to analyse complex chemical, biological, and environmental data and provide insights into adverse effect potential for humans and ecosystems. AI systems support the prediction of chemical hazards, exposure levels, and adverse effects by learning from experimental results, mechanistic models, and regulatory datasets, thereby enhancing the efficiency of safety evaluations. In October 2024, ECETOC held an international workshop, with experts from academia, industry, and regulatory bodies, to reflect upon the historical challenges in integrating multidimensional omics technologies into chemical regulation and explore the current capabilities and future potential of AI in toxicology and regulatory science. Discussions emphasised that implementation of Findable, Accessible, Interoperable, and Reusable (FAIR) data principles is not just a best practice but rather a prerequisite for building transparent, reliable, and unbiased AI systems. The reliability of AI in producing scientifically valid and socially responsible outcomes depends fundamentally on the availability of FAIR data. However, ensuring trustworthiness also requires robust governance frameworks that go beyond data and human oversight. Critical enablers of responsible AI in chemical risk assessment are rigorous governance, explainability, fit-for-purpose applications, and human oversight. ECETOC supports the development of flexible and iterative frameworks advancing development, validation, transparency, accountability, and trust in AI applications in chemicals regulation.

Bridging the Energy Balance Gap in Eddy‐Covariance Measurements: Insights From Standardized Network Data - Giacomo Nicolini; David Durden; Luca Di Fiore; Christopher Florian; Simone Sabbatini; Bert Gielen; Arne Iserbyt; Benjamin Loubet; Ivan Mammarella; Adriana Mariotti; Maarten Op de Beeck; Caleb Slemmons; et al. (Global Change Biology, 2026)
The lack of energy balance closure in Eddy‐Covariance (EC) measurements is a well‐known, still unresolved challenge in micrometeorology, with energy balance closure (EBC) rates typically ranging between 60% and 80%. While numerous hypotheses have been proposed to explain this imbalance, the relative contributions of neglected energy storage terms, data quality and flux processing options remain insufficiently disentangled. Using standardized ICOS and NEON datasets, we show that a significant portion of the observed energy imbalance can be attributed to overlooked or inconsistently handled energy components and turbulent flux quality control. Using data drawn from 84 sites, we show that comprehensive energy accounting—including soil heat flux, storage terms (soil, air, biomass), photosynthetic energy demand, and strict quality filtering of turbulent fluxes—improved EBC by 16% on average, with site‐specific gains up to 40%. However, we also identify a persistent residual imbalance that is unlikely to be resolved through methodological refinements or additional measurements alone, pointing to fundamental physical processes that are not accounted for in the standard measurement and processing. We argue that this unresolved imbalance should be explicitly acknowledged and bounded, rather than implicitly absorbed into correction schemes, and we outline practical guidance for diagnosing and interpreting EBC in standardized flux networks. This perspective evaluates methodological advances and residual uncertainties, providing an actionable framework for the appropriate use of EC energy fluxes in carbon, water, and climate research.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Associations Between Mothers’ and Fathers’ Food Skills and Children’s Diet Quality - Amar Laila; Maude Perreault; Adam Sadowski; Scott Maitland; David W.L. Ma; Jess Haines (Journal of Nutrition Education and Behavior, 2026)

Bridging gaps in agro-ecosystem integration: a multi-level modelling study in semi-arid Burkina Faso - Gildas G.C. Assogba; David Berre; Myriam Adam; Etienne Delay; Erika Speelman; Katrien Descheemaeker (Ecological Modelling, 2026)

Shell trace elemental fingerprints of the deep-sea methane seep mussel Gigantidas childressi vary by depth, site, and shell growth region - Ian J. Grace; Luciana Génio; David B. Eggleston; Brandon J. Puckett; F. Joel Fodrie; Adam N.H. Smith; Craig M. Young (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Cerebrolysin after Endovascular Thrombectomy in Stroke: 12‑Month Functional Outcomes in a Propensity‑Matched Cohort - Jacek Staszewski; Aleksander Dębiec; Katarzyna Gniadek-Olejniczak; Adam Stępień; Renata Piusinska-Macoch; Stefan Strilciuc; David Balo; George Harston; Krzysztof Brzozowski; Piotr Zięcina; Jerzy Narloch; Marek Wierzbicki; et al. (Translational Stroke Research, 2026)

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

Genetic structure in a previously extirpated population of gray wolves following reintroduction and natural recolonization - Heather R. Clendenin; David E. Ausband; Jennifer R. Adams; Paul A. Hohenlohe; Lisette P. Waits (Conservation Genetics, 2026)
Genetic structuring in wildlife populations is driven by barriers that restrict gene flow as well as the history of population demography. Mechanisms driving genetic structuring can be nuanced in group-living species, such as gray wolves ( Canis lupus ). Behavioral factors, such as social affiliation and resistance, natal habitat imprinting, and trade-offs between dispersal from natal packs and territorial biding, affect habitat selection of wolves despite landscape barriers providing little resistance to their extensive dispersal capabilities. Wolves were previously extirpated from Idaho, USA, and current populations are the result of both reintroductions in 1995 and 1996 and natural dispersal from Canada. In this context we examined genetic structure of wolves in Idaho using 101 individuals genotyped at 18 nuclear DNA microsatellite loci and a subset of 38 individuals genotyped at 1019 single nucleotide polymorphism markers. We hypothesized panmictic (i.e., random mating) genetic structure in Idaho due to the long-distance dispersal abilities of gray wolves. Contrary to our hypothesis, we found three genetic clusters of gray wolves in Idaho, primarily supported by SNP markers. Microsatellite data suggested similar patterns, but permutation tests indicated these differences were not statistically significant. The extent of differentiation and evidence of gene flow, however, suggests that the three genetic clusters are not wholly isolated from one another. The distinctions between clusters spatially align with areas of reintroduction into central Idaho and Yellowstone National Park, as well ongoing natural recolonization from adjacent populations in Canada and Montana. Wolves at the periphery of analysis areas showed more admixture than those in the core, consistent with territoriality and mating behaviors contributing to genetic structuring. We demonstrate how management history, including reintroduction efforts, and animal behavior may interact and contribute to patterns of genetic structure in wild populations.

HUTG: a next-generation IGS real‑time combined GIM via two‑step global and regional correction with robust weighting from HENU and UPC‑IonSAT - Kualong Xu; Qi Liu; Manuel Hernández-Pajares; Enric Monte-Moreno; Heng Yang; Germán Olivares-Pulido; David Roma-Dollase; Alberto García-Rigo; Ningbo Wang; Zishen Li; Ang Liu; Clément Ubelmann; et al. (GPS Solutions, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Multiple Mechanisms Required to Predict Grass Community Composition - Jane A. Catford; Laura J. Graham; Harry E. R. Shepherd; Cindy E. Hauser; Nicola T. Munro; Brendan A. Wintle; John G. Donohue; David Tilman; Adam T. Clark (Ecology Letters, 2026)
Accurate prediction of community assembly is a central goal in ecology but is challenging because assembly is governed by numerous mechanisms. Few theoretical models explicitly incorporate or test multiple mechanisms at once. We empirically tested the predictive performance of a plant community assembly model built using all possible combinations of four ‘mechanisms’ (soil resource competition, dispersal and colonisation, spatiotemporal niche differentiation, population growth rates) and 11 underlying ‘attributes’ based on measured traits (e.g., fecundity, phenology). The full model accurately predicted out‐of‐sample biomass observations of five grasses sown in mixture along a soil nitrogen gradient (overall R 2 = 0.65). Alternative model variants, parameterised using subsets of the mechanisms and their nested attributes, still retained high explanatory power if the model included at least three of the four mechanisms. Our results suggest that plant community composition is determined by simultaneous effects of multiple mechanisms, and simpler theories have much lower predictive abilities.

Astaxanthin, meclizine, mitoglitazone, pioglitazone, alpha-ketoglutarate, mifepristone, methotrexate, and atorvastatin-telmisartan do not increase lifespan in UM-HET3 mice - Ron Korstanje; Randy Strong; Adam B. Salmon; Molly A. Bogue; Sean P. Curran; Vivian Diaz; Elizabeth Fernandez; Brett Ginsburg; Melissa Han; David E. Harrison; Catherine Kaczorowski; Matt Kaeberlein; et al. (GeroScience, 2026)

High-resolution surface and rootzone soil moisture over US cropland: A novel framework assimilating multi-source remote sensing data, machine learning, and the Layered Green and Ampt Infiltration with Redistribution model - Shuohao Cai; Yijia Xu; Zhengwei Yang; Wade T. Crow; Zhou Zhang; Jiali Shang; Jiangui Liu; Peter La Follette; Chris Reberg-Horton; Harry Schomberg; Steven Mirsky; Brian Davis; et al. (Remote Sensing of Environment, 2026)

Proof-of-concept and model validation of chemical looping reforming of glycerol at relevant conditions - Adam Zaidi; Christopher de Leeuwe; Claudia Navarro; Eimear McCann; Andrew David Wright; Gemma Grasa; Vincenzo Spallina (Fuel, 2026)

Performance evaluation and methods comparison of transcriptomic-based approaches for the characterization of wastewater treatment effluent - Adam D. Biales; Morgan S. Hu; David C. Bencic; Mary Jean See; Susan T. Glassmeyer; Edward T. Furlong; Julia M. Stelman; Weichun Huang; Dana W. Kolpin; Marc A. Mills; Laura D. Brunelle; Angela L. Batt; et al. (Environmental Pollution, 2026)

Two-stage process and strain engineering for continuous bioconversion of CO2 to butanol - Hye-Jin Jo; Hee-Jeong Cha; Jinhyun Kim; Jeremy David Adams; Peidong Yang; Douglas S. Clark (Bioresource Technology, 2026)

Algal biogenic synthesis of SiO2–CaO–P2O5 system bioactive glass using Cyclotella meneghiniana and waste fish bone - Enobong R. Essien; Victor A. Ajisafe; David A. Faluyi; Ngozi A. Adeleye; Violette N. Atasie; Taofikat Abosede Adesalu; Luqman A. Adams; Matthew Julius (Algal Research, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

A Proposed Novel Neurovascular Mechanism for Brain Network Dysfunction After Traumatic Injury - Taotao Wu; Jared A. Rifkin; Adam C. Rayfield; Keith A. Kroma-Wiley; Dani S. Bassett; David F. Meaney (Annals of Biomedical Engineering, 2026)
Current research in predicting traumatic brain injury risk focuses on the relationship between head impacts and the likelihood of white matter damage, often overlooking the role of neurovascular coupling in the injury response. To fill this gap, we combined biomechanical and neurodynamic principles to simulate alterations to large-scale resting-state brain activity following head impacts. We simulated cortical neural activity with a network of Kuramoto phase oscillators, using structural connectivity to define coupling and a vascular-informed local resource term to capture neurovascular coupling. By combining the neurodynamic model with a brain mechanics model, we investigated two mechanistic pathways of network dysfunction: (1) white matter damage, reflected in degrading network edges, and (2) local tissue oxygenation decline, reflected in adjusting the resource term at each network node. We simulated 53 real-world head impacts using a vasculature template to evaluate the changes in simulated functional connectivity (FC) and neural dynamics relative to injury outcomes (concussion vs. no concussion). To assess vascular variability, simulations were repeated across 41 individual vasculature maps. Our results show simulated FC changes (measured by Pearson’s correlation) consistently correlated well with injury outcomes, regardless of injury mechanism (AUC = 0.89 and 0.90), However, the two injury models yielded distinct FC patterns as indicated by graph metrics. Vascular variability substantially influenced how injury affected FC, with some brains exhibiting resilience to synchrony disruption depending on their vascular structure. These findings offer testable insight into the neurovascular mechanism of brain dysfunction after TBI and have important implications for individualized protection and treatment.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Explainable AI reveals temporal risk pathways in fall prediction: Extracting clinical insights from multi-horizon machine learning models - Masoud Khani; David R. Friedland; Michael Widlansky; Michael S. Harris; Jazzmyne Adams; Lei Fan; Hyunkyoung Oh; Qiang Lu; Jake Luo (GeroScience, 2026)
Falls are a leading cause of injury in older adults, making risk prediction a clinical priority. While many machine learning (ML) models exist, they typically provide a static assessment, predicting risk for a single, fixed timeframe. This approach overlooks how the clinical drivers of risk evolve over time, failing to distinguish between acute factors that signal an imminent fall and chronic conditions that confer long-term vulnerability. This study uses an explainable ML framework across multiple time horizons to unlock deeper clinical insights into the temporal nature of fall risk. We conducted a retrospective, matched case-control study using electronic health record (EHR) data from 99,078 patients who fell and 99,078 matched controls. Seven ML models were trained to predict fall risk across seven distinct prediction windows (3, 6, 12, 24, 36, 48, and 60 months). The best-performing model for each horizon, consistently XGBoost, was interpreted using SHAP (SHapley Additive exPlanations) to identify how the importance of clinical and demographic predictors changed over time. A clear performance trade-off emerged across time horizons. Short-term models (3–12 months) delivered balanced discrimination (best model XGBoost, AUC ≈ 0.75), while long-term models became progressively better at identifying eventual fallers (recall ≈ 80% at 60 months) at the cost of lower specificity (≈ 46%). SHAP analysis revealed distinct temporal patterns: short-term risk was driven by acute conditions like syncope, respiratory symptoms, and urinary tract infections, while long-term risk was predicted by chronic, cumulative factors such as spondylopathies, nutritional deficiencies, and benign neoplasms. Three primary risk trajectories (increasing, steady, and decreasing) were identified, each corresponding to distinct underlying clinical profiles. Fall risk is a dynamic process, not a static state. By analyzing risk across multiple timeframes, we can distinguish between acute triggers requiring immediate intervention and chronic vulnerabilities demanding long-term management. This multi-horizon framework provides a data-driven foundation for a new paradigm in fall prevention: moving beyond generic “high-risk” labels to personalized, temporally aware strategies that align the type and timing of interventions with the specific nature of a patient’s evolving risk.

Sustainable agriculture creates management trade-offs, not conflicts, between crop productivity and soil carbon storage goals - David G. Encarnation; Robert S. Powell; Pete Smith; Adam F.A. Pellegrini (Science of The Total Environment, 2026)

Outcomes of Bypass Surgery in Patients with Moyamoya Syndrome Secondary To Sickle Cell Disease: a Multicenter Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Celine Yacoub; Nimer Adeeb; Antony A. Fuleihan; Sravanthi Koduri; Michael Baldassari; Matthews Lan; Pious Patel; Arbaz A. Momin; Elias Atallah; et al. (Translational Stroke Research, 2026)

Angler Heterogeneity in Newfoundland and Labrador, Canada: Insights From Nearly Three Decades (1994–2022) of Atlantic Salmon Angler License and Activity Records - Travis E. Van Leeuwen; Michelle G. Fitzsimmons; J. Brian Dempson; Christopher W. White; Mark Young; Donald Keefe; Isabelle Schmelzer; Nicholas I. Kelly; Craig F. Purchase; Blair Adams; David Coté (Fisheries Management and Ecology, 2026)
Angler demographics and motivations are an important consideration to successful fisheries management. We examined 29 years of angler license and activity records from the recreational Atlantic salmon fishery in Newfoundland and Labrador, Canada to: (1) provide a contemporary evaluation of angler demographic trends; (2) evaluate age and regional differences between anglers who prioritized retention versus catch‐and‐release; and (3) discuss how various management and COVID restrictions affected angler participation and activity. Resident license holders made up 91.3% of total licenses purchased. The average age of license holders increased from 39 years of age in 1994 to 54 years of age in 2022, with 6–20 year olds making up

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Identifying and quantifying greenhouse gas emissions with the AVIRIS-3 airborne imaging spectrometer - Red Willow Coleman; Andrew K. Thorpe; Philip G. Brodrick; Adam Chlus; Jay E. Fahlen; Brian Bue; John Chapman; Regina F. Eckert; Daniel J. Jensen; Michael L. Eastwood; David R. Thompson; Clayton D. Elder; et al. (Remote Sensing of Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Open-Coast Eelgrass (Zostera marina) Transplant Catalyzes Rapid Mirroring of Structure and Function of Extant Eelgrasses - Rilee D. Sanders; Adam K. Obaza; David W. Ginsburg; Olivia C. Carmack; Benjamin C. Grime; Heather Burdick; Tom K. Ford; James J. Leichter (Estuaries and Coasts, 2026)
Seagrasses are marine angiosperms that function as ecosystem engineers, forming complex structure that enhance nearshore environments. Globally, seagrass habitats are threatened by intensifying impacts from climate change, which exacerbate non-climatic stressors such as coastal development, invasive species, and overfishing. Advances in the methodological efficacy of active seagrass restoration efforts have sought to mitigate substantial anthropogenic-induced losses. Restoration efforts along the U.S. West Coast have primarily focused on Zostera marina (common eelgrass) in shallow, sheltered estuarine environments, where most coastal development occurs. However, within the Southern California Bight, Zostera spp. also occurs along the exposed coastlines of the California Channel Islands archipelago. Despite their unique location and the ecosystem services they provide, a paucity of information persists on open-coast seagrass systems and restoration efforts. In this study, we conducted a novel transplant of Z. marina on Catalina Island and tracked temporal and spatial performance metrics (i.e., areal coverage, morphometrics, and fish assemblages) at the restoration site and seven extant Z. marina reference beds on the island from 2021 to 2024. The transplant activities successfully established over 0.18 hectares of Z. marina habitat. The transplant site paralleled or exceeded extant reference beds morphometrically (shoot density and blade length) and functionally (fish composition and fish diversity), while concomitantly providing habitat for the occupancy of, and utilization by, federally listed endangered and managed species. Our results provide a model for broadening the scope of, and augmenting strategies for, seagrass habitat recovery beyond conventional restoration spaces by underscoring the role of open-coast seagrasses in enhancing nearshore ecosystem function and resilience.

An investigation of corrective approaches for uncertain winds and analysis of impacts on smoke model performance - Zongrun Li; Susan M. O’Neill; Rime El Asmar; Yongtao Hu; Adam K. Kochanski; Angel Farguell; Jan Mandel; David J. Tanner; L. Gregory Huey; Armistead G. Russell; Rodney J. Weber; M. Talat Odman (Agricultural and Forest Meteorology, 2026)

Late pregnancy is associated with an increase in regulatory cytokines and a decline in nematode-specific antibody levels in sheep infected with Teladorsagia circumcincta - Adam D. Hayward; Andrew W. Greer; David Frew; Margaret Oliver; Alison A. Morrison; Yvonne Bartley; Yolanda Corripio-Miyar; David J. Bartley; Fiona Kenyon; Mara Rocchi; Alasdair J. Nisbet; Tom N. McNeilly (Veterinary Parasitology, 2025)

Benchmarking CO₂ storage simulations: Results from the 11th Society of Petroleum Engineers Comparative Solution Project - Jan M. Nordbotten; Martin A. Fernø; Bernd Flemisch; Anthony R. Kovscek; Knut-Andreas Lie; Jakub W. Both; Olav Møyner; Tor Harald Sandve; Etienne Ahusborde; Sebastian Bauer; Zhangxing Chen; Holger Class; et al. (International Journal of Greenhouse Gas Control, 2025)

Tectonic modulation of caldera volcanism on the South Aegean Volcanic Arc - Abigail Metcalfe; Tim Druitt; Katharina Pank; Steffen Kutterolf; Jonas Preine; Sarah Beethe; Axel Schmitt; Christian Hübscher; Paraskevi Nomikou; Thomas A. Ronge; Carole Berthod; Hehe Chen; et al. (Earth and Planetary Science Letters, 2025)

Linearized quantum lattice-Boltzmann method for the advection-diffusion equation using dynamic circuits - David Wawrzyniak; Josef Winter; Steffen Schmidt; Thomas Indinger; Christian F. Janßen; Uwe Schramm; Nikolaus A. Adams (Computer Physics Communications, 2025)

First record of acid sulfate soils in a southern African Ramsar estuarine lake - Janine B. Adams; Julia Penaluna; Chuene P. Lakane; Taryn Riddin; Gavin M. Rishworth; David Turner; Lara Van Niekerk; Daniel A. Lemley (Wetlands Ecology and Management, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

Efficacy of Cerebrolysin Treatment as an Add-On Therapy to Mechanical Thrombectomy in Patients with Acute Ischemic Stroke Due to Large Vessel Occlusion in Anterior Circulation: Results of a 3-Month Follow-up of a Prospective, Open Label, Single-Center Study - Jacek Staszewski; Aleksander Dębiec; Stefan Strilciuc; Katarzyna Gniadek-Olejniczak; Renata Piusinska-Macoch; David Balo; George Harston; Adam Stępień; Krzysztof Brzozowski; Piotr Zięcina; Jerzy Narloch; Marek Wierzbicki; et al. (Translational Stroke Research, 2025)

Comprehensive quantification of production costs for large-scale kelp aquaculture and cost reduction opportunities - Zachary Moscicki; Adam T. St. Gelais; Struan Coleman; Alexander Kinley; Tobias Dewhurst; Scott Lindell; David W. Fredriksson; Damian C. Brady (Algal Research, 2025)

Assessing recovery and conservation of Australian freshwater fishes with the IUCN Green Status of Species and structured expert elicitation - Maiko L. Lutz; David G. Chapple; Molly K. Grace; Luciano B. Beheregaray; Chris J. Brauer; Iain Ellis; Adam Kerezsy; John D. Koehn; Mark Lintermans; Jarod P. Lyon; Matthew McLellan; Luke Pearce; et al. (Conservation Biology, 2025)
The International Union for Conservation of Nature (IUCN) Green Status of Species (GSS), introduced in 2021, is a global standard of measurement used to assess the level to which a species has recovered (i.e., is viable and providing its ecological function across its entire range). It is also used to evaluate how a species has responded to past conservation actions and the expected conservation gains and recovery potential it would receive in the short‐ and long‐term future. Preliminary application of the GSS method has relied on expert knowledge from individuals or small groups of specialists. However, more accurate and reliable results are likely to be produced by formally eliciting individual judgments from a diverse range of experts, followed by discussion, reevaluation, and synthesis of these judgments. We developed a method in which 2 structured expert elicitation workshops are used to conduct GSS assessments and applied this method to 8 Australian freshwater fish species from the Murray–Darling Basin. We integrated the investigate, discuss, evaluate, aggregate protocol into the GSS methods; experts assessed the species’ IUCN Green Score (percent recovery) in the current state and for 5 other scenarios in the past and future with and without conservation. Four GSS conservation impact metrics were calculated based on the averages of expert judgments. Experts forecasted that impact in the short‐term would be minimal (i.e., conservation gain metric = zero or low) for 5 of the 8 species because targeted and maintained conservation actions are often lacking. In contrast, experts indicated long‐term recovery potential would be considerably higher if implementation of appropriate recovery activities could be sustained (all 8 species had medium or high recovery potential). We concluded that the GSS is well suited to a modified workshop approach because it aims to reduce biases associated with expert judgments and encourages valuable knowledge sharing among experts.

Spatial and Temporal Variation in Wave Overtopping Across a Coastal Structure Based on One Year of Field Observations - Jennifer Brown; Gerd Masselink; Margaret Yelland; Christopher Stokes; Timothy Poate; Robin Pascal; David Jones; John Walk; Christopher Cardwell; Barry Martin; Peter Ganderton; Julie Gregory; et al. (Journal of Marine Science and Engineering, 2025)
Coastal managers worldwide must prepare for changes in annual wave overtopping events due to climate change and sea-level rise. Research often assesses overtopping discharges by extreme events at a sea wall crest, typically using data from physical models or empirical rules based on scaled experiments. Here, we analyse a unique 1-year field dataset of coastal wave overtopping, from SW England, to determine the number of individual waves, regardless of their size, overtopping two locations across a coastal structure. The coastal conditions causing the most frequent overtopping differ from those driving it landward, complicating hazard communications for multiuse infrastructure. These data are the first field observations covering a year of tide, wave and wind conditions that cause overtopping of a vertical sea wall. Storms have a minimal (

Correction: Positive and negative impacts of electrical infrastructure on animal biodiversity: A systematic review - Adam J. Bennett; David M. Watson; Maggie J. Watson (Oecologia, 2025)

Understanding and predicting the geographic distributions of phlebotomine sand flies in and around Europe - Danyang Wang; Anouschka R. Hof; Kevin D. Matson; Frank van Langevelde; Vít Dvořák; Ognyan Mikov; Ivelina Katerinova; Simona Tchakarova; Maria Antoniou; Jorian Prudhomme; Denis Sereno; Baptiste Vergnes; et al. (Climatic Change, 2025)
Climate and land-use changes influence the transmission of vector-borne diseases by affecting the distribution and survival of disease vectors. Numerous diseases are transmitted by phlebotomine sand flies (Diptera: Psychodidae: Phlebotominae), including leishmaniasis. Several major sand fly-borne diseases are responsible for high global disease burdens and high socio-economic costs. In Europe, over 20 known sand fly vector species are largely confined to the Mediterranean Basin, yet records of sand fly presence further north increase. Global warming is predicted to drive the spread of sand flies to large areas of Europe in the 21th century, an effect likely to be exacerbated by anthropogenic factors. However, the constraints to the geographic distributions of sand flies are not well understood. This study aims to increase the understanding of the drivers of the geographic distributions of sand flies, using species distribution modelling to systematically test links between sand fly occurrences and climatic, land-use, lithological, biodiversity and human population variables in Europe and adjacent Mediterranean regions. We found that moisture is the most important environmental variable both in explaining and in predicting sand fly occurrences. The projected suitable habitats are larger than the current known sand fly distributions, and these habitats are expected to expand due to changes in climate and land-use.

The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

Extreme Heatwave Causes Immediate, Widespread Mortality of Forest Canopy Foliage, Highlighting Modes of Forest Sensitivity to Extreme Heat - Adam Sibley; Christopher Still; Matthew Gregory; Constance Harrington; David Shaw; Nina Ferrari; Alex Dye; Mark Schulze; Glenn Howe; David E. Rupp; Christopher Daly; Daniel DePinte; et al. (Global Change Biology, 2025)
In late June 2021, multiple days of record‐breaking heat caused an unprecedented amount of foliage death in the forests of the Pacific Northwest, USA. Portions of tree canopies with healthy green foliage prior to the heat changed to red or orange shortly after the event. The change in foliage color could be readily seen in satellite imagery and was corroborated as foliar death (heat scorch) by aerial surveys and extensive observations on the ground. To better understand the patterns and processes driving foliar death, we used satellite imagery to identify 293,546 ha of forest, or ~4.7% of forest area, that were damaged in western Oregon and Washington by this extreme heat event. Analysis of underlying drivers of the observed heat damage indicated greater sensitivity was related to abiotic factors such as sun exposure, aspect, and microclimate, as well as biotic factors like tree species and stand age, budburst phenology, and foliar pathogens impacting tree health. Iconic, culturally and economically significant species like western redcedar, western hemlock, and Sitka spruce were disproportionately sensitive to heat damage, including in old‐growth stands where they are canopy dominants. These findings highlight the multifaceted challenges posed to forests by extreme heat waves, and the need to better understand their impact on forest ecosystems in a rapidly warming climate.

Publisher Correction: On-field Head Acceleration Exposure Measurement Using Instrumented Mouthguards: Missing Data Imputation for Complete Exposure Analysis - David Luke; Zaryan Masood; Daniel Bondi; Chaokai Zhang; Rebecca Kenny; Adam Clansey; Paul van Donkelaar; Alexander Rauscher; Songbai Ji; Lyndia Wu (Annals of Biomedical Engineering, 2025)

One for all and all for one health: Harmonizing SARS-CoV-2 wastewater surveillance results across a laboratory network - Alex H.S. Chik; Christopher Adam; Jane J.Y. Ho; Taylor Aris; Eric J. Arts; R. Stephen Brown; David Bulir; Ryland Corchis-Scott; Christopher T. DeGroot; Robert Delatolla; Philip Dennis; Hadi A. Dhiyebi; et al. (Science of The Total Environment, 2025)

Fault zone deformation and fracture intensity in chalk-dominated carbonates - David A. Ferrill; Adam J. Cawood; Kevin J. Smart; Daniel J. Lehrmann; Mark A. Evans; Lisa D. Stockli; Daniel F. Stockli (Journal of Structural Geology, 2025)

Indirect effects of soil amendments on plant traits and the microbiome in post-wildfire forest recovery - David M. Barnard; Adam L. Mahood; Jacob A. Macdonald; Kaela K. Amundson; Timothy S. Fegel; Sean M. Gleason; Madeline Guimond; Sophie Kaiser; Kya Sparks; Michael J. Wilkins; Charles C. Rhoades (Forest Ecology and Management, 2025)

Forest restoration treatments increase native plant diversity but open the door to invasion in the Colorado Front Range - Adam L. Mahood; Camille S. Stevens-Rumann; Allison E. Rhea; Scott M. Ritter; Kevin Barrett; Paula J. Fornwalt; David M. Barnard (Forest Ecology and Management, 2025)

Experimental study on response of axially loaded steel and steel-concrete composite columns to blast loading - Marek Foglar; Vojtěch Šulc; Radek Hájek; David Čítek; Adam Čítek; Jiří Kolísko; Jiří Pachman (Engineering Structures, 2025)

Non-native grass invasion drives biodiversity loss after a single fire in a semi-arid shrubland - Adam L. Mahood; Jennifer K. Balch; David M. Barnard; Katherine N. Suding; Jeanne C. Chambers (Biological Conservation, 2025)

Mesophotic protected habitats as refugia for the most at-risk elasmobranch species - Franck Pichot; Stéphanie Manel; Laure Velez; Jean-Baptiste Juhel; Laurent Ballesta; Pierre Boissery; Morgane Bruno; Maddy Cancemi; Florian Holon; Jean-Jacques Riutort; Marieke Schultz; Nicolas Tomasi; et al. (Biological Conservation, 2025)

The Impact of Postprocedural Anticoagulant Use in Patients Undergoing Woven EndoBridge: A Multicenter Propensity Score-Matched Study - Basel Musmar; Hamza Adel Salim; Joanna M. Roy; Nimer Adeeb; Antony A. Fuleihan; Elias Atallah; Saman Sizdahkhani; Sravanthi Koduri; Spyridon Karadimas; Bachar El Baba; Brian M. Howard; Jonathan A. Grossberg; et al. (Translational Stroke Research, 2025)

Analysis of a Novel Human Protein, ORF3, Encoded by Spacer rDNA - Yaohui Chen; Jung-Hyun Kim; Hee-Sheung Lee; Sergey Koren; Vladimir Larionov; Adam M. Phillippy; David Schlessinger; Ramaiah Nagaraja (Journal of Molecular Evolution, 2025)
An open reading frame in the intergenic spacer of human ribosomal (r)DNA codes for a 190 amino acid, 22 kDa protein that we have named ORF3. It comprises a 5’AluSx repeat sequence encoding 96 amino acids followed by a stretch of 94 amino acids containing a unique repeated stretch of 5 hydrophobic residues. Full copies of ORF3 have been isolated as transformation-associated recombination clones from mouse:human hybrid cell lines containing human chromosomes 21 or 22. In initial instances where the chromosome complement of rDNA repeats is fully resolved in whole genomes, in CHM13 cells, complete copies of ORF3 are mainly concentrated in a tandem cluster on chromosome 21, while other chromosomes contain 1 or 2 full copies, with the sequence in other rDNA repeats interrupted by a frameshift mutation. A diploid cell complement (HG002) again has both complete open reading frames (ORFs) and other copies with the frameshift or deletions. In searches among non-human primate sequences to assess the evolutionary history of ORF3, a > 93% conserved copy of the full sequence of the ORF, as well as copies with in-frame deletions, was found in bonobo, but only fragments homologous to the ORF were seen in chimpanzee, orangutan, and gorilla rDNA examined thus far. ORF3 was expressed as a V5-tagged chimeric protein in human kidney epithelial HEK293 cells, and both ORF3-V5 and endogenous ORF3 were detected with a newly generated antibody. The protein is found in both cytoplasm and nucleus. However, upon treatment of cells with RNase A, the protein is excluded from the nucleus, suggesting that it is in complexes with RNA. Although any function is currently unknown, the ORF3 protein is upregulated, speculatively associated with changes in chromatin, in viral-transformed HEK293 cells and in human diploid fibroblast cells rendered senescent by treatment with etoposide, ionizing radiation, or an oxidant (H 2 O 2 ).

A global meta‐analysis of ecological functions and regulating ecosystem services of freshwater bivalves - Alexandra Zieritz; Joshua I. Brian; Ronaldo Sousa; David C. Aldridge; Carla L. Atkinson; Karel Douda; Caryn Vaughn; Yulia Bespalaya; Tabitha Richmond; Adam M. Ćmiel; Alma Crisp; Andreas H. Dobler; et al. (Limnology and Oceanography, 2025)
Freshwater bivalves are globally distributed, diverse, and common in benthic communities. Many taxa, particularly in the most species‐rich order, Unionida, are declining due to anthropogenic stressors, while a small number of non‐native species have become increasingly abundant and widespread, commonly replacing native bivalve assemblages. To understand how these global changes may impact ecosystems and people, we conducted a meta‐analysis of existing literature quantifying the ecological functions (= supporting or intermediate ecosystem services) and regulating ecosystem services of freshwater bivalves (hereafter “ecosystem services”). Random effects meta‐analysis modeling across 447 case studies revealed a positive effect on human health, safety, or comfort of freshwater bivalve ecosystem services overall and specifically, via effects on native macrofauna, microorganisms, wastes, and pollutants, and the physico‐chemical condition or quantity of sediments. Generally, effects of native species and species within the orders Unionida and Venerida were more significant and positive than those of other freshwater bivalves. No significant overall effect was found for ecosystem services related to zooplankton, algae, invasive species, and the physico‐chemical condition of ambient water. Moreover, a significant bias toward publication of positive results existed for studies quantifying ecosystem services related to algae. These findings illustrate the global importance of the ecosystem services of freshwater bivalves and highlight the need for large‐scale conservation and restoration efforts for their species and populations globally, including those of common species. Our findings also question common assumptions of strong and ubiquitous effects of freshwater bivalves on algae and water condition, cautioning against extrapolating observations across systems.

Viral Nervous Necrosis due to Betanodavirus: A Case Study in Pot‐Bellied Seahorses ( Hippocampus abdominals ) - Stephen M. Pefanis; Graeme Knowles; Peter G. Mohr; Kate Swift; Jemma Bergfeld; Teresa K. Wilson; Marianne Douglas; Rachelle Hawkins; John Hoad; Adam Costin; Jacqueline Morris; David Cummins; et al. (Journal of Fish Diseases, 2025)
Betanodaviruses, members of the Nodaviridae family, are the causative agents of viral nervous necrosis in fish, resulting in great economic losses worldwide. This is the first case study describing the detection and confirmation of viral nervous necrosis in pot‐bellied seahorses ( Hippocampus abdominalis ) in Australia. Clinical signs of this infection in the seahorses included whirling, floating and cessation of feeding. Histopathological findings included prominent vacuolation in the grey matter of the brain and in the retina of the eye. Betanodavirus infection was initially detected by betanodavirus reverse transcriptase quantitative PCR and nested PCR. Sequencing confirmed the red‐spotted grouper nervous necrosis virus (RGNNV) genotype of betanodavirus. The RGNNV genotype of betanodavirus has previously been detected in Australia in fish, including barramundi ( Lates calcarifer ) and striped trumpeter ( Latris lineata ). Immunohistochemistry using antibodies directed against the capsid protein of betanodavirus demonstrated intralesional virus antigen. Betanodavirus targeted the brain, spinal cord and retina, causing intracytoplasmic vacuolation of neuronal processes and neuronal necrosis.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Delirium in hospitalized COVID-19 patients is associated with dynamic changes in peripheral immune gene expression - Sara C. LaHue; Naoki Takegami; Rubinee Simmasalam; Abiya Baqai; Elena Munoz; Anya Sikri; Thibault du Buisson de Courson; Nilika S. Singhal; Walter Eckalbar; Charles R. Langelier; Carolyn M. Hendrickson; Carolyn S. Calfee; et al. (GeroScience, 2025)
Delirium is a neurologic syndrome characterized by inattention and cognitive impairment frequently encountered in medically ill older adults. As a hallmark of age-related brain vulnerability, delirium offers a clinical model to investigate how peripheral immune responses contribute to acute brain dysfunction. Peripheral inflammation is a key trigger of delirium, but the patient-specific immune responses that drive delirium onset and recovery remain poorly understood. This retrospective cohort study of prospectively collected biospecimens examines RNA sequencing from peripheral blood mononuclear cells of adults hospitalized for COVID-19 to better understand patient-specific factors associated with delirium ( n = 64). Longitudinal transcriptomic analyses highlight persistent immune dysregulation in delirium, marked by increasing expression trajectories of genes linked to innate immune pathways, including complement activation, cytokine production, and monocyte/macrophage recruitment. Genes involved adaptive immunity showed a declining trajectory over time in patients with delirium. Although corticosteroid treatment suppressed some aspects of immune hyperactivation, aberrant responses contributing to delirium were exacerbated. Delirium resolution was characterized by normalization of key transcripts such as CCL2 and innate immune markers. Novel associations with delirium included transcripts related to stress granule assembly and the T cell regulators DUSP2 and KLF10 . Delirium in COVID-19 is associated with distinct and dynamic peripheral immune trajectories that are modulated by corticosteroids. Further understanding these mechanisms has important implications for preventing delirium in older adults. These findings provide novel mechanistic insights with translational relevance for immunomodulatory strategies targeting maladaptive immune responses to prevent or treat delirium in medically ill populations.

Extension of lifespan by epicatechin, halofuginone and mitoglitazone in male but not female genetically heterogeneous mice - Randy Strong; James F. Nelson; Molly A. Bogue; Jerry R. Colca; Martin Denzel; Vivian Diaz; Brian N. Finck; Vadim N. Gladyshev; Steve Horvath; Nisi Jiang; Tracy Keller; Rolf F. Kletzien; et al. (GeroScience, 2025)
Mice bred in 2021 were tested by the Interventions Testing Program (ITP) for possible lifespan benefits of 2BAct (2BA), dichloroacetate (DCA), Epicatechin (EPI), Forskolin (FSK), Halofuginone (HAL) and Mitoglitazone (MIT). All agents were administered in the diet ad libitum beginning at 7 months of age. In male mice, EPI increased median lifespan by ~ 5%, and HAL and MIT each increased median lifespan by ~ 9%. EPI and HAL, but not MIT, increased 90% survival. In addition to adding 3 new agents to the list of interventions identified by the ITP that extend lifespan, this report continues the strong male bias in the efficacy of life-extending drugs identified so far.

Time Series Changes of Surficial Sediments on Eastern Ship Shoal, Louisiana Shelf - Adam Gartelman; Kehui Xu; Brian J. Roberts; David Samuel Johnson; Madison Liotta (Journal of Marine Science and Engineering, 2025)
Ship Shoal, a large transgressive sand body on the Louisiana continental shelf, is a critical sediment source for coastal restoration. This study evaluates spatial and temporal variability in sediment grain size, percents organic matter (%OM), and carbonate (%CO3) across the shoal crest (REF), Caminada Dredge Pit (CAM), and Terrebonne Dredge Pit (TER). Sediment samples were collected between 2020 and 2022 using box cores and analyzed for grain size, %OM, and %CO3, with temporal and spatial patterns assessed through statistical comparisons, correlation analyses, and random forest regression models. Results show that dredged areas act as sinks for fine-grained, organic-rich sediments, with CAM consistently exhibiting the smallest median grain sizes and highest %OM, while REF maintained coarse, well-sorted sands. Carbonate enrichment reflected long-term depositional regimes, with REF exhibiting the highest %CO3 due to the absence of dredging disturbance. Grain size and %CO3 were identified as the strongest predictors of %OM, while %CO3 was only weakly correlated with other sedimentary variables. Collectively, these findings demonstrate that dredge pits function as persistent repositories, with implications for benthic habitat resilience, sediment management, and coastal restoration planning. Future integration of hydrodynamic modeling with sediment transport and biogeochemical processes is needed to enhance predictive capability for managing dredged environments.

Do natural resources determine Chinese education aid? A subnational analysis of Chinese aid to Africa - Dickson David Agbaji; Itunu Grace Ishola; Adams Bodomo (The Extractive Industries and Society, 2025)

Variation in patterns of production and water-use efficiency among agroecosystems - Olivia L. Hajek; Nicole E. Kaplan; Shefali Azad; Philip A. Fay; Makki Khorchani; Amanda M. Nelson; Adam P. Schreiner-McGraw; Lori J. Abendroth; Claire Baffaut; John Baker; Brandon T. Bestelmeyer; Elizabeth H. Boughton; et al. (Science of The Total Environment, 2025)

Apatite in situ Lu-Hf and U-Pb geochronology in layered mafic intrusions - Melissa Kharkongor; Stijn Glorie; Adam Abersteiner; Sarah Dare; Christopher Kirkland; David Chew; Jacob Mulder; Sarah Gilbert (Geochimica et Cosmochimica Acta, 2025)

Introducing ‘miniRECgap’ R package for simple gap-filling of missing eddy covariance CO2 flux measurements with classic nonlinear environmental response functions via GUI-supported R-scripts (case-study: In-sample gap-filling with ‘miniRECgap’ vs. MDS and an optimised shallow ANN in a ‘challenging’ peatland ecosystem) - Alina Premrov; Jagadeesh Yeluripati; Richard Slevin; Adam Bates; Magdalena Matysek; Stephen Barry; Kenneth A. Byrne; Rowan Fealy; Bernard Hyde; Gary Lanigan; Mark McCorry; Rachael Murphy; et al. (Environmental Modelling & Software, 2025)

Large cobblestone dams for natural flood management in wide peatland gullies - Adam Ryan Johnston; David Brown; Tim Allott; Salim Goudarzi; Martin Kay; David Milledge; Emma Shuttleworth; Tom Spencer; Martin Evans (Ecological Engineering, 2025)

Positive and negative impacts of electrical infrastructure on animal biodiversity: A systematic review - Adam J. Bennett; David M. Watson; Maggie J. Watson (Oecologia, 2025)
Electrical infrastructure networks are predicted to greatly expand in response to the expected 48% increase in global energy demand by 2040. While assessments of electrical infrastructure are abundant, mixed effects on animal diversity have been reported, warranting further evaluation to determine true effects. We conducted a systematic literature review covering individual, population, and community-level assessments to determine the impacts posed to animal biodiversity by electrical infrastructure and the measures to reduce impacts. Our results show that the literature around electrical infrastructure and animal biodiversity has grown exponentially since the start of the millennium and is biased towards birds and mammals in economically developed countries. We found the majority of reported impacts were negative, occurring primarily through barrier effects (collision) and use of linear features as a resource (electrocution), causing significant population impacts in select species. However, we also found that electrical infrastructure provided positive effects (increased habitat provisioning) to certain taxonomic groups (e.g. corvids, storks), which suggests the potential to encourage conservation efforts using appropriate mitigation on electrical infrastructure. We found the majority of current literature detailed mitigation measures focused on reducing collisions through line (51%) and tower alterations (30%), but often omitted the impacts of EMF, noise, and UV, indicating significant knowledge gaps. On a wider scale, we found that mortality from electrical infrastructure ranked lower than building collisions and predation from feral cats, but remained higher than other anthropogenic energy sources, indicating the potential to cause significant impacts to large-bodied bird species if not addressed.

Surface boundary layer stability and meteorological drivers of temporal microclimate variability in a semiarid grassland - David M Barnard; Jacob Macdonald; Robert H. Erskine; Timothy R. Green; Adam Mahood; Sean M. Gleason (Agricultural and Forest Meteorology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

On-field Head Acceleration Exposure Measurement Using Instrumented Mouthguards: Missing Data Imputation for Complete Exposure Analysis - David Luke; Zaryan Masood; Daniel Bondi; Chaokai Zhang; Rebecca Kenny; Adam Clansey; Paul van Donkelaar; Alexander Rauscher; Songbai Ji; Lyndia Wu (Annals of Biomedical Engineering, 2025)

Intercomparison of the U.S. National Water Model with OpenET over the Bear River Basin, U.S. - Ayman Nassar; David Tarboton; Martha Anderson; Yun Yang; Joshua B. Fisher; Adam J. Purdy; Furqan Baig; Cenlin He; David Gochis; Forrest Melton; John Volk (Journal of Hydrology, 2025)

Influence of ENSO on moisture provenance and stable isotope dynamics during the North American Monsoon - Ricardo Sánchez-Murillo; Omar A. López-Mireles; Felipe A. Vázquez-Gálvez; Enrico A. Yépez; Kritan Subedi; Mark Stone; Elí R. Pérez-Ruiz; Yazmin G. Hernández-García; Juan Camacho-Puerto; David K. Adams (Journal of Arid Environments, 2025)

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Understanding (and appreciating) behavioral complexity of zebrafish novel tank assays - Nikita I. Golushko; Daniil Matrynov; David S. Galstyan; Kirill V. Apukhtin; Murilo S. de Abreu; Longen Yang; Adam Michael Stewart; Allan V. Kalueff (Behavioural Processes, 2025)

Leveraging Remote Sensing and Theory to Predict Tree Size Abundance Distributions Across Space - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; J. Marcos Rodriguez; Ben Weinstein; David A. Orwig; Sydne Record (Global Ecology and Biogeography, 2025)
Background Remote sensing (RS) technologies provide unprecedented opportunities to assess forest structure at broad spatial scales. Light detection and ranging (LiDAR) is a powerful tool that offers detailed vertical information, but its consistent high‐resolution coverage can be limited across vast areas and quantifying understory vegetation remains challenging due to occlusion. Conversely, while high‐resolution RGB imagery is more accessible and valuable for large‐scale analyses, it comes with higher uncertainty and only captures canopy‐level information. Integrating RGB data with ecological theory and existing LiDAR‐derived products (e.g., canopy height models, CHM) allows us to enhance predictions and broaden the applicability of forest size structure mapping from the understory to the canopy, particularly through tree size–abundance relationships. Theory Tree size and abundance generally follow known distributions, where smaller trees are exponentially more common than larger trees. This pattern emerges from fundamental ecological constraints, including volume packing, metabolic scaling and light competition, which collectively govern forest self‐organisation across spatial scales. Proposed Approach We present a workflow that integrates size‐abundance scaling theory with RGB data and CHMs to improve predictions of forest structure. By estimating tree size distributions from RGB imagery, we extend the applicability of ecological scaling models to broader spatial scales and offer an approach that complements traditional methods. Assessment We apply this approach to forest monitoring networks, including NEON and ForestGEO, to assess its accuracy and generalisability across a range of forests (e.g., subtropical pine, boreal, low and dry, tall and dense) in North America. Our results show that RGB‐based estimates can successfully recover size‐abundance distributions from the understory to the canopy. Future Directions Further refinement of our approach could enhance predictions by incorporating species classifications from hyperspectral data and using more spatially or taxonomically specific allometric equations. These additions would enable more precise scaling of tree diameter from remote sensing data.

End-of-life pathology in UM-HET3 mice treated with 16 α‑hydroxyestradiol or late‑start canagliflozin - Jessica M. Snyder; David E. Harrison; Ron Korstanje; Brett Ginsburg; Peter C. Reifsnyder; James Nelson; Scott Leiser; Catherine Kaczorowski; Denise M. Imai; Adam B. Salmon; Randy Strong; Warren Ladiges; et al. (GeroScience, 2025)
Canagliflozin (Cana) started at 16 months of age and 16-hydroxy-estradiol (OH_Est) started at 12 months each led to significant increases in lifespan in male UM-HET3 mice but significant decreases in female lifespan. To seek insights into the basis for these sex-specific effects, we performed end-of-life histopathological analyses of control and treated mice for all three interventions testing program sites. There were no significant drug-induced alterations in inferred cause of death, although statistical power was low for such comparisons. Tabulation of incidental lesions (i.e., combining lethal and non-lethal lesions) revealed a complex set of significant and near-significant changes caused by each of the two agents, in some cases absent, or even opposite in direction, in one of the two sexes. The analysis did not, however, reveal a clear pattern that would explain the selective sex-specific effects of either agent on lifespan. It is plausible that the female-specific harm induced by each of these agents could reflect harmful or toxic effects that are not easily detectable by histopathological examination.

Fracturing in basinal siliciclastic deposits of the Wolfcampian Alta Formation, Marfa Basin, west Texas - David A. Ferrill; Kevin J. Smart; Adam J. Cawood; Daniel J. Lehrmann; Giovanni Zanoni; R. Ryan King (Marine and Petroleum Geology, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Rapid Ocean Warming Drives Sexually Divergent Habitat Use in a Threatened Predatory Marine Ectotherm - Lucy R. Mead; Adam Piper; David Jiménez Alvarado; Eva Meyers; Joanna Barker; Hector Toledo‐Padilla; Edy Herraiz; Alberto F. Campoamor; Michael Sealey; Maria Belén Caro; Tomàs Bañeras; Charlotte Pike; et al. (Global Change Biology, 2025)
Climate change poses one of the greatest threats to marine ecosystems worldwide, altering physical, chemical, and biological processes at unprecedented rates. Severe impacts on marine species and habitats have been extensively documented, with shifts in phenology, spatial distribution, and migratory behaviour increasingly pervasive. However, there is a lack of species‐specific data examining responses and adaptation to rapid warming and environmental extremes, especially for marine ectotherms. In this study, we investigate the broad‐scale environmental drivers of distribution in a Critically Endangered ectothermic marine predator, the angelshark Squatina squatina , and report on a behavioural anomaly observed in 2022. Between 2018 and 2023, 112 adult S. squatina were tracked using acoustic telemetry in La Graciosa Marine Reserve in the Canary Islands. Relationships between seasonal presence of S. squatina and remotely sensed environmental parameters were examined with Boosted Regression Tree and Generalised Additive Modelling. Major sex differences were found, with female sharks strongly influenced by environmental conditions and particularly sensitive to temperature, with a possible upper thermal threshold close to 22.5°C. Peak sea surface temperature in the study area increased from 22.99°C to 23.81°C, and the number of days above 22.5°C nearly tripled. Absence of females during the 2022 breeding season coincided with widespread thermal anomalies across the Northeast Atlantic Ocean, with unusually high temperatures persisting later into the year. We conclude that this potentially disrupted seasonal thermal cues for S. squatina movement, leading to sexually divergent habitat use. Given the warming projected for this region, thermal thresholds may increasingly be exceeded, and key areas may become inhospitable for female S. squatina , which is of huge concern for this already highly threatened species. These findings highlight the urgency of identifying species‐specific environmental tolerances and incorporating these into conservation so that management remains ecologically relevant in a rapidly warming ocean.

The Seaward Migration of European Eel at a Continental Scale: A Europe‐Wide Biotelemetry Meta‐Analysis - Pieterjan Verhelst; David Righton; Kim Aarestrup; Pedro R. Almeida; Tea Bašić; Jonathan D. Bolland; Liam Carter; Johan Coeck; José Lino Costa; Justas Dainys; Jan Grimsrud Davidsen; Isabel Domingos; et al. (Fish and Fisheries, 2025)
The European eel ( Anguilla anguilla L.) has a catadromous life cycle, with a single panmictic population that colonises continental Europe and northern Africa yet migrates 5000 to 9000 km to spawn in the Atlantic Ocean. It is unknown how this continental migration is organised so individual eels arrive in time for spawning with conspecifics. This meta‐analysis combined tracking data from 18 water bodies in freshwater and transitional systems distributed along the southwest‐northeast axis of Europe, resulting in a dataset of 2306 eels, making it the most comprehensive in terms of geographical coverage and number of eels tagged. The eels were tracked using acoustic telemetry and the Nedap Trail System and allowed us to study the eel's migration phenology at a continental scale. The findings reveal that the day when eels arrive at sea varies significantly with latitude, with northern eels arriving earlier. Migration speed differs between tidal and non‐tidal habitats, suggesting that tidal currents facilitate faster movement. However, despite these patterns, we observed substantial variability in arrival at sea time and migration speed within water bodies, suggesting that the eel's migration phenology is considerably plastic. The presence of water regulating structures such as weirs, pumping stations and hydropower plants can impact migration timing and speed, potentially delaying eels, but is likely dependent on local hydrological conditions which can be water body specific.

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16-hydroxyestradiol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2025)

Microplastic consumption elevates fish oxidative stress but does not affect predator-driven mortality - Amelia M. Mannering; David J. Burritt; Valeriya Komyakova; Maud C.O. Ferrari; George Vamvounis; Alexandra M. Gulizia; Adam Staples; Mark I. McCormick; Bridie J.M. Allan (Science of The Total Environment, 2025)

Harnessing stemflow as a diagnostic tool for canopy disease detection and monitoring - D. Alex R. Gordon; David J. Burke; Sarah R. Carino-Kyker; Claudia Bashian-Victoroff; Adam I. Mabrouk; John T. Van Stan (Forest Ecology and Management, 2025)

Prolonged 5-week and 12-week chronic stress differentially modulates CNS expression of pro- and anti-neuroinflammatory biomarkers, brain monoamines and affective behavior in adult zebrafish - Maria M. Kotova; Sahil V. Amikishiev; Kirill V. Apukhtin; David S. Galstyan; Murilo S. de Abreu; Adam Michael Stewart; Longen Yang; Allan V. Kalueff (Journal of Comparative Physiology B, 2025)

Exploring opportunities to improve crop-livestock integration and production in mixed farms with a serious game: The case of semi-arid Burkina Faso - Gildas G.C. Assogba; Erika N. Speelman; David Berre; Myriam Adam; Katrien Descheemaeker (Agricultural Systems, 2025)

Staying hooked: effective science engagement and communication in recreational fisheries - Pablo Pita; Sean Tracey; Robert Arlinghaus; Eneko Bachiller; Filipa Pinho-Duarte; Keno Ferter; Filipe Henriques; Samantha Hook; Kieran Hyder; Alejo Irigoyen; María P. Jiménez; Martín Laporta; et al. (Frontiers in Marine Science, 2025)
● This abstract summarizes the results of two expert consultations conducted to gather insights into effective communication and engagement strategies in recreational fisheries. ● Effective science communication fosters knowledge, understanding, and trust in both science and management decisions. ● Public involvement and stakeholder engagement are essential for effective management. ● Simplifying complex research findings and using diverse communication tools enhance awareness and understanding. ● Strong communication strategies are necessary to implement sustainable recreational fisheries management frameworks. ● Funding for communication efforts is often insufficient but remains crucial for success. ● Participatory workshops and data-sharing arrangements enhance collaboration and involvement. ● Multi-stakeholder consortiums and tailored communication strategies strengthen stakeholder engagement and promote adaptive governance. Interdisciplinary outreach and strategic social media use play vital roles in raising environmental awareness.

Freeze-thaw stability of oilseed rape oleosome emulsions - Filippo Bramante; Vincenzo di Bari; Gary Adams; Frederic Beaudoin; Gustav Waschatko; Ralf Jakobi; Nils Billecke; David A. Gray (Journal of Food Engineering, 2025)

A Future of Self-Directed Patient Internet Research: Large Language Model-Based Tools Versus Standard Search Engines - Arya Rao; Andrew Mu; Elizabeth Enichen; Dhruva Gupta; Nathan Hall; Erica Koranteng; William Marks; Michael J. Senter-Zapata; David C. Whitehead; Benjamin A. White; Sanjay Saini; Adam B. Landman; et al. (Annals of Biomedical Engineering, 2025)

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

What acoustic telemetry can and cannot tell us about fish biology - David M. P. Jacoby; Adam T. Piper (Journal of Fish Biology, 2025)
Acoustic telemetry (AT) has become ubiquitous in aquatic monitoring and fish biology, conservation, and management. Since the early use of active ultrasonic tracking that required researchers to follow at a distance their species of interest, the field has diversified considerably, with exciting advances in both hydrophone and transmitter technology. Once a highly specialized methodology, however, AT is fast becoming a generalist tool for those wishing to study or conserve fishes, leading to diversifying application by non‐specialists. With this transition in mind, we evaluate exactly what AT has become useful for, discussing how the technological and analytical advances around AT can address important questions within fish biology. In doing so, we highlight the key ecological and applied research areas where AT continues to reveal crucial new insights and, in particular, when combined with complimentary research approaches. We provide a comprehensive breakdown of the state of the art for applications of AT, discussing the ongoing challenges, where its strengths lie, and how future developments may revolutionize fisheries management, behavioral ecology and species protection. Through selected papers we illustrate specific applications across the broad spectrum of fish biology. By bringing together the recent and future developments in this field under categories designed to broadly capture many aspects of fish biology, we hope to offer a useful guide for the non‐specialist practitioner as they attempt to navigate the dizzying array of considerations and ongoing developments within this diverse toolkit.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Breaking barriers: Transoceanic movement by a bull shark - Ryan Daly; Taryn S. Murray; Michael J. Roberts; David S. Schoeman; Nicolas Lubitz; Adam Barnett; Riaan Cedras; Dunsin A. Bolaji; Grant M. Brokensha; Pamela M. Le Noury; Fabien Forget; Stephanie K. Venables (Ecology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Noise results in lower quality of an important forage fish, the Pacific sand lance, Ammodytes personatus - Nora V. Carlson; Meredith A.V. White; Jose Tavera; Patrick D. O'Hara; Matthew R. Baker; Douglas F. Bertram; Adam Summers; David A. Fifield; Francis Juanes (Marine Pollution Bulletin, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Where giants roam: The importance of remote islands and seamount corridors to adult tiger sharks in the South Pacific Ocean - Jordan K. Matley; Lauren Meyer; Adam Barnett; Mark Scott; Elizabeth A. Dinsdale; Michael P. Doane; David Harasti; Lisa A. Hoopes; Charlie Huveneers (Marine Environmental Research, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Projections of future climate for U.S. national assessments: past, present, future - Samantha Basile; Allison Crimmins; Fredric Lipschultz; Kenneth E. Kunkel; Kate Marvel; Adam Terando; Claudia Tebaldi; David Pierce; Wenying Su; L. Ruby Leung; Katharine Hayhoe (Climatic Change, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Physiological Traits for Predicting Poleward Extensions in Tropical Fishes: From Lab to Management - Adam T. Downie; Curtis Champion; David J. Booth (Global Change Biology, 2025)
Tropicalization, the phenomena by which tropical organisms are extending their distributions poleward into temperate latitudes in response to increasing temperatures and strengthening boundary currents, is occurring globally. Vagrant tropical species have large ecological and economic ramifications for the temperate habitats they invade. However, not all vagrants are able to persist long term in temperate habitats, with the first winter being a potential bottleneck for their persistence. This brings into question how some tropical vagrant species are successful at surviving temperate conditions and the physiology underpinning this success. This provides the opportunity to not only look at the available data introspectively but also forward‐thinking by applying a range of holistic physiological traits relevant for biology and management. Therefore, the aim of our review is twofold: to review the current state‐of‐knowledge of the physiological mechanisms underpinning tropicalization and to develop a physiological framework by which current practices can complement new perspectives and tools. We use range‐expanding tropical reef fishes as a model group of over 100 species undergoing climate‐driven range shifts and eastern Australia as a case‐study location due to it being a primary focal “living laboratory” for understanding tropicalization dynamics since the early 2000s. Current studies suggest that diet, behavior, and metabolic trade‐offs may explain vagrant fish persistence, but these studies focus on whole‐animal traits. Our framework helps expand upon focal traits, life stages, experimental design, physiological traits (e.g., we highlight the value of genetic and cellular markers for metabolic pathway changes under cold stress as potential biomarkers) and species to improve our understanding of the mechanisms underpinning tropicalization. Taken together, our framework places emphasis on measuring a suite of complimentary physiological traits, from cellular to whole‐animal, to help guide future predictions of the long‐term persistence of tropical species in temperate habitats.

Persistent pollutant exposure impacts metabolomic profiles in polar bears and ringed seals from the High Arctic and Hudson Bay, Canada - Anaïs Remili; Adam D. Morris; Derek C.G. Muir; Magali Houde; Tanya M. Brown; Steven H. Ferguson; David A.D. Blair; Robert J. Letcher (Environmental Research, 2025)

Associations between iKaluk/Arctic charr (Salvelinus alpinus) and estuarine benthic diatom habitats in nearshore Nunatsiavut waters - Zachary MacMillan-Kenny; Mary Denniston; Evan Edinger; Adam Templeton; David Côté; Audrey Limoges; Katleen Robert (Polar Biology, 2025)
iKaluk, Inuttitut for Arctic charr ( Salvelinus alpinus ), holds significant commercial and cultural value for Inuit communities throughout Nunatsiavut. Studies evaluating iKaluk habitat associations in freshwater are plentiful; however, there is limited information on the ecological makeup and sediment characteristics of anadromous charr habitats in marine environments. This study investigated the benthic associations of Arctic charr during their marine residency period in Nain, Nunatsiavut, using underwater videos, harvester-identified fishing locations, and acoustic telemetry. Drop-camera surveys were deployed on previously placed hydrophone acoustic receivers and within harvester-identified fishing locations to describe and quantify available benthic habitats in the study area. Telemetry information was used to identify charr occupancy hotspots, and calculate habitat suitability indices. A total of 248,056 benthic organisms belonging to 63 morphotaxa were identified within the 125 video drops used for benthic community characterization and these represented five faunal assemblages. Marine phase charr occupied estuaries to a greater degree than other fjord or coastal headland environments and these habitats were typically characterized by fine sediments covered by high densities of brittle stars (Ophiuroidea spp.) and benthic diatom mats. The consistent presence of diatomaceous sediments is indicative of abundant foraging opportunities. The importance of these habitats to iKaluk, need to be considered in future marine planning given the cultural and ecological value of this species to many northern communities that face growing threats from environmental change.

Crown complementarity rather than crown selection contributes to stem complementarity in genetic mixtures of Pinus taeda L - David R. Carter; Timothy J. Albaugh; Matthew Sumnall; Jake J. Grossman; Otávio C. Campoe; Rachel L. Cook; Rafael A. Rubilar; Chris A. Maier; T. Adam Coates; Julia DeFeo; Grady J. Boyle; Megan Van Spanje (Acta Oecologica, 2025)

Rapid Zooplankton Assessment: Evaluating a Tool for Ecosystem‐Based Fisheries Management in the Large Marine Ecosystems of Alaska - David G. Kimmel; Deana C. Crouser; Colleen E. Harpold; Jesse F. Lamb; Adam H. Spear (Fisheries Oceanography, 2025)
Ecosystem‐based fisheries management (EBFM) remains an aspirational goal for management throughout the world. One of the primary limitations of EBFM is the incorporation of basic lower trophic level information, particularly for zooplankton, despite the importance of zooplankton to fish. The generation of zooplankton abundance estimates requires significant time and expertise to generate. The rapid zooplankton assessment (RZA) is introduced as a tool whereby nontaxonomic experts may produce rapid zooplankton counts shipboard that can be applied to management in near real time. Zooplankton are rapidly counted shipboard and placed into three broad groups of zooplankton relevant to higher trophic levels: large copepods (> 2 mm), small copepods ( R 2 = 0.80) and euphausiids (Bayes R 2 = 0.84). These factors also improved the fit for small copepods when the fixed effect of season was also included (Bayes R 2 = 0.65). Additional RZA data were used to predict laboratory‐processed abundances for each zooplankton category and the results were consistent with model training data: large copepods (Bayes R 2 = 0.80), small copepods (Bayes R 2 = 0.64), and euphausiids (Bayes R 2 = 0.88). The Bayesian models were therefore able to predict laboratory‐processed abundances with an associated error when accounting for these fixed and random effects. To demonstrate the utility of zooplankton data in management, zooplankton time series from the Bering Sea shelf were shown to vary in relation to warm and cold conditions. This variability impacted commercially important fish, notably Walleye Pollock ( Gadus chalcogrammus ), and these time series were used by managers using a risk table approach. The RZA method provides a rapid zooplankton population estimation in near real time that can be applied to the management process quickly, thus helping to fill a gap in EBFM.

Assessing survey design changes of long-term fishery-independent groundfish trawl surveys in the Gulf of Mexico - Adam G. Pollack; Eric R. Hoffmayer; Theodore S. Switzer; David S. Hanisko; Jill M. Hendon; John Mareska; Fernando Martinez-Andrade; Jeff Rester; Zachary C. Zuckerman; Gilmore Pellegrin (Frontiers in Marine Science, 2025)
Long-term fishery-independent surveys provide a wealth of information on fisheries stocks that inform stock assessments. One of the strengths of these surveys is that the design and methods are consistent through time. However, maintaining an unchanged time series can pose several potential issues as management needs change resulting in the need to alter either the survey design or its spatial extent. In the United States Gulf of Mexico, bottom trawl surveys targeting groundfish and shrimp (hereafter, groundfish surveys) have been conducted since the 1950s, with standardized surveys beginning in 1972. The resulting data can provide a great deal of information on commercially and recreationally important species. However, many of the alterations to the survey design have been buried in gray literature or otherwise poorly noted. The history of these surveys is discussed, along with the rationale behind these changes and the impacts they had on stock assessments in the region. Starting in 1981, the Southeast Area Monitoring and Assessment Program began groundfish surveys, continuing the time series. Over time, the survey’s spatial extent and design have been altered to meet changing management needs. Delta-lognormal models are used to draw inferences concerning the effects of the survey design change on the relative abundance and their associated coefficients of variation for several commercially and recreationally important species. The expansion of the surveys across the Gulf of Mexico is examined in relation to stock assessments. Overall, the design changes and spatial expansion have been beneficial from a stock assessment standpoint, resulting in an increase in the number of indices used for single-species stock assessments and the utility of survey data in support of ecosystem modeling efforts. Finally, a discussion around the lesson learned (i.e., the critical need for overlap of survey designs), emphasizing the potential impacts of these changes on the overall time series concerning stock assessments, is presented.

Use of alternatives to animal testing for Environmental Safety Assessment (ESA): Report from the 2023 EPAA partners’ forum - Jose V. Tarazona; Ana Fernandez-Agudo; Ondrej Adamovsky; Marta Baccaro; Natalie Burden; Bruno Campos; Björn Hidding; Karen Jenner; David John; Katia Lacasse; Adam Lillicrap; Delina Lyon; et al. (Regulatory Toxicology and Pharmacology, 2025)

Tsunami boulder transport in coastal environments: insights from physical experiments and dimensional analysis - Storm Roberts; Alison Raby; Sarah J. Boulton; William Allsop; Alessandro Antonini; Ivo van Balen; David McGovern; Keith Adams; Ian Chandler; Jonas Cels; Irene Manzella (Marine Geology, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Risk of mortality in Fusobacterium species bloodstream infection from a large Australian cohort - Adam G. Stewart; Felicity Edwards; Patrick N. A. Harris; David L. Paterson; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

A computational framework to support probabilistic criticality modelling for the geological disposal of radioactive waste - E. Adam Paxton; Jiejie Wu; Tim Hicks; Slimane Doudou; David Applegate; Robert Mason; Andrew Price; Liam Payne (Annals of Nuclear Energy, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Synchrotron X-ray Fluorescence Microscopy Reveals Trace Elemental Indicators of Life History in Marsupial Teeth - William M. G. Parker; Justin W. Adams; David P. Hocking; Erich M. G. Fitzgerald; Geoff Shaw; Marilyn B. Renfree; Alistair R. Evans (Biological Trace Element Research, 2025)
As teeth develop, their mineralised composition is a bio-recorder of diet, environment, and growth. High-resolution elemental mapping provides a tool to reveal records of life history within teeth. The relative concentrations of a range of trace elements change between in utero development, birth, and weaning in eutherian mammals. Marsupials, however, have a different mode of development: altricial birth and growth within the pouch facilitated by compositional transitions in milk. How these differences alter patterns of elemental mineralisation and become recorded in marsupial teeth is previously unknown. This study analyses the distribution of calcium (major element), zinc (actively incorporated trace element), and strontium (passively incorporated trace element) in the teeth of five species of diprotodontian marsupial using synchrotron X-ray fluorescence microscopy. We find that the diprotodontian lower incisor concatenates elemental variation from across the molariform dentition, preserving a prolonged record of life history in four of the five species. Patterns of elemental incorporation in enamel, dentine, and cementum are presented, with Ca, Zn, and Sr having differing distributions. Zn accretion indicates a role in mineralisation and/or prevention of tooth degradation. Zn also demarcates incremental cementum lines. Sr is shown to be passively incorporated into marsupial teeth, with increasing Sr concentration in milk recorded in dental tissues formed contemporaneously. Older individuals have oscillatory signals in Sr that appear linked to seasonality. These findings highlight some similarities between eutherian and marsupial trace element incorporation, particularly in the distribution of Zn. Sr signals in marsupial teeth record key aspects of life history.

Insecticide application prevents honey bees from realizing benefits of native forage in an agricultural landscape - Ashley L. St. Clair; Adam G. Dolezal; Randall P. Cass; Harmen P. Hendriksma; David S. Stein; Kate E. Borchardt; Erin W. Hodgson; Matthew E. O'Neal; Amy L. Toth (Science of The Total Environment, 2025)

Intraspecific interactions and thermal refuge availability interactively influence ectotherm thermoregulation but not energy dynamics - David R. Adams; Matthew E. Gifford (Journal of Thermal Biology, 2025)

Long-term soil nutrient and understory plant responses to post-fire rehabilitation in a lodgepole pine forest - Sophia Kaiser; Timothy S. Fegel; David M. Barnard; Adam L. Mahood; Kya Sparks; Kaela K. Amundson; Michael J. Wilkins; Charles C. Rhoades (Forest Ecology and Management, 2025)

Reconciling global and local benefits of forest restoration: A shared interdisciplinary perspective - Stephanie Mansourian; William M. Adams; Karma Bouazza; Joice Nunes Ferreira; David J. Ganz; Jack Hurd; Stefano Pagiola; John Parrotta; Bruno Ramamonjisoa; Nanie Ratsifandrihamanana; Roger Villalobos; Gretchen Walters; et al. (Forest Policy and Economics, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

A quantum algorithm for the lattice-Boltzmann method advection-diffusion equation - David Wawrzyniak; Josef Winter; Steffen Schmidt; Thomas Indinger; Christian F. Janßen; Uwe Schramm; Nikolaus A. Adams (Computer Physics Communications, 2025)

Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

The Coastal Ocean Environment Summer School In Nigeria and Ghana: The Value of Long-Term, Sustained Capacity Sharing - Brian Arbic; Johnson Adjetey; Andrews Agyekumhene; Mosunmola Akinwunmi; Lailah Akita; Lois Anderson; Joseph Ansong; Kwasi Appeaning Addo; Eunice Asamoah; Olawale Awe; Christian Buckingham; Janae’ Collier; et al. (Oceanography, 2025)
The Coastal Ocean Environment Summer School In Nigeria and Ghana (COESSING; https://coessing.org) has been run for one week every year since 2015. The school, an endorsed project of the United Nations Decade of Ocean Science for Sustainable Development (2021–2030), has provided a platform for approximately 1,000 scientists from Africa, the United States, and Europe to exchange scientific knowledge, to network, to learn, and to collaborate. Our interdisciplinary, multicultural, and multi-institutional approach offers a model for knowledge exchange across the globe and across different educational levels.

Ten Pressing Questions (and Answers) About Marine Fungi and Opportunities for Collaborations in the Ocean Sciences - Anthony Amend; Nina Gunde-Cimerman; Marco Coelho; Colleen Durkin; Cassandra Ettinger; Hugh Gifford; Amy Gladfelter; Cene Gostinčar; Lior Granit; Igor Grigoriev; Marcelo Gutiérrez; KJE Hickman; et al. (Oceanography, 2025)
Nearly 200 years have passed since the first marine fungus, collected from the shores of North Africa, was described. In that time, marine mycologists have continued to observe, describe, and study fungi in every marine ecosystem examined. Nevertheless, fungi remain functionally “dark matter” of the ocean, presenting a grand opportunity to unravel their roles in ecosystem processes. This report outlines the discussion among participants of the second occasional meeting of marine mycologists at Asilomar, California, in March 2024, in which a diverse and interdisciplinary consortium of researchers enumerated the most pressing, and often basic, unanswered questions in marine fungi. We report on the questions facing the field of marine mycology, identify challenges in addressing those questions, and propose concrete and practical solutions for obtaining their answers. A common thread is the need for increasing cross talk and collaboration between mycologists and oceanographers that would present opportunities for readers to participate in a rapidly growing field.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Increased monetary equity and health wellbeing benefits for marginal urban socioeconomic groups from access to green space - Adam Loch; Stuart Sexton; John Maclean; Patrick O’Connor; David Adamson; Glen Scholz (Urban Forestry & Urban Greening, 2024)

Fluvial-lacustrine influences on linear dune erosion at Lake Caroline in the Simpson Desert of Australia - Rachel Rotz; Adam Milewski; Robert Craddock; Alex Morgan; David S. Leigh (Geomorphology, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

The mouse metabolic phenotyping center (MMPC) live consortium: an NIH resource for in vivo characterization of mouse models of diabetes and obesity - Maren Laughlin; Richard McIndoe; Sean H. Adams; Renee Araiza; Julio E. Ayala; Lucy Kennedy; Louise Lanoue; Louise Lantier; James Macy; Eann Malabanan; Owen P. McGuinness; Rachel Perry; et al. (Mammalian Genome, 2024)
The Mouse Metabolic Phenotyping Center (MMPC) Live Program was established in 2023 by the National Institute for Diabetes, Digestive and Kidney Diseases (NIDDK) at the National Institutes of Health (NIH) to advance biomedical research by providing the scientific community with standardized, high quality phenotyping services for mouse models of diabetes and obesity. Emerging as the next iteration of the MMPC Program which served the biomedical research community for 20 years (2001–2021), MMPC Live is designed as an outwardly-facing consortium of service cores that collaborate to provide reduced-cost consultation and metabolic, physiologic, and behavioral phenotyping tests on live mice for U.S. biomedical researchers. Four MMPC Live Centers located at universities around the country perform complex and often unique procedures in vivo on a fee for service basis, typically on mice shipped from the client or directly from a repository or vendor. Current areas of expertise include energy balance and body composition, insulin action and secretion, whole body carbohydrate and lipid metabolism, cardiovascular and renal function, food intake and behavior, microbiome and xenometabolism, and metabolic pathway kinetics. Additionally, an opportunity arose to reduce barriers to access and expand the diversity of the biomedical research workforce by establishing the VIBRANT Program. Directed at researchers historically underrepresented in the biomedical sciences, VIBRANT-eligible investigators have access to testing services, travel and career development awards, expert advice and experimental design consultation, and short internships to learn test technologies. Data derived from experiments run by the Centers belongs to the researchers submitting mice for testing which can be made publicly available and accessible from the MMPC Live database following publication. In addition to services, MMPC Live staff provide expertise and advice to researchers, develop and refine test protocols, engage in outreach activities, publish scientific and technical papers, and conduct educational workshops and training sessions to aid researchers in unraveling the heterogeneity of diabetes and obesity.

Hawaiian legends of coastal devastation and paleotsunami reconstruction, Nu'u, Kaupō, Maui, Hawai'i - Scott Fisher; James Goff; Andrew Cundy; David Sear; James Terry; Randall J. LeVeque; Loyce M. Adams; Diana Sahy (Marine Geology, 2024)

Validating costly protected area restoration after (increasing) disasters - Adam Loch; Glen Scholz; David Adamson; Stuart Sexton; Alexandra Peralta (Journal of Environmental Management, 2024)

Limited effects of thinning on laminated root rot induced tree mortality in Douglas-fir forests of the Pacific Northwest, USA - Shawn B. McMurtrey; David N. Showalter; Adam R. Carson; Michael McWilliams; (Irene) Blakey Lockman; Everett M. Hansen; Jared M. LeBoldus (Forest Ecology and Management, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Importance of tides and winds in influencing the nonstationary behaviour of coastal currents in offshore Singapore - Jun Yu Puah; Ivan D. Haigh; David Lallemant; Kyle Morgan; Dongju Peng; Masashi Watanabe; Adam D. Switzer (Ocean Science, 2024)
Coastal currents significantly impact port activities, coastal landform morphodynamics, and ecosystem functioning. It is therefore necessary to understand the physical characteristics and natural variability of these currents within coastal settings. Traditional methods, such as harmonic analysis, assume stationarity of tide-driven currents and may thus not be applicable to systems modulated by variable nontidal inputs and processes. Here we deployed eight tilt current meters in shallow (

Incorporating functional traits with habitat maps: patterns of diversity in coastal benthic assemblages - Shreya Nemani; Benjamin Misiuk; David Cote; Evan Edinger; Julia Mackin-McLaughlin; Adam Templeton; Katleen Robert (Frontiers in Marine Science, 2024)
Benthic species assemblages are groups of species that co-occur on the seafloor. Linking assemblages to physical environmental features allows for understanding and predicting their spatial distribution. Species identity and abundance are commonly quantified using a taxonomic approach to assess benthic diversity, yet functional traits that describe the behavior, life history, and morphology of a species may be equally or more important. Here, we investigate the biodiversity of five benthic species assemblages in relation to their habitat and environmental conditions in an Ecologically and Biologically Significant Area (EBSA) along Canada’s east coast, using both a taxonomic approach and biological traits analysis. Random Forest regression was applied to map spatial patterns of functional and taxonomic diversity metrics, including richness, Shannon index, and Rao’s quadratic entropy. We evaluate discrepancies between related taxonomic and trait measures, and the community-weighted mean of trait data was calculated to characterize each assemblage. Taxonomic and functional richness – representing the number of species and the species community volume in the trait space, respectively – showed similar spatial patterns. However, when considering diversity, which also accounts for the relative abundance and differences among species or traits, these patterns diverged. Taxonomically different assemblages exhibited similar trait compositions for two assemblages, indicating potential trait equivalencies, while one assemblage exhibited traits potentially indicating sensitivity to human activity. The taxonomic and functional metrics of richness and diversity were low close to the coast, which could be indicative of disturbance. Consideration of functional metrics can support spatial planning and prioritization for management and conservation efforts by assessing the sensitivity of traits to different stressors.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Analytically Confirmed Intentional Overdose of the Antidepressant Vortioxetine - Adam Daneshmend; Allon Gould; Simon Hudson; John Robert Howard Archer; Paul Ivor Dargan; David Michael Wood (Journal of Medical Toxicology, 2024)
Introduction Vortioxetine is an antidepressant with a multimodal mechanism of action. It is used as a treatment option for patients with major depressive episodes. There have only been two previously reported non-fatal overdoses of vortioxetine; neither of these were analytically confirmed There has also been one case of serotonin syndrome potentially related to vortioxetine and two deaths where vortioxetine was detected. We report here a non-fatal analytically confirmed case of vortioxetine overdose. Case report A 32-year-old male presented to the emergency department (ED) 12–13 h after oral ingestion of 1,260 mg of vortioxetine and 350 mg of diazepam. A family member reported that he had been drowsy after the overdose, but his level of consciousness and observations (heart rate, blood pressure and temperature) were normal on review by the pre-hospital emergency services and on arrival to the ED. During a period of observation, he did not develop any features of serotonin syndrome or any other significant toxicity. Toxicological analysis of a blood sample taken in the ED detected vortioxetine (plasma concentration 457 ng/mL 10 h after ingestion) and sub-therapeutic concentrations of diazepam and pregabalin. Discussion Despite having a plasma vortioxetine concentration nearly 15-times therapeutic vortioxetine concentrations, this patient did not develop any significant toxicity. In particular he did not develop any clinical or biochemical features of serotonin toxicity that would be expected with this class of antidepressant. Additional reporting of analytically confirmed vortioxetine overdoses will allow clinicians and licensing authorities to further understand the safety of this medication in overdose.

Anisotropic Forbush decrease of 24 March 2024: First look - Alexander Mishev; Nicholas Larsen; Eleanna Asvestari; Alejandro Sáiz; Margaret Ann Shea; Du Toit Strauss; David Ruffolo; Chanoknan Banglieng; Surujhdeo Seunarine; Marc L. Duldig; Agnieszka Gil; Juan José Blanco; et al. (Advances in Space Research, 2024)

On-field Head Acceleration Exposure Measurements Using Instrumented Mouthguards: Multi-stage Screening to Optimize Data Quality - Adam C. Clansey; Daniel Bondi; Rebecca Kenny; David Luke; Zaryan Masood; Yuan Gao; Marko Elez; Songbai Ji; Alexander Rauscher; Paul van Donkelaar; Lyndia C. Wu (Annals of Biomedical Engineering, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Biologging reveals rapid movements of harbour seals between freshwater and marine habitats in the subarctic - Katie R.N. Florko; David J. Yurkowski; C-Jae C. Breiter; Steven H. Ferguson; Holly E.L. Gamblin; Adam Grottoli; Andrea Nace; Courtney R. Shuert; Stephen D. Petersen (Frontiers in Marine Science, 2024)
Biologging tools can provide invaluable information on the movement and behaviour of animals, facilitating the elucidation of ecological dynamics, especially for wide-ranging species, and supporting conservation and management efforts. Harbour seals ( Phoca vitulina ) exhibit extensive habitat plasticity in their vast range across the northern hemisphere, with likely recent increases in abundance at northern latitudes, yet details of their movement behaviour in subarctic areas remain largely unknown. We used satellite-telemetry data, including nearly 5,000 locations and over 12,000 dives, obtained from six harbour seals tagged in western Hudson Bay from 2021 to 2023, to address the knowledge gap on their movement behaviour between marine and freshwater habitats in subarctic regions. We document the behavioural patterns, transit speeds, and diverse aquatic system usage, including detailed records of a harbour seal track traversing over 170 km upriver on three separate trips along the Seal River, Canada. Notably, we observed a rapid downstream transit from the Seal River to Hudson Bay, covering 214 km within a single day. Additionally, we highlight the prevalence of short dive durations in the Seal and Churchill Rivers, in contrast to longer dive durations in Hudson Bay. These insights complement existing evidence of harbour seal occurrences and river use at northern latitudes, as well as enhance our understanding of harbour seal movement ecology within Hudson Bay which can be used to better inform conservation and management strategies between connected freshwater and marine environments in the Arctic.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Antioxidant-related enzymes and peptides as biomarkers of metallic nanoparticles (eco)toxicity in the aquatic environment - Tomas Do; Silvia Vaculciakova; Katarzyna Kluska; Manuel David Peris-Díaz; Jan Priborsky; Roman Guran; Artur Krężel; Vojtech Adam; Ondrej Zitka (Chemosphere, 2024)

Molecular determinants of the selectivity and potency of α-conotoxin Vc1.1 for human nicotinic acetylcholine receptor subtypes - Han-Shen Tae; Andrew Hung; David J. Adams (Toxicon, 2024)

Palaeogenomic data from a Late Pleistocene coprolite clarifies the phylogenetic position of Sicilian cave hyena - Giulio Catalano; Dawid Adam Iurino; Alessandra Modi; Johanna L.A. Paijmans; Raffaele Sardella; Luca Sineo; David Caramelli; Axel Barlow (Quaternary Science Reviews, 2024)

Brominated oxime nucleophiles are efficiently reactivating cholinesterases inhibited by nerve agents - Eliska Prchalova; Rudolf Andrys; Jaroslav Pejchal; Zuzana Kohoutova; Karolina Knittelova; Tereza Hofmanova; Adam Skarka; Alzbeta Dlabkova; Miroslav Psotka; Lukas Prchal; Kamil Musilek; Jana Zdarova Karasova; et al. (Archives of Toxicology, 2024)

Weak phylogenetic effect on specialist plant assemblages and their persistence on habitat islands - Adam Klimeš; Rafael Molina‐Venegas; Angelino Carta; Milan Chytrý; Luisa Conti; Lars Götzenberger; Michal Hájek; Michal Horsák; Borja Jiménez‐Alfaro; Jitka Klimešová; Francisco E. Méndez‐Castro; David Zelený; et al. (Journal of Biogeography, 2024)
Aim The influence of species phylogenetic relatedness on the formation of insular assemblages remains understudied in functional island biogeography, especially for terrestrial habitat islands (i.e. distinct habitat patches embedded in a matrix that differ in the prevailing environmental conditions). Here, we tested three eco‐evolutionary hypotheses: (1) functional specialization of species (i.e. specialism) is associated with phylogenetic clustering at the habitat archipelago scale, (2) such clustering increases with insularity at the habitat island scale and (3) traits indicative of effective local persistence strategies shape island specialism. Location Terrestrial habitat islands, Europe (Fens in the Western Carpathians, Outcrops in Moravia and Mountaintops in the Cantabrian Range). Taxon Angiosperms. Methods We assessed the phylogenetic relatedness of habitat specialists in three different archipelagos composed of terrestrial habitat islands based on phylogenetic signals and phylogenetic diversity (PD) measures. We estimated the effect of insularity on PD using linear models and the effect of persistence traits on specialism using phylogenetic logistic regressions. Results Our hypotheses were largely not supported. Outcrop and mountaintop specialist assemblages did not exhibit any phylogenetic structuring, whereas fen specialists were clustered at the archipelago scale. Therefore, insularity seems not to act as a selective force for phylogenetic structure, and ecologically important persistence traits do not operate as precursors of specialism. Main Conclusions Our results show that species phylogenetic relatedness plays a minor role in shaping habitat island specialist assemblages. Furthermore, the effects of phylogenetic relatedness on assemblages of island specialists are system and scale dependent. Finally, accounting for species' phylogenetic relatedness on persistence traits yielded results similar to previous studies, which corroborates the positive relationship between insularity and functional traits (indicative of enhanced plant persistence abilities with increasing within‐archipelago insularity).

Increased intake of tree forage by moose is associated with intake of crops rich in nonstructural carbohydrates - Annika M. Felton; Robert Spitzer; David Raubenheimer; Per‐Ola Hedwall; Adam Felton; Ruth V. Nichols; Brendan L. O'Connell; Jonas Malmsten; Erik Löfmarck; Hilde K. Wam (Ecology, 2024)
Animals representing a wide range of taxonomic groups are known to select specific food combinations to achieve a nutritionally balanced diet. The nutrient balancing hypothesis suggests that, when given the opportunity, animals select foods to achieve a particular target nutrient balance, and that balancing occurs between meals and between days. For wild ruminants who inhabit landscapes dominated by human land use, nutritionally imbalanced diets can result from ingesting agricultural crops rich in starch and sugar (nonstructural carbohydrates [NCs]), which can be provided to them by people as supplementary feeds. Here, we test the nutrient balancing hypothesis by assessing potential effects that the ingestion of such crops by Alces alces (moose) may have on forage intake. We predicted that moose compensate for an imbalanced intake of excess NC by selecting tree forage with macro‐nutritional content better suited for their rumen microbiome during wintertime. We applied DNA metabarcoding to identify plants in fecal and rumen content from the same moose during winter in Sweden. We found that the concentration of NC‐rich crops in feces predicted the presence of Picea abies (Norway spruce) in rumen samples. The finding is consistent with the prediction that moose use tree forage as a nutritionally complementary resource to balance their intake of NC‐rich foods, and that they ingested P. abies in particular (normally a forage rarely eaten by moose) because it was the most readily available tree. Our finding sheds new light on the foraging behavior of a model species in herbivore ecology, and on how habitat alterations by humans may change the behavior of wildlife.

Determining evolutionary origin and phylogenetic relationships of mallard-like ducks of Oceania, greater Indonesia, and the Philippines with ddRAD-seq data - Marissa Kaminski; Joshua I. Brown; Sara R. Seibert; Flor Hernández; Melizar V. Duya; Ian Kendrich C. Fontanilla; David Roshier; Adam Miles; Leo Joseph; Jeffrey L. Peters; Philip Lavretsky (Molecular Phylogenetics and Evolution, 2024)

Optimising parameters for pilot scale steam explosion and continuous pressurised disc refining of Miscanthus and sugarcane bagasse for xylose and xylo-oligosaccharide release - David Warren-Walker; Sreenivas Rao Ravella; Joe Gallagher; Ana Winters; Adam Charlton; David N. Bryant (Bioresource Technology, 2024)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16‑hydroxyestriol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Nisi Jiang; Catherine C. Kaczorowski; Navasuja Kumar; et al. (GeroScience, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Unified 200 kyr paleohydrologic history of the Southern Great Basin: Death Valley, Searles Valley, Owens Valley and the Devils Hole cave - Tim K. Lowenstein; Kristian J. Olson; Brian W. Stewart; David McGee; Justin S. Stroup; Adam M. Hudson; Kathleen A. Wendt; Mark D. Peaple; Sarah J. Feakins; Tripti Bhattacharya; Steve Lund (Quaternary Science Reviews, 2024)

A process-based geochemical framework for carbonate sediments during marine diagenesis - Mohammed S. Hashim; Stephen E. Kaczmarek; Gemakrisindo Wolfram Naa; David L. Bish; Adam V. Subhas (Geochimica et Cosmochimica Acta, 2024)

neonPlantEcology: An R package for preparing NEON plant data for use in ecological research - Adam L. Mahood; Ranjan Muthukrishnan; Jacob A. Macdonald; David T. Barnett; Eric R. Sokol; Samuel M. Simkin (Ecological Modelling, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Forecasting potential invaders to prevent future biological invasions worldwide - Arman N. Pili; Boris Leroy; John G. Measey; Jules E. Farquhar; Adam Toomes; Phillip Cassey; Sebastian Chekunov; Matthias Grenié; Dylan van Winkel; Lisa Maria; Mae Lowe L. Diesmos; Arvin C. Diesmos; et al. (Global Change Biology, 2024)
The ever‐increasing and expanding globalisation of trade and transport underpins the escalating global problem of biological invasions. Developing biosecurity infrastructures is crucial to anticipate and prevent the transport and introduction of invasive alien species. Still, robust and defensible forecasts of potential invaders are rare, especially for species without known invasion history. Here, we aim to support decision‐making by developing a quantitative invasion risk assessment tool based on invasion syndromes (i.e., generalising typical attributes of invasive alien species). We implemented a workflow based on ‘Multiple Imputation with Chain Equation’ to estimate invasion syndromes from imputed datasets of species' life‐history and ecological traits and macroecological patterns. Importantly, our models disentangle the factors explaining (i) transport and introduction and (ii) establishment. We showcase our tool by modelling the invasion syndromes of 466 amphibians and reptile species with invasion history. Then, we project these models to amphibians and reptiles worldwide (16,236 species [c.76% global coverage]) to identify species with a risk of being unintentionally transported and introduced, and risk of establishing alien populations. Our invasion syndrome models showed high predictive accuracy with a good balance between specificity and generality. Unintentionally transported and introduced species tend to be common and thrive well in human‐disturbed habitats. In contrast, those with established alien populations tend to be large‐sized, are habitat generalists, thrive well in human‐disturbed habitats, and have large native geographic ranges. We forecast that 160 amphibians and reptiles without known invasion history could be unintentionally transported and introduced in the future. Among them, 57 species have a high risk of establishing alien populations. Our reliable, reproducible, transferable, statistically robust and scientifically defensible quantitative invasion risk assessment tool is a significant new addition to the suite of decision‐support tools needed for developing a future‐proof preventative biosecurity globally.

The C. elegans Myc-family of transcription factors coordinate a dynamic adaptive response to dietary restriction - Adam B. Cornwell; Yun Zhang; Manjunatha Thondamal; David W. Johnson; Juilee Thakar; Andrew V. Samuelson (GeroScience, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Lifespan effects in male UM-HET3 mice treated with sodium thiosulfate, 16-hydroxyestriol, and late-start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2024)

Sea surface microplastics in the Galapagos: Grab samples reveal high concentrations of particles <200 μm in size - Katie Deakin; Georgie Savage; Jen S. Jones; Adam Porter; Juan Pablo Muñoz-Pérez; David Santillo; Ceri Lewis (Science of The Total Environment, 2024)

Thrust v. stylolite - David A. Ferrill; Adam J. Cawood; Mark A. Evans; Kevin J. Smart; R. Ryan King; Giovanni Zanoni (Journal of Structural Geology, 2024)

Abatement and transaction costs of water reallocation - C. Dionisio Pérez-Blanco; Adam Loch; Juan Mejino-López; Laura Gil-García; David Adamson; Pablo Saiz-Santiago; José Antonio Ortega (Journal of Hydrology, 2024)

Structure, dynamics, and functional properties of hybrid alginate-pectin gels dually crosslinked by Ca2+ and Zn2+ ions designed as a delivery device for self-emulsifying systems for lipophilic phytotherapeutics - Martina Urbanova; Jan Macku; Katerina Kubova; Jakub Vyslouzil; Jan Muselík; Miroslav Slouf; Ivana Sedenkova; Olga Kockova; Larisa Janisova; Josef Masek; Eliska Maskova; Adam Novobilsky; et al. (Food Hydrocolloids, 2024)

A framework for the systematic evaluation of a novel cigarette filter technology - Ian Crooks; David Thorne; Mark West; Krishna Prasad; Adam Gray; Casandra West; Peter Wan; Richard Savory; Ignacio Suarez; Carolina Garcia-Canton (Food and Chemical Toxicology, 2024)

Fibrosis and expression of extracellular matrix proteins in human interventricular septum in aortic valve stenosis and regurgitation - David Sedmera; Alena Kvasilova; Adam Eckhardt; Petr Kacer; Martin Penicka; Matej Kocka; Dana Schindler; Ron Kaban; Radka Kockova (Histochemistry and Cell Biology, 2024)
Valvular heart disease leads to ventricular pressure and/or volume overload. Pressure overload leads to fibrosis, which might regress with its resolution, but the limits and details of this reverse remodeling are not known. To gain more insight into the extent and nature of cardiac fibrosis in valve disease, we analyzed needle biopsies taken from the interventricular septum of patients undergoing surgery for valve replacement focusing on the expression and distribution of major extracellular matrix protein involved in this process. Proteomic analysis performed using mass spectrometry revealed an excellent correlation between the expression of collagen type I and III, but there was little correlation with the immunohistochemical staining performed on sister sections, which included antibodies against collagen I, III, fibronectin, sarcomeric actin, and histochemistry for wheat germ agglutinin. Surprisingly, the immunofluorescence intensity did not correlate significantly with the gold standard for fibrosis quantification, which was performed using Picrosirius Red (PSR) staining, unless multiplexed on the same tissue section. There was also little correlation between the immunohistochemical markers and pressure gradient severity. It appears that at least in humans, the immunohistochemical pattern of fibrosis is not clearly correlated with standard Picrosirius Red staining on sister sections or quantitative proteomic data, possibly due to tissue heterogeneity at microscale, comorbidities, or other patient-specific factors. For precise correlation of different types of staining, multiplexing on the same section is the best approach.

Comparing Transcriptomic Points of Departure to Apical Effect Concentrations For Larval Fathead Minnow Exposed to Chemicals with Four Different Modes Of Action - Kevin Flynn; Michelle Le; Monique Hazemi; Adam Biales; David C. Bencic; Brett R. Blackwell; Kendra Bush; Robert Flick; John X. Hoang; John Martinson; Mackenzie Morshead; Kelvin Santana Rodriguez; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Muscle Morphology Does Not Solely Determine Knee Flexion Weakness After Anterior Cruciate Ligament Reconstruction with a Semitendinosus Tendon Graft: A Combined Experimental and Computational Modeling Study - Adam Kositsky; Lauri Stenroth; Rod S. Barrett; Rami K. Korhonen; Christopher J. Vertullo; Laura E. Diamond; David J. Saxby (Annals of Biomedical Engineering, 2024)
The distal semitendinosus tendon is commonly harvested for anterior cruciate ligament reconstruction, inducing substantial morbidity at the knee. The aim of this study was to probe how morphological changes of the semitendinosus muscle after harvest of its distal tendon for anterior cruciate ligament reconstruction affects knee flexion strength and whether the knee flexor synergists can compensate for the knee flexion weakness. Ten participants 8–18 months after anterior cruciate ligament reconstruction with an ipsilateral distal semitendinosus tendon autograft performed isometric knee flexion strength testing (15°, 45°, 60°, and 90°; 0° = knee extension) positioned prone on an isokinetic dynamometer. Morphological parameters extracted from magnetic resonance images were used to inform a musculoskeletal model. Knee flexion moments estimated by the model were then compared with those measured experimentally at each knee angle position. A statistically significant between-leg difference in experimentally-measured maximal isometric strength was found at 60° and 90°, but not 15° or 45°, of knee flexion. The musculoskeletal model matched the between-leg differences observed in experimental knee flexion moments at 15° and 45° but did not well estimate between-leg differences with a more flexed knee, particularly at 90°. Further, the knee flexor synergists could not physiologically compensate for weakness in deep knee flexion. These results suggest additional factors other than knee flexor muscle morphology play a role in knee flexion weakness following anterior cruciate ligament reconstruction with a distal semitendinosus tendon graft and thus more work at neural and microscopic levels is required for informing treatment and rehabilitation in this demographic.

Genetic structuring and species boundaries in the Atlantic stony coral Favia (Scleractinia, Faviidae) - Carolina de Lima Adam; Robert J. Toonen; David B. Carlon; Carla Zilberberg; Marcos Soares Barbeitos (Zoologica Scripta, 2024)
Scleractinian corals are the main modern builders of coral reefs, which are major hot spots of marine biodiversity. Southern Atlantic reef corals are understudied compared to their Caribbean and Indo‐Pacific counterparts and many hypotheses about their population dynamics demand further testing. We employed thousands of single nucleotide polymorphisms (SNPs) recovered via ezRAD to characterize genetic population structuring and species boundaries in the amphi‐Atlantic hard coral genus Favia . Coalescent‐based species delimitation (BFD* – Bayes Factor Delimitation) recovered F. fragum and F. gravida as separate species. Although our results agree with depth‐related genetic structuring in F. fragum , they did not support incipient speciation of the ‘tall’ and ‘short’ morphotypes. The preferred scenario also revealed a split between two main lineages of F. gravida , one from Ascension Island and the other from Brazil. The Brazilian lineage is further divided into a species that occurs throughout the Northeastern coast and another that ranges from the Abrolhos Archipelago to the state of Espírito Santo. BFD* scenarios were corroborated by analyses of SNP matrices with varying levels of missing data and by a speciation‐based delimitation approach (DELINEATE). Our results challenge current notions about Atlantic reef corals because they uncovered surprising genetic diversity in Favia and rejected the long‐standing hypothesis that Abrolhos Archipelago may have served as a Pleistocenic refuge during the last glaciations.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Host response signature trends in persistent bacteraemia and metastatic infection due to Staphylococcus aureus and Gram-negative bacilli: a prospective multicentre observational study - Anna Maria Peri; Nastaran Rafiei; Kevin O’Callaghan; Anna Brischetto; Bianca Graves; Holly Sinclair; Matthew Eustace; Karen Lim; Jill Parkes-Smith; Adam Stewart; Natalie Davidson; Alexis Tabah; et al. (Infectious Diseases, 2024)

Ambient air pollution and rate of spontaneous abortion - Amelia K. Wesselink; Kipruto Kirwa; Perry Hystad; Joel D. Kaufman; Adam A. Szpiro; Mary D. Willis; David A. Savitz; Jonathan I. Levy; Kenneth J. Rothman; Ellen M. Mikkelsen; Anne Sofie Dam Laursen; Elizabeth E. Hatch; et al. (Environmental Research, 2024)

Corrigendum to “Impacts of environmental feedbacks on the production of a Central Queensland beef enterprise in a future climate” [Agricultural Systems 214 (2024) 1–13/103838] - Duc-Anh An-Vo; David Cobon; Jyoteshna Owens; Adam Liedloff; Tim Cowan; Scott Power (Agricultural Systems, 2024)

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Fathers’ use of social media for social comparison is associated with their food parenting practices - Amina Saher; Lisa Tang; Sabrina Douglas; Raphaëlle Jacob; Kathryn Walton; Adam Sadowski; David W.L. Ma; Jess Haines (Appetite, 2024)

Not all information is informative: An exploration of educational content on recycled potable water knowledge and acceptance - Braden Tanner; Portia McDonald; Dana Mahmoud-Elhaj; David Sabatini; Jim F. Chamberlain; Anisha Nijhawan; Eleanor Rainbolt-Forbes; Adam Feltz (Water Research, 2024)

Utility assistance and pricing structures for energy impoverished households: A review of the literature - Jeffrey A. Adams; Sanya Carley; David M. Konisky (The Electricity Journal, 2024)

Heterozygous MAP3K20 variants cause ectodermal dysplasia, craniosynostosis, sensorineural hearing loss, and limb anomalies - Daniel Brooks; Elizabeth Burke; Sukyeong Lee; Tanya N. Eble; Melanie O’Leary; Ikeoluwa Osei-Owusu; Heidi L. Rehm; Shweta U. Dhar; Lisa Emrick; David Bick; Michelle Nehrebecky; Ellen Macnamara; et al. (Human Genetics, 2024)

The role of automatic pollen and fungal spore monitoring across major end-user domains - Fiona Tummon; Beverley Adams-Groom; Célia M. Antunes; Nicolas Bruffaerts; Jeroen Buters; Paloma Cariñanos; Sevcan Celenk; Marie Choël; Bernard Clot; Antonella Cristofori; Benoît Crouzy; Athanasios Damialis; et al. (Aerobiologia, 2024)
The advent of automatic pollen and fungal spore monitoring over the past few years has brought about a paradigm change. The provision of real-time information at high temporal resolution opens the door to a wide range of improvements in terms of the products and services made available to a widening range of end-users and stakeholders. As technology and methods mature, it is essential to properly quantify the impact automatic monitoring has on the different end-user domains to better understand the real long-term benefits to society. In this paper, we focus the main domains where such impacts are expected, using Europe as a basis to provide qualitative estimates and to describe research needs to better quantify impacts in future. This will, in part, also serve to justify further investment and help to expand monitoring networks.

Automatic detection of airborne pollen: an overview - Jeroen Buters; Bernard Clot; Carmen Galán; Regula Gehrig; Stefan Gilge; François Hentges; David O’Connor; Branko Sikoparija; Carsten Skjoth; Fiona Tummon; Beverley Adams-Groom; Célia M. Antunes; et al. (Aerobiologia, 2024)
Pollen monitoring has traditionally been carried out using manual methods first developed in the early 1950s. Although this technique has been recently standardised, it suffers from several drawbacks, notably data usually only being available with a delay of 3–9 days and usually delivered at a daily resolution. Several automatic instruments have come on to the market over the past few years, with more new devices also under development. This paper provides a comprehensive overview of all available and developing automatic instruments, how they measure, how they identify airborne pollen, what impacts measurement quality, as well as what potential there is for further advancement in the field of bioaerosol monitoring.

Shallow carbonate geochemistry in the Bahamas since the last interglacial period - Stacey Edmonsond; Matthew D. Nadeau; Andrew C. Turner; Ziman Wu; Emily C. Geyman; Anne-Sofie C. Ahm; Blake Dyer; Sergey Oleynik; David McGee; Daniel A. Stolper; John A. Higgins; Adam C. Maloof (Earth and Planetary Science Letters, 2024)

Groundwater quality status in the Division of Fitri (Chad) - Atteib Adam Baye; Suzanne Ngo Boum-Nkot; Mohammad Bello; Bertil Nlend; Boris Djieugoue; Fricelle Song; David Komba; Djibrine Adoum Oumar; Jacques Etame (Sustainable Water Resources Management, 2024)

Impacts of environmental feedbacks on the production of a Central Queensland beef enterprise in a future climate - Duc-Anh An-Vo; David Cobon; Jo Owens; Adam Liedloff; Tim Cowan; Scott Power (Agricultural Systems, 2024)

How to cross the desert if you are small and need mountains? Out‐of‐Ethiopia dispersal in Afromontane shrews - Malahat Dianat; Adam Konečný; Leonid A. Lavrenchenko; Julian C. Kerbis Peterhans; Terrence C. Demos; Violaine Nicolas; David Ortiz; Josef Bryja (Journal of Biogeography, 2024)
Aim The Eastern Afromontane Biodiversity Hotspot (EABH) offers an ideal location to investigate the evolutionary mechanisms producing a high level of endemic biodiversity. We tested the hypothesis that the cradle of Eastern Afromontane diversity is in the largest sub‐region of the EABH montane archipelago, that is the Ethiopian Highlands. Further, we expected that climate oscillations followed by elevational shifts in montane habitats facilitated the dispersal of small mammal populations across unsuitable arid lowlands. Location Mountains and highlands of East Africa. Taxon Shrews of the genus Crocidura (Eastern Afromontane phylogenetic clade). Methods We collected comprehensive genetic data from 511 (mitochondrial gene for cytochrome b ) and 147 (double digest Restriction‐Associated DNA sequencing) samples of Crocidura shrews across the EABH. We estimated phylogenetic relationships with Bayesian and Maximum Likelihood approaches. Population genetic analyses were performed in STRUCTURE to evaluate the internal structure of species outside Ethiopia. Ancestral area and dispersal routes were analysed by the BioGeoBears package. Results Six major phylogenomic clades were delimited based on concatenated nuclear loci. The mitochondrial phylogeny roughly matches nuclear phylogenies, but with poorer resolution. Five of the six revealed clades are restricted to the Ethiopian Highlands, which is unambiguously the cradle of the diversity of this group of mammals (also confirmed by the biogeographic analysis). All non‐Ethiopian and a single Ethiopian species fall into the sixth clade with poorly resolved internal relationships. Detailed population genetic analysis of SNP data revealed a pronounced structure with multiple gene pools in this clade; however, this structure only partly corresponds with the current taxonomy. Main Conclusions Eastern Afromontane Crocidura shrews originated in the Ethiopian Highlands. They radiated there, and through a single southward dispersal event across the Turkana depression, they colonised the rest of the EABH in response to diverse geomorphology and climatic changes during the Plio‐Pleistocene.

Illegal incidents and violations related to Atlantic salmon fishing in Newfoundland and Labrador, Canada, during 2001–2020 - Travis E. Van Leeuwen; David Cote; Sarah J. Lehnert; Sky Ann Lewis; Daryl Walsh; Kerry Bungay; Nicholas I. Kelly; Jason McGinn; Blair Adams; J. Brian Dempson (Fisheries Management and Ecology, 2024)
Resource user compliance is a key element in effective fisheries management. Herein, we examine two decades of enforcement records pertaining to Atlantic salmon from Newfoundland and Labrador, Canada. Illegal incidents were negatively correlated with the number of licensed anglers but not salmon abundance. Over two decades, illegal incidents declined by 66%, even after correcting for the positive relationship between enforcement effort and illegal incidents. This decline was primarily driven by a 67% reduction in netting and jigging‐related violations, which were likely to impose the highest levels of mortality on adult salmon among violations examined. Additionally, illegal incidents and violation types did not increase as a result of management changes. While Newfoundland and Labrador remains one of the last strongholds for Atlantic salmon, we encourage other jurisdictions to monitor fisheries compliance to better understand the social‐ecological landscape that is crucial to supporting healthy fisheries.

Degradation kinetics of veterinary antibiotics and estrogenic hormones in a claypan soil - Adam H. Moody; Robert N. Lerch; Keith W. Goyne; Stephen H. Anderson; David G. Mendoza-Cózatl; David A. Alvarez (Chemosphere, 2024)

Use of a commercial oral moxidectin plus praziquantel combination for treatment of the respiratory nematode Crenosoma striatum in rescued Southern white-breasted hedgehogs (Erinaceus concolor) - Nitzan Adam; David Eshar (Journal of Exotic Pet Medicine, 2024)

Sustainable pathways to oxicams via heterogeneous biosourced catalysts - Recyclable and reusable materials - Christophe Waterlot; Alina Ghinet; Pierrick Dufrénoy; Marie Hechelski; Adam Daïch; Damien Betrancourt; David Bulteel (Journal of Cleaner Production, 2024)

Migration patterns and navigation cues of Atlantic salmon post‐smolts migrating from 12 rivers through the coastal zones around the Irish Sea - Jessie Lilly; Hannele H. Honkanen; Jessica R. Rodger; Diego del Villar; Patrick Boylan; Amy Green; Diego Pereiro; Lorna Wilkie; Richard Kennedy; Andrea Barkley; Robert Rosell; Niall Ó. Maoiléidigh; et al. (Journal of Fish Biology, 2024)
The freshwater phase of the first seaward migration of juvenile Atlantic salmon ( Salmo salar ) is relatively well understood when compared with our understanding of the marine phase of their migration. In 2021, 1008 wild and 60 ranched Atlantic salmon smolts were tagged with acoustic transmitters in 12 rivers in England, Scotland, Northern Ireland and Ireland. Large marine receiver arrays were deployed in the Irish Sea at two locations: at the transition of the Irish Sea into the North Atlantic between Ireland and Scotland, and between southern Scotland and Northern Ireland, to examine the early phase of the marine migration of Atlantic salmon smolts. After leaving their natal rivers' post‐smolt migration through the Irish Sea was rapid with minimum speeds ranging from 14.03 to 38.56 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal river, to 9.69–39.94 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal estuary. Population minimum migration success through the study area was strongly correlated with the distance of travel, populations further away from the point of entry to the open North Atlantic exhibited lower migration success. Post‐smolts from different populations experienced different water temperatures on entering the North Atlantic. This was largely driven by the timing of their migration and may have significant consequences for feeding and ultimately survivorship. The influence of water currents on post‐smolt movement was investigated using data from previously constructed numerical hydrodynamic models. Modeled water current data in the northern Irish Sea showed that post‐smolts had a strong preference for migrating when the current direction was at around 283° (west‐north‐west) but did not migrate when exposed to strong currents in other directions. This is the most favorable direction for onward passage from the Irish Sea to the continental shelf edge current, a known accumulation point for migrating post‐smolts. These results strongly indicate that post‐smolts migrating through the coastal marine environment are: (1) not simply migrating by current following (2) engage in active directional swimming (3) have an intrinsic sense of their migration direction and (4) can use cues other than water current direction to orientate during this part of their migration.

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Astaxanthin and meclizine extend lifespan in UM-HET3 male mice; fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate do not significantly affect lifespan in either sex at the doses and schedules used - David E. Harrison; Randy Strong; Peter Reifsnyder; Nadia Rosenthal; Ron Korstanje; Elizabeth Fernandez; Kevin Flurkey; Brett C. Ginsburg; Meredith D. Murrell; Martin A. Javors; Marisa Lopez-Cruzan; James F. Nelson; et al. (GeroScience, 2023)
In genetically heterogeneous (UM-HET3) mice produced by the CByB6F1 × C3D2F1 cross, the Nrf2 activator astaxanthin (Asta) extended the median male lifespan by 12% ( p = 0.003, log-rank test), while meclizine (Mec), an mTORC1 inhibitor, extended the male lifespan by 8% ( p = 0.03). Asta was fed at 1840 ± 520 (9) ppm and Mec at 544 ± 48 (9) ppm, stated as mean ± SE ( n ) of independent diet preparations. Both were started at 12 months of age. The 90th percentile lifespan for both treatments was extended in absolute value by 6% in males, but neither was significant by the Wang–Allison test. Five other new agents were also tested as follows: fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate. None of these increased lifespan significantly at the dose and method of administration tested in either sex. Amounts of dimethyl fumarate in the diet averaged 35% of the target dose, which may explain the absence of lifespan effects. Body weight was not significantly affected in males by any of the test agents. Late life weights were lower in females fed Asta and Mec, but lifespan was not significantly affected in these females. The male-specific lifespan benefits from Asta and Mec may provide insights into sex-specific aspects of aging.

Thirty-five-year timber harvesting disturbance effects on composition and biomass of tupelo-cypress (Nyssa-Taxodium) forested wetlands, southwest Alabama, USA - Cora Every; W. Michael Aust; David R. Carter; T. Adam Coates; Erik B. Schilling (Wetlands, 2023)

Improved net carbon budgets in the US Midwest through direct measured impacts of enhanced weathering - Ilsa B. Kantola; Elena Blanc‐Betes; Michael D. Masters; Elliot Chang; Alison Marklein; Caitlin E. Moore; Adam von Haden; Carl J. Bernacchi; Adam Wolf; Dimitar Z. Epihov; David J. Beerling; Evan H. DeLucia (Global Change Biology, 2023)
Terrestrial enhanced weathering (EW) through the application of Mg‐ or Ca‐rich rock dust to soil is a negative emission technology with the potential to address impacts of climate change. The effectiveness of EW was tested over 4 years by spreading ground basalt (50 t ha −1 year −1 ) on maize/soybean and miscanthus cropping systems in the Midwest US. The major elements of the carbon budget were quantified through measurements of eddy covariance, soil carbon flux, and biomass. The movement of Mg and Ca to deep soil, released by weathering, balanced by a corresponding alkalinity flux, was used to measure the drawdown of CO 2 , where the release of cations from basalt was measured as the ratio of rare earth elements to base cations in the applied rock dust and in the surface soil. Basalt application stimulated peak biomass and net primary production in both cropping systems and caused a small but significant stimulation of soil respiration. Net ecosystem carbon balance (NECB) was strongly negative for maize/soybean (−199 to −453 g C m −2 year −1 ) indicating this system was losing carbon to the atmosphere. Average EW (102 g C m −2 year −1 ) offset carbon loss in the maize/soybean by 23%–42%. NECB of miscanthus was positive (63–129 g C m −2 year −1 ), indicating carbon gain in the system, and EW greatly increased inorganic carbon storage by an additional 234 g C m −2 year −1 . Our analysis indicates a co‐deployment of a perennial biofuel crop (miscanthus) with EW leads to major wins—increased harvested yields of 29%–42% with additional carbon dioxide removal (CDR) of 8.6 t CO 2 ha −1 year −1 . EW applied to maize/soybean drives a CDR of 3.7 t CO 2 ha −1 year −1 , which partially offsets well‐established carbon losses from soil from this crop rotation. EW applied in the US Midwest creates measurable improvements to the carbon budgets perennial bioenergy crops and conventional row crops.

Ocean Color Image Sequences Reveal Diurnal Changes in Water Column Stability Driven by Air–Sea Interactions - Jason K. Jolliff; Travis A. Smith; Sherwin Ladner; Ewa Jarosz; Mark David Lewis; Stephanie Anderson; Sean McCarthy; Adam Lawson (Journal of Marine Science and Engineering, 2023)
The southward propagation of cold-air frontal boundaries into the Gulf of Mexico region initiates a cascade of coupled air–sea processes that manifests along the coastlines as an apparent brightness anomaly in the ocean color signals. Our hypothesis is that the color anomaly is largely due to the turbulent resuspension of sedimentary particles. Initially, there is significant wind-driven ocean turbulence as the frontal boundary passes, followed by the potential for sustained convective instability due to significant heat losses from the ocean surface. These cold front events occur during boreal autumn, winter, and into early spring, and the latter episodes occur in the context of the seasonally recurring thermal stratification of shelf waters. Here, we show that as stratification reasserts thermal stability in the waning days of a cold front episode, daily to hourly ocean color patterns are temporally coherent with the air–sea heat flux changes and the resulting impact on water column stability. Concomitant results from a nested, data-assimilative, and two-way coupled ocean-atmosphere numerical modeling system provides both corroboration and insight into how surface air–sea fluxes and in-water turbulent mixing manifest as hourly changes in apparent surface water turbidity due to the potential excitation and settling of reflective particles. A simple model of particle mixing and settling driven by the simulated turbulence mimics patterns seen in the satellite image sequences. This study offers a preview of potential application areas that may emerge following the launch of a dedicated ocean color geostationary sensor.

Designing an automatic pollen monitoring network for direct usage of observations to reconstruct the concentration fields - Mikhail Sofiev; Jeroen Buters; Fiona Tummon; Yalda Fatahi; Olga Sozinova; Beverley Adams-Groom; Karl Christian Bergmann; Åslög Dahl; Regula Gehrig; Stefan Gilge; Andrea Kofol Seliger; Rostislav Kouznetsov; et al. (Science of The Total Environment, 2023)

Can low-input agriculture in semi-arid Burkina Faso feed its soil, livestock and people? - Gildas G.C. Assogba; David Berre; Myriam Adam; Katrien Descheemaeker (European Journal of Agronomy, 2023)

Immune markers in goats selected for reduced gastrointestinal nematode egg count under artificial infection conditions - David McBean; Adam Hayward; Keith Ballingall; Frank Jackson; Tom McNeilly (Veterinary Parasitology, 2023)

Hepatic phytotoxins in herbal medicines: A review of Africa's pyrrolizidine alkaloid-containing plants, their traditional uses, contamination pathways and associated health risks - Emmanuel Letsyo; John Dzikunoo; Courage Sedem Dzah; Zeenatu Suglo Adams; David Asante-Donyinah (South African Journal of Botany, 2023)

When are environmental DNA early detections of invasive species actionable? - Adam J. Sepulveda; Christine E. Dumoulin; Denise L. Blanchette; John McPhedran; Colin Holme; Nathan Whalen; Margaret E. Hunter; Christopher M. Merkes; Catherine A. Richter; Matthew E. Neilson; Wesley M. Daniel; Devin N. Jones; et al. (Journal of Environmental Management, 2023)

Peatland gully restoration with stone and timber dams (Kinder Plateau, UK) - Tim Howson; Martin Evans; Tim Allott; Emma Shuttleworth; Adam Johnston; Joe Rees; David Milledge; Donald Edokpa; Chris Lockyer; Martin Kay; Tom Spencer; David Brown; et al. (Ecological Engineering, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Mercury in Neotropical birds: a synthesis and prospectus on 13 years of exposure data - Christopher J. Sayers; David C. Evers; Viviana Ruiz-Gutierrez; Evan Adams; Claudia M. Vega; Jessica N. Pisconte; Vania Tejeda; Kevin Regan; Oksana P. Lane; Abidas A. Ash; Reynold Cal; Stevan Reneau; et al. (Ecotoxicology, 2023)
Environmental mercury (Hg) contamination of the global tropics outpaces our understanding of its consequences for biodiversity. Knowledge gaps of pollution exposure could obscure conservation threats in the Neotropics: a region that supports over half of the world’s species, but faces ongoing land-use change and Hg emission via artisanal and small-scale gold mining (ASGM). Due to their global distribution and sensitivity to pollution, birds provide a valuable opportunity as bioindicators to assess how accelerating Hg emissions impact an ecosystem’s ability to support biodiversity, and ultimately, global health. We present the largest database on Neotropical bird Hg concentrations ( n = 2316) and establish exposure baselines for 322 bird species spanning nine countries across Central America, South America, and the West Indies. Patterns of avian Hg exposure in the Neotropics broadly align with those in temperate regions: consistent bioaccumulation across functional groups and high spatiotemporal variation. Bird species occupying higher trophic positions and aquatic habitats exhibited elevated Hg concentrations that have been previously associated with reductions in reproductive success. Notably, bird Hg concentrations were over four times higher at sites impacted by ASGM activities and differed by season for certain trophic niches. We developed this synthesis via a collaborative research network, the Tropical Research for Avian Conservation and Ecotoxicology (TRACE) Initiative, which exemplifies inclusive, equitable, and international data-sharing. While our findings signal an urgent need to assess sampling biases, mechanisms, and consequences of Hg exposure to tropical avian communities, the TRACE Initiative provides a meaningful framework to achieve such goals. Ultimately, our collective efforts support and inform local, scientific, and government entities, including Parties of the United Nations Minamata Convention on Mercury, as we continue working together to understand how Hg pollution impacts biodiversity conservation, ecosystem function, and public health in the tropics.

Distribution and trends of mercury in aquatic and terrestrial biota of New York, USA: a synthesis of 50 years of research and monitoring - Evan M. Adams; Julia E. Gulka; Yang Yang; Mark E. H. Burton; Douglas A. Burns; Valerie Buxton; Lisa Cleckner; Christopher R. DeSorbo; Charles T. Driscoll; David C. Evers; Nicholas Fisher; Oksana Lane; et al. (Ecotoxicology, 2023)

BioDeepTime: A database of biodiversity time series for modern and fossil assemblages - Jansen Smith; Marina C. Rillo; Ádám T. Kocsis; Maria Dornelas; David Fastovich; Huai‐Hsuan M. Huang; Lukas Jonkers; Wolfgang Kiessling; Qijian Li; Lee Hsiang Liow; Miranda Margulis‐Ohnuma; Stephen Meyers; et al. (Global Ecology and Biogeography, 2023)
Motivation We have little understanding of how communities respond to varying magnitudes and rates of environmental perturbations across temporal scales. BioDeepTime harmonizes assemblage time series of presence and abundance data to help facilitate investigations of community dynamics across timescales and the response of communities to natural and anthropogenic stressors. BioDeepTime includes time series of terrestrial and aquatic assemblages of varying spatial and temporal grain and extent from the present‐day to millions of years ago. Main Types of Variables Included BioDeepTime currently contains 7,437,847 taxon records from 10,062 assemblage time series, each with a minimum of 10 time steps. Age constraints, sampling method, environment and taxonomic scope are provided for each time series. Spatial Location and Grain The database includes 8752 unique sampling locations from freshwater, marine and terrestrial ecosystems. Spatial grain represented by individual samples varies from quadrats on the order of several cm 2 to grid cells of ~100 km 2 . Time Period and Grain BioDeepTime in aggregate currently spans the last 451 million years, with the 10,062 modern and fossil assemblage time series ranging in extent from years to millions of years. The median extent of modern time series is 18.7 years and for fossil series is 54,872 years. Temporal grain, the time encompassed by individual samples, ranges from days to tens of thousands of years. Major Taxa and Level of Measurement The database contains information on 28,777 unique taxa with 4,769,789 records at the species level and another 271,218 records known to the genus level, including time series of benthic and planktonic foraminifera, coccolithophores, diatoms, ostracods, plants (pollen), radiolarians and other invertebrates and vertebrates. There are to date 7012 modern and 3050 fossil time series in BioDeepTime. Software Format SQLite, Comma‐separated values.

Changes in oral health during aging in a novel non-human primate model - Parveez Ahamed Abdul-Azees; Hanzhou Wang; Yong-Hee P. Chun; Jason Pizzini; David D. Dean; Kelly R. Reveles; Milos Marinkovic; Xiao-Dong Chen; Adam B. Salmon; Chih-Ko Yeh (GeroScience, 2023)

Exposome and unhealthy aging: environmental drivers from air pollution to occupational exposures - Tamas Pandics; David Major; Vince Fazekas-Pongor; Zsofia Szarvas; Anna Peterfi; Peter Mukli; Rafal Gulej; Anna Ungvari; Monika Fekete; Anna Tompa; Stefano Tarantini; Andriy Yabluchanskiy; et al. (GeroScience, 2023)
The aging population worldwide is facing a significant increase in age-related non-communicable diseases, including cardiovascular and brain pathologies. This comprehensive review paper delves into the impact of the exposome, which encompasses the totality of environmental exposures, on unhealthy aging. It explores how environmental factors contribute to the acceleration of aging processes, increase biological age, and facilitate the development and progression of a wide range of age-associated diseases. The impact of environmental factors on cognitive health and the development of chronic age-related diseases affecting the cardiovascular system and central nervous system is discussed, with a specific focus on Alzheimer’s disease, Parkinson’s disease, stroke, small vessel disease, and vascular cognitive impairment (VCI). Aging is a major risk factor for these diseases. Their pathogenesis involves cellular and molecular mechanisms of aging such as increased oxidative stress, impaired mitochondrial function, DNA damage, and inflammation and is influenced by environmental factors. Environmental toxicants, including ambient particulate matter, pesticides, heavy metals, and organic solvents, have been identified as significant contributors to cardiovascular and brain aging disorders. These toxicants can inflict both macro- and microvascular damage and many of them can also cross the blood–brain barrier, inducing neurotoxic effects, neuroinflammation, and neuronal dysfunction. In conclusion, environmental factors play a critical role in modulating cardiovascular and brain aging. A deeper understanding of how environmental toxicants exacerbate aging processes and contribute to the pathogenesis of neurodegenerative diseases, VCI, and dementia is crucial for the development of preventive strategies and interventions to promote cardiovascular, cerebrovascular, and brain health. By mitigating exposure to harmful environmental factors and promoting healthy aging, we can strive to reduce the burden of age-related cardiovascular and brain pathologies in the aging population.

Patterns and drivers of macroalgal ‘blue carbon’ transport and deposition in near-shore coastal environments - Erlania; Alecia Bellgrove; Peter I. Macreadie; Mary A. Young; Owen J. Holland; Zach Clark; Daniel Ierodiaconou; Rafael C. Carvalho; David Kennedy; Adam D. Miller (Science of The Total Environment, 2023)

The effect of terrain-influenced winds on fire spread in QUIC-Fire - David Robinson; Sara Brambilla; Julia Oliveto; Michael J. Brown; Adam Atchley; Rodman R. Linn (Environmental Modelling & Software, 2023)

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

Loss of the large conductance calcium-activated potassium channel causes an increase in mitochondrial reactive oxygen species in glioblastoma cells - Bogusz Kulawiak; Monika Żochowska; Piotr Bednarczyk; Andrzej Galuba; David A. Stroud; Adam Szewczyk (Pflügers Archiv - European Journal of Physiology, 2023)
Mitochondrial potassium (mitoK) channels play an important role in cellular physiology. These channels are expressed in healthy tissues and cancer cells. Activation of mitoK channels can protect neurons and cardiac tissue against injury induced by ischemia–reperfusion. In cancer cells, inhibition of mitoK channels leads to an increase in mitochondrial reactive oxygen species, which leads to cell death. In glioma cell activity of the mitochondrial, large conductance calcium-activated potassium (mitoBK Ca ) channel is regulated by the mitochondrial respiratory chain. In our project, we used CRISPR/Cas9 technology in human glioblastoma U-87 MG cells to generate knockout cell lines lacking the α-subunit of the BK Ca channel encoded by the KCNMA1 gene, which also encodes cardiac mitoBK Ca . Mitochondrial patch-clamp experiments showed the absence of an active mitoBK Ca channel in knockout cells. Additionally, the absence of this channel resulted in increased levels of mitochondrial reactive oxygen species. However, analysis of the mitochondrial respiration rate did not show significant changes in oxygen consumption in the cell lines lacking BK Ca channels compared to the wild-type U-87 MG cell line. These observations were reflected in the expression levels of selected mitochondrial genes, organization of the respiratory chain, and mitochondrial morphology, which did not show significant differences between the analyzed cell lines. In conclusion, we show that in U-87 MG cells, the pore-forming subunit of the mitoBK Ca channel is encoded by the KCNMA1 gene. Additionally, the presence of this channel is important for the regulation of reactive oxygen species levels in mitochondria.

Parasite manipulation of host phenotypes inferred from transcriptional analyses in a trematode‐amphipod system - David M. Rand; Joaquin C. B. Nunez; Shawn Williams; Stephen Rong; John T. Burley; Kimberly B. Neil; Adam N. Spierer; Wilson McKerrow; David S. Johnson; Yevgeniy Raynes; Thomas J. Fayton; Nicholas Skvir; et al. (Molecular Ecology, 2023)
Manipulation of host phenotypes by parasites is hypothesized to be an adaptive strategy enhancing parasite transmission across hosts and generations. Characterizing the molecular mechanisms of manipulation is important to advance our understanding of host–parasite coevolution. The trematode ( Levinseniella byrdi ) is known to alter the colour and behaviour of its amphipod host ( Orchestia grillus ) presumably increasing predation of amphipods which enhances trematode transmission through its life cycle. We sampled 24 infected and 24 uninfected amphipods from a salt marsh in Massachusetts to perform differential gene expression analysis. In addition, we constructed novel genomic tools for O. grillus including a de novo genome and transcriptome. We discovered that trematode infection results in upregulation of amphipod transcripts associated with pigmentation and detection of external stimuli, and downregulation of multiple amphipod transcripts implicated in invertebrate immune responses, such as vacuolar ATPase genes. We hypothesize that suppression of immune genes and the altered expression of genes associated with coloration and behaviour may allow the trematode to persist in the amphipod and engage in further biochemical manipulation that promotes transmission. The genomic tools and transcriptomic analyses reported provide new opportunities to discover how parasites alter diverse pathways underlying host phenotypic changes in natural populations.

Proteomic changes induced by longevity-promoting interventions in mice - Adam R. Burns; Jack Wiedrick; Alicia Feryn; Michal Maes; Mukul K. Midha; David H. Baxter; Seamus R. Morrone; Timothy J. Prokop; Charu Kapil; Michael R. Hoopmann; Ulrike Kusebauch; Eric W. Deutsch; et al. (GeroScience, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Evidence of population-level impacts and resiliency for Gulf of Mexico shelf taxa following the Deepwater Horizon oil spill - William F. Patterson; Kelly Lynn Robinson; Beverly K. Barnett; Matthew D. Campbell; David C. Chagaris; Jeffrey P. Chanton; Kendra L. Daly; David S. Hanisko; Frank J. Hernandez; Steven A. Murawski; Adam G. Pollack; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The goal of this paper was to review the evidence of population-level impacts of the Deepwater Horizon Oil Spill (DWH) on Gulf of Mexico (GOM) continental shelf taxa, as well as evidence of resiliency following the DWH. There is considerable environmental and biological evidence that GOM shelf taxa were exposed to and suffered direct and indirect impacts of the DWH. Numerous assessments, from mesocosm studies to analysis of biopsied tissue or tissue samples from necropsied animals, revealed a constellation of physiological effects related to DWH impacts on GOM biota, some of which clearly or likely resulted in mortality. While the estimated concentrations of hydrocarbons in shelf waters and sediments were orders of magnitude lower than measured in inshore or deep GOM environments, the level of mortality observed or predicted was substantial for many shelf taxa. In some cases, such as for zooplankton, community shifts following the spill were ephemeral, likely reflecting high rates of population turnover and productivity. In other taxa, such as GOM reef fishes, impacts of the spill are confounded with other stressors, such as fishing mortality or the appearance and rapid population growth of invasive lionfish ( Pterois spp.). In yet others, such as cetaceans, modeling efforts to predict population-level effects of the DWH made conservative assumptions given the species’ protected status, which post-DWH population assessments either failed to detect or population increases were estimated. A persistent theme that emerged was the lack of precise population-level data or assessments prior to the DWH for many taxa, but even when data or assessments did exist, examining evidence of population resiliency was confounded by other stressors impacting GOM biota. Unless efforts are made to increase the resolution of the data or precision of population assessments, difficulties will likely remain in estimating the scale of population-level effects or resiliency in the case of future large-scale environmental catastrophes.

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

Head Start’s Role in Addressing Food and Nutrition Insecurity: Focus Group Findings - Shani A. Jones; David G. Schlundt; Kemberlee R. Bonnet; Laura E. Adams; Filoteia Popescu; Margaret R. Mahoney; Shari L. Barkin (Journal of Nutrition Education and Behavior, 2023)

Evaluation of approaches to recruitment of racially and ethnically diverse breast cancer patients from an integrated health care setting for collection of observational social network data - Candyce H. Kroenke; Elaine Kurtovich; Rhonda Aoki; Veronica C. Shim; Tracy D. Chan; Leslie Manace Brenman; Jane Bethard-Tracy; Alyce S. Adams; David P. Kennedy (Cancer Causes & Control, 2023)

The ecological causes of functional distinctiveness in communities - François Munoz; Christopher A. Klausmeier; Pierre Gaüzère; Gaurav Kandlikar; Elena Litchman; Nicolas Mouquet; Annette Ostling; Wilfried Thuiller; Adam C. Algar; Arnaud Auber; Marc W. Cadotte; Léo Delalandre; et al. (Ecology Letters, 2023)
Recent work has shown that evaluating functional trait distinctiveness, the average trait distance of a species to other species in a community offers promising insights into biodiversity dynamics and ecosystem functioning. However, the ecological mechanisms underlying the emergence and persistence of functionally distinct species are poorly understood. Here, we address the issue by considering a heterogeneous fitness landscape whereby functional dimensions encompass peaks representing trait combinations yielding positive population growth rates in a community. We identify four ecological cases contributing to the emergence and persistence of functionally distinct species. First, environmental heterogeneity or alternative phenotypic designs can drive positive population growth of functionally distinct species. Second, sink populations with negative population growth can deviate from local fitness peaks and be functionally distinct. Third, species found at the margin of the fitness landscape can persist but be functionally distinct. Fourth, biotic interactions (positive or negative) can dynamically alter the fitness landscape. We offer examples of these four cases and guidelines to distinguish between them. In addition to these deterministic processes, we explore how stochastic dispersal limitation can yield functional distinctiveness. Our framework offers a novel perspective on the relationship between fitness landscape heterogeneity and the functional composition of ecological assemblages.

Associations between physical exercise type, fluid intelligence, executive function, and processing speed in the oldest-old (85 +) - Brian Duy Ho; Joseph M. Gullett; Stephen Anton; Mary Kathryn Franchetti; Pradyumna K. Bharadwaj; David A. Raichlen; Gene E. Alexander; Tatjana Rundek; Bonnie Levin; Kristina Visscher; Adam J. Woods; Ronald A. Cohen (GeroScience, 2023)

Toward more rigorous and informative nutritional epidemiology: The rational space between dismissal and defense of the status quo - Andrew W. Brown; Stella Aslibekyan; Dennis Bier; Rafael Ferreira da Silva; Adam Hoover; David M. Klurfeld; Eric Loken; Evan Mayo-Wilson; Nir Menachemi; Greg Pavela; Patrick D. Quinn; Dale Schoeller; et al. (Critical Reviews in Food Science and Nutrition, 2023)

A Global Review of Catch Efficiencies of Towed Fishing Gears Targeting Scallops - Adam J. Delargy; Lynda Blackadder; Isobel Bloor; Carrie McMinn; David B. Rudders; Claire L. Szostek; Helen Dobby; Mervi Kangas; Bryce D. Stewart; James R. Williams; Kevin D.E. Stokesbury (Reviews in Fisheries Science & Aquaculture, 2023)

Age, Growth and Maturity of the Bonnethead Sphyrna tiburo in the U.S. Gulf of Mexico - Bryan S. Frazier; Elizabeth A. Vinyard; Andrew T. Fields; William B. Driggers; R. Dean Grubbs; Douglas H. Adams; J. Marcus Drymon; Jayne M. Gardiner; Jill M. Hendon; Eric Hoffmayer; Robert E. Hueter; R. J. David Wells; et al. (Environmental Biology of Fishes, 2023)

Isotopic life‐history signatures are retained in modern and ancient Atlantic bluefin tuna vertebrae - Adam J. Andrews; David Orton; Vedat Onar; Piero Addis; Fausto Tinti; Michelle Alexander (Journal of Fish Biology, 2023)
Isotopic, tagging and diet studies of modern‐day teleosts lacked the ability to contextualise life‐history and trophic dynamics with a historical perspective, when exploitation rates were lower and climatic conditions differed. Isotopic analysis of vertebrae, the most plentiful hard‐part in archaeological and museum collections, can potentially fill this data‐gap. Chemical signatures of habitat and diet use during growth are retained by vertebrae during bone formation. Nonetheless, to fulfil their potential to reveal life‐history and trophic dynamics, we need a better understanding of the time frame recorded by vertebrae, currently lacking due to a poor understanding of fish bone remodelling. To address this issue, the authors serially‐sectioned four vertebral centra of the highly migratory Atlantic bluefin tuna ( Thunnus thynnus ; BFT) captured off Sardinia (Italy) and analysed their isotopic composition. They show how carbon (δ 13 C), nitrogen (δ 15 N) and sulphur (δ 34 S) isotope values can vary significantly across BFT vertebrae growth‐axes, revealing patterning in dietary life histories. Further, they find that similar patterns are revealed through incremental isotopic analysis of inner and outer vertebrae centra samples from 13 archaeological BFT vertebrae dating between the 9th and13th centuries CE. The results indicate that multi‐year foraging signatures are retained in vertebrae and allow for the study of life histories in both modern and paleo‐environments. These novel methods can be extended across teleost taxa owing to their potential to inform management and conservation on how teleost trophic dynamics change over time and what their long‐term environmental, ecological and anthropological drivers are.

Integrated field, model, and theoretical advances inform a predictive understanding of transport and transformation in the critical zone - Joel Singley; Martin Briggs; Beth Hoagland; Rachel Lauer; Jessie Meeks; Aaron B. Regberg; David M. Rey; Kenny Swift Bird; Adam S. Ward (Journal of Hydrology, 2023)

Long-range transport and deposition on the Arctic snowpack of nuclear contaminated particulate matter - David Cappelletti; Žilvinas Ežerinskis; Justina Šapolaitė; Laurynas Bučinskas; Bartłomiej Luks; Adam Nawrot; Catherine Larose; Paolo Tuccella; Jean Charles Gallet; Stefano Crocchianti; Federica Bruschi; Beatrice Moroni; et al. (Journal of Hazardous Materials, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Topography Mediates the Response of Soil CO2 Efflux to Precipitation Over Days, Seasons, and Years - Marissa Kopp; Jason Kaye; Yuting He Smeglin; Thomas Adams; Edward J. Primka; Brosi Bradley; Yuning Shi; David Eissenstat (Ecosystems, 2023)

Spatial insurance against a heatwave differs between trophic levels in experimental aquatic communities - Csaba F. Vad; Anett Hanny‐Endrédi; Pavel Kratina; András Abonyi; Ekaterina Mironova; David S. Murray; Larysa Samchyshyna; Ioannis Tsakalakis; Evangelia Smeti; Sofie Spatharis; Hanrong Tan; Christian Preiler; et al. (Global Change Biology, 2023)
Climate change‐related heatwaves are major threats to biodiversity and ecosystem functioning. However, our current understanding of the mechanisms governing community resistance to and recovery from extreme temperature events is still rudimentary. The spatial insurance hypothesis postulates that diverse regional species pools can buffer ecosystem functioning against local disturbances through the immigration of better‐adapted taxa. Yet, experimental evidence for such predictions from multi‐trophic communities and pulse‐type disturbances, like heatwaves, is largely missing. We performed an experimental mesocosm study to test whether species dispersal from natural lakes prior to a simulated heatwave could increase the resistance and recovery of plankton communities. As the buffering effect of dispersal may differ among trophic groups, we independently manipulated the dispersal of organisms from lower (phytoplankton) and higher (zooplankton) trophic levels. The experimental heatwave suppressed total community biomass by having a strong negative effect on zooplankton biomass, probably due to a heat‐induced increase in metabolic costs, resulting in weaker top‐down control on phytoplankton. While zooplankton dispersal did not alleviate the negative heatwave effects on zooplankton biomass, phytoplankton dispersal enhanced biomass recovery at the level of primary producers, providing partial evidence for spatial insurance. The differential responses to dispersal may be linked to the much larger regional species pool of phytoplankton than of zooplankton. Our results suggest high recovery capacity of community biomass independent of dispersal. However, community composition and trophic structure remained altered due to the heatwave, implying longer‐lasting changes in ecosystem functioning.

Best practices for operating underwater gliders in Atlantic Canada - Nicolai von Oppeln-Bronikowski; Brad de Young; Melany Belzile; Adam Comeau; Frédéric Cyr; Richard Davis; Pamela Emery; Clark Richards; David Hebert; Jude Van Der Meer (Frontiers in Marine Science, 2023)
Ocean gliders are versatile tools for making ocean observations. This paper summarizes the experience, of nearly two decades, of glider observing activity in Atlantic Canada. It reviews key considerations for operating gliders based on the experience and the lessons learned. This paper has three main goals: 1. To provide new and emerging glider users with guidance and considerations for developing a glider program. 2. Review the literature on sensor development for gliders and the use of gliders. 3. To highlight different mission scenarios that include enough practical considerations to support operating gliders. The use of gliders is rapidly expanding, but the documentation and consolidation of best practices for their operational use in Atlantic Canada remains underdeveloped. This summary provides a guide that should be helpful both to new and experienced glider operators and potential users, to observe the oceanography of this region and addresses regional challenges. We believe documenting our experience will be also helpful to the global glider community. We summarize the most critical considerations of utilizing gliders. We review the issues specific to the platform use and concerns about how to optimize the use of key sensors to contribute to an oceanographic observing program.

Mooring tension assessment of a single line kelp farm with quantified biomass, waves, and currents - David W. Fredriksson; Adam T. St. Gelais; Tobias Dewhurst; Struan Coleman; Damian C. Brady; Barry Antonio Costa-Pierce (Frontiers in Marine Science, 2023)
While the number of kelp farms have steadily increased, few have been deployed with sensors to measure mooring tensions with substantial biomass. During the kelp farming season of 2018–2019 in Saco Bay, Maine USA, a field study was conducted to assess mooring loads due to environmental conditions and kelp growth. The effort included the deployment of a farm with a 122 m cultivation line and spread mooring with rope, chain, and anchors in 15.2 m of water. The system was deployed with seeded twine in late November and harvested in May. In April, with kelp biomass estimated at 7.8 kg m −1 , two load cells were installed to measure mooring tensions in response to currents and waves. The currents and waves were measured with two Acoustic Doppler Current Profilers deployed adjacent to the load cells. From these measurements, we characterized the maximum loading case in response to a complex hydrodynamic environment. The maximum tension occurred on the landward side of the farm even though wave exposure was seaward. The tension in the landward side mooring was dominated by steady drag from the currents going to the east southeast. During this event, the two profilers were positioned on the leading and trailing edges of the farm relative to the prevailing current direction. Velocities measured at 0.5 m bins showed a 26.7% reduction at the depths where the kelp was located. To analyze the dynamic portion of the load cell datasets, the oscillatory components were processed into energy density spectra. Results showed that mooring tensions were not affected by waves at frequencies greater than 0.175 Hz, with most of the energy occurring near 0.12 Hz. The tension spectra did reveal energy at frequencies between 0.0075 and 0.01 Hz, indicating a low frequency response, possibly due to nonuniform velocity profiles inducing vertical motion of the cultivation line. It was also observed that the landward mooring, subjected to higher currents, was more sensitive to oscillating loads than the slack seaward side. The high-fidelity dataset will be useful for numerical modeling validation to further understand these dynamics and to optimize kelp farm designs.

Measuring riverine macroplastic: Methods, harmonisation, and quality control - Rachel Hurley; Hans Fredrik Veiteberg Braaten; Luca Nizzetto; Eirik Hovland Steindal; Yan Lin; François Clayer; Tim van Emmerik; Nina Tuscano Buenaventura; David Petersen Eidsvoll; Asle Økelsrud; Magnus Norling; Hans Nicolai Adam; et al. (Water Research, 2023)

Phylogenomics and biogeography of arid-adapted Chlamydogobius goby fishes - Krystina D. Mossop; Alan R. Lemmon; Emily Moriarty Lemmon; Ron Eytan; Mark Adams; Peter J. Unmack; Katie Smith Date; Hernán E. Morales; Michael P. Hammer; Bob B.M. Wong; David G. Chapple (Molecular Phylogenetics and Evolution, 2023)

Effect of low-permeability layers on vadose well recharge rates - Erik M. Patton; Claudia Adam; David R. Steward; Saugata Datta (Groundwater for Sustainable Development, 2023)

A Systematic Review of the Genetic Predisposition to Injury in Football - Alexander B. T. McAuley; David C. Hughes; Loukia G. Tsaprouni; Ian Varley; Bruce Suraci; Thomas R. Roos; Adam J. Herbert; Daniel T. Jackson; Adam L. Kelly (Journal of Science in Sport and Exercise, 2023)
Purpose Synthesise genetic association studies investigating injury involving football players to identify which genetic variants have the most empirical evidence to date. Methods A comprehensive search of the PubMed, SPORTDiscus, and MEDLINE databases until March 11th 2022 identified 34 studies. Inclusion criteria: primary investigations, included football players, examined the association of a genetic variant with injury, and were published in English. Risk of bias was assessed using the Newcastle–Ottawa Scale. A narrative synthesis summarised results. Results There were 33 candidate gene studies and one genome-wide study, with 9642 participants across all studies (range = 43–1311; median = 227). Ninety-nine polymorphisms were assessed within 63 genes. Forty-one polymorphisms were associated with injury once. Three polymorphisms had their specific allelic associations with injury replicated twice in independent cohorts: ACTN3 (rs1815739) XX genotype was associated with an increased susceptibility to non-contact muscle injuries, ACAN (rs1516797) G allele was associated with increased susceptibility to anterior cruciate ligament (ACL) injuries, and VEGFA (rs2010963) CC genotype was associated with an increased susceptibility to ACL and ligament or tendon injuries. However, several methodological issues (e.g., small sample sizes, cohort heterogeneity, and population stratification) are prevalent that limit the reliability and external validity of findings. Conclusion At present, the evidence base supporting the integration of genetic information as a prognostic or diagnosis tool for injury risk in football is weak. Future participation of organisations in international consortia is suggested to combat the current methodological issues and subsequently improve clarity concerning the underlying genetic contribution to injury susceptibility.

Fishing for hosts: Larval spurting by the endangered thick‐shelled river mussel, U nio c rassus - David C. Aldridge; Joshua I. Brian; Adam Ćmiel; Anna Lipińska; Manuel Lopes‐Lima; Ronaldo Sousa; Amilcar Teixeira; Katarzyna Zając; Tadeusz Zając (Ecology, 2023)

Global water level variability observed after the Hunga Tonga-Hunga Ha'apai volcanic tsunami of 2022 - Adam T. Devlin; David A. Jay; Stefan A. Talke; Jiayi Pan (Ocean Science, 2023)
The eruption of the Hunga Tonga-Hunga Ha'apai volcano on 15 January 2022 provided a rare opportunity to understand global tsunami impacts of explosive volcanism and to evaluate future hazards, including dangers from “volcanic meteotsunamis” (VMTs) induced by the atmospheric shock waves that followed the eruption. The propagation of the volcanic and marine tsunamis was analyzed using globally distributed 1 min measurements of air pressure and water level (WL) (from both tide gauges and deep-water buoys). The marine tsunami propagated primarily throughout the Pacific, reaching nearly 2 m at some locations, though most Pacific locations recorded maximums lower than 1 m. However, the VMT resulting from the atmospheric shock wave arrived before the marine tsunami and propagated globally, producing water level perturbations in the Indian Ocean, the Mediterranean, and the Caribbean. The resulting water level response of many Pacific Rim gauges was amplified, likely related to wave interaction with bathymetry. The meteotsunami repeatedly boosted tsunami wave energy as it circled the planet several times. In some locations, the VMT was amplified by as much as 35-fold relative to the inverse barometer due to near-Proudman resonance and topographic effects. Thus, a meteotsunami from a larger eruption (such as the Krakatoa eruption of 1883) could yield atmospheric pressure changes of 10 to 30 mb, yielding a 3–10 m near-field tsunami that would occur in advance of (usually) larger marine tsunami waves, posing additional hazards to local populations. Present tsunami warning systems do not consider this threat.

Corrigendum to “Machine learning for classifying and predicting grape maturity indices using absorbance and fluorescence spectra” [Food Chemistry 403 (2023) 134321] - Claire E.J. Armstrong; Adam M. Gilmore; Paul K. Boss; Vinay Pagay; David W. Jeffery (Food Chemistry, 2023)

Albitization and oxidation of Variscan granitoid rocks related to the post-Variscan paleosurface in the Sudetes (Bohemian Massif, SW Poland) - Médard Thiry; Christine Franke; Kouakou F. E. Yao; Adam Szuszkiewicz; Carles Fàbrega; Maria Jeleńska; Magdalena Kądziałko-Hofmokl; Andrey Gurenko; David Parcerisa; Artur Sobczyk; Krzysztof Turniak; Paweł Aleksandrowski (International Journal of Earth Sciences, 2023)

RNA virus discoveries in the electric ant, Wasmannia auropunctata - Steven M. Valles; Chaoyang Zhao; Adam R. Rivers; Ryo L. Iwata; David H. Oi; Dong H. Cha; R. Max Collignon; Nastassja A. Cox; Gary J. Morton; Luis A. Calcaterra (Virus Genes, 2023)
Despite being one of the most destructive invasive species of ants, only two natural enemies are known currently for Wasmannia auropunctata, commonly known as the electric ant or little fire ant. Because viruses can be effective biological control agents against many insect pests, including ants, a metagenomics/next-generation sequencing approach was used to facilitate discovery of virus sequences from the transcriptomes of W. auropunctata . Five new and complete positive sense, single-stranded RNA virus genomes, and one new negative sense, single-stranded RNA virus genome were identified, sequenced, and characterized from W. auropunctata collected in Argentina by this approach, including a dicistrovirus (Electric ant dicistrovirus), two polycipiviruses (Electric ant polycipivirus 1; Electric ant polycipivirus 2), a solinvivirus (Electric ant solinvivirus), a divergent genome with similarity to an unclassified group in the Picornavirales (Electric ant virus 1), and a rhabdovirus (Electric ant rhabdovirus). An additional virus genome was detected that is likely Solenopsis invicta virus 10 (MH727527). The virus genome sequences were absent from the transcriptomes of W. auropunctata collected in the USA (Hawaii and Florida). Additional limited field surveys corroborated the absence of these viruses in regions where the electric ant is invasive (the USA and Australia). The replicative genome strand of four of the viruses (Electric ant polycipivirus 2, Electric ant solinvivirus, Electric ant virus 1, and Solenopsis invicta virus 10 (in the electric ant) was detected in Argentinean-collected W. auropunctata indicating that the ant is a host for these viruses. These are the first virus discoveries to be made from W. auropunctata .

Combined application of exogenous phytohormones and blue light illumination to the marine diatom Phaeodactylum tricornutum - David Fierli; Maria Elena Barone; Adam Mc Donnell; Thomas Conlon; Nicolas Touzet (Algal Research, 2023)

Cryptic diversity of Crocidura shrews in the savannahs of Eastern and Southern Africa - Malahat Dianat; Inessa Voet; David Ortiz; Joëlle Goüy de Bellocq; Laura N. Cuypers; Boris Kryštufek; Michal Bureš; Dagmar Čížková; Anna Bryjová; Josef Bryja; Violaine Nicolas; Adam Konečný (Molecular Phylogenetics and Evolution, 2023)

Machine learning for classifying and predicting grape maturity indices using absorbance and fluorescence spectra - Claire E.J. Armstrong; Adam M. Gilmore; Paul K. Boss; Vinay Pagay; David W. Jeffery (Food Chemistry, 2023)

Including imprecisely georeferenced specimens improves accuracy of species distribution models and estimates of niche breadth - Adam B. Smith; Stephen J. Murphy; David Henderson; Kelley D. Erickson (Global Ecology and Biogeography, 2023)
Aim Museum and herbarium specimen records are frequently used to assess the conservation status of species and their responses to climate change. Typically, occurrences with imprecise geolocality information are discarded because they cannot be matched confidently to environmental conditions and are thus expected to increase uncertainty in downstream analyses. However, using only precisely georeferenced records risks undersampling of the environmental and geographical distributions of species. We present two related methods to allow the use of imprecisely georeferenced occurrences in biogeographical analysis. Innovation Our two procedures assign imprecise records to the (1) locations or (2) climates that are closest to the geographical or environmental centroid of the precise records of a species. For virtual species, including imprecise records alongside precise records improved the accuracy of ecological niche models projected to the present and the future, especially for species with c . 20 or fewer precise occurrences. Using only precise records underestimated loss of suitable habitat and overestimated the amount of suitable habitat in both the present and the future. Including imprecise records also improves estimates of niche breadth and extent of occurrence. An analysis of 44 species of North American Asclepias (Apocynaceae) yielded similar results. Main conclusions Existing studies examining the effects of spatial imprecision typically compare outcomes based on precise records against the same records with spatial error added to them. However, in real‐world cases, analysts possess a mix of precise and imprecise records and must decide whether to retain or discard the latter. Discarding imprecise records can undersample the geographical and environmental distributions of species and lead to mis‐estimation of responses to past and future climate change. Our method, for which we provide a software implementation in the enmSdmX package for R, is simple to use and can help leverage the large number of specimen records that are typically deemed “unusable” because of spatial imprecision in their geolocation.

Changes in the vertical distribution of age‐0 walleye pollock ( Gadus chalcogrammus ) during warm and cold years in the southeastern Bering Sea - Adam Spear; Alexander G. Andrews; Janet Duffy‐Anderson; Tayler Jarvis; David Kimmel; Denise McKelvey (Fisheries Oceanography, 2023)
In the last 20 years, the southeastern Bering Sea has shifted its thermal variability to longer‐term (4–6 years) ocean–ecosystem temperature stanzas. Age‐0 walleye pollock ( Gadus chalcogrammus ) populations respond to thermal changes with horizontal (east–west) shifts in spatial distribution over the continental shelf, though there are limited data on whether thermally mediated vertical shifts in distribution also occur. Vertical shifts may impact predator–prey overlap between age‐0 pollock and their lipid‐rich prey, calanoid copepods and euphausiids, resulting in different feeding conditions that ultimately affect fish body condition prior to winter onset. For this study, we analyzed acoustic backscatter measured during acoustic trawl surveys over the southeastern Bering Sea shelf in cold years (2011, 2012) and warm years (2014 and 2016) to determine the vertical distribution of age‐0 pollock. This study presents evidence that age‐0 pollock changes in vertical distribution were related to changes in ocean annual temperature. Age‐0 pollock went from occurring deeper in the water column during cold periods to being surface‐oriented during warm periods, potentially exacerbating spatial mismatches between pollock and prey. We relate patterns in a vertical position to physical water column properties, feeding, and bioenergetic condition of collected pollock and discuss implications for recruitment success during different thermal oceanographic stanzas.

The use of recovery animals in nonclinical safety assessment studies with monoclonal antibodies: further 3Rs opportunities remain - Helen Prior; Laura Andrews; Annick Cauvin; Hsiaotzu Chien; David O. Clarke; Kaushik Datta; Maggie Dempster; Noel Dybdal; Wendy Freebern; Lolke de Haan; Danuta Herzyk; Adam Hey; et al. (Regulatory Toxicology and Pharmacology, 2023)

Re-evaluating the need for chronic toxicity studies with therapeutic monoclonal antibodies, using a weight of evidence approach - Hsiao-Tzu Chien; Helen Prior; Laura Andrews; Leon van Aerts; Annick Cauvin; David O. Clarke; Kaushik Datta; Maggie Dempster; Noel Dybdal; Wendy Freebern; Lolke de Haan; Danuta Herzyk; et al. (Regulatory Toxicology and Pharmacology, 2023)

Absorbance-transmission and fluorescence excitation-emission matrix (A-TEEM) with multi-block data analysis and machine learning for accurate intraregional classification of Barossa Shiraz wine - Ranaweera K.R. Ranaweera; Susan E.P. Bastian; Adam M. Gilmore; Dimitra L. Capone; David W. Jeffery (Food Control, 2023)

Thermochemical syngas generation via solid looping process: An experimental demonstration using Fe-based material - Christopher de Leeuwe; Syed Zaheer Abbas; Panagiotis Alexandros Argyris; Adam Zaidi; Alvaro Amiero; Stephen Poultson; David Wails; Vincenzo Spallina (Chemical Engineering Journal, 2023)

Canagliflozin retards age-related lesions in heart, kidney, liver, and adrenal gland in genetically heterogenous male mice - Jessica M. Snyder; Kerriann M. Casey; Andrzej Galecki; David E. Harrison; Hashan Jayarathne; Navasuja Kumar; Francesca Macchiarini; Nadia Rosenthal; Marianna Sadagurski; Adam B. Salmon; Randy Strong; Richard A. Miller; et al. (GeroScience, 2023)
Canagliflozin (Cana), a clinically important anti-diabetes drug, leads to a 14% increase in median lifespan and a 9% increase in the 90th percentile age when given to genetically heterogeneous male mice from 7 months of age, but does not increase lifespan in female mice. A histopathological study was conducted on 22-month-old mice to see if Cana retarded diverse forms of age-dependent pathology. This agent was found to diminish incidence or severity, in male mice only, of cardiomyopathy, glomerulonephropathy, arteriosclerosis, hepatic microvesicular cytoplasmic vacuolation (lipidosis), and adrenal cortical neoplasms. Protection against atrophy of the exocrine pancreas was seen in both males and females. Thus, the extension of lifespan in Cana-treated male mice, which is likely to reflect host- or tumor-mediated delay in lethal neoplasms, is accompanied by parallel retardation of lesions, in multiple tissues, that seldom if ever lead to death in these mice. Canagliflozin thus can be considered a drug that acts to slow the aging process and should be evaluated for potential protective effects against many other late-life conditions.

Evolving insights into the epidemiology of Moraxella species bloodstream infection from two decades of surveillance in Queensland, Australia - Jessica Schults; Felicity Edwards; Karina Charles; Adam D. Irwin; Claire M. Rickard; Patrick N. A. Harris; David L. Paterson; Kevin Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

A new approach to define an economically important fish as an umbrella flagship species to enhance collaborative stakeholder-management agency habitat conservation - JoEllen K. Wilson; Philip W. Stevens; David A. Blewett; Ross Boucek; Aaron J. Adams (Environmental Biology of Fishes, 2023)

Mutated Pkhd1 alone is sufficient to cause autoimmune biliary disease on the nonobese diabetic (NOD) genetic background - David E. Adams; Luke S. Heuer; Manuel Rojas; Weici Zhang; William M. Ridgway (Immunogenetics, 2023)
We previously reported that nonobese diabetic (NOD) congenic mice (NOD. c3c4 mice) developed an autoimmune biliary disease (ABD) with similarities to human primary biliary cholangitis (PBC), including anti-mitochondrial antibodies and organ-specific biliary lymphocytic infiltrates. We narrowed the possible contributory regions in a novel NOD. Abd3 congenic mouse to a B10 congenic region on chromosome 1 (“ Abd3 ”) and a mutated Pkhd1 gene ( Pkhd1 del36−67 ) upstream from Abd3 , and we showed via backcrossing studies that the NOD genetic background was necessary for disease. Here, we show that NOD. Abd3 mice develop anti-PDC-E2 autoantibodies at high levels, and that placing the chromosome 1 interval onto a scid background eliminates disease, demonstrating the critical role of the adaptive immune system in pathogenesis. While the NOD genetic background is essential for disease, it was still unclear which of the two regions in the Abd3 locus were necessary and sufficient for disease. Here, using a classic recombinant breeding approach, we prove that the mutated Pkhd1 del36−67 alone, on the NOD background, causes ABD. Further characterization of the mutant sequence demonstrated that the Pkhd1 gene is disrupted by an ETnII-beta retrotransposon inserted in intron 35 in an anti-sense orientation. Homozygous Pkhd1 mutations significantly affect viability, with the offspring skewed away from a Mendelian distribution towards NOD Pkhd1 homozygous or heterozygous genotypes. Cell-specific abnormalities, on a susceptible genetic background, can therefore induce an organ-specific autoimmunity directed to the affected cells. Future work will aim to characterize how mutant Pkhd1 can cause such an autoimmune response.

Boundary Layer Height Characteristics in Mexico City from Two Remote Sensing Techniques - Andrea Burgos-Cuevas; Adolfo Magaldi; David K. Adams; Michel Grutter; Jorge L. García Franco; Angel Ruiz-Angulo (Boundary-Layer Meteorology, 2023)
The Atmospheric Boundary Layer (ABL) height is a key parameter in air quality research as well as for numerical simulations and forecasts. The identification of thermally stable layers, often with radiosondes, has been a common approach for estimating ABL height, though with limited temporal coverage. Remote sensing techniques offer essentially continuous measurements. Nevertheless, ABL height retrievals from different methods can vary greatly when compared, which is particularly notable for topographically complex terrains, such as that surrounding Mexico City. This study, employing one year of data in Mexico City, reveals that the daytime convective boundary layer height (retrieved from Doppler lidar data) is typically lower than the aerosol layer height (retrieved from ceilometer data). Although both estimated heights evolved diurnally, the more elevated aerosol layer decays more slowly, suggesting that the mechanisms that elevate aerosols are not limited to convective motions. Additionally, both diurnal and seasonal variability are investigated, comparing remotely sensed-retrieved heights with thermally stable layers estimated from radiosonde data. Multiple stable layers often develop, those at higher levels have similar values to the ceilometer-retrieved heights, while stable layers at lower heights are similar to Doppler lidar height retrievals. The present research constitutes the first detailed analysis of ceilometer backscatter and Doppler lidar thresholding methods for estimating ABL height over Mexico City, and our results illustrate the complexity of mixing mechanisms on the ABL in this region of complex orography.

The drivers of anguillid eel movement in lentic water bodies: a systematic map - Michael J. Williamson; David M. P. Jacoby; Adam T. Piper (Reviews in Fish Biology and Fisheries, 2023)
Anguillid eels are near globally distributed catadromous fishes with marine spawning areas and inshore and inland growth areas in both lotic (rivers, estuaries) and lentic (lakes, ponds, lagoons) water bodies. As predators, anguillid eels play an important ecological role in both marine and freshwater systems, and several species are harvested commercially for food. However, some of the more widely distributed species have undergone severe declines in recruitment and their population status is now of significant concern. Given the multiple and lengthy migrations undertaken by anguillid eels, understanding of the drivers of movement is fundamental for species conservation and management. Yet, despite the importance of lentic systems to their ecology, most studies on anguillid eel movement have been conducted in lotic systems. Given that key influences on eel migration in lotic water bodies, such as fluctuations in flow and water temperature, may be minimised in lentic environments, the transferability of findings between lotic and lentic systems cannot be assumed. A systematic map was constructed to synthesise current knowledge on the extrinsic and intrinsic drivers of anguillid eel movement in lentic systems. The current state of knowledge of the drivers of eel movement in lentic systems is presented and compared to the relatively well-understood drivers of movement in lotic systems. We also discuss current knowledge gaps and limitations, and identify key future research requirements to inform the management and conservation of anguillid eels in understudied lentic systems. Graphical abstract

Awareness, use and understanding of nutrition labels among adults from five countries: Findings from the 2018–2020 International Food Policy Study - Rachel B. Acton; Vicki L. Rynard; Jean Adams; Jasmin Bhawra; Adrian J. Cameron; Alejandra Contreras-Manzano; Rachel E. Davis; Alejandra Jáuregui; Gary Sacks; James F. Thrasher; Lana Vanderlee; Christine M. White; et al. (Appetite, 2023)

Temporal and geographic extent of the late Holocene dry period in the central Great Basin, USA - Scott Mensing; Wei Wang; David Rhode; Douglas J. Kennett; Adam Csank; David Hurst Thomas; Cedar Briem; Thomas K. Harper; Brendan J. Culleton; Richard J. George; John Southon (Quaternary Science Reviews, 2023)

Ocular pathology in aquarium fish with a focus on the Syngnathidae and Apogonidae families - Vim Kumaratunga; Vicki J Adams; David Donaldson; Roser T Pont; Mark F Stidworthy (Journal of Comparative Pathology, 2023)

Threat-abatement framework confirms habitat retention and invasive species management are critical to conserve Australia's threatened species - Stephen G. Kearney; James E.M. Watson; April E. Reside; Diana O. Fisher; Martine Maron; Tim S. Doherty; Sarah M. Legge; John C.Z. Woinarski; Stephen T. Garnett; Brendan A. Wintle; Euan G. Ritchie; Don A. Driscoll; et al. (Biological Conservation, 2023)

Large-scale evaluation of microorganism inactivation by bipolar ionization and photocatalytic devices - Katherine M. Ratliff; Lukas Oudejans; John Archer; Worth Calfee; Jerome U. Gilberry; David Adam Hook; William E. Schoppman; Robert W. Yaga; Lance Brooks; Shawn Ryan (Building and Environment, 2023)

Integrating knowledge on green infrastructure, health and well-being in ageing populations: Principles for research and practice - Matthew Dennis; Adam Barker; Jamie Anderson; Jenna C. Ashton; Gina Cavan; Penny A. Cook; David French; Anna Gilchrist; Philip James; Christopher Phillipson; Konstantinos Tzoulas; C. Philip Wheater; et al. (Ambio, 2023)
Ageing and urbanisation pose significant challenges for public health and urban planning. Ageing populations are at particular risk from hazards arising from urbanisation processes, some of which are in turn exacerbated by climate change. One approach for mitigating the negative effects of urbanisation on ageing populations is the leveraging of the beneficial effects of urban green infrastructure as a public health intervention in the planning process. We assessed the potential of available theoretical frameworks to provide the context for such leverage. This involved active engagement with academics and practitioners specialising in ageing, green infrastructure and health and well-being through a knowledge-brokering approach. We concluded that an integrated and comprehensive framework on the socio-cultural-ecological determinants of health is lacking. To address this, we present a set of principles for overcoming challenges to knowledge integration when working at the intersection of green infrastructure, ageing, health and well-being. Our findings—and the co-production process used to generate them—have wider significance for trans-disciplinary research into the benefits of the natural environment to human health and well-being as well as other complex and interconnected topics associated with global grand challenges.

Combining acoustic telemetry with a mechanistic model to investigate characteristics unique to successful Atlantic salmon smolt migrants through a standing body of water - Jessie Lilly; Hannele M. Honkanen; Joseph M. McCallum; Matthew Newton; David M. Bailey; Colin E. Adams (Environmental Biology of Fishes, 2022)
The Atlantic salmon, Salmo salar Linnaeus 1758, is a charismatic, anadromous species that has faced dramatic declines throughout its range. There is currently a lack of information on the effect of free-standing bodies of water on a key life event, sea migration, for the species. This study extends our understanding in this area by combining acoustic telemetry with a correlated random walk model to try to examine potential morphological and behavioural factors that differentiate successful from unsuccessful migrants through Scotland’s largest lake. Consistent with other studies, we found that smolts experienced a high rate of mortality in the lake (~ 43%), with approximately 14% potentially predated upon by birds and 4% by Northern pike. Migration speed in the lake was slow (the mean minimum movement speed between centres of activity was 0.13 m/s), and pathways frequently deviated away from the outlet river. There was no evidence of a morphological or behavioural trait or migratory pathway that distinguished successful from unsuccessful smolts. This suggests that migration movement direction in the main body of Loch Lomond appeared to be random. This was further supported by the output of a correlated random walk model which closely resembled the pathway and migration speed and distance patterns displayed by successful migrants. However, once successful smolts came within ~2 km of the lake exit, a high proportion remained in this region prior to entering the River Leven. We suggest that this “goldilocks zone” is where directional cues become apparent to migrating fish. Future studies should combine random walk models with environmental variables to determine if external factors are driving the apparently random movement patterns exhibited by smolts in lakes.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Genetic structure and historic demography of endangered unarmoured threespine stickleback at southern latitudes signals a potential new management approach - Rachel Turba; Jonathan Q. Richmond; Sorel Fitz‐Gibbon; Marco Morselli; Robert N. Fisher; Camm C. Swift; Gorgonio Ruiz‐Campos; Adam R. Backlin; Chris Dellith; David K. Jacobs (Molecular Ecology, 2022)
Habitat loss, flood control infrastructure, and drought have left most of southern California and northern Baja California's native freshwater fish near extinction, including the endangered unarmoured threespine stickleback ( Gasterosteus aculeatus williamsoni ). This subspecies, an unusual morph lacking the typical lateral bony plates of the G. aculeatus complex, occurs at arid southern latitudes in the eastern Pacific Ocean and survives in only three inland locations. Managers have lacked molecular data to answer basic questions about the ancestry and genetic distinctiveness of unarmoured populations. These data could be used to prioritize conservation efforts. We sampled G. aculeatus from 36 localities and used microsatellites and whole genome data to place unarmoured populations within the broader evolutionary context of G. aculeatus across southern California/northern Baja California. We identified three genetic groups with none consisting solely of unarmoured populations. Unlike G. aculeatus at northern latitudes, where Pleistocene glaciation has produced similar historical demographic profiles across populations, we found markedly different demographics depending on sampling location, with inland unarmoured populations showing steeper population declines and lower heterozygosity compared to low armoured populations in coastal lagoons. One exception involved the only high elevation population in the region, where the demography and alleles of unarmoured fish were similar to low armoured populations near the coast, exposing one of several cases of artificial translocation. Our results suggest that the current “management‐by‐phenotype” approach, based on lateral plates, is incidentally protecting the most imperilled populations; however, redirecting efforts toward evolutionary units, regardless of phenotype, may more effectively preserve adaptive potential.

Could atmospheric carbon be driving sedimentation? - Andrija Vinković; Gennadiy Laptyev; Günseli Yaprak; Krasimira Slavova; Danijela Joksimović; Tamara Troskot-Čorbić; Marina Frontasyeva; Octavian G. Duliu; Elida Bylyku; Manjola Shyti; Famil Humbatov; Mirza Nuhanović; et al. (Journal of Soils and Sediments, 2022)

Concussion Prone Scenarios: A Multi-Dimensional Exploration in Impact Directions, Brain Morphology, and Network Architectures Using Computational Models - Taotao Wu; Jared A. Rifkin; Adam C. Rayfield; Erin D. Anderson; Matthew B. Panzer; David F. Meaney (Annals of Biomedical Engineering, 2022)

Investigating the behaviour of Atlantic salmon ( Salmo salar L.) post‐smolts during their early marine migration through the Clyde Marine Region - Jessie Lilly; Hannele M. Honkanen; David M. Bailey; Colin W. Bean; Ruaidhri Forrester; Jessica R. Rodger; Colin E. Adams (Journal of Fish Biology, 2022)
It is thought that survival during migration is particularly poor for Atlantic salmon post‐smolts immediately after entry into sea and particularly in the estuarine environment. Nonetheless, there is currently a lack of information on Atlantic salmon post‐smolt movement behaviour in estuaries in the UK. This study used acoustic tagging to estimate loss rates and compare the behaviour of Atlantic salmon post‐smolts migrating from two distinctly different rivers draining into the Clyde Estuary, the River Endrick ( n = 145) and the Gryffe ( n = 102). Contrary to most literature, post‐smolts undertook rapid migrations through the estuary, potentially decreasing their exposure to predators/anthropogenic stressors and reducing their estimated loss rates (river: 1%–3% km –1 ; estuary: 0.20%–0.60% km –1 ). The low loss rates in the estuary occurred despite post‐smolts engaging in passive reversal movements with the tide upon entering the estuary, possibly allowing them more time to adapt to the increased salinity. Atlantic salmon post‐smolts from both the rivers used similar migration pathways exiting into the coastal marine zone during ebbing tide. This study provides novel information on the timing and migratory routes of Atlantic salmon post‐smolts in the Clyde Estuary that can ultimately be used to inform management decisions on how to assess and reduce the potential impacts of current natural and anthropogenic stressors. Temporal repeatability of this study over multiple years is required to determine if there is variation in the factors driving the migratory patterns and loss rates of smolts in this system.

Ecophysiological and genomic analyses of a representative isolate of highly abundant Bacillus cereus strains in contaminated subsurface sediments - Jennifer L. Goff; Elizabeth G. Szink; Michael P. Thorgersen; Andrew D. Putt; Yupeng Fan; Lauren M. Lui; Torben N. Nielsen; Kristopher A. Hunt; Jonathan P. Michael; Yajiao Wang; Daliang Ning; Ying Fu; et al. (Environmental Microbiology, 2022)
Bacillus cereus strain CPT56D‐587‐MTF (CPTF) was isolated from the highly contaminated Oak Ridge Reservation (ORR) subsurface. This site is contaminated with high levels of nitric acid and multiple heavy metals. Amplicon sequencing of the 16S rRNA genes (V4 region) in sediment from this area revealed an amplicon sequence variant (ASV) with 100% identity to the CPTF 16S rRNA sequence. Notably, this CPTF‐matching ASV had the highest relative abundance in this community survey, with a median relative abundance of 3.77% and comprised 20%–40% of reads in some samples. Pangenomic analysis revealed that strain CPTF has expanded genomic content compared to other B. cereus species—largely due to plasmid acquisition and expansion of transposable elements. This suggests that these features are important for rapid adaptation to native environmental stressors. We connected genotype to phenotype in the context of the unique geochemistry of the site. These analyses revealed that certain genes (e.g. nitrate reductase, heavy metal efflux pumps) that allow this strain to successfully occupy the geochemically heterogenous microniches of its native site are characteristic of the B. cereus species while others such as acid tolerance are mobile genetic element associated and are generally unique to strain CPTF.

Evaluating technological innovation impact: an empirical analysis of the offshore wind sector - Junguo Shi; Xuhua Hu; Shanshan Dou; David Alemzero; Elvis Adam Alhassan (Environmental Science and Pollution Research, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Using Biological Responses to Monitor Freshwater Post-Spill Conditions over 3 years in Blacktail Creek, North Dakota, USA - Aїda M. Farag; David D. Harper; Isabelle M. Cozzarelli; Douglas B. Kent; Adam C. Mumford; Denise M. Akob; Travis Schaeffer; Luke R. Iwanowicz (Archives of Environmental Contamination and Toxicology, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Coastal seascape variability in the intensifying East Australian Current Southern Extension - Lachlan R. Phillips; Neil Malan; Moninya Roughan; Robert Harcourt; Ian Jonsen; Martin Cox; Andrew S. Brierley; David Slip; Adam Wilkins; Gemma Carroll (Frontiers in Marine Science, 2022)
Coastal pelagic ecosystems are highly variable in space and time, with environmental conditions and the distribution of biomass being driven by complex processes operating at multiple scales. The emergent properties of these processes and their interactive effects result in complex and dynamic environmental mosaics referred to as “seascapes”. Mechanisms that link large-scale oceanographic processes and ecological variability in coastal environments remain poorly understood, despite their importance for predicting how ecosystems will respond to climate change. Here we assessed seascape variability along the path of the rapidly intensifying East Australian Current (EAC) Southern Extension in southeast Australia, a hotspot of ocean warming and ecosystem tropicalisation. Using satellite and in situ measures of temperature, salinity and current velocity coupled with contemporaneous measurements of pelagic biomass distribution from nine boat-based active acoustic surveys in five consecutive years, we investigated relationships between the physical environment and the distribution of pelagic biomass (zooplankton and fish) at multiple timescales. Survey periods were characterised by high variability in oceanographic conditions, with variation in coastal conditions influenced by meso-to-large scale processes occurring offshore, including the position and strength of eddies. Intra-annual variability was often of a similar or greater magnitude to inter-annual variability, suggesting highly dynamic conditions with important variation occurring at scales of days to weeks. Two seascape categories were identified being characterised by (A) warmer, less saline water and (B) cooler, more saline water, with the former indicating greater influence of the EAC on coastal processes. Warmer waters were also associated with fewer, deeper and less dense biological aggregations. As the EAC continues to warm and penetrate further south, it is likely that this will have substantial effects on biological activity in coastal pelagic ecosystems, including a potential reduction in the accessibility of prey aggregations to surface-feeding predators and to fisheries. These results highlight the import role of offshore oceanographic processes in driving coastal seascape variability and biological activity in a region undergoing rapid oceanic warming and ecological change.

Quantifying baseline costs and cataloging potential optimization strategies for kelp aquaculture carbon dioxide removal - Struan Coleman; Tobias Dewhurst; David W. Fredriksson; Adam T. St. Gelais; Kelly L. Cole; Michael MacNicoll; Eric Laufer; Damian C. Brady (Frontiers in Marine Science, 2022)
To keep global surface warming below 1.5°C by 2100, the portfolio of cost-effective CDR technologies must expand. To evaluate the potential of macroalgae CDR, we developed a kelp aquaculture bio-techno-economic model in which large quantities of kelp would be farmed at an offshore site, transported to a deep water “sink site”, and then deposited below the sequestration horizon (1,000 m). We estimated the costs and associated emissions of nursery production, permitting, farm construction, ocean cultivation, biomass transport, and Monitoring, Reporting, and Verification (MRV) for a 1,000 acre (405 ha) “baseline” project located in the Gulf of Maine, USA. The baseline kelp CDR model applies current systems of kelp cultivation to deep water (100 m) exposed sites using best available modeling methods. We calculated the levelized unit costs of CO 2 eq sequestration (LCOC; $ tCO 2 eq -1 ). Under baseline assumptions, LCOC was $17,048 tCO 2 eq -1 . Despite annually sequestering 628 tCO 2 eq within kelp biomass at the sink site, the project was only able to net 244 C credits (tCO 2 eq) each year, a true sequestration “additionality” rate (AR) of 39% (i.e., the ratio of net C credits produced to gross C sequestered within kelp biomass). As a result of optimizing 18 key parameters for which we identified a range within the literature, LCOC fell to $1,257 tCO 2 eq -1 and AR increased to 91%, demonstrating that substantial cost reductions could be achieved through process improvement and decarbonization of production supply chains. Kelp CDR may be limited by high production costs and energy intensive operations, as well as MRV uncertainty. To resolve these challenges, R&D must (1) de-risk farm designs that maximize lease space, (2) automate the seeding and harvest processes, (3) leverage selective breeding to increase yields, (4) assess the cost-benefit of gametophyte nursery culture as both a platform for selective breeding and driver of operating cost reductions, (5) decarbonize equipment supply chains, energy usage, and ocean cultivation by sourcing electricity from renewables and employing low GHG impact materials with long lifespans, and (6) develop low-cost and accurate MRV techniques for ocean-based CDR.

Shifts in root dynamics along a hillslope in a mixed, mesic temperate forest - Edward J. Primka; Thomas S. Adams; Alexandra S. Buck; David M. Eissenstat (Plant and Soil, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Extinction risk of the endemic vascular flora of Kauai, Hawaii, based on IUCN assessments - Nina Rønsted; Seana K. Walsh; Margaret Clark; Merlin Edmonds; Tim Flynn; Scott Heintzman; Alexander Loomis; David Lorence; Uma Nagendra; Ben Nyberg; Michael Opgenorth; Lauren Weisenberger; et al. (Conservation Biology, 2022)
The International Union for Conservation of Nature's Red List of Threatened Species (IUCN Red List) is the world's most comprehensive information source on the global conservation status of species. Governmental agencies and conservation organizations increasingly rely on IUCN Red List assessments to develop conservation policies and priorities. Funding agencies use the assessments as evaluation criteria, and researchers use meta‐analysis of red‐list data to address fundamental and applied conservation science questions. However, the circa 143,000 IUCN assessments represent a fraction of the world's biodiversity and are biased in regional and organismal coverage. These biases may affect conservation priorities, funding, and uses of these data to understand global patterns. Isolated oceanic islands are characterized by high endemicity, but the unique biodiversity of many islands is experiencing high extinction rates. The archipelago of Hawaii has one of the highest levels of endemism of any floristic region; 90% of its 1367 native vascular plant taxa are classified as endemic. We used the IUCN's assessment of the complete single‐island endemic (SIE) vascular plant flora of Kauai, Hawaii, to assess the proportion and drivers of decline of threatened plants in an oceanic island setting. We compared the IUCN assessments with federal, state, and other local assessments of Kauai species or taxa of conservation concern. Finally, we conducted a preliminary assessment for all 1044 native vascular plants of Hawaii based on IUCN criterion B by estimating area of occupancy, extent of occurrence, and number of locations to determine whether the pattern found for the SIE vascular flora of Kauai is comparable to the native vascular flora of the Hawaiian Islands. We compared our results with patterns observed for assessments of other floras. According to IUCN, 256 SIE vascular plant taxa are threatened with extinction and 5% are already extinct. This is the highest extinction risk reported for any flora to date. The preliminary assessment of the native vascular flora of Hawaii showed that 72% (753 taxa) is threatened. The flora of Hawaii may be one of the world's most threatened; thus, increased and novel conservation measures in the state and on other remote oceanic islands are urgently needed.

PlanktoScope: Affordable Modular Quantitative Imaging Platform for Citizen Oceanography - Thibaut Pollina; Adam G. Larson; Fabien Lombard; Hongquan Li; David Le Guen; Sébastien Colin; Colomban de Vargas; Manu Prakash (Frontiers in Marine Science, 2022)
The oceans represent 97% of all water on Earth and contain microscopic, drifting life, plankton, which drives global biogeochemical cycles. A major hurdle in assessing marine plankton is the planetary scale of the oceans and the logistical and economic constraints associated with their sampling. This difficulty is reflected in the limited amount of scientifically equipped fleets and affordable equipment. Here we present a modular hardware/software open-source strategy for building a versatile, re-configurable imaging platform - the PlanktoScope - that can be adapted to a number of applications in aquatic biology and ecology. We demonstrate high-throughput quantitative imaging of laboratory and field plankton samples while enabling rapid device reconfiguration to match the evolving needs of the sampler. The presented versions of PlanktoScope are capable of autonomously imaging 1.7 ml per minute with a 2.8 µm/px resolution and can be controlled from any WiFi-enabled device. The PlanktoScope’s small size, ease of use, and low cost - under $1000 in parts - enable its deployment for customizable monitoring of laboratory cultures or natural micro-plankton communities. This also paves the way toward consistent and long-term measurement of plankton diversity by an international fleet of citizen vessels at the planetary scale.

Identification of genetic loci in lettuce mediating quantitative resistance to fungal pathogens - Harry Pink; Adam Talbot; Abi Graceson; Juliane Graham; Gill Higgins; Andrew Taylor; Alison C. Jackson; Maria Truco; Richard Michelmore; Chenyi Yao; Frances Gawthrop; David Pink; et al. (Theoretical and Applied Genetics, 2022)
Key message We demonstrate genetic variation for quantitative resistance against important fungal pathogens in lettuce and its wild relatives, map loci conferring resistance and predict key molecular mechanisms using transcriptome profiling. Abstract Lactuca sativa L. (lettuce) is an important leafy vegetable crop grown and consumed globally. Chemicals are routinely used to control major pathogens, including the causal agents of grey mould ( Botrytis cinerea ) and lettuce drop ( Sclerotinia sclerotiorum ) . With increasing prevalence of pathogen resistance to fungicides and environmental concerns, there is an urgent need to identify sources of genetic resistance to B. cinerea and S. sclerotiorum in lettuce. We demonstrated genetic variation for quantitative resistance to B. cinerea and S. sclerotiorum in a set of 97 diverse lettuce and wild relative accessions, and between the parents of lettuce mapping populations. Transcriptome profiling across multiple lettuce accessions enabled us to identify genes with expression correlated with resistance, predicting the importance of post-transcriptional gene regulation in the lettuce defence response. We identified five genetic loci influencing quantitative resistance in a F 6 mapping population derived from a Lactuca serriola (wild relative) × lettuce cross, which each explained 5–10% of the variation. Differential gene expression analysis between the parent lines, and integration of data on correlation of gene expression and resistance in the diversity set, highlighted potential causal genes underlying the quantitative trait loci.

Correction: International Regulatory Collaboration on the Analysis of Nitrosamines in Metformin-Containing Medicines - David A. Keire; Robert Bream; Uwe Wollein; Schmaler-Ripcke; Annette Burchardt; Massimiliano Conti; Adam Zmysłowski; Peter Keizers; Justin Morin; Jalene Poh; Mark George; Michael Wierer (The AAPS Journal, 2022)

Physical characteristics of northern forested lakes predict sensitivity to climate change - Mark B. Edlund; Joy M. Ramstack Hobbs; Adam J. Heathcote; Daniel R. Engstrom; Jasmine E. Saros; Kristin E. Strock; William O. Hobbs; Norman A. Andresen; David D. VanderMeulen (Hydrobiologia, 2022)
Evidence suggests that boreal-lake ecosystems are changing rapidly, but with variable ecological responses, due to climate warming. Paleolimnological analysis of 27 undeveloped northern forested lakes showed significant and potentially climate-mediated shifts in diatom communities and increased carbon and biogenic silica burial. We hypothesize the sensitivity of northern forested lakes to climate change will vary along two physical gradients: one reflecting direct, in-lake climate effects (propensity to thermally stratify), the other reflecting indirect watershed effects (watershed to lake-surface area ratio). We focus on the historical response of algal communities to test our two-dimensional sensitivity framework. Historical algal response was summarized by measures of diatom community turnover, changes in species and diagnostic species groups, and measures of siliceous algal and overall primary production (biogenic silica, carbon burial). Measures of algal production increased across all lake types, with carbon burial proportionately higher in polymictic lakes. Greater diatom community change occurred in deep, stratified lakes with smaller watersheds, whereas diatom species groups showed variable responses along our two-dimensional sensitivity framework. Physical characteristics of lakes and watersheds could serve as predictors of sensitivity to climate change based on paleo-indicators that are mechanistically linked to direct and indirect limnological effects of climate change.

In Vivo Changes in Dynamic Adjacent Segment Motion 1 Year After One and Two-Level Cervical Arthrodesis - Clarissa M. LeVasseur; Samuel W. Pitcairn; David O. Okonkwo; Adam S. Kanter; Jeremy D. Shaw; William F. Donaldson; Joon Y. Lee; William J. Anderst (Annals of Biomedical Engineering, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Neck Loads During Head-First Entries into Trampoline Dismount Foam Pits: Considerations for Trampoline Park Safety - Tom Whyte; Edward Lind; Adam Richards; David Eager; Lynne E. Bilston; Julie Brown (Annals of Biomedical Engineering, 2022)
Serious cervical spine injuries have been documented from falls into foam pits at trampoline parks. To address the lack of evidence on how foam pits should be designed for mitigating neck injury risk, this study aimed to quantify neck loads during head-first entry into varying foam pit designs. An instrumented Hybrid III anthropomorphic test device was dropped head-first from a height of up to 1.5 m into three differently constructed foam pits, each using a different mechanism to prevent direct contact between the falling person and the floor (foam slab, trampoline or net bed). Measured neck loads were compared to published injury reference values. In the simplest, foam-only pit design, increasing foam depth tended to reduce peak compressive force. At least one injury assessment reference metric was exceeded in all pit conditions tested for 1.5 m falls, most commonly the time-dependent neck compression criterion. The results highlight the importance of adequate foam depth in combination with appropriate pit design in minimizing injury risk. The risk of cervical spine injury may not be reduced sufficiently with current foam pit designs.

Identifying Scaling Pathways and Research Priorities for Kelp Aquaculture Nurseries Using a Techno-Economic Modeling Approach - Struan Coleman; Adam T. St. Gelais; David W. Fredriksson; Tobias Dewhurst; Damian C. Brady (Frontiers in Marine Science, 2022)
Aquaculture of seaweeds, particularly in emerging farming regions such as North America, Europe, and South America, is steadily increasing. The growth of the sector has been supported by public and private R&D investment with the long-term goal of reducing farm-gate production costs. Reducing expenses would potentially allow growers to target high volume, low value markets, such as hydrocolloids, animal feeds, food thickening agents, biofuels, and carbon dioxide removal (CDR), as well as the higher value, “whole foods” markets. Regardless of the eventual fate of farmed seaweed, nursery production must increase in parallel with ocean cultivation to support the raw materials needs of the expanding industry. We quantified S. latissima (hereafter kelp) nursery production costs and identified potential barriers to cost-effective scaling using a techno-economic model (TEM). Semi-structured interviews with nursery operators in the U.S. and Europe were supplemented by an extensive literature review to parameterize the TEM. Reducing the sporophyte grow-out duration, increasing labor capacity, de-risking energy efficient flow-through systems, and optimizing tank and PVC “spool” size emerged as the most important research priorities based on our analysis. We point towards expanded gametophyte culture, and an associated policy framework to protect wild kelp population structure from monocultures, as necessary elements to support these potential improvements. The results of this work, as well as the open-source nursery TEM, are relevant to seaweed aquaculture producers, policy makers, and researchers, and can be used to guide future decision making regarding the cost-benefit of best available nursery technology.

Corrigendum: Large Vessel Activity and Low-Frequency Underwater Sound Benchmarks in United States Waters - Samara M. Haver; Jeffrey D. Adams; Leila T. Hatch; Sofie M. Van Parijs; Robert P. Dziak; Joseph Haxel; Scott A. Heppell; Megan F. McKenna; David K. Mellinger; Jason Gedamke (Frontiers in Marine Science, 2022)

International Regulatory Collaboration on the Analysis of Nitrosamines in Metformin-Containing Medicines - David A. Keire; Robert Bream; Uwe Wollein; Jeannette Schmaler-Ripcke; Annette Burchardt; Massimiliano Conti; Adam Zmysłowski; Peter Keizers; Justin Morin; Jalene Poh; Mark George; Michael Wierer (The AAPS Journal, 2022)
Recalls of some batches of metformin have occurred due to the detection of N -nitrosodimethylamine (NDMA) in amounts above the acceptable intake (AI) of 96 ng per day. Prior to the recalls, an international regulatory laboratory network had been monitoring drugs for nitrosamine impurities with each laboratory independently developing and validating multiple analytical procedures to detect and measure nitrosamines in metformin drugs used in their jurisdictions. Here, we provide an overview of the analysis of metformin active pharmaceutical ingredients (APIs) and drug products with 1090 samples (875 finished dosage forms (FDFs) and 215 API samples) tested beginning in November of 2019 through July of 2020. Samples were obtained internationally by a variety of approaches, including purchased, received from firms via information requests or selected by regional regulatory authorities (either at wholesalers or during GMP inspections). Only one nitrosamine (NDMA) was detected and was only present in some batches of metformin products. For API samples, 213 out of 215 lots tested had no measurable level of NDMA. For FDF samples tested, the number of batches with NDMA above the AI amount for patient safety was 17.8% (156/875). Based on these data, although the presence of NDMA was of concern, 82.2% of the samples of metformin drug products tested met quality and safety standards for patients. Regulatory agencies continue to collaborate extensively and work with marketing authorization holders to understand root causes of nitrosamine formation and agree on corrective actions to mitigate the presence of NDMA in future metformin batches. Graphical abstract

Is Neuroscience FAIR? A Call for Collaborative Standardisation of Neuroscience Data - Jean-Baptiste Poline; David N. Kennedy; Friedrich T. Sommer; Giorgio A. Ascoli; David C. Van Essen; Adam R. Ferguson; Jeffrey S. Grethe; Michael J. Hawrylycz; Paul M. Thompson; Russell A. Poldrack; Satrajit S. Ghosh; David B. Keator; et al. (Neuroinformatics, 2022)
In this perspective article, we consider the critical issue of data and other research object standardisation and, specifically, how international collaboration, and organizations such as the International Neuroinformatics Coordinating Facility (INCF) can encourage that emerging neuroscience data be Findable, Accessible, Interoperable, and Reusable (FAIR) . As neuroscientists engaged in the sharing and integration of multi-modal and multiscale data, we see the current insufficiency of standards as a major impediment in the Interoperability and Reusability of research results. We call for increased international collaborative standardisation of neuroscience data to foster integration and efficient reuse of research objects.

Pasteurella species bloodstream infections in Queensland, Australia, 2000–2019 - Kevin B. Laupland; Adam G. Stewart; Felicity Edwards; Patrick Harris; Claire Heney; Narelle George; Sonali Coulter; David L. Paterson (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Pasteurella species are infrequent but potentially severe causes of bloodstream infection (BSI). The objective of this study was to determine the incidence, risk factors, and outcomes of Pasteurella species BSI in a large Australian population. Retrospective, laboratory-based surveillance was conducted in Queensland, Australia (population ≈ 5 million) during 2000–2019, and clinical and outcome information was established by linkage to state hospital admissions and vital statistics databases. During more than 86 million person-years of surveillance, 272 incident Pasteurella species BSI occurred for an overall age- and sex-standardized annual incidence of 3.3 per million residents. The incidence of Pasteurella species BSI was highest in recent years and older individuals were at greatest risk. The median (interquartile range) Charlson Comorbidity Index was 2 (0–4) with scores of zero, 1, 2, and 3 + observed in 81 (30%), 37 (14%), 44 (16%), and 110 (40%) of cases. The 30-day all-cause case fatality was 9% (24/272) and patients who died had more comorbidities and were less likely to have community-associated disease. Although Pasteurella species are infrequent causes of BSI, older individuals and those with comorbidities are at highest risk. The burden of this disease may be expected to increase with an aging and more comorbid population.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Genetic Testing in Professional Football: Perspectives of Key Stakeholders - Alexander B. T. McAuley; David C. Hughes; Loukia G. Tsaprouni; Ian Varley; Bruce Suraci; Thomas R. Roos; Adam J. Herbert; Adam L. Kelly (Journal of Science in Sport and Exercise, 2022)
Purpose Genetic research in football is currently in it’s infancy but is growing rapidly. However, the practical application of genetic testing in football and the views concerning its use are unknown. Thus, the purpose of this study was to assess the current practical application of genetic testing in professional football and provide an insight into the perspectives of key stakeholders (i.e., coaches, practitioners, players). Methods In total, 122 participants completed an online anonymous survey. This consisted of 21 multiple choice and Likert scale questions, with the option of providing an explanation for each response. Results Findings revealed genetic testing is rarely utilised by key stakeholders (10%) or their respective organisations (14%). However, three quarters (75%) had the opinion that genetic testing will have great utility in the future. The majority (72%) believed genetic testing should be used for athlete development and injury risk, whilst 35% believed that genetic testing should be utilised for talent identification purposes. However, most key stakeholders viewed their own (89%) and their colleagues’ (79%) knowledge related to genetic testing as insufficient; mainly due to ineffective current communication methods (91%). Most believed educational workshops are required (71%), whilst nearly all (91%) were interested in developing their expertise on the utility of genetic testing. Conclusion Genetic testing is rarely used within professional football, although key stakeholders anticipate that it will be utilised more in the future. As such, educational support may prove valuable in improving key stakeholder knowledge and the practical application of genetic testing in professional football.

Mechanisms of breast cancer metastasis - S. David Nathanson; Michael Detmar; Timothy P. Padera; Lucy R. Yates; Danny R. Welch; Thomas C. Beadnell; Adam D. Scheid; Emma D. Wrenn; Kevin Cheung (Clinical & Experimental Metastasis, 2022)
Invasive breast cancer tends to metastasize to lymph nodes and systemic sites. The management of metastasis has evolved by focusing on controlling the growth of the disease in the breast/chest wall, and at metastatic sites, initially by surgery alone, then by a combination of surgery with radiation, and later by adding systemic treatments in the form of chemotherapy, hormone manipulation, targeted therapy, immunotherapy and other treatments aimed at inhibiting the proliferation of cancer cells. It would be valuable for us to know how breast cancer metastasizes; such knowledge would likely encourage the development of therapies that focus on mechanisms of metastasis and might even allow us to avoid toxic therapies that are currently used for this disease. For example, if we had a drug that targeted a gene that is critical for metastasis, we might even be able to cure a vast majority of patients with breast cancer. By bringing together scientists with expertise in molecular aspects of breast cancer metastasis, and those with expertise in the mechanical aspects of metastasis, this paper probes interesting aspects of the metastasis cascade, further enlightening us in our efforts to improve the outcome from breast cancer treatments.

Biogeochemical consequences of a changing Arctic shelf seafloor ecosystem - Christian März; Felipe S. Freitas; Johan C. Faust; Jasmin A. Godbold; Sian F. Henley; Allyson C. Tessin; Geoffrey D. Abbott; Ruth Airs; Sandra Arndt; David K. A. Barnes; Laura J. Grange; Neil D. Gray; et al. (Ambio, 2022)
Unprecedented and dramatic transformations are occurring in the Arctic in response to climate change, but academic, public, and political discourse has disproportionately focussed on the most visible and direct aspects of change, including sea ice melt, permafrost thaw, the fate of charismatic megafauna, and the expansion of fisheries. Such narratives disregard the importance of less visible and indirect processes and, in particular, miss the substantive contribution of the shelf seafloor in regulating nutrients and sequestering carbon. Here, we summarise the biogeochemical functioning of the Arctic shelf seafloor before considering how climate change and regional adjustments to human activities may alter its biogeochemical and ecological dynamics, including ecosystem function, carbon burial, or nutrient recycling. We highlight the importance of the Arctic benthic system in mitigating climatic and anthropogenic change and, with a focus on the Barents Sea, offer some observations and our perspectives on future management and policy.

Marine phytoplankton resilience may moderate oligotrophic ecosystem responses and biogeochemical feedbacks to climate change - Adam C. Martiny; George I. Hagstrom; Tim DeVries; Robert T. Letscher; Gregory L. Britten; Catherine A. Garcia; Eric Galbraith; David Karl; Simon A. Levin; Michael W. Lomas; Allison R. Moreno; David Talmy; et al. (Limnology and Oceanography, 2022)
Are the oceans turning into deserts? Rising temperature, increasing surface stratification, and decreasing vertical inputs of nutrients are expected to cause an expansion of warm, nutrient deplete ecosystems. Such an expansion is predicted to negatively affect a trio of key ocean biogeochemical features: phytoplankton biomass, primary productivity, and carbon export. However, phytoplankton communities are complex adaptive systems with immense diversity that could render them at least partially resilient to global changes. This can be illustrated by the biology of the Prochlorococcus “collective.” Adaptations to counter stress, use of alternative nutrient sources, and frugal resource allocation can allow Prochlorococcus to buffer climate‐driven changes in nutrient availability. In contrast, cell physiology is more sensitive to temperature changes. Here, we argue that biogeochemical models need to consider the adaptive potential of diverse phytoplankton communities. However, a full understanding of phytoplankton resilience to future ocean changes is hampered by a lack of global biogeographic observations to test theories. We propose that the resilience may in fact be greater in oligotrophic waters than currently considered with implications for future predictions of phytoplankton biomass, primary productivity, and carbon export.

Proteomic responses of the coccolithophore Emiliania huxleyi to zinc limitation and trace metal substitution - David M. Shire; Adam B. Kustka (Environmental Microbiology, 2022)
Summary Zinc concentrations in pelagic surface waters are within the range that limits growth in marine phytoplankton cultures. However, the influence of zinc on marine primary production and phytoplankton communities is not straightforward due to largely uncharacterized abilities for some phytoplankton to access zinc species that may not be universally bioavailable and substitute zinc with cobalt or cadmium. We used a quantitative proteomic approach to investigate these strategies and other responses to zinc limitation in the coccolithophore Emiliania huxleyi , a dominant species in low zinc waters. Zinc limitation resulted in the upregulation of metal transport proteins (ZIP, TroA‐like) and COG0523 metallochaperones. Some proteins were uniquely sensitive to growth under replete zinc, substitution of zinc with cobalt, or enhancement of growth with cadmium, and may be useful as biomarkers of zinc stress or substitution in situ . Several proteins specifically upregulated under cobalt‐supported or cadmium‐enhanced growth appear to reflect stress responses, despite titration of these metals to optimal nutritive levels. Relief from zinc limitation by zinc or cadmium resulted in increased expression of a δ‐carbonic anhydrase. Our inability to detect metal binding enzymes that are specifically induced under cobalt‐ or cadmium‐supported growth suggests cambialism is important for zinc substitution in E. huxleyi .

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Participatory multi-stakeholder assessment of alternative development scenarios in contested landscapes - Milena Kiatkoski Kim; Jorge G. Álvarez-Romero; Ken Wallace; David Pannell; Rosemary Hill; Vanessa M. Adams; Michael Douglas; Robert L. Pressey (Sustainability Science, 2022)

Rapid spatial expansion and population increase of invasive lionfish (Pterois spp.) observed on natural habitats in the northern Gulf of Mexico - Matthew D. Campbell; Adam G. Pollack; Kevin Thompson; Ted Switzer; William B. Driggers; Eric R. Hoffmayer; Sean Keenan; Chris Gardner; David Hanisko; Kevin R. Rademacher; Kate Overly (Biological Invasions, 2022)

Interannual climate variability mediates changes in carbon and nitrogen pools caused by annual grass invasion in a semiarid shrubland - Adam L. Mahood; Rachel O. Jones; David I. Board; Jennifer K. Balch; Jeanne C. Chambers (Global Change Biology, 2022)
Exotic plant invasions alter ecosystem properties and threaten ecosystem functions globally. Interannual climate variability (ICV) influences both plant community composition (PCC) and soil properties, and interactions between ICV and PCC may influence nitrogen (N) and carbon (C) pools. We asked how ICV and non‐native annual grass invasion covary to influence soil and plant N and C in a semiarid shrubland undergoing widespread ecosystem transformation due to invasions and altered fire regimes. We sampled four progressive stages of annual grass invasion at 20 sites across a large (25,000 km 2 ) landscape for plant community composition, plant tissue N and C, and soil total N and C in 2013 and 2016, which followed 2 years of dry and wet conditions, respectively. Multivariate analyses and ANOVAs showed that in invasion stages where native shrub and perennial grass and forb communities were replaced by annual grass‐dominated communities, the ecosystem lost more soil N and C in wet years. Path analysis showed that high water availability led to higher herbaceous cover in all invasion stages. In stages with native shrubs and perennial grasses, higher perennial grass cover was associated with increased soil C and N, while in annual‐dominated stages, higher annual grass cover was associated with losses of soil C and N. Also, soil total C and C:N ratios were more homogeneous in annual‐dominated invasion stages as indicated by within‐site standard deviations. Loss of native shrubs and perennial grasses and forbs coupled with annual grass invasion may lead to long‐term declines in soil N and C and hamper restoration efforts. Restoration strategies that use innovative techniques and novel species to address increasing temperatures and ICV and emphasize maintaining plant community structure—shrubs, grasses, and forbs—will allow sagebrush ecosystems to maintain C sequestration, soil fertility, and soil heterogeneity.

Report of the ACPSEM radiation oncology medical physics workforce modelling project task group - Scott Crowe; Trent Aland; Lotte Fog; Lynne Greig; Lynsey Hamlett; Jenny Lydon; David Waterhouse; Darren Doromal; Adam Sawers; Howell Round (Physical and Engineering Sciences in Medicine, 2021)

Hotter droughts alter resource allocation to chemical defenses in piñon pine - Amy M. Trowbridge; Henry D. Adams; Adam Collins; Lee Turin Dickman; Charlotte Grossiord; Megan Hofland; Shealyn Malone; David K. Weaver; Sanna Sevanto; Paul C. Stoy; Nate G. McDowell (Oecologia, 2021)
Heat and drought affect plant chemical defenses and thereby plant susceptibility to pests and pathogens. Monoterpenes are of particular importance for conifers as they play critical roles in defense against bark beetles. To date, work seeking to understand the impacts of heat and drought on monoterpenes has primarily focused on young potted seedlings, leaving it unclear how older age classes that are more vulnerable to bark beetles might respond to stress. Furthermore, we lack a clear picture of what carbon resources might be prioritized to support monoterpene synthesis under drought stress. To address this, we measured needle and woody tissue monoterpene concentrations and physiological variables simultaneously from mature piñon pines ( Pinus edulis ) from a unique temperature and drought manipulation field experiment. While heat had no effect on total monoterpene concentrations, trees under combined heat and drought stress exhibited ~ 85% and 35% increases in needle and woody tissue, respectively, over multiple years. Plant physiological variables like maximum photosynthesis each explained less than 10% of the variation in total monoterpenes for both tissue types while starch and glucose + fructose measured 1-month prior explained ~ 45% and 60% of the variation in woody tissue total monoterpene concentrations. Although total monoterpenes increased under combined stress, some key monoterpenes with known roles in bark beetle ecology decreased. These shifts may make trees more favorable for bark beetle attack rather than well defended, which one might conclude if only considering total monoterpene concentrations. Our results point to cumulative and synergistic effects of heat and drought that may reprioritize carbon allocation of specific non-structural carbohydrates toward defense.

Establishment of a microsatellite genetic baseline for North American Atlantic sturgeon (Acipenser o. oxyrhinchus) and range-wide analysis of population genetics - Shannon L. White; David C. Kazyak; Tanya L. Darden; Daniel J. Farrae; Barbara A. Lubinski; Robin L. Johnson; Michael S. Eackles; Matthew T. Balazik; Harold M. Brundage; Adam G. Fox; Dewayne A. Fox; Christian H. Hager; et al. (Conservation Genetics, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Large Vessel Activity and Low-Frequency Underwater Sound Benchmarks in United States Waters - Samara M. Haver; Jeffrey D. Adams; Leila T. Hatch; Sofie M. Van Parijs; Robert P. Dziak; Joseph Haxel; Scott A. Heppell; Megan F. McKenna; David K. Mellinger; Jason Gedamke (Frontiers in Marine Science, 2021)
Chronic low-frequency noise from commercial shipping is a worldwide threat to marine animals that rely on sound for essential life functions. Although the U.S. National Oceanic and Atmospheric Administration recognizes the potential negative impacts of shipping noise in marine environments, there are currently no standard metrics to monitor and quantify shipping noise in U.S. marine waters. However, one-third octave band acoustic measurements centered at 63 and 125 Hz are used as international (European Union Marine Strategy Framework Directive) indicators for underwater ambient noise levels driven by shipping activity. We apply these metrics to passive acoustic monitoring data collected over 20 months in 2016–2017 at five dispersed sites throughout the U.S. Exclusive Economic Zone: Alaskan Arctic, Hawaii, Gulf of Mexico, Northeast Canyons and Seamounts Marine National Monument (Northwest Atlantic), and Cordell Bank National Marine Sanctuary (Northeast Pacific). To verify the relationship between shipping activity and underwater sound levels, vessel movement data from the Automatic Identification System (AIS) were paired to each passive acoustic monitoring site. Daily average sound levels were consistently near to or higher than 100 dB re 1 μPa in both the 63 and 125 Hz one-third octave bands at sites with high levels of shipping traffic (Gulf of Mexico, Northeast Canyons and Seamounts, and Cordell Bank). Where cargo vessels were less common (the Arctic and Hawaii), daily average sound levels were comparatively lower. Specifically, sound levels were ∼20 dB lower year-round in Hawaii and ∼10-20 dB lower in the Alaskan Arctic, depending on the season. Although these band-level measurements can only generally facilitate differentiation of sound sources, these results demonstrate that international acoustic indicators of commercial shipping can be applied to data collected in U.S. waters as a unified metric to approximate the influence of shipping as a driver of ambient noise levels, provide critical information to managers and policy makers about the status of marine environments, and to identify places and times for more detailed investigation regarding environmental impacts.

Rapid detection of NDM and VIM carbapenemase encoding genes by recombinase polymerase amplification and lateral flow–based detection - Abdulrahman K. S. Ayfan; Joanne Macdonald; Patrick N. A. Harris; Claire Heney; David L. Paterson; Ella Trembizki; Claire Y. T. Wang; David M. Whiley; Hosam M. Zowawi; Adam D. Irwin (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

First Assessment of the Impacts of the COVID-19 Pandemic on Global Marine Recreational Fisheries - Pablo Pita; Gillian B. Ainsworth; Bernardino Alba; Antônio B. Anderson; Manel Antelo; Josep Alós; Iñaki Artetxe; Jérôme Baudrier; José J. Castro; Belén Chicharro; Karim Erzini; Keno Ferter; et al. (Frontiers in Marine Science, 2021)
This work is the result of an international research effort to determine the main impacts of the COVID-19 pandemic on marine recreational fishing. Changes were assessed on (1) access to fishing, derived from lockdowns and other mobility restrictions; (2) ecosystems, because of alterations in fishing intensity and human presence; (3) the blue economy, derived from alterations in the investments and expenses of the fishers; and (4) society, in relation to variations in fishers’ health and well-being. For this, a consultation with experts from 16 countries was carried out, as well as an international online survey aimed at recreational fishers, that included specific questions designed to capture fishers’ heterogeneity in relation to behavior, skills and know-how, and vital involvement. Fishers’ participation in the online survey (5,998 recreational fishers in 15 countries) was promoted through a marketing campaign. The sensitivity of the fishers’ clustering procedure, based on the captured heterogeneity, was evaluated by SIMPER analysis and by generalized linear models. Results from the expert consultation highlighted a worldwide reduction in marine recreational fishing activity. Lower human-driven pressures are expected to generate some benefits for marine ecosystems. However, experts also identified high negative impacts on the blue economy, as well as on fisher health and well-being because of the loss of recreational fishing opportunities. Most (98%) of the fishers who participated in the online survey were identified as advanced , showing a much higher degree of commitment to recreational fishing than basic fishers (2%). Advanced fishers were, in general, more pessimistic about the impacts of COVID-19, reporting higher reductions in physical activity and fish consumption, as well as poorer quality of night rest, foul mood, and raised more concerns about their health status. Controlled and safe access to marine recreational fisheries during pandemics would provide benefits to the health and well-being of people and reduce negative socioeconomic impacts, especially for vulnerable social groups.

Life cycle GHG assessment of magnetic bearing and oil lubricated bearing water cooled chillers - Emillo Byrd; Benjamin Netzel; David Brent Adams; Hao Zhang (Journal of Industrial Ecology, 2021)
Chillers are an important component of the heating ventilation, and air conditioning industry which is one of the largest energy consuming sectors. Magnetic bearing systems have been adopted in the chiller industry to improve compressor efficiency. A life cycle assessment (LCA) of greenhouse gas emissions of magnetic bearing chillers, with a particular focus on the manufacturing stage, has not previously been conducted. This study evaluated global warming potentials of two water chiller systems, an oil lubricated bearing system, and a magnetic bearing system, over their life cycle stages including raw material extraction, manufacturing, transportation, use, and the end of life. The standard ISO 14044 LCA framework was employed to assess the two 500‐ton cooling capacity chillers from a US chiller manufacturing company. Uncertainty analysis was conducted on carbon emission factors from the research literature and sensitivity analysis was conducted on key variables including power mix emission factor, chiller efficiency, and transportation method. The results show that magnetic bearing systems perform better with respect to life cycle GHG emissions. For a general water chiller system life cycle, over 90% of the emissions result from electricity consumption during the use stage with the next largest emissions arising from material extraction and manufacturing. While the material use and manufacturing GHG emissions are similar in the two systems, due to its higher compressor efficiency the magnetic bearing system generates fewer GHG emissions in the use stage. Sensitivity analysis was conducted on electricity mix, non‐standard part load value (NPLV), and transportation method. When the factor values were varied with 5% steps to ±25%, the chiller efficiency and power mix emission factors behaved in similar ways in improving life cycle GHG emissions. NPLV, however, becomes more challenging to improve despite the long history of research on compressor efficiency. This study not only provides analytical data at the product level as to how much GHG emissions can be reduced by improving compressor efficiency and incorporating clean energy, but also provides life cycle GHG inventory data for different end of life and transportation strategies.

The San Diego Nathan Shock Center: tackling the heterogeneity of aging - Gerald S. Shadel; Peter D. Adams; W. Travis Berggren; Jolene K. Diedrich; Kenneth E. Diffenderfer; Fred H. Gage; Nasun Hah; Malene Hansen; Martin W. Hetzer; Anthony J. A. Molina; Uri Manor; Kurt Marek; et al. (GeroScience, 2021)

Local Treatment of Non-small Cell Lung Cancer with a Spray-Dried Bevacizumab Formulation - Kimberly B. Shepard; David T. Vodak; Philip J. Kuehl; David Revelli; Yue Zhou; Amanda M. Pluntze; Molly S. Adam; Julia C. Oddo; Lauren Switala; Jonathan L. Cape; John M. Baumann; Michael Banks (AAPS PharmSciTech, 2021)
Local delivery of biotherapeutics to the lung holds great promise for treatment of lung diseases, but development of physically stable, biologically active dry powder formulations of large molecules for inhalation has remained a challenge. Here, spray drying was used to manufacture a dry powder pulmonary formulation of bevacizumab, a monoclonal antibody approved to treat non-small cell lung cancer (NSCLC) by intravenous infusion. By reformulating bevacizumab for local delivery, reduced side effects, lower doses, and improved patient compliance are possible. The formulation had aerosol properties suitable for delivery to the deep lung, as well as good physical stability at ambient temperature for at least 6 months. Bevacizumab’s anti-VEGF bioactivity was not impacted by the manufacturing process. The formulation was efficacious in an in vivo rat model for NSCLC at a 10-fold decrease in dose relative to the intravenous control.

Quota allocation for stocks that span multiple management zones: analysis with a vector autoregressive spatiotemporal model - Charles F. Adams; Elizabeth N. Brooks; Christopher M. Legault; Melanie A. Barrett; David F. Chevrier (Fisheries Management and Ecology, 2021)
Allocating quotas among stakeholders requires an agreed‐upon formula. If the stock unit spans multiple management jurisdictions, the formula may require updated biomass estimates of the stock's spatial distribution with respect to those jurisdictions. Data for calculating stock biomass often come from fishery‐independent surveys. While stratified random sampling is a common design, strata boundaries may not always align with state or national jurisdictions, requiring post hoc stratification and imputation to calculate area‐specific biomass. The vector autoregressive spatiotemporal (VAST) model was explored as a tool for calculating fish biomass within subareas of a defined stock unit for three different stocks jointly managed by the United States and Canada on Georges Bank in the Northwest Atlantic Ocean. VAST estimated proportions of stock biomass in each nation's waters were compared with an existing allocation algorithm that utilises a loess smooth through the average design‐based swept area biomass from three fishery‐independent surveys. The ability of VAST to impute biomass when no tows occur in a subarea of a survey stratum was demonstrated, as well as the relatively smoother biomass trend compared with design‐based estimates, which may be desirable if the intent is to avoid large inter‐annual swings in allocated quota.

Correction to: Field evaluation of seven products to control cyanobacterial blooms in aquaculture - Riley P. Buley; Catie Adams; Angelea P. Belfiore; Edna G. Fernandez-Figueroa; Matthew F. Gladfelter; Brynne Garner; David L. Straus; Alan E. Wilson (Environmental Science and Pollution Research, 2021)

Dihydroceramide Desaturase Functions as an Inducer and Rectifier of Apoptosis: Effect of Retinol Derivatives, Antioxidants and Phenolic Compounds - Mariam Alsanafi; Ryan D. R. Brown; Jeongah Oh; David R. Adams; Federico Torta; Nigel J. Pyne; Susan Pyne (Cell Biochemistry and Biophysics, 2021)
Dihydroceramide desaturase (Degs1) catalyses the introduction of a 4,5- trans double bond into dihydroceramide to form ceramide. We show here that Degs1 is polyubiquitinated in response to retinol derivatives, phenolic compounds or anti-oxidants in HEK293T cells. The functional predominance of native versus polyubiquitinated forms of Degs1 appears to govern cytotoxicity. Therefore, 4-HPR or celecoxib appear to stimulate the de novo ceramide pathway (with the exception of C24:0 ceramide), using native Degs1, and thereby promote PARP cleavage and LC3B-I/II processing (autophagy/apoptosis). The ubiquitin-proteasomal degradation of Degs1 is positively linked to cell survival via XBP-1s and results in a concomitant increase in dihydroceramides and a decrease in C24:0 ceramide levels. However, in the case of 4-HPR or celecoxib, the native form of Degs1 functionally predominates, such that the apoptotic programme is sustained. In contrast, 4-HPA or AM404 do not produce apoptotic ceramide, using native Degs1, but do promote a rectifier function to induce ubiquitin-proteasomal degradation of Degs1 and are not cytotoxic. Therefore, Degs1 appears to function both as an ‘inducer’ and ‘rectifier’ of apoptosis in response to chemical cellular stress, the dynamic balance for which is dependent on the nature of chemical stress, thereby determining cytotoxicity. The de novo synthesis of ceramide or the ubiquitin-proteasomal degradation of Degs1 in response to anti-oxidants, retinol derivatives and phenolic compounds appear to involve sensors, and for rectifier function, this might be Degs1 itself.

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

The dimensionality and structure of species trait spaces - David Mouillot; Nicolas Loiseau; Matthias Grenié; Adam C. Algar; Michele Allegra; Marc W. Cadotte; Nicolas Casajus; Pierre Denelle; Maya Guéguen; Anthony Maire; Brian Maitner; Brian J. McGill; et al. (Ecology Letters, 2021)
Trait‐based ecology aims to understand the processes that generate the overarching diversity of organismal traits and their influence on ecosystem functioning. Achieving this goal requires simplifying this complexity in synthetic axes defining a trait space and to cluster species based on their traits while identifying those with unique combinations of traits. However, so far, we know little about the dimensionality, the robustness to trait omission and the structure of these trait spaces. Here, we propose a unified framework and a synthesis across 30 trait datasets representing a broad variety of taxa, ecosystems and spatial scales to show that a common trade‐off between trait space quality and operationality appears between three and six dimensions. The robustness to trait omission is generally low but highly variable among datasets. We also highlight invariant scaling relationships, whatever organismal complexity, between the number of clusters, the number of species in the dominant cluster and the number of unique species with total species richness. When species richness increases, the number of unique species saturates, whereas species tend to disproportionately pack in the richest cluster. Based on these results, we propose some rules of thumb to build species trait spaces and estimate subsequent functional diversity indices.

Estimating Fishing Effort and Spatio-Temporal Distribution of Longline Vessels in the Indian Ocean - Febrianto W. Utama; Xavier Hoenner; Britta Denise Hardesty; David Peel; Jessica H. Ford; Vanessa Adams; Chris Wilcox (Frontiers in Marine Science, 2021)
Protein from fish is essential for feeding the world’s population and is increasingly recognized as critical for food security. To ensure that fisheries resources can be sustainably maintained, fisheries management must be appropriately implemented. When logbook and landing records data are not complete or are incorrect, it is challenging to have an accurate understanding of catch volume. Focusing on Indonesian longline vessels operating in the Indian Ocean from 2012–2019 ( n = 1124 vessels), our aims were to (1) assess compliance through identification of landing sites and potentially illicit behavior inferred by interruptions in VMS transmission, and (2) understand how the fishery operates along with quantifying the spatio-temporal distribution of fishing intensity by applying a Hidden Markov Model, which automatically classified each VMS position as fishing, steaming and anchoring. We found vessel compliance gaps in 90% of vessels in the dataset. Compliance was questionable due both to the widespread occurrence of long intermissions in relaying VMS positions (mean = 17.8 h, n = 973 vessels) and the use of unauthorized landing sites. We also observed substantial changes in fishing effort locations among years. The introduction of regulatory measures during the study period banning transshipment and foreign vessels may be responsible for the spatial shift in fishing activity we observed, from encompassing nearly the whole Indian Ocean to more recent intense efforts off western Sumatra and northern Australia.

Consensus Guidelines for Advancing Coral Holobiont Genome and Specimen Voucher Deposition - Christian R. Voolstra; Kate M. Quigley; Sarah W. Davies; John Everett Parkinson; Raquel S. Peixoto; Manuel Aranda; Andrew C. Baker; Adam R. Barno; Daniel J. Barshis; Francesca Benzoni; Victor Bonito; David G. Bourne; et al. (Frontiers in Marine Science, 2021)
Coral research is being ushered into the genomic era. To fully capitalize on the potential discoveries from this genomic revolution, the rapidly increasing number of high-quality genomes requires effective pairing with rigorous taxonomic characterizations of specimens and the contextualization of their ecological relevance. However, to date there is no formal framework that genomicists, taxonomists, and coral scientists can collectively use to systematically acquire and link these data. Spurred by the recently announced “Coral symbiosis sensitivity to environmental change hub” under the “Aquatic Symbiosis Genomics Project” - a collaboration between the Wellcome Sanger Institute and the Gordon and Betty Moore Foundation to generate gold-standard genome sequences for coral animal hosts and their associated Symbiodiniaceae microalgae (among the sequencing of many other symbiotic aquatic species) - we outline consensus guidelines to reconcile different types of data. The metaorganism nature of the coral holobiont provides a particular challenge in this context and is a key factor to consider for developing a framework to consolidate genomic, taxonomic, and ecological (meta)data. Ideally, genomic data should be accompanied by taxonomic references, i.e., skeletal vouchers as formal morphological references for corals and strain specimens in the case of microalgal and bacterial symbionts (cultured isolates). However, exhaustive taxonomic characterization of all coral holobiont member species is currently not feasible simply because we do not have a comprehensive understanding of all the organisms that constitute the coral holobiont. Nevertheless, guidelines on minimal, recommended, and ideal-case descriptions for the major coral holobiont constituents (coral animal, Symbiodiniaceae microalgae, and prokaryotes) will undoubtedly help in future referencing and will facilitate comparative studies. We hope that the guidelines outlined here, which we will adhere to as part of the Aquatic Symbiosis Genomics Project sub-hub focused on coral symbioses, will be useful to a broader community and their implementation will facilitate cross- and meta-data comparisons and analyses.

Pandora: 4-D White Matter Bundle Population-Based Atlases Derived from Diffusion MRI Fiber Tractography - Colin B Hansen; Qi Yang; Ilwoo Lyu; Francois Rheault; Cailey Kerley; Bramsh Qamar Chandio; Shreyas Fadnavis; Owen Williams; Andrea T. Shafer; Susan M. Resnick; David H. Zald; Laurie E Cutting; et al. (Neuroinformatics, 2021)

A Seasonal Climatology of the Mexico City Atmospheric Boundary Layer - Andrea Burgos-Cuevas; David K. Adams; Jorge Luis García-Franco; Angel Ruiz-Angulo (Boundary-Layer Meteorology, 2021)

Isotopic analyses of prehistoric human remains from the Flinders Group, Queensland, Australia, support an association between burial practices and status - Shaun Adams; Michael C. Westaway; David McGahan; Doug Williams; Jian-Xin Zhao; Yuexing Feng; Ai Nguyen; John Pearce; Clarence Flinders; Mark Collard (Archaeological and Anthropological Sciences, 2021)

Unravelling the taxonomy and identification of a problematic group of benthic fishes from tropical rivers (Gobiidae: Glossogobius ) - Michael P. Hammer; Laura Taillebois; Alison J. King; David A. Crook; Dion Wedd; Mark Adams; Peter J. Unmack; Doug F. Hoese; Terry Bertozzi (Journal of Fish Biology, 2021)
Flathead gobies (genus Glossogobius ) include c . 40 small‐ to medium‐sized benthic fishes found primarily in freshwater habitats across the Indo‐Pacific, having biodiversity value as well as cultural and economic value as food fishes, especially in developing countries. To help resolve considerable confusion regarding the identification of some of the larger‐growing Glossogobius species, a systematic framework was established using nuclear genetic markers, mitochondrial DNA barcoding and phenotypic evidence for a geographically widespread collection of individuals from the waterways of tropical northern Australia. Species boundaries and distribution patterns were discordant with those previously reported, most notably for the tank goby Glossogobius giuris , which included a cryptic species. Genetic divergence was matched with accompanying unique visual characters that aid field identification. Additional taxonomic complexity was also evident, by comparison with DNA barcodes from international locations, suggesting that the specific names applicable for two of the candidate species in Australia remain unresolved due to confusion surrounding type specimens. Although flathead gobies are assumed to be widespread and common, this study demonstrates that unrealised taxonomic and ecological complexity is evident, and this will influence assessments of tropical biodiversity and species conservation. This study supports the need for taxonomic studies of freshwater fishes to underpin management in areas subject to significant environmental change.

Important questions to progress science and sustainable management of anguillid eels - David Righton; Adam Piper; Kim Aarestrup; Elsa Amilhat; Claude Belpaire; John Casselman; Martin Castonguay; Estibaliz Díaz; Hendrik Dörner; Elisabeth Faliex; Eric Feunteun; Nobuto Fukuda; et al. (Fish and Fisheries, 2021)
Anguillid eels are found globally in fresh, transitional and saline waters and have played an important role in human life for centuries. The population status of several species is now of significant concern. The threats to populations include direct exploitation at different life stages, blockages to migratory routes by dams and other structures, changes in river basin management that impact habitat carrying capacity and suitability, pollution, climate change, diseases and parasites. While much has been done to understand eel biology and ecology, a major challenge is to identify the key research and management questions so that effective and targeted studies can be designed to inform conservation, management and policy. We gathered 30 experts in the field of eel biology and management to review the current state of knowledge for anguillid eel species and to identify the main topics for research. The identified research topics fell into three themes: (a) Lifecycle and Biology; (b) Impacts and (c) Management. Although tropical anguillid eels are by far the least well understood, significant knowledge gaps exist for all species. Considerable progress has been made in the last 20 years, but the status of many species remains of great concern, particularly for northern temperate species. Without improved engagement and coordination at the regional, national and international level, the situation is unlikely to improve. Further, adaptive management mechanisms to respond to developments in science, policy and our knowledge of potential threats are required to ensure the future of these important and enigmatic species.

Efficacy and Safety of Intravenous rtPA in Ischemic Strokes Due to Small-Vessel Occlusion: Systematic Review and Meta-Analysis - Bartosz Karaszewski; Adam Wyszomirski; Bartosz Jabłoński; David J. Werring; Dominika Tomaka (Translational Stroke Research, 2021)
Intravenous recombinant tissue plasminogen activator (iv-rtPA) has been routinely used to treat ischemic stroke for 25 years, following large clinical trials. However, there are few prospective studies on the efficacy and safety of this therapy in strokes attributed to cerebral small vessel disease (SVD). We evaluated functional outcome (modified Rankin scale, mRS) and symptomatic intracerebral hemorrhage (sICH) using all available data on the effects of iv-rtPA in SVD-related ischemic stroke (defined either using neuroimaging, clinical features, or both). Using fixed-effect and random-effects models, we calculated the pooled effect estimates with regard to excellent and favorable outcomes (mRS=0–1 and 0–2 respectively, at 3 months), and the rate of sICH. Twenty-three studies fulfilled the eligibility criteria, 11 of which were comparative, and there were only 3 randomized clinical trials. In adjusted analyses, there was an increased odds of excellent outcome (adjusted OR=1.53, 95% CI: 1.29–1.82, I2: 0%) or favorable outcome (adjusted OR=1.68, 95% CI: 1.31–2.15,I2: 0%) in patients who received iv-rtPA compared with placebo. Across the six studies which reported it, the incidence of sICH was higher in the treatment group (M-H RR = 8.83, 95% CI: 2.76–28.27). The pooled rate of sICH in patients with SVD administered iv-rtPA was only 0.72% (95% CI: 0.12%–1.64%). We conclude that when ischemic stroke attributed to SVD is considered separately, available data on the effects of iv-rtPA therapy are insufficient for the highest level of recommendation, but it seems to be safe. Although further therapeutic trials in SVD-related ischemic stroke appear to be justified, our findings should not prevent its continued use for this group of patients in clinical practice.

Evidence of historical isolation and genetic structuring among broadnose sevengill sharks (Notorynchus cepedianus) from the world’s major oceanic regions - Alicia C. J. Schmidt-Roach; Christine C. Bruels; Adam Barnett; Adam D. Miller; Craig D. H. Sherman; David A. Ebert; Sebastian Schmidt-Roach; Charlene da Silva; Christopher G. Wilke; Craig Thorburn; Jeffrey C. Mangel; Juan Manuel Ezcurra; et al. (Reviews in Fish Biology and Fisheries, 2021)

Is impaired dopaminergic function associated with mobility capacity in older adults? - Simon Moskowitz; David W. Russ; Leatha A. Clark; Nathan P. Wages; Dustin R. Grooms; Adam J. Woods; Julie Suhr; Janet E. Simon; Andrew O’Shea; Cody R. Criss; Paolo Fadda; Brian C. Clark (GeroScience, 2021)

Genetic structure and effective population size of Sydney rock oysters in eastern Australia - Jessica A. O’Hare; Paolo Momigliano; David A. Raftos; Adam J. Stow (Conservation Genetics, 2021)

Novel atypical Aeromonas salmonicida bath challenge model for juvenile ballan wrasse ( Labrus bergylta, Ascanius) - Athina Papadopoulou; Kathryn Garvey; Tom Hill; Jose G. Ramirez‐Paredes; Sean J. Monaghan; Johanna L. Baily; Andrew Davie; Ioanna Katsiadaki; David Verner‐Jeffreys; Timothy Wallis; Herve Migaud; Alexandra Adams (Journal of Fish Diseases, 2021)
Atypical Aeromonas salmonicida (a As ) is currently one of the most routinely recovered bacterial pathogens isolated during disease outbreaks in farmed cleaner fish, ballan wrasse ( Labrus bergylta , Ascanius). Vibrionaceae family bacteria have also been isolated from ballan wrasse in Scotland. This study determined the infectivity, pathogenicity and virulence of a As and Vibrionaceae isolates in juvenile farmed ballan wrasse ( n = 50; approx. 2 g) using a bath challenge, and fish were monitored for a period of 16 days. Atypical As caused significant mortalities in contrast to Vibrionaceae isolates. Notably, differential virulence was observed between two a As vapA type V strains at similar challenge doses. Diseased fish exhibited a systemic infection where a As was detected in all analysed tissues (liver, spleen and kidney) by PCR and qPCR. Macroscopically, moribund and survivor fish exhibited hepatomegaly and splenomegaly. In moribund and surviving fish, histopathology showed granulomatous hepatitis with eosinophilic granular cells surrounding bacterial colonies and endocarditis along with splenic histiocytosis. This is the first report of a successful a As bath challenge model for juvenile ballan wrasse which provides an important tool for future studies on vaccine efficacy and immunocompetence.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Correction to: Neighbourhood effects modify deer herbivory on tree seedlings - Jan Holík; David Janík; Libor Hort; Dušan Adam (European Journal of Forest Research, 2021)

Neighbourhood effects modify deer herbivory on tree seedlings - Jan Holík; David Janík; Libor Hort; Dušan Adam (European Journal of Forest Research, 2021)

Correction to: conceptual framing to link climate risk assessments and climate-migration scholarship - Robert McLeman; David Wrathall; Elisabeth Gilmore; Philip Thornton; Helen Adams; François Gemenne (Climatic Change, 2021)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Conceptual framing to link climate risk assessments and climate-migration scholarship - Robert McLeman; David Wrathall; Elisabeth Gilmore; Philip Thornton; Helen Adams; François Gemenne (Climatic Change, 2021)

Ontogenetic scaling of the gastrointestinal tract of a marsupial foregut fermenter, the western grey kangaroo Macropus fuliginosus melanops - Adam J. Munn; Edward P. Snelling; David A. Taggart; Roger S. Seymour (Journal of Comparative Physiology B, 2021)

Turbulence in a small boreal lake: Consequences for air–water gas exchange - Sally MacIntyre; David Bastviken; Lars Arneborg; Adam T. Crowe; Jan Karlsson; Andreas Andersson; Magnus Gålfalk; Anna Rutgersson; Eva Podgrajsek; John M. Melack (Limnology and Oceanography, 2021)
The hydrodynamics within small boreal lakes have rarely been studied, yet knowing whether turbulence at the air–water interface and in the water column scales with metrics developed elsewhere is essential for computing metabolism and fluxes of climate‐forcing trace gases. We instrumented a humic, 4.7 ha, boreal lake with two meteorological stations, three thermistor arrays, an infrared (IR) camera to quantify surface divergence, obtained turbulence as dissipation rate of turbulent kinetic energy ( ε ) using an acoustic Doppler velocimeter and a temperature‐gradient microstructure profiler, and conducted chamber measurements for short periods to obtain fluxes and gas transfer velocities ( k ). Near‐surface ε varied from 10 −8 to 10 −6 m 2 s −3 for the 0–4 m s −1 winds and followed predictions from Monin–Obukhov similarity theory. The coefficient of eddy diffusivity in the mixed layer was up to 10 −3 m 2 s −1 on the windiest afternoons, an order of magnitude less other afternoons, and near molecular at deeper depths. The upper thermocline upwelled when Lake numbers ( L N ) dropped below four facilitating vertical and horizontal exchange. k computed from a surface renewal model using ε agreed with values from chambers and surface divergence and increased linearly with wind speed. Diurnal thermoclines formed on sunny days when winds were −1 , a condition that can lead to elevated near‐surface ε and k . Results extend scaling approaches developed in the laboratory and for larger water bodies, illustrate turbulence and k are greater than expected in small wind‐sheltered lakes, and provide new equations to quantify fluxes.

Directed evolution of the B. subtilis nitroreductase YfkO improves activation of the PET-capable probe SN33623 and CB1954 prodrug - Michelle H. Rich; Abigail V. Sharrock; Amir Ashoorzadeh; Adam V. Patterson; Jeff B. Smaill; David F. Ackerley (Biotechnology Letters, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Mercury exposure in songbird communities along an elevational gradient on Whiteface Mountain, Adirondack Park (New York, USA) - Amy K. Sauer; Charles T. Driscoll; David C. Evers; Evan M. Adams; Yang Yang (Ecotoxicology, 2020)

Mercury exposure in songbird communities within Sphagnum bog and upland forest ecosystems in the Adirondack Park (New York, USA) - Amy K. Sauer; Charles T. Driscoll; David C. Evers; Evan M. Adams; Yang Yang (Ecotoxicology, 2020)

The effects of climate, habitat, and trophic position on methylmercury bioavailability for breeding New York songbirds - Evan M. Adams; Amy K. Sauer; Oksana Lane; Kevin Regan; David C. Evers (Ecotoxicology, 2020)

Volatile Organic Compounds as Insect Repellents and Plant Elicitors: an Integrated Pest Management (IPM) Strategy for Glasshouse Whitefly (Trialeurodes vaporariorum) - Niall J.A. Conboy; Thomas McDaniel; David George; Adam Ormerod; Martin Edwards; Paul Donohoe; Angharad M. R Gatehouse; Colin R. Tosh (Journal of Chemical Ecology, 2020)
The glasshouse whitefly ( Trialeurodes vaporariorum Westwood) is a polyphagous arthropod pest that is of particular detriment to glasshouse grown tomato ( Solanum lycopersicum ) across temperate regions of the world. Control of whiteflies with synthetic pesticides has resulted in the evolution of resistant genotypes and a reduction in natural enemies, thus highlighting the need for environmentally sound control strategies. Volatile organic compounds (VOCs) offer an environmentally benign alternative to synthetic chemical sprays and this study explored the use of VOCs as insect repellents and plant defence elicitors to control whiteflies on tomato in a commercial glasshouse setting. Limonene in the form of a volatile dispenser system was found to successfully repel whitefly from the target crop and increased fruit yield by 32% during a heavy whitefly infestation. Analysis of tomato herbivore induced plant volatiles (HIPVs) led us to select methyl salicylate (MeSA) as the plant elicitor and application of MeSA to un-infested tomato plants was found to successfully reduce whitefly population development and increase yield by 11%, although this difference was marginally statistically significant. Combination of these two methods was also effective but whitefly abundance in combined plots was similar to the standalone limonene treatment across the course of the experiment. All of the VOC based control methods we used had a negative impact on whitefly performance, with more pronounced effects during the first few weeks of infestation. In subsequent laboratory experiments, we found elevated peroxidase (POD) activity and a significant increase in TPX1 and PR1 transcripts in MeSA treated plants. This led us to deduce that MeSA immediately induced plant defences, rather than priming them. We did however see evidence for residual priming, as plants treated with MeSA and infested with whiteflies produced significantly higher levels of POD activity than whitefly infestation alone. Despite the fact that our treatments failed to synergise, our methods can be optimised further, and the effectiveness of the standalone treatments is promising for future studies. In particular, our repellent limonene dispensers were extremely effective at deterring whiteflies and offer a low economic cost and easy to implement whitefly control option. The methods we have used here could be incorporated into current integrated pest management (IPM) systems, a sustainable approach to pest control which will be central to our efforts to manage whitefly populations under glass in the future.

Improving Situational Awareness in the Arctic Ocean - Luc Rainville; Jeremy Wilkinson; Mary Ellen J. Durley; Scott Harper; Julia DiLeo; Martin J. Doble; Andrew Fleming; David Forcucci; Hans Graber; John T. Hargrove; John Haverlack; Nick Hughes; et al. (Frontiers in Marine Science, 2020)
To successfully operate in a harsh environment like the Arctic Ocean, one must be able to understand and predict how that environment will evolve over different spatial and temporal scales. This is particularly challenging given the on-going and significant environmental changes that are occurring in the region. Access to the most recent environmental information provides timely knowledge that enables ship-based operations to proceed efficiently, effectively and safely in this difficult arena. Knowledge of the evolving environmental conditions during a field campaign is critical for effective planning, optimal execution of sampling strategies, and to provide a broader context to data collected at specific times and places. We describe the collaborations and processes that enabled an operational system to be developed to provide a remote field-team, located on USCGC Healy in the Beaufort Sea, with near real-time situational awareness information regarding the weather, sea ice conditions, and oceanographic processes. The developed system included the punctual throughput of near real-time products such as satellite imagery, meteorological forecasts, ice charts, model outputs, and up to date locations of key sea ice and ocean-based assets. Science and operational users, as well as onshore personnel, used this system for real-time practical considerations such as ship navigation, and to time scientific operations to ensure the appropriate sea ice and weather conditions prevailed. By presenting the outputs of the system within the context of case studies our results clearly demonstrate the benefits that improved situational awareness brings to ship-based operations in the Arctic Ocean, both today and in the future.

Maternal provisioning gives young-of-the-year Hammerheads a head start in early life - Kady Lyons; Ashley S. Galloway; Douglas H. Adams; Eric A. Reyier; Amanda M. Barker; David S. Portnoy; Bryan S. Frazier (Marine Biology, 2020)
For species that do not provide parental care after birth, excess maternal provisioning during development, beyond what is required for embryogenesis, provides offspring with resources to increase their chances of survival. Maternally derived resources are expected to be important for buffering offspring against limited food resources at birth or time needed to learn how to properly feed. Young-of-the-year (YOY) cryptic Scalloped Hammerheads ( Sphyrna lewini ) and Carolina Hammerheads ( Sphyrna gilberti ) were sampled from nurseries along the US Atlantic Coast and compared for a number of biological condition metrics across three developmental stages. Large declines in liver lipid content and hepatosomatic indices were found in neonatal sharks, using umbilical scar healing as a proxy for time since birth. Feeding commenced quickly as 96% of sharks had prey remnants in their stomachs. The combination of rapid exhaustion of maternally provided resources and high occurrence of stomachs with prey contents indicate that nursery quality, with respect to prey availability, may be important for YOY hammerhead survivorship. While externally the two species are morphologically similar, longer length-at-birth in S. lewini and higher hepatic condition in neonatal S. gilberti suggest that aspects of reproductive biology, including physiology, may differ between species. While more information is needed to distinguish life history differences between these two species, data collected from YOY may serve as a useful proxy to inform management when adult samples of cryptic species are difficult to collect.

Ultraviolet-assisted oiling assessment improves detection of oiled birds experiencing clinical signs of hemolytic anemia after exposure to the Deepwater Horizon oil spill - Jesse A. Fallon; Eric P. Smith; Nina Schoch; James D. Paruk; Evan M. Adams; David C. Evers; Patrick G. R. Jodice; Marie Perkins; Dustin E. Meattey; William A. Hopkins (Ecotoxicology, 2020)

Temporally Altered miRNA Expression in a Piglet Model of Hypoxic Ischemic Brain Injury - Sophie Casey; Kate Goasdoue; Stephanie M. Miller; Gary P. Brennan; Gary Cowin; Adam G. O’Mahony; Christopher Burke; Boubou Hallberg; Geraldine B. Boylan; Aideen M. Sullivan; David C. Henshall; Gerard W. O’Keeffe; et al. (Molecular Neurobiology, 2020)

Mercury exposure in migrating songbirds: correlations with physical condition - Evan M. Adams; Kathryn A. Williams; Brian J. Olsen; David C. Evers (Ecotoxicology, 2020)

Historical patterns in mercury exposure for North American songbirds - Marie Perkins; Oksana P. Lane; David C. Evers; Amy Sauer; Evan M. Adams; Nelson J. O’Driscoll; Samuel T. Edmunds; Allyson K. Jackson; Julie C. Hagelin; Jeremiah Trimble; Elsie M. Sunderland (Ecotoxicology, 2020)

Spatial, climate and ploidy factors drive genomic diversity and resilience in the widespread grass Themeda triandra - Collin W. Ahrens; Elizabeth A. James; Adam D. Miller; Ferguson Scott; Nicola C. Aitken; Ashley W. Jones; Patricia Lu‐Irving; Justin O. Borevitz; David J. Cantrill; Paul D. Rymer (Molecular Ecology, 2020)
Global climate change poses a significant threat to natural communities around the world, with many plant species showing signs of climate stress. Grassland ecosystems are not an exception, with climate change compounding contemporary pressures such as habitat loss and fragmentation. In this study, we assess the climate resilience of Themeda triandra , a foundational species and the most widespread plant in Australia, by assessing the relative contributions of spatial, environmental and ploidy factors to contemporary genomic variation. Reduced‐representation genome sequencing on 472 samples from 52 locations was used to test how the distribution of genomic variation, including ploidy polymorphism, supports adaptation to hotter and drier climates. We explicitly quantified isolation by distance (IBD) and isolation by environment (IBE) and predicted genomic vulnerability of populations to future climates based on expected deviation from current genomic composition. We found that a majority (54%) of genomic variation could be attributed to IBD, while an additional 22% (27% when including ploidy information) could be explained by two temperature and two precipitation climate variables demonstrating IBE. Ploidy polymorphisms were common within populations (31/52 populations), indicating that ploidy mixing is characteristic of T. triandra populations. Genomic vulnerabilities were found to be heterogeneously distributed throughout the landscape, and our analysis suggested that ploidy polymorphism, along with other factors linked to polyploidy, reduced vulnerability to future climates by 60% (0.25–0.10). Our data suggests that polyploidy may facilitate adaptation to hotter climates and highlight the importance of incorporating ploidy in adaptive management strategies to promote the resilience of this and other foundation species.

Temporal variability in size and growth of Atlantic herring in the Gulf of Maine - James R. Becker; Matthew D. Cieri; David A. Libby; Adam St. Gelais; Graham Sherwood; Yong Chen (Journal of Fish Biology, 2020)
Variability in life history traits and structural diversity of commercially exploited fishes in response to stress can impact their population dynamics and sustainability. Using data from a fishery dependent sampling program from 1978 to 2011, we evaluated temporal variability of size and growth of adult Atlantic herring ( Clupea harengus ) in the Gulf of Maine. We then developed and tested the hypotheses on the links of such temporal changes to population density and environmental factors and found decreases in size and growth potential. Generalized additive models found that density dependence was the main driver of such changes over sea surface temperature and salinity. Our results highlight the importance of density dependent processes in regulating growth and population size structure for Atlantic herring in the Gulf of Maine.

Determining Stingray Movement Patterns in a Wave-Swept Coastal Zone Using a Blimp for Continuous Aerial Video Surveillance - David Ruiz-García; Kye Adams; Heidi Brown; Andrew R. Davis (Fishes, 2020)
Stingrays play a key role in the regulation of nearshore ecosystems. However, their movement ecology in high-energy surf areas remains largely unknown due to the notorious difficulties in conducting research in these environments. Using a blimp as an aerial platform for video surveillance, we overcame some of the limitations of other tracking methods, such as the use of tags and drones. This novel technology offered near-continuous coverage to characterise the fine-scale movements of stingrays in a surf area in Kiama, Australia, without any invasive procedures. A total of 98 stingray tracks were recorded, providing 6 h 27 min of movement paths. The tracking data suggest that stingrays may use a depth gradient located in the sandflat area of the bay for orientating their movements and transiting between locations within their home range. Our research also indicates that stingray behaviour was influenced by diel periods and tidal states. We observed a higher stingray occurrence during the afternoon, potentially related to foraging and anti-predatory strategies. We also saw a reduced route fidelity during low tide, when the bathymetric reference was less accessible due to stranding risk. Considering the increasing threat of anthropogenic development to nearshore coastal environments, the identification of these patterns can better inform the management and mitigation of threats.

Generation of Alkalinity by Stimulation of Microbial Iron Reduction in Acid Rock Drainage Systems: Impact of Natural Organic Matter Types - Martha E. Jimenez-Castaneda; Carolina Scarinci; Adam Burke; Christopher Boothman; David J. Vaughan; Jonathan R. Lloyd; Bart E. van Dongen (Water, Air, & Soil Pollution, 2020)
To determine the role of organic matter in the attenuation of acid rock drainage (ARD), microcosm-based experiments were performed using ARD stimulated with plants and manures. Initial mineralogical, organic geochemical and microbial analyses indicated a predominance of goethite, a substantial amount of organic carbon originating from local sources, and a bacterial community comparable with those detected in a range of ARD sites worldwide. After 100 days of incubation, changes in the mineralogical, organic and microbiological composition of the ARD demonstrated that the plant additions stimulate microbes with the potential to degrade this organic matter but do not necessarily cause substantial Fe(III) reduction. Conversely, the greatest observed stimulation of Fe(III) reduction, associated with an increase in pH to near-neutral values, was observed using manure additions. These results demonstrate that the use of the optimal natural carbon source is important and can promote the metabolism of microorganisms potentially fuelling a range of geomicrobial processes, including iron and sulfate reduction.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Administration of the Probiotic Escherichia coli Strain A0 34/86 Resulted in a Stable Colonization of the Human Intestine During the First Year of Life - Lenka Micenková; Juraj Bosák; Stanislav Smatana; Adam Novotný; Eva Budinská; David Šmajs (Probiotics and Antimicrobial Proteins, 2020)

Bacterial communities on the gills of bonefish (Albula vulpes) in the Florida Keys and The Bahamas show spatial structure and differential abundance of disease-associated bacteria - Christopher D. Dunn; Lewis J. Campbell; Elizabeth M. Wallace; Andy J. Danylchuk; Steven J. Cooke; Aaron D. Shultz; Brooke D. Black; Jacob W. Brownscombe; Lucas P. Griffin; David P. Philipp; Aaron J. Adams; Tony L. Goldberg (Marine Biology, 2020)

Nitrogen Identity Drives Differential Impacts of Nutrients on Coral Bleaching and Mortality - Deron E. Burkepile; Andrew A. Shantz; Thomas C. Adam; Katrina S. Munsterman; Kelly E. Speare; Mark C. Ladd; Mallory M. Rice; Leïla Ezzat; Shelby McIlroy; Jane C. Y. Wong; David M. Baker; Andrew J. Brooks; et al. (Ecosystems, 2020)

Implementation of a Data Management Quality Management Framework at the Marine Institute, Ireland - Adam Leadbetter; Ramona Carr; Sarah Flynn; Will Meaney; Siobhan Moran; Yvonne Bogan; Laura Brophy; Kieran Lyons; David Stokes; Rob Thomas (Earth Science Informatics, 2020)
The International Oceanographic Data and Information Exchange of UNESCO’s Intergovernmental Oceanographic Commission (IOC-IODE) released a quality management framework for its National Oceanographic Data Centre (NODC) network in 2013. This document is intended, amongst other goals, to provide a means of assistance for NODCs to establish organisational data management quality management systems. The IOC-IODE’s framework also promotes the accreditation of NODCs which have implemented a Data Management Quality Management Framework adhering to the guidelines laid out in the IOC-IODE’s framework. In its submission for IOCE-IODE accreditation, Ireland’s National Marine Data Centre (hosted by the Marine Institute) included a Data Management Quality Management model; a manual detailing this model and how it is implemented across the scientific and environmental data producing areas of the Marine Institute; and, at a more practical level, an implementation pack consisting of a number of templates to assist in the compilation of the documentation required by the model and the manual.

Lifeform indicators reveal large‐scale shifts in plankton across the North‐West European shelf - Jacob Bedford; Clare Ostle; David G. Johns; Angus Atkinson; Mike Best; Eileen Bresnan; Margarita Machairopoulou; Carolyn A. Graves; Michelle Devlin; Alex Milligan; Sophie Pitois; Adam Mellor; et al. (Global Change Biology, 2020)
Increasing direct human pressures on the marine environment, coupled with climate‐driven changes, is a concern to marine ecosystems globally. This requires the development and monitoring of ecosystem indicators for effective management and adaptation planning. Plankton lifeforms (broad functional groups) are sensitive indicators of marine environmental change and can provide a simplified view of plankton biodiversity, building an understanding of change in lower trophic levels. Here, we visualize regional‐scale multi‐decadal trends in six key plankton lifeforms as well as their correlative relationships with sea surface temperature (SST). For the first time, we collate trends across multiple disparate surveys, comparing the spatially and temporally extensive Continuous Plankton Recorder (CPR) survey (offshore) with multiple long‐term fixed station‐based time‐series (inshore) from around the UK coastline. These analyses of plankton lifeforms showed profound long‐term changes, which were coherent across large spatial scales. For example, ‘diatom’ and ‘meroplankton’ lifeforms showed strong alignment between surveys and coherent regional‐scale trends, with the 1998–2017 decadal average abundance of meroplankton being 2.3 times that of 1958–1967 for CPR samples in the North Sea. This major, shelf‐wide increase in meroplankton correlated with increasing SSTs, and contrasted with a general decrease in holoplankton (dominated by small copepods), indicating a changing balance of benthic and pelagic fauna. Likewise, inshore‐offshore gradients in dinoflagellate trends, with contemporary increases inshore contrasting with multi‐decadal decreases offshore (approx. 75% lower decadal mean abundance), urgently require the identification of causal mechanisms. Our lifeform approach allows the collation of many different data types and time‐series across the NW European shelf, providing a crucial evidence base for informing ecosystem‐based management, and the development of regional adaptation plans.

Role of Quaternary glacial-outburst megaflood paleochannel deposits in a basalt-dominated aquifer system in the West Plains area of eastern Washington, USA - Chad J. Pritchard; David R. Gaylord; Drew B. Adams; Shawna Ernst; Michael Hermanson (Hydrogeology Journal, 2020)

Inter-trial phase coherence of visually evoked postural responses in virtual reality - David Engel; Adrian Schütz; Milosz Krala; Jakob C. B. Schwenk; Adam P. Morris; Frank Bremmer (Experimental Brain Research, 2020)
Vision plays a central role in maintaining balance. When humans perceive their body as moving, they trigger counter movements. This results in body sway, which has typically been investigated by measuring the body’s center of pressure (COP). Here, we aimed to induce visually evoked postural responses (VEPR) by simulating self-motion in virtual reality (VR) using a sinusoidally oscillating “moving room” paradigm. Ten healthy subjects participated in the experiment. Stimulation consisted of a 3D-cloud of random dots, presented through a VR headset, which oscillated sinusoidally in the anterior–posterior direction at different frequencies. We used a force platform to measure subjects’ COP over time and quantified the resulting trajectory by wavelet analyses including inter-trial phase coherence (ITPC). Subjects exhibited significant coupling of their COP to the respective stimulus. Even when spectral analysis of postural sway showed only small responses in the expected frequency bands (power), ITPC revealed an almost constant strength of coupling to the stimulus within but also across subjects and presented frequencies. Remarkably, ITPC even revealed a strong phase coupling to stimulation at 1.5 Hz, which exceeds the frequency range that has generally been attributed to the coupling of human postural sway to an oscillatory visual scenery. These findings suggest phase-locking to be an essential feature of visuomotor control.

Accounting for multiple ecosystem services in a simulation of land‐use decisions: Does it reduce tropical deforestation? - Thomas Knoke; Carola Paul; Anja Rammig; Elizabeth Gosling; Patrick Hildebrandt; Fabian Härtl; Thorsten Peters; Michael Richter; Karl‐Heinz Diertl; Luz Maria Castro; Baltazar Calvas; Santiago Ochoa; et al. (Global Change Biology, 2020)
Conversion of tropical forests is among the primary causes of global environmental change. The loss of their important environmental services has prompted calls to integrate ecosystem services (ES) in addition to socio‐economic objectives in decision‐making. To test the effect of accounting for both ES and socio‐economic objectives in land‐use decisions, we develop a new dynamic approach to model deforestation scenarios for tropical mountain forests. We integrate multi‐objective optimization of land allocation with an innovative approach to consider uncertainty spaces for each objective. These uncertainty spaces account for potential variability among decision‐makers, who may have different expectations about the future. When optimizing only socio‐economic objectives, the model continues the past trend in deforestation (1975–2015) in the projected land‐use allocation (2015–2070). Based on indicators for biomass production, carbon storage, climate and water regulation, and soil quality, we show that considering multiple ES in addition to the socio‐economic objectives has heterogeneous effects on land‐use allocation. It saves some natural forest if the natural forest share is below 38%, and can stop deforestation once the natural forest share drops below 10%. For landscapes with high shares of forest (38%–80% in our study), accounting for multiple ES under high uncertainty of their indicators may, however, accelerate deforestation. For such multifunctional landscapes, two main effects prevail: (a) accelerated expansion of diversified non‐natural areas to elevate the levels of the indicators and (b) increased landscape diversification to maintain multiple ES, reducing the proportion of natural forest. Only when accounting for vascular plant species richness as an explicit objective in the optimization, deforestation was consistently reduced. Aiming for multifunctional landscapes may therefore conflict with the aim of reducing deforestation, which we can quantify here for the first time. Our findings are relevant for identifying types of landscapes where this conflict may arise and to better align respective policies.

Migrations and movements of Atlantic tarpon revealed by two decades of satellite tagging - Jiangang Luo; Jerald S. Ault; Bruce T. Ungar; Steven G. Smith; Michael F. Larkin; Thomas N. Davidson; David R. Bryan; Nicholas A. Farmer; Scott A. Holt; A. Scott Alford; Aaron J. Adams; Robert Humston; et al. (Fish and Fisheries, 2020)
Understanding large‐scale migratory behaviours, local movement patterns and population connectivity are critical to determining the natural processes and anthropogenic stressors that influence population dynamics and for developing effective conservation plans. Atlantic tarpon occur over a broad geographic range in the Atlantic Ocean where they support valuable subsistence, commercial and recreational fisheries. From 2001 through 2018, we deployed 292 satellite telemetry tags on Atlantic tarpon in coastal waters off three continents to document: (a) seasonal migrations and regional population connectivity; (b) freshwater and estuarine habitat utilization; (c) spawning locations; and (d) shark predation across the south‐eastern United States, Gulf of Mexico and northern Caribbean Sea. These results showed that some mature tarpon make long seasonal migrations over thousands of kilometres crossing state and national jurisdictional borders. Others showed more local movements and habitat use. The tag data also revealed potential spawning locations consistent with those inferred in other studies from observations of early life stage tarpon leptocephalus larvae. Our analyses indicated that shark predation mortality on released tarpon is higher than previously estimated, especially at ocean passes, river mouths and inlets to bays. To date, there has been no formal stock assessment of Atlantic tarpon, and regional fishery management plans do not exist. Our findings will provide critical input to these important efforts and assist the multinational community in the development of a stock‐wide management information system to support informed decision‐making for sustaining Atlantic tarpon fisheries.

Identification and QTL mapping of resistance to Turnip yellows virus (TuYV) in oilseed rape, Brassica napus - Dieter Hackenberg; Elvis Asare-Bediako; Adam Baker; Peter Walley; Carol Jenner; Shannon Greer; Lawrence Bramham; Jacqueline Batley; David Edwards; Regine Delourme; Guy Barker; Graham Teakle; et al. (Theoretical and Applied Genetics, 2020)
Key message Partially dominant resistance to Turnip yellows virus associated with one major QTL was identified in the natural allotetraploid oilseed rape cultivar Yudal. Abstract Turnip yellows virus (TuYV) is transmitted by the peach-potato aphid ( Myzus persicae ) and causes severe yield losses in commercial oilseed rape crops ( Brassica napus ). There is currently only one genetic resource for resistance to TuYV available in brassica, which was identified in the re-synthesised B. napus line ‘R54’. In our study, 27 mostly homozygous B. napus accessions, either doubled-haploid (DH) or inbred lines, representing a diverse subset of the B. napus genepool, were screened for TuYV resistance/susceptibility. Partial resistance to TuYV was identified in the Korean spring oilseed rape, B. napus variety Yudal, whilst the dwarf French winter oilseed rape line Darmor- bzh was susceptible. QTL mapping using the established Darmor- bzh × Yudal DH mapping population (DYDH) revealed one major QTL explaining 36% and 18% of the phenotypic variation in two independent experiments. A DYDH line was crossed to Yudal, and reciprocal backcross (BC 1 ) populations from the F 1 with either the susceptible or resistant parent revealed the dominant inheritance of the TuYV resistance. The QTL on ChrA04 was verified in the segregating BC 1 population. A second minor QTL on ChrC05 was identified in one of the two DYDH experiments, and it was not observed in the BC 1 population. The TuYV resistance QTL in ‘R54’ is within the QTL interval on Chr A04 of Yudal; however, the markers co-segregating with the ‘R54’ resistance are not conserved in Yudal, suggesting an independent origin of the TuYV resistances. This is the first report of the QTL mapping of TuYV resistance in natural B. napus .

Relationships among white-tailed deer density, harvest, and landscape metrics in TN, USA - Heidi L. Adams; Robert E. Kissell; Daryl Ratajczak; Edward L. Warr; Roger D. Applegate; Lynn Barrett; Tabitha Lavacot; David Graves (European Journal of Wildlife Research, 2020)
Landscape and harvest indices are frequently used to represent white-tailed deer ( Odocoileus virginianus ) density. However, the relationship between deer density and specific landscape indices is unclear. Harvest is another metric often used to estimate deer density. Our objective was to model the relationship among deer density, landscape metrics, and harvest density of deer in TN, USA. We estimated deer density across 11 regions in 2011 using distance sampling techniques. We developed 18 a priori models to assess relationships among deer density, harvest density, and landscape metrics. Estimates of deer density ranged from 1.85 to 19.99 deer/km 2 . Deer density was best predicted by harvest density and harvest density + percent woody area. However, harvest density was the only important variable in predicting deer density (Σω i = 0.700). Results of this study emphasize the significance of harvest density in deer management. While the importance of harvest as a management tool for deer is likely to increase as landscapes are fragmented and urbanized, specific management guidelines should be based upon deer densities and landscape metrics when they are important.

S-Adenosylmethionine (SAMe) monotherapy for depression: an 8-week double-blind, randomised, controlled trial - Jerome Sarris; Jenifer Murphy; Con Stough; David Mischoulon; Chad Bousman; Patricia MacDonald; Laura Adams; Sonia Nazareth; Georgina Oliver; Lachlan Cribb; Karen Savage; Ranjit Menon; et al. (Psychopharmacology, 2020)

Experimental evaluation of the potential for crayfish plague transmission through the digestive system of warm‐blooded predators - Jiří Svoboda; David Fischer; Eva Kozubíková‐Balcarová; Andrea Šťástková; Marie Brůčková; Antonín Kouba; Adam Petrusek (Journal of Fish Diseases, 2020)
The crayfish plague pathogen ( Aphanomyces astaci ) can be transmitted through the digestive system of fish, but its dispersal through mammalian and bird digestive tracts has been considered unlikely, and direct experimental evidence remains scarce. We present a small‐scale transmission experiment with European otter and American mink fed with infected crayfish, and experiments testing survival of cultures of five A. astaci strains at temperatures corresponding to those inside mammal and bird bodies. The pathogen was neither isolated from predator excrements nor transmitted to susceptible crayfish exposed to excrements. In agar‐based artificial media, it occasionally survived for 15 min at 40.5°C and for 45 min at 37.5°C, but not so when incubated at those temperatures for 45 min and 75 min, respectively. The five tested strains differed in resistance to high temperatures, two (of genotype groups E and D) being more susceptible than other three (of groups A, B and D). Their survival to some extent varied when exposed to the same temperature after several weeks or months, suggesting that some yet‐unknown factors may influence A. astaci resistance to temperature stress. Overall, we support the notion that passage through the digestive tract of warm‐blooded predators makes A. astaci transmission unlikely.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Long‐term changes in the water quality of a deep temperate oligotrophic lake in response to catchment disturbance: evidence from sediment cores - Alfred Theodore N. K. Kpodonu; David P. Hamilton; Christopher H. Lusk; Adam Hartland; Daniel C. Laughlin; Piet Verburg (New Zealand Journal of Marine and Freshwater Research, 2019)
This study examined long‐term stability in water quality of Lake Okataina, North Island, New Zealand, inferred from sediments deposited from 1836 to 2009, during which time there was a pyroclastic volcanic eruption (Tarawera 1886) and successive introductions of invasive mammals. Multiple geochemical proxies were analysed stratigraphically for organic matter loading, primary productivity, redox potential and phosphorus retention capacity. Organic matter loading to the lake is mostly authochthonous (algae) although there was increased allochthonous (terrestrial) loading immediately after the Tarawera eruption. After 1920, there was a sustained increase in inorganic erosion flux. Primary productivity appeared to increase considerably about 1960, but has remained relatively unchanged more recently. Our results suggest that the lake could recover from the impact of the volcanic eruption within a few decades, but the introduction of mammals may affect its resilience and lead to more pervasive impacts on the biogeochemistry.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Twine selection is essential for successful hatchery cultivation of Saccharina latissima, seeded with either meiospores or juvenile sporophytes - Philip D. Kerrison; Gail Twigg; Michele Stanley; David De Smet; Guy Buyle; Adrián Martínez Pina; Adam D. Hughes (Journal of Applied Phycology, 2019)

Genetic knockout of myosin light chain kinase (MLCK210) prevents cerebral microhemorrhages and attenuates neuroinflammation in a mouse model of vascular cognitive impairment and dementia - David J. Braun; Adam D. Bachstetter; Tiffany L. Sudduth; Donna M. Wilcock; D. Martin Watterson; Linda J. Van Eldik (GeroScience, 2019)

Climate Change Vulnerability of American Lobster Fishing Communities in Atlantic Canada - Blair J. W. Greenan; Nancy L. Shackell; Kiyomi Ferguson; Philip Greyson; Andrew Cogswell; David Brickman; Zeliang Wang; Adam Cook; Catherine E. Brennan; Vincent S. Saba (Frontiers in Marine Science, 2019)

Current and Future Variations of the Monsoons of the Americas in a Warming Climate - Salvatore Pascale; Leila M. V. Carvalho; David K. Adams; Christopher L. Castro; Iracema F. A. Cavalcanti (Current Climate Change Reports, 2019)

Fish community responses to invasive fish removal and installation of an exclusion barrier at Lake Ohinewai, Waikato - Grant W. Tempero; Brendan J. Hicks; Nicholas Ling; Dai Morgan; Adam J. Daniel; Deniz Özkundakci; Bruno David (New Zealand Journal of Marine and Freshwater Research, 2019)
Introduced common carp ( Cyprinus carpio ) are a recognised threat to New Zealand’s freshwater ecosystems. In 2011, an invasive fish removal programme was undertaken in 16.8 ha Lake Ohinewai, a Waikato riverine lake. Active fish removal using netting and boat electrofishing was supported by installation of a one‐way exclusion barrier on the outflow to Lake Ohinewai. The barrier was designed to allow fish passage downstream out of the lake, while preventing adult carp from moving upstream. The estimated carp population was reduced from 8,548 fish (5,863–12,937, 95% confidence limits) in 2011–454 fish (251–889, 95% CL) in 2014. However, by 2016 the carp population had recovered to 2,063 fish (1,070–4,328, 95% CL) with increased abundance in invasive brown bullhead catfish ( Ameiurus nebulosus ) also observed. This research demonstrates that carp populations can be reduced to low abundances in the short to medium term, but continued removal will be required for on‐going control.

Whole cell inactivated autogenous vaccine effectively protects red Nile tilapia ( Oreochromis niloticus ) against francisellosis via intraperitoneal injection - José Gustavo Ramírez‐Paredes; Miguel Angel Mendoza‐Roldan; Benjamin Lopez‐Jimena; Khalid Shahin; Matthijs Metselaar; Kim D. Thompson; David J. Penman; Randolph H. Richards; Alexandra Adams (Journal of Fish Diseases, 2019)
Francisella noatunensis subsp. orientalis is a pathogen of tilapia and other warm‐water fish for which no vaccines are commercially available. In this study, a whole cell formalin‐inactivated vaccine was developed for the first time using the highly virulent isolate STIR‐GUS‐F2f7 and the oil‐based adjuvant Montanide™ ISA 763A VG. The efficacy of the vaccine was assessed in red Nile tilapia via intraperitoneal (i.p.) injection using homologous experimental infection and correlates of protection such as seral antibody production and bacterial loads in the spleen. For immunization, fish were i.p. injected with 0.1 ml of the vaccine, the adjuvant alone or PBS. At 840 degree days post‐vaccination, all fish were i.p. injected with 4.0 × 10 3 CFU/fish of pathogenic bacteria. The RPS at the end of the trial was 100% in the vaccinated group with significantly higher survival than in the adjuvant and control groups. The RPS in the adjuvant group was 42%, and no significant difference was seen in survival between this and the PBS group. Moreover, significantly higher antibody titres in the serum and significantly lower bacterial loads in the spleen were detected in the vaccinated fish by ELISA and qPCR, respectively. These findings highlight the potential of autogenous vaccines for controlling francisellosis in tilapia.

Soil biota, carbon cycling and crop plant biomass responses to biochar in a temperate mesocosm experiment - Sarah A. McCormack; Nick Ostle; Richard D. Bardgett; David W. Hopkins; M. Glória Pereira; Adam J. Vanbergen (Plant and Soil, 2019)

Physical and biological drivers of zooplankton communities in the Chukchi Sea - Adam Spear; Janet Duffy-Anderson; David Kimmel; Jeffrey Napp; Jessica Randall; Phyllis Stabeno (Polar Biology, 2019)

Novel observations of Atlantic walruses (Odobenus rosmarus rosmarus) in Archer Fjord, northern Ellesmere Island, Nunavut, Canada - David J. Yurkowski; Cody G. Carlyle; Uluriak Amarualik; Benjamin A. Lange; Andrew Platt; Jeff W. Higdon; D. Bruce Stewart; Adam Ferguson; Steven H. Ferguson; Christine Michel (Polar Biology, 2019)

Spatial and temporal variation in mountain hare (Lepus timidus) abundance in relation to red grouse (Lagopus lagopus scotica) management in Scotland - Nicholas Hesford; Kathy Fletcher; David Howarth; A Adam Smith; Nicholas J. Aebischer; David Baines (European Journal of Wildlife Research, 2019)

Citizen-Science for the Future: Advisory Case Studies From Around the Globe - Christina Simoniello; Jennifer Jencks; Federico M. Lauro; Jon Derek Loftis; Jan Marcin Weslawski; Kajetan Deja; David R. Forrest; Sarah Gossett; Thomas C. Jeffries; Rachelle M. Jensen; Shinichi Kobara; Lindsey Nolan; et al. (Frontiers in Marine Science, 2019)

Assessing the Effects of Climate Change and Air Pollution on Soil Properties and Plant Diversity in Northeastern U.S. Hardwood Forests: Model Setup and Evaluation - Salim Belyazid; Jennifer Phelan; Bengt Nihlgård; Harald Sverdrup; Charles Driscoll; Ivan Fernandez; Julian Aherne; Leslie M. Teeling-Adams; Scott Bailey; Matt Arsenault; Natalie Cleavitt; Brett Engstrom; et al. (Water, Air, & Soil Pollution, 2019)

Large birds travel farther in homogeneous environments - Marlee A. Tucker; Olga Alexandrou; Richard O. Bierregaard; Keith L. Bildstein; Katrin Böhning‐Gaese; Chloe Bracis; John N. Brzorad; Evan R. Buechley; David Cabot; Justin M. Calabrese; Carlos Carrapato; Andre Chiaradia; et al. (Global Ecology and Biogeography, 2019)
Aim Animal movement is an important determinant of individual survival, population dynamics and ecosystem structure and function. Nonetheless, it is still unclear how local movements are related to resource availability and the spatial arrangement of resources. Using resident bird species and migratory bird species outside the migratory period, we examined how the distribution of resources affects the movement patterns of both large terrestrial birds (e.g., raptors, bustards and hornbills) and waterbirds (e.g., cranes, storks, ducks, geese and flamingos). Location Global. Time period 2003–2015. Major taxa studied Birds. Methods We compiled GPS tracking data for 386 individuals across 36 bird species. We calculated the straight‐line distance between GPS locations of each individual at the 1‐hr and 10‐day time‐scales. For each individual and time‐scale, we calculated the median and 0.95 quantile of displacement. We used linear mixed‐effects models to examine the effect of the spatial arrangement of resources, measured as enhanced vegetation index homogeneity, on avian movements, while accounting for mean resource availability, body mass, diet, flight type, migratory status and taxonomy and spatial autocorrelation. Results We found a significant effect of resource spatial arrangement at the 1‐hr and 10‐day time‐scales. On average, individual movements were seven times longer in environments with homogeneously distributed resources compared with areas of low resource homogeneity. Contrary to previous work, we found no significant effect of resource availability, diet, flight type, migratory status or body mass on the non‐migratory movements of birds. Main conclusions We suggest that longer movements in homogeneous environments might reflect the need for different habitat types associated with foraging and reproduction. This highlights the importance of landscape complementarity, where habitat patches within a landscape include a range of different, yet complementary resources. As habitat homogenization increases, it might force birds to travel increasingly longer distances to meet their diverse needs.

Contrasting Controls on Microzooplankton Grazing and Viral Infection of Microbial Prey - David Talmy; Stephen J. Beckett; Adam B. Zhang; Darcy A. A. Taniguchi; Joshua S. Weitz; Michael J. Follows (Frontiers in Marine Science, 2019)

Injury Rate Comparisons for Nonmechanized and Mechanized Logging Operations, Washington State, 2005-2014 - David K. Bonauto; Sara E. Wuellner; Jennifer L. Marcum; Darrin A. Adams (Journal of Agromedicine, 2019)

Kynurenine 3-Monooxygenase Activity in Human Primary Neurons and Effect on Cellular Bioenergetics Identifies New Neurotoxic Mechanisms - Gloria Castellano-Gonzalez; Kelly R. Jacobs; Emily Don; Nicholas J. Cole; Seray Adams; Chai K. Lim; David B. Lovejoy; Gilles J. Guillemin (Neurotoxicity Research, 2019)

Spatial and feature-based attention to expressive faces - Kestutis Kveraga; David De Vito; Cody Cushing; Hee Yeon Im; Daniel N. Albohn; Reginald B. Adams (Experimental Brain Research, 2019)

Traits linked with species invasiveness and community invasibility vary with time, stage and indicator of invasion in a long‐term grassland experiment - Jane A. Catford; Annabel L. Smith; Peter D. Wragg; Adam T. Clark; Margaret Kosmala; Jeannine Cavender‐Bares; Peter B. Reich; David Tilman (Ecology Letters, 2019)
Much uncertainty remains about traits linked with successful invasion – the establishment and spread of non‐resident species into existing communities. Using a 20‐year experiment, where 50 non‐resident (but mostly native) grassland plant species were sown into savannah plots, we ask how traits linked with invasion depend on invasion stage (establishment, spread), indicator of invasion success (occupancy, relative abundance), time, environmental conditions, propagule rain, and traits of invaders and invaded communities. Trait data for 164 taxa showed that invader occupancy was primarily associated with traits of invaders, traits of recipient communities, and invader‐community interactions. Invader abundance was more strongly associated with community traits (e.g. proportion legume) and trait differences between invaders and the most similar resident species. Annuals and invaders with high‐specific leaf area were only successful early in stand development, whereas invaders with conservative carbon capture strategies persisted long‐term. Our results indicate that invasion is context‐dependent and long‐term experiments are required to comprehensively understand invasions.

Correction to: Pharmacological characterization of the LSD analog N-ethyl-N-cyclopropyl lysergamide (ECPLA) - Adam L. Halberstadt; Landon M. Klein; Muhammad Chatha; Laura B. Valenzuela; Alexander Stratford; Jason Wallach; David E. Nichols; Simon D. Brandt (Psychopharmacology, 2019)

Pharmacological characterization of the LSD analog N-ethyl-N-cyclopropyl lysergamide (ECPLA) - Adam L. Halberstadt; Landon M. Klein; Muhammad Chatha; Laura B. Valenzuela; Alexander Stratford; Jason Wallach; David E. Nichols; Simon D. Brandt (Psychopharmacology, 2019)

Modifying mosquito impoundment management to enhance nursery habitat value for juvenile common Snook (Centropomus undecimalis) and Atlantic tarpon (Megalops atlanticus) - Anthony C. Cianciotto; Jonathan M. Shenker; Aaron J. Adams; Jacob J. Rennert; David Heuberger (Environmental Biology of Fishes, 2019)

Tropical rainfall predictions from multiple seasonal forecast systems - Adam A. Scaife; Laura Ferranti; Oscar Alves; Panos Athanasiadis; Johanna Baehr; Michel Dequé; Tina Dippe; Nick Dunstone; David Fereday; Richard G. Gudgel; Richard J. Greatbatch; Leon Hermanson; et al. (International Journal of Climatology, 2019)
We quantify seasonal prediction skill of tropical winter rainfall in 14 climate forecast systems. High levels of seasonal prediction skill exist for year‐to‐year rainfall variability in all tropical ocean basins. The tropical East Pacific is the most skilful region, with very high correlation scores, and the tropical West Pacific is also highly skilful. Predictions of tropical Atlantic and Indian Ocean rainfall show lower but statistically significant scores. We compare prediction skill (measured against observed variability) with model predictability (using single forecasts as surrogate observations). Model predictability matches prediction skill in some regions but it is generally greater, especially over the Indian Ocean. We also find significant inter‐basin connections in both observed and predicted rainfall. Teleconnections between basins due to El Niño–Southern Oscillation (ENSO) appear to be reproduced in multi‐model predictions and are responsible for much of the prediction skill. They also explain the relative magnitude of inter‐annual variability, the relative magnitude of predictable rainfall signals and the ranking of prediction skill across different basins. These seasonal tropical rainfall predictions exhibit a severe wet bias, often in excess of 20% of mean rainfall. However, we find little direct relationship between bias and prediction skill. Our results suggest that future prediction systems would be best improved through better model representation of inter‐basin rainfall connections as these are strongly related to prediction skill, particularly in the Indian and West Pacific regions. Finally, we show that predictions of tropical rainfall alone can generate highly skilful forecasts of the main modes of extratropical circulation via linear relationships that might provide a useful tool to interpret real‐time forecasts.

Compatibility, Development, and Estimation of Taper and Volume Equation Systems - Dehai Zhao; Thomas B Lynch; James Westfall; John Coulston; Michael Kane; David E Adams (Forest Science, 2019)

Iron‐ and aluminium‐induced depletion of molybdenum in acidic environments impedes the nitrogen cycle - Xiaoxuan Ge; Brian J. Vaccaro; Michael P. Thorgersen; Farris L. Poole; Erica L. Majumder; Grant M. Zane; Kara B. De León; W. Andrew Lancaster; Ji Won Moon; Charles J. Paradis; Frederick von Netzer; David A. Stahl; et al. (Environmental Microbiology, 2019)
Summary Anthropogenic nitrate contamination is a serious problem in many natural environments. Nitrate removal by microbial action is dependent on the metal molybdenum (Mo), which is required by nitrate reductase for denitrification and dissimilatory nitrate reduction to ammonium. The soluble form of Mo, molybdate (MoO 4 2− ), is incorporated into and adsorbed by iron (Fe) and aluminium (Al) (oxy) hydroxide minerals. Herein we used Oak Ridge Reservation (ORR) as a model nitrate‐contaminated acidic environment to investigate whether the formation of Fe‐ and Al‐precipitates could impede microbial nitrate removal by depleting Mo. We demonstrate that Fe and Al mineral formation that occurs as the pH of acidic synthetic groundwater is increased, decreases soluble Mo to low picomolar concentrations, a process proposed to mimic environmental diffusion of acidic contaminated groundwater. Analysis of ORR sediments revealed recalcitrant Mo in the contaminated core that co‐occurred with Fe and Al, consistent with Mo scavenging by Fe/Al precipitates. Nitrate removal by ORR isolate Pseudomonas fluorescens N2A2 is virtually abolished by Fe/Al precipitate‐induced Mo depletion. The depletion of naturally occurring Mo in nitrate‐ and Fe/Al‐contaminated acidic environments like ORR or acid mine drainage sites has the potential to impede microbial‐based nitrate reduction thereby extending the duration of nitrate in the environment.

Monitoring programs of the U.S. Gulf of Mexico: inventory, development and use of a large monitoring database to map fish and invertebrate spatial distributions - Arnaud Grüss; Holly A. Perryman; Elizabeth A. Babcock; Skyler R. Sagarese; James T. Thorson; Cameron H. Ainsworth; Evan John Anderson; Kenneth Brennan; Matthew D. Campbell; Mary C. Christman; Scott Cross; Michael D. Drexler; et al. (Reviews in Fish Biology and Fisheries, 2018)

Storylines: an alternative approach to representing uncertainty in physical aspects of climate change - Theodore G. Shepherd; Emily Boyd; Raphael A. Calel; Sandra C. Chapman; Suraje Dessai; Ioana M. Dima-West; Hayley J. Fowler; Rachel James; Douglas Maraun; Olivia Martius; Catherine A. Senior; Adam H. Sobel; et al. (Climatic Change, 2018)

Real-World Variability in the Prediction of Intracranial Aneurysm Wall Shear Stress: The 2015 International Aneurysm CFD Challenge - Kristian Valen-Sendstad; Aslak W. Bergersen; Yuji Shimogonya; Leonid Goubergrits; Jan Bruening; Jordi Pallares; Salvatore Cito; Senol Piskin; Kerem Pekkan; Arjan J. Geers; Ignacio Larrabide; Saikiran Rapaka; et al. (Cardiovascular Engineering and Technology, 2018)

Paul Lawrence Younger 1962–2018 - Adam Jarvis; David Banks (Mine Water and the Environment, 2018)

Ambient changes exceed treatment effects on plant species abundance in global change experiments - J. Adam Langley; Samantha K. Chapman; Kimberly J. La Pierre; Meghan Avolio; William D. Bowman; David S. Johnson; Forest Isbell; Kevin R. Wilcox; Bryan L. Foster; Mark J. Hovenden; Alan K. Knapp; Sally E. Koerner; et al. (Global Change Biology, 2018)
The responses of species to environmental changes will determine future community composition and ecosystem function. Many syntheses of global change experiments examine the magnitude of treatment effect sizes, but we lack an understanding of how plant responses to treatments compare to ongoing changes in the unmanipulated (ambient or background) system. We used a database of long‐term global change studies manipulating CO 2 , nutrients, water, and temperature to answer three questions: (a) How do changes in plant species abundance in ambient plots relate to those in treated plots? (b) How does the magnitude of ambient change in species‐level abundance over time relate to responsiveness to global change treatments? (c) Does the direction of species‐level responses to global change treatments differ from the direction of ambient change? We estimated temporal trends in plant abundance for 791 plant species in ambient and treated plots across 16 long‐term global change experiments yielding 2,116 experiment–species–treatment combinations. Surprisingly, for most species (57%) the magnitude of ambient change was greater than the magnitude of treatment effects. However, the direction of ambient change, whether a species was increasing or decreasing in abundance under ambient conditions, had no bearing on the direction of treatment effects. Although ambient communities are inherently dynamic, there is now widespread evidence that anthropogenic drivers are directionally altering plant communities in many ecosystems. Thus, global change treatment effects must be interpreted in the context of plant species trajectories that are likely driven by ongoing environmental changes.

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Mechanistically derived dispersal kernels explain species‐level patterns of recruitment and succession - Lauren L. Sullivan; Adam T. Clark; David Tilman; Allison K. Shaw (Ecology, 2018)
Species‐level dispersal information can give mechanistic insights into how spatial processes impact plant communities. Unfortunately, field‐based estimates of the dispersal abilities of multiple members of a community are often lacking for many plant systems. Here, we provide a simple method for measuring dispersal ability for large numbers of grassland plant species based on functional traits. Using this method, we estimated the dispersal ability of 50 co‐occurring grassland species using the Wald Analytical Long‐distance Dispersal ( WALD ) model. Grassland plants species are often used for developing community theory, yet species‐level estimates of their dispersal abilities are comparatively rare. We use these dispersal measurements to examine the relationship between species dispersal abilities and successional dynamics using data from a 90‐yr old field chronosequence. We find that our estimated dispersal measurements matched field‐based establishment observations well, and estimated species colonization, competitive, and establishment abilities. We hope that this method for measuring dispersal ability of multiple species within a community, and its demonstrated ability to generate predictions for spatial ecology, will encourage more studies of the explicit role of dispersal in plant community ecology.

Root and mycorrhizal fungal foraging responses to fruit removal in apple trees - Emily K. Lavely; Jianghong Zhang; Thomas S. Adams; David R. Bryla; Jared L. DeForest; Richard P. Marini; Robert Crassweller; David M. Eissenstat (Plant and Soil, 2018)

How do reaching and walking costs affect movement path selection? - Cory Adam Potts; Chloe Callahan-Flintoft; David A. Rosenbaum (Experimental Brain Research, 2018)

Three-Dimensional Printing of Cell Exclusion Spacers (CES) for Use in Motility Assays - Christen J. Boyer; David H. Ballard; Jungmi W. Yun; Adam Y. Xiao; Jeffery A. Weisman; Mansoureh Barzegar; Jonathan Steven Alexander (Pharmaceutical Research, 2018)

Proteomic analysis of cardiac ventricles: baso-apical differences - Adam Eckhardt; Lucie Kulhava; Ivan Miksik; Statis Pataridis; Marketa Hlavackova; Jana Vasinova; Frantisek Kolar; David Sedmera; Bohuslav Ostadal (Molecular and Cellular Biochemistry, 2018)

Regional variation in drivers of connectivity for two frog species ( Rana pretiosa and R. luteiventris ) from the U.S. Pacific Northwest - Jeanne M. Robertson; Melanie A. Murphy; Christopher A. Pearl; Michael J. Adams; Mónica I. Páez‐Vacas; Susan M. Haig; David S. Pilliod; Andrew Storfer; W. Chris Funk (Molecular Ecology, 2018)
Comparative landscape genetics has uncovered high levels of variability in which landscape factors affect connectivity among species and regions. However, the relative importance of species traits versus environmental variation for predicting landscape patterns of connectivity is unresolved. We provide evidence from a landscape genetics study of two sister taxa of frogs, the Oregon spotted frog ( Rana pretiosa ) and the Columbia spotted frog ( Rana luteiventris ) in Oregon and Idaho, USA . Rana pretiosa is relatively more dependent on moisture for dispersal than R. luteiventris , so if species traits influence connectivity, we predicted that connectivity among R. pretiosa populations would be more positively associated with moisture than R. luteiventris . However, if environmental differences are important drivers of gene flow, we predicted that connectivity would be more positively related to moisture in arid regions. We tested these predictions using eight microsatellite loci and gravity models in two R. pretiosa regions and four R. luteiventris regions ( n = 1,168 frogs). In R. pretiosa , but not R. luteiventris , connectivity was positively related to mean annual precipitation, supporting our first prediction. In contrast, connectivity was not more positively related to moisture in more arid regions. Various temperature metrics were important predictors for both species and in all regions, but the directionality of their effects varied. Therefore, the pattern of variation in drivers of connectivity was consistent with predictions based on species traits rather than on environmental variation.

Sky, sea, and forest islands: Diversification in the African leaf‐folding frog Afrixalus paradorsalis (Anura: Hyperoliidae) of the Lower Guineo‐Congolian rain forest - Kristin L. Charles; Rayna C. Bell; David C. Blackburn; Marius Burger; Matthew K. Fujita; Václav Gvoždík; Gregory F.M. Jongsma; Marcel Talla Kouete; Adam D. Leaché; Daniel M. Portik (Journal of Biogeography, 2018)
Aim To investigate how putative barriers, forest refugia, and ecological gradients across the lower Guineo‐Congolian rain forest shape genetic and phenotypic divergence in the leaf‐folding frog Afrixalus paradorsalis , and examine the role of adjacent land bridge and sky‐islands in diversification. Location The Lower Guineo‐Congolian Forest, the Cameroonian Volcanic Line (CVL), and Bioko Island, Central Africa. Taxon Afrixalus paradorsalis (Family: Hyperoliidae), an African leaf‐folding frog. Methods We used molecular and phenotypic data to investigate diversity and divergence among the A. paradorsalis species complex distributed across lowland rain forests, a land bridge island, and mountains in Central Africa. We examined the coincidence of population boundaries, landscape features, divergence times, and spatial patterns of connectivity and diversity, and subsequently performed demographic modelling using genome‐wide SNP variation to distinguish among divergence mechanisms in mainland (riverine barriers, forest refugia, ecological gradients) and land bridge island populations (vicariance, overwater dispersal). Results We detected four genetically distinct allopatric populations corresponding to Bioko Island, the CVL, and two lowland rain forest populations split by the Sanaga River. Although lowland populations are phenotypically indistinguishable, pronounced body size evolution occurs at high elevation, and the timing of the formation of the high elevation population coincides with mountain uplift in the CVL. Spatial analyses and demographic modelling revealed population divergence across mainland Lower Guinea is best explained by forest refugia rather than riverine barriers or ecological gradients, and that the Bioko Island population divergence is best explained by vicariance (marine incursion) rather than overseas dispersal. Main conclusions We provide growing support for the important role of forest refugia in driving intraspecific divergences in the Guineo‐Congolian rain forest. In A. paradorsalis , sky‐islands in the CVL have resulted in greater genetic and phenotypic divergences than marine incursions of the land bridge Bioko Island, highlighting important differences in patterns of island‐driven diversification in Lower Guinea.

Linking tree genetics and stream consumers: isotopic tracers elucidate controls on carbon and nitrogen assimilation - Zacchaeus G. Compson; Bruce A. Hungate; Thomas G. Whitham; George W. Koch; Paul Dijkstra; Adam C. Siders; Todd Wojtowicz; Ryan Jacobs; David N. Rakestraw; Kiel E. Allred; Chelsea K. Sayer; Jane C. Marks (Ecology, 2018)
Leaf litter provides an important nutrient subsidy to headwater streams, but little is known about how tree genetics influence energy pathways from litter to higher trophic levels. Despite the charge to quantify carbon (C) and nitrogen (N) pathways from decomposing litter, the relationship between litter decomposition and aquatic consumers remains unresolved. We measured litter preference (attachments to litter), C and N assimilation rates, and growth rates of a shredding caddisfly ( Hesperophylax magnus , Limnephilidae) in response to leaf litter of different chemical and physical phenotypes using Populus cross types ( P. fremontii , P. angustifolia , and F 1 hybrids) and genotypes within P. angustifolia . We combined laboratory mesocosm studies using litter from a common garden with a field study using doubly labeled litter ( 13 C and 15 N) grown in a greenhouse and incubated in Oak Creek, Arizona, USA. We found that, in the lab, shredders initially chose relatively labile (low lignin and condensed tannin concentrations, rapidly decomposing) cross type litter, but preference changed within 4 d to relatively recalcitrant (high lignin and condensed tannin concentrations, slowly decomposing) litter types. Additionally, in the lab, shredder growth rates were higher on relatively recalcitrant compared to labile cross type litter. Over the course of a three‐week field experiment, shredders also assimilated more C and N from relatively recalcitrant compared to labile cross type litter. Finally, among P. angustifolia genotypes, N assimilation by shredders was positively related to litter lignin and C:N, but negatively related to condensed tannins and decomposition rate. C assimilation was likewise positively related to litter C:N, and also to litter %N. C assimilation was not associated with condensed tannins or lignin. Collectively, these findings suggest that relatively recalcitrant litter of Populus cross types provides more nutritional benefit, in terms of N fluxes and growth, than labile litter, but among P. angustifolia genotypes the specific trait of litter recalcitrance (lignin or tannins) determines effects on C or N assimilation. As shredders provide nutrients and energy to higher trophic levels, the influence of these genetically based plant decomposition pathways on shredder preference and performance may affect community and food web structure.

The role of resveratrol on skeletal muscle cell differentiation and myotube hypertrophy during glucose restriction - Hannah F. Dugdale; David C. Hughes; Robert Allan; Colleen S. Deane; Christopher R. Coxon; James P. Morton; Claire E. Stewart; Adam P. Sharples (Molecular and Cellular Biochemistry, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Water guns affect abundance and behavior of bigheaded carp and native fish differently - José M. Rivera; David C. Glover; Patrick M. Kocovsky; James E. Garvey; Mark P. Gaikowski; Nathan R. Jensen; Ryan F. Adams (Biological Invasions, 2018)

Identifying mechanisms that structure ecological communities by snapping model parameters to empirically observed tradeoffs - Adam Thomas Clark; Clarence Lehman; David Tilman (Ecology Letters, 2018)
Theory predicts that interspecific tradeoffs are primary determinants of coexistence and community composition. Using information from empirically observed tradeoffs to augment the parametrisation of mechanism‐based models should therefore improve model predictions, provided that tradeoffs and mechanisms are chosen correctly. We developed and tested such a model for 35 grassland plant species using monoculture measurements of three species characteristics related to nitrogen uptake and retention, which previous experiments indicate as important at our site. Matching classical theoretical expectations, these characteristics defined a distinct tradeoff surface, and models parameterised with these characteristics closely matched observations from experimental multi‐species mixtures. Importantly, predictions improved significantly when we incorporated information from tradeoffs by ‘snapping’ characteristics to the nearest location on the tradeoff surface, suggesting that the tradeoffs and mechanisms we identify are important determinants of local community structure. This ‘snapping’ method could therefore constitute a broadly applicable test for identifying influential tradeoffs and mechanisms.

Recreational sea fishing in Europe in a global context—Participation rates, fishing effort, expenditure, and implications for monitoring and assessment - Kieran Hyder; Marc Simon Weltersbach; Mike Armstrong; Keno Ferter; Bryony Townhill; Anssi Ahvonen; Robert Arlinghaus; Andrei Baikov; Manuel Bellanger; Janis Birzaks; Trude Borch; Giulia Cambie; et al. (Fish and Fisheries, 2018)
Marine recreational fishing ( MRF ) is a high‐participation activity with large economic value and social benefits globally, and it impacts on some fish stocks. Although reporting MRF catches is a European Union legislative requirement, estimates are only available for some countries. Here, data on numbers of fishers, participation rates, days fished, expenditures, and catches of two widely targeted species were synthesized to provide European estimates of MRF and placed in the global context. Uncertainty assessment was not possible due to incomplete knowledge of error distributions; instead, a semi‐quantitative bias assessment was made. There were an estimated 8.7 million European recreational sea fishers corresponding to a participation rate of 1.6%. An estimated 77.6 million days were fished, and expenditure was €5.9 billion annually. There were higher participation, numbers of fishers, days fished and expenditure in the Atlantic than the Mediterranean, but the Mediterranean estimates were generally less robust. Comparisons with other regions showed that European MRF participation rates and expenditure were in the mid‐range, with higher participation in Oceania and the United States, higher expenditure in the United States, and lower participation and expenditure in South America and Africa. For both northern European sea bass ( Dicentrarchus labrax , Moronidae) and western Baltic cod ( Gadus morhua , Gadidae) stocks, MRF represented 27% of the total removals. This study highlights the importance of MRF and the need for bespoke, regular and statistically sound data collection to underpin European fisheries management. Solutions are proposed for future MRF data collection in Europe and other regions to support sustainable fisheries management.

Designing connected marine reserves in the face of global warming - Jorge G. Álvarez‐Romero; Adrián Munguía‐Vega; Maria Beger; Maria del Mar Mancha‐Cisneros; Alvin N. Suárez‐Castillo; Georgina G. Gurney; Robert L. Pressey; Leah R. Gerber; Hem Nalini Morzaria‐Luna; Héctor Reyes‐Bonilla; Vanessa M. Adams; Melanie Kolb; et al. (Global Change Biology, 2018)
Marine reserves are widely used to protect species important for conservation and fisheries and to help maintain ecological processes that sustain their populations, including recruitment and dispersal. Achieving these goals requires well‐connected networks of marine reserves that maximize larval connectivity, thus allowing exchanges between populations and recolonization after local disturbances. However, global warming can disrupt connectivity by shortening potential dispersal pathways through changes in larval physiology. These changes can compromise the performance of marine reserve networks, thus requiring adjusting their design to account for ocean warming. To date, empirical approaches to marine prioritization have not considered larval connectivity as affected by global warming. Here, we develop a framework for designing marine reserve networks that integrates graph theory and changes in larval connectivity due to potential reductions in planktonic larval duration ( PLD ) associated with ocean warming, given current socioeconomic constraints. Using the Gulf of California as case study, we assess the benefits and costs of adjusting networks to account for connectivity, with and without ocean warming. We compare reserve networks designed to achieve representation of species and ecosystems with networks designed to also maximize connectivity under current and future ocean‐warming scenarios. Our results indicate that current larval connectivity could be reduced significantly under ocean warming because of shortened PLD s. Given the potential changes in connectivity, we show that our graph‐theoretical approach based on centrality (eigenvector and distance‐weighted fragmentation) of habitat patches can help design better‐connected marine reserve networks for the future with equivalent costs. We found that maintaining dispersal connectivity incidentally through representation‐only reserve design is unlikely, particularly in regions with strong asymmetric patterns of dispersal connectivity. Our results support previous studies suggesting that, given potential reductions in PLD due to ocean warming, future marine reserve networks would require more and/or larger reserves in closer proximity to maintain larval connectivity.

iDNA at Sea: Recovery of Whale Shark (Rhincodon typus) Mitochondrial DNA Sequences from the Whale Shark Copepod (Pandarus rhincodonicus) Confirms Global Population Structure - Mark Meekan; Christopher M. Austin; Mun H. Tan; Nu-Wei V. Wei; Adam Miller; Simon J. Pierce; David Rowat; Guy Stevens; Tim K. Davies; Alessandro Ponzo; Han Ming Gan (Frontiers in Marine Science, 2017)

A spatial analysis of integrated risk: vulnerability of ecosystem services provisioning to different hazards in the Czech Republic - Adam Pártl; David Vačkář; Blanka Loučková; Eliška Krkoška Lorencová (Natural Hazards, 2017)

The Oxygen Paradox, the French Paradox, and age-related diseases - Joanna M. S. Davies; Josiane Cillard; Bertrand Friguet; Enrique Cadenas; Jean Cadet; Rachael Cayce; Andrew Fishmann; David Liao; Anne-Laure Bulteau; Frédéric Derbré; Amélie Rébillard; Steven Burstein; et al. (GeroScience, 2017)

Energetic requirements of green sturgeon (Acipenser medirostris) feeding on burrowing shrimp (Neotrypaea californiensis) in estuaries: importance of temperature, reproductive investment, and residence time - Joshua M. Borin; Mary L. Moser; Adam G. Hansen; David A. Beauchamp; Stephen C. Corbett; Brett R. Dumbauld; Casey Pruitt; Jennifer L. Ruesink; Cinde Donoghue (Environmental Biology of Fishes, 2017)

Mechanisms and clinical implications of tumor heterogeneity and convergence on recurrent phenotypes - Jasmine A. McQuerry; Jeffrey T. Chang; David D. L. Bowtell; Adam Cohen; Andrea H. Bild (Journal of Molecular Medicine, 2017)

Using Numerical Modeling to Understand the Discharge from a Flooded Abandoned Underground Mine - Tomáš Kuchovský; Adam Říčka; David Grycz (Mine Water and the Environment, 2017)

Optimal intensity measure based on spectral acceleration for P-delta vulnerable deteriorating frame structures in the collapse limit state - Christoph Adam; David Kampenhuber; Luis F. Ibarra (Bulletin of Earthquake Engineering, 2017)

Evaluating mechanisms of diversification in a Guineo‐Congolian tropical forest frog using demographic model selection - Daniel M. Portik; Adam D. Leaché; Danielle Rivera; Michael F. Barej; Marius Burger; Mareike Hirschfeld; Mark‐Oliver Rödel; David C. Blackburn; Matthew K. Fujita (Molecular Ecology, 2017)
The accumulation of biodiversity in tropical forests can occur through multiple allopatric and parapatric models of diversification, including forest refugia, riverine barriers and ecological gradients. Considerable debate surrounds the major diversification process, particularly in the West African Lower Guinea forests, which contain a complex geographic arrangement of topographic features and historical refugia. We used genomic data to investigate alternative mechanisms of diversification in the Gaboon forest frog, Scotobleps gabonicus , by first identifying population structure and then performing demographic model selection and spatially explicit analyses. We found that a majority of population divergences are best explained by allopatric models consistent with the forest refugia hypothesis and involve divergence in isolation with subsequent expansion and gene flow. These population divergences occurred simultaneously and conform to predictions based on climatically stable regions inferred through ecological niche modelling. Although forest refugia played a prominent role in the intraspecific diversification of S. gabonicus , we also find evidence for potential interactions between landscape features and historical refugia, including major rivers and elevational barriers such as the Cameroonian Volcanic Line. We outline the advantages of using genomewide variation in a model‐testing framework to distinguish between alternative allopatric hypotheses, and the pitfalls of limited geographic and molecular sampling. Although phylogeographic patterns are often species‐specific and related to life‐history traits, additional comparative studies incorporating genomic data are necessary for separating shared historical processes from idiosyncratic responses to environmental, climatic and geological influences on diversification.

Assessment of the Neuroprotective Effects of Arginine-Rich Protamine Peptides, Poly-Arginine Peptides (R12-Cyclic, R22) and Arginine–Tryptophan-Containing Peptides Following In Vitro Excitotoxicity and/or Permanent Middle Cerebral Artery Occlusion in Rats - Bruno P. Meloni; Diego Milani; Jane L. Cross; Vince W. Clark; Adam B. Edwards; Ryan S. Anderton; David J. Blacker; Neville W. Knuckey (NeuroMolecular Medicine, 2017)

Parabolic variation in sexual selection intensity across the range of a cold‐water pipefish: implications for susceptibility to climate change - Nuno Monteiro; Mário Cunha; Lídia Ferreira; Natividade Vieira; Agostinho Antunes; David Lyons; Adam G. Jones (Global Change Biology, 2017)
While an understanding of evolutionary processes in shifting environments is vital in the context of rapid ecological change, one of the most potent selective forces, sexual selection, remains curiously unexplored. Variation in sexual selection across a species range, especially across a gradient of temperature regimes, has the potential to provide a window into the possible impacts of climate change on the evolution of mating patterns. Here, we investigated some of the links between temperature and indicators of sexual selection, using a cold‐water pipefish as model. We found that populations differed with respect to body size, length of the breeding season, fecundity, and sexual dimorphism across a wide latitudinal gradient. We encountered two types of latitudinal patterns, either linear, when related to body size, or parabolic in shape when considering variables related to sexual selection intensity, such as sexual dimorphism and reproductive investment. Our results suggest that sexual selection intensity increases toward both edges of the distribution and that the large differences in temperature likely play a significant role. Shorter breeding seasons in the north and reduced periods for gamete production in the south certainly have the potential to alter mating systems, breeding synchrony, and mate monopolization rates. As latitude and water temperature are tightly coupled across the European coasts, the observed patterns in traits related to sexual selection can lead to predictions regarding how sexual selection should change in response to climate change. Based on data from extant populations, we can predict that as the worm pipefish moves northward, a wave of decreasing selection intensity will likely replace the strong sexual selection at the northern range margin. In contrast, the southern populations will be followed by heightened sexual selection, which may exacerbate the problem of local extinction at this retreating boundary.

The colonization of decaying logs by vascular plants and the consequences of fallen logs for herb layer diversity in a lowland alluvial forest - Pavel Unar; David Janík; Dušan Adam; Marie Vymazalová (European Journal of Forest Research, 2017)

International consensus principles for ethical wildlife control - Sara Dubois; Nicole Fenwick; Erin A. Ryan; Liv Baker; Sandra E. Baker; Ngaio J. Beausoleil; Scott Carter; Barbara Cartwright; Federico Costa; Chris Draper; John Griffin; Adam Grogan; et al. (Conservation Biology, 2017)
Human–wildlife conflicts are commonly addressed by excluding, relocating, or lethally controlling animals with the goal of preserving public health and safety, protecting property, or conserving other valued wildlife. However, declining wildlife populations, a lack of efficacy of control methods in achieving desired outcomes, and changes in how people value animals have triggered widespread acknowledgment of the need for ethical and evidence‐based approaches to managing such conflicts. We explored international perspectives on and experiences with human–wildlife conflicts to develop principles for ethical wildlife control. A diverse panel of 20 experts convened at a 2‐day workshop and developed the principles through a facilitated engagement process and discussion. They determined that efforts to control wildlife should begin wherever possible by altering the human practices that cause human–wildlife conflict and by developing a culture of coexistence; be justified by evidence that significant harms are being caused to people, property, livelihoods, ecosystems, and/or other animals; have measurable outcome‐based objectives that are clear, achievable, monitored, and adaptive; predictably minimize animal welfare harms to the fewest number of animals; be informed by community values as well as scientific, technical, and practical information; be integrated into plans for systematic long‐term management; and be based on the specifics of the situation rather than negative labels (pest, overabundant) applied to the target species. We recommend that these principles guide development of international, national, and local standards and control decisions and implementation.

Restoring Ovarian Endocrine Function with Encapsulated Ovarian Allograft in Immune Competent Mice - Anu David; James Ronald Day; Alexa Leigh Cichon; Adam Lefferts; Marilia Cascalho; Ariella Shikanov (Annals of Biomedical Engineering, 2017)

Development of a Three-Dimensional Adipose Tissue Model for Studying Embryonic Exposures to Obesogenic Chemicals - Rebecca Y. Wang; Rosalyn D. Abbott; Adam Zieba; Francis E. Borowsky; David L. Kaplan (Annals of Biomedical Engineering, 2017)

Quantitative trait loci controlling vegetative propagation traits mapped in European pear (Pyrus communis L.) - Mareike Knäbel; Adam P. Friend; John W. Palmer; Robert Diack; Susan E. Gardiner; Stuart Tustin; Robert Schaffer; Toshi Foster; David Chagné (Tree Genetics & Genomes, 2017)

The SAVE Trial: Has the Importance of CPAP for Preventing Cardiovascular Events been Discounted? - Ahmed S. Bahammam; Seithikurippu R. Pandi-Perumal; David Warren Spence; Adam Moscovitch; David L. Streiner (Sleep and Vigilance, 2017)

Evaluating species-specific changes in hydrologic regimes: an iterative approach for salmonids in the Greater Yellowstone Area (USA) - Robert Al-Chokhachy; Adam J. Sepulveda; Andrew M. Ray; David P. Thoma; Michael T. Tercek (Reviews in Fish Biology and Fisheries, 2017)

Effects of climate change on coral grouper (Plectropomus spp.) and possible adaptation options - Morgan S. Pratchett; Darren S. Cameron; Jennifer Donelson; Louisa Evans; Ashley J. Frisch; Alistair J. Hobday; Andrew S. Hoey; Nadine A. Marshall; Vanessa Messmer; Philip L. Munday; Rachel Pears; Gretta Pecl; et al. (Reviews in Fish Biology and Fisheries, 2017)

Improved full-length killer cell immunoglobulin-like receptor transcript discovery in Mauritian cynomolgus macaques - Trent M. Prall; Michael E. Graham; Julie A. Karl; Roger W. Wiseman; Adam J. Ericsen; Muthuswamy Raveendran; R. Alan Harris; Donna M. Muzny; Richard A. Gibbs; Jeffrey Rogers; David H. O’Connor (Immunogenetics, 2017)

Ecological niche partitioning within a large predator guild in a nutrient‐limited estuary - Philip Matich; Jerald S. Ault; Ross E. Boucek; David R. Bryan; Kirk R. Gastrich; Christine L. Harvey; Michael R. Heithaus; Jeremy J. Kiszka; Valeria Paz; Jennifer S. Rehage; Adam E. Rosenblatt (Limnology and Oceanography, 2017)
Within oligotrophic ecosystems, resource limitations coupled with interspecific variation in morphology, physiology, and life history traits may lead to niche partitioning among species. How generalist predators partition resources and their mechanisms, however, remain unclear across many ecosystems. We quantified niche partitioning among upper trophic level coastal and estuarine species: American alligators ( Alligator mississippiensis ), bull sharks ( Carcharhinus leucas ), common bottlenose dolphins ( Tursiops truncatus ), common snook ( Centropomus undecimalis ), and Atlantic tarpon ( Megalops atlanticus ) in the Shark River Estuary of the Florida Coastal Everglades, USA using acoustic telemetry, stable isotope analysis, and visual surveys, combined with published diet and life history demographic information. Spatial and isotopic niche overlap occurred among most species, with variability in partitioning among interspecific interactions. However, seasonal variability in habitat use, movements patterns, and trophic interactions may promote coexistence within this resource‐limited estuary. Beyond guild‐level niche partitioning, predators within the Shark River Estuary also exhibit partitioning within species through individual specializations and divergent phenotypes, which may lead to intraspecific variability in niche overlap with other predators. Niche differentiation expressed across multiple organizational levels (i.e., populations and communities) coupled with behavioral plasticity among predators in oligotrophic ecosystems may promote high species diversity despite resource limitations, which may be important when species respond to natural and human‐driven environmental change.

A Mechanistic Model for Secchi Disk Depth, Driven by Light Scattering Constituents - Steven W. Effler; Christopher Strait; David M. O’Donnell; Adam J.P. Effler; Feng Peng; Anthony R. Prestigiacomo; Susan M. O’Donnell; MaryGail Perkins; Steve C. Chapra (Water, Air, & Soil Pollution, 2017)

Canopy trees in an urban landscape – viable forests or long-lived gardens? - Adam C. Labatore; David J. Spiering; Daniel L. Potts; Robert J. Warren (Urban Ecosystems, 2017)

Application of novel analytical ultracentrifuge analysis to solutions of fungal mannans - Richard B. Gillis; Gary G. Adams; David T. M. Besong; Eva Machová; Anna Ebringerová; Arthur J. Rowe; Stephen E. Harding; Trushar R. Patel (European Biophysics Journal, 2017)

Golden Eagle fatalities and the continental‐scale consequences of local wind‐energy generation - Todd E. Katzner; David M. Nelson; Melissa A. Braham; Jacqueline M. Doyle; Nadia B. Fernandez; Adam E. Duerr; Peter H. Bloom; Matthew C. Fitzpatrick; Tricia A. Miller; Renee C. E. Culver; Loan Braswell; J. Andrew DeWoody (Conservation Biology, 2017)
Renewable energy production is expanding rapidly despite mostly unknown environmental effects on wildlife and habitats. We used genetic and stable isotope data collected from Golden Eagles (Aquila chrysaetos) killed at the Altamont Pass Wind Resource Area (APWRA) in California in demographic models to test hypotheses about the geographic extent and demographic consequences of fatalities caused by renewable energy facilities. Geospatial analyses of δ 2 H values obtained from feathers showed that ≥25% of these APWRA‐killed eagles were recent immigrants to the population, most from long distances away (>100 km). Data from nuclear genes indicated this subset of immigrant eagles was genetically similar to birds identified as locals from the δ 2 H data. Demographic models implied that in the face of this mortality, the apparent stability of the local Golden Eagle population was maintained by continental‐scale immigration. These analyses demonstrate that ecosystem management decisions concerning the effects of local‐scale renewable energy can have continental‐scale consequences.

Wave hazards on microtidal shore platforms: testing the relationship between morphology and exposure - David M. Kennedy; Daniel Ierodiaconou; Adam Weir; Barbara Brighton (Natural Hazards, 2017)

Identification and classification of storm surge events at Red Dog Dock, Alaska, 2004–2014 - Adam J. Wicks; David E. Atkinson (Natural Hazards, 2017)

By their own devices: invasive Argentine ants have shifted diet without clear aid from symbiotic microbes - Yi Hu; David A. Holway; Piotr Łukasik; Linh Chau; Adam D. Kay; Edward G. LeBrun; Katie A. Miller; Jon G. Sanders; Andrew V. Suarez; Jacob A. Russell (Molecular Ecology, 2017)
The functions and compositions of symbiotic bacterial communities often correlate with host ecology. Yet cause–effect relationships and the order of symbiont vs. host change remain unclear in the face of ancient symbioses and conserved host ecology. Several groups of ants exemplify this challenge, as their low‐nitrogen diets and specialized symbioses appear conserved and ancient. To address whether nitrogen‐provisioning symbionts might be important in the early stages of ant trophic shifts, we studied bacteria from the Argentine ant, Linepithema humile – an invasive species that has transitioned towards greater consumption of sugar‐rich, nitrogen‐poor foods in parts of its introduced range. Bacteria were present at low densities in most L. humile workers, and among those yielding quality 16S rRNA amplicon sequencing data, we found just three symbionts to be common and dominant. Two, a Lactobacillus and an Acetobacteraceae species, were shared between native and introduced populations. The other, a Rickettsia , was found only in two introduced supercolonies. Across an eight‐year period of trophic reduction in one introduced population, we found no change in symbionts, arguing against a relationship between natural dietary change and microbiome composition. Overall, our findings thus argue against major changes in symbiotic bacteria in association with the invasion and trophic shift of L. humile . In addition, genome content from close relatives of the identified symbionts suggests that just one can synthesize most essential amino acids; this bacterium was only modestly abundant in introduced populations, providing little support for a major role of nitrogen‐provisioning symbioses in Argentine ant's dietary shift.

Decoupling of latitudinal gradients in species and genus geographic range size: a signature of clade range expansion - Adam Tomašových; David Jablonski (Global Ecology and Biogeography, 2017)
Aim Clade range size is a function of species range sizes but also depends on the geographic deployment of species: clade range expansion should therefore depend partly on the tendency of a clade to produce new species. Previous work has shown empirically that species‐rich clades are more likely to expand outside their present distributions, i.e. to overcome niche conservatism, than species‐poor ones. This pattern can follow from a neutral probabilistic model of clade‐level range expansion arising from differences in net species diversification between clades. We show that predictions of this model discriminate between weaker and stronger climatic niche conservatism, and compare these predictions with range‐size patterns of marine bivalves at the species and clade (genus) level. Location Western Pacific, eastern Pacific and western Atlantic. Methods We decompose the latitudinal and thermal distribution of genera into within‐species and among‐species components. We use a neutral model in which species range expansion does not vary with latitude and descendants originate within the ranges of their ancestors (model with spatial dependency) or where descendants originate independently of ancestral ranges (model without spatial dependency). Result In accord with model predictions: (1) genus latitudinal range size is weakly related to the latitudinal range sizes of congeneric species, but strongly depends on per‐genus species richness; (2) among‐species latitudinal distances correlate positively with per‐genus species richness; and (3) genus latitudinal and thermal range sizes increase towards higher latitudes because genera that are species rich anywhere within their range increase in proportion towards higher latitudes. Main conclusions Application of the neutral probabilistic model to marine bivalves shows that tropical niche conservatism is only moderately strong, and that species diversification plays a significant role in range expansion of bivalve genera to new latitudes and climates, even when thermal range sizes and limits of congeneric species show significant correlations, and are thus conserved to some degree.

Assessing uncertainties in land cover projections - Peter Alexander; Reinhard Prestele; Peter H. Verburg; Almut Arneth; Claudia Baranzelli; Filipe Batista e Silva; Calum Brown; Adam Butler; Katherine Calvin; Nicolas Dendoncker; Jonathan C. Doelman; Robert Dunford; et al. (Global Change Biology, 2017)
Understanding uncertainties in land cover projections is critical to investigating land‐based climate mitigation policies, assessing the potential of climate adaptation strategies and quantifying the impacts of land cover change on the climate system. Here, we identify and quantify uncertainties in global and European land cover projections over a diverse range of model types and scenarios, extending the analysis beyond the agro‐economic models included in previous comparisons. The results from 75 simulations over 18 models are analysed and show a large range in land cover area projections, with the highest variability occurring in future cropland areas. We demonstrate systematic differences in land cover areas associated with the characteristics of the modelling approach, which is at least as great as the differences attributed to the scenario variations. The results lead us to conclude that a higher degree of uncertainty exists in land use projections than currently included in climate or earth system projections. To account for land use uncertainty, it is recommended to use a diverse set of models and approaches when assessing the potential impacts of land cover change on future climate. Additionally, further work is needed to better understand the assumptions driving land use model results and reveal the causes of uncertainty in more depth, to help reduce model uncertainty and improve the projections of land cover.

Rehabilitation of community-owned, mixed-use rangelands: lessons from the Ewaso ecosystem in Kenya - David W. Kimiti; Anne-Marie C. Hodge; Jeffrey E. Herrick; Adam W. Beh; Laurie E. Abbott (Plant Ecology, 2017)

Evidence for sex-specific reproductive senescence in monogamous cooperatively breeding red wolves - Amanda M. Sparkman; Matthew Blois; Jennifer Adams; Lisette Waits; David A.W. Miller; Dennis L. Murray (Behavioral Ecology and Sociobiology, 2017)

Resistance training intensity and volume affect changes in rate of force development in resistance-trained men - Gerald T. Mangine; Jay R. Hoffman; Ran Wang; Adam M. Gonzalez; Jeremy R. Townsend; Adam J. Wells; Adam R. Jajtner; Kyle S. Beyer; Carleigh H. Boone; Amelia A. Miramonti; Michael B. LaMonica; David H. Fukuda; et al. (European Journal of Applied Physiology, 2016)

Resistance exercise increases intramuscular NF-κb signaling in untrained males - Jeremy R. Townsend; Jeffrey R. Stout; Adam R. Jajtner; David D. Church; Kyle S. Beyer; Leonardo P. Oliveira; Michael B. La Monica; Joshua J. Riffe; Tyler W. D. Muddle; Kayla M. Baker; David H. Fukuda; Michael D. Roberts; et al. (European Journal of Applied Physiology, 2016)

Climate regulation, energy provisioning and water purification: Quantifying ecosystem service delivery of bioenergy willow grown on riparian buffer zones using life cycle assessment - David Styles; Pål Börjesson; Tina D’Hertefeldt; Klaus Birkhofer; Jens Dauber; Paul Adams; Sopan Patil; Tim Pagella; Lars B. Pettersson; Philip Peck; Céline Vaneeckhaute; Håkan Rosenqvist (Ambio, 2016)

Enhancing conservation of A ustralian freshwater ecosystems: identification of freshwater flagship fishes and relevant target audiences - Brendan C Ebner; David L Morgan; Adam Kerezsy; Scott Hardie; Stephen J Beatty; Jamie E Seymour; James A Donaldson; Simon Linke; Stirling Peverell; David Roberts; Thomas Espinoza; Nadine Marshall; et al. (Fish and Fisheries, 2016)
Flagship species, especially mammals and birds, are commonly used to increase awareness of conservation issues in marine and terrestrial ecosystems. However, flagship species oriented programs are often ad hoc with initiatives scarce in the freshwater context. Here, we aim to identify potential flagship candidates that would appeal to a broad cross section of society at a continental scale where freshwater ecosystems are under threat from human impacts. We identified 19 species from a list of 299 Australian freshwater fishes on the basis of body size, trophic guild and threatened species status assuming these characteristics of flagship species are transferable from previous work on terrestrial flagship species. We considered the potential of species to be of international appeal but focused mostly on eight relevant interest groups within Australia. This followed the rationale that public engagement with conservation issues in freshwater systems might be more effective if the link between fish species and the decisions people make were better understood, and we acknowledge the diverging interests of stakeholders. This scoping work contributes towards addressing the challenges of connecting societies to the principles of sharing water resources with ecosystems, and represents the first continental‐scale assessment of its kind.

Synthesis and antimicrobial studies of azomethine and N-arylamine derivatives of 4-(4-formyl-3-phenyl-1H-pyrazol-1-yl)benzoic acid as potent anti-methicillin-resistant Staphylococcus aureus agents - Jamarcus Brider; Trent Rowe; Danielle Jamie Gibler; Adam Gottsponer; Evan Delancey; Michael Drew Branscum; Allyn Ontko; David Gilmore; Mohammad A. Alam (Medicinal Chemistry Research, 2016)

Mycorrhizal fungi and roots are complementary in foraging within nutrient patches - Lei Cheng; Weile Chen; Thomas S. Adams; Xing Wei; Le Li; Michael Luke McCormack; Jared L. DeForest; Roger T. Koide; David M. Eissenstat (Ecology, 2016)
The roots of the majority of tree species are associated with either arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi. The absorptive roots of tree species also vary widely in their diameter. The linkages between root thickness, mycorrhiza type and nutrient foraging are poorly understood. We conducted a large root ingrowth experiment in the field to investigate how absorptive roots of varying thickness and their associated fungi (AM vs. EM) exploit different nutrient patches (inorganic and organic) in a common garden. In nutrient‐rich patches, thin‐root tree species more effectively proliferated absorptive roots than thick‐root tree species, whereas thick‐root tree species proliferated more mycorrhizal fungal biomass than thin‐root tree species. Moreover, nutrient patches enriched with organic materials resulted in greater root and mycorrhizal fungal proliferation compared to those enriched with inorganic nutrients. Irrespective of root morphology, AM tree species had higher root foraging precision than mycorrhizal hyphae foraging precision within organic patches, whereas EM tree species exhibited the opposite. Our findings that roots and mycorrhizal fungi are complementary in foraging within nutrient patches provide new insights into species coexistence and element cycling in terrestrial ecosystems.

Erratum to: Key aspects of the biology, fisheries and management of Coral grouper - Ashley J. Frisch; Darren S. Cameron; Morgan S. Pratchett; David H. Williamson; Ashley J. Williams; Adam D. Reynolds; Andrew S. Hoey; Justin R. Rizzari; Louisa Evans; Brigid Kerrigan; Geoffrey Muldoon; David J. Welch; et al. (Reviews in Fish Biology and Fisheries, 2016)

Key aspects of the biology, fisheries and management of Coral grouper - Ashley J. Frisch; Darren S. Cameron; Morgan S. Pratchett; David H. Williamson; Ashley J. Williams; Adam D. Reynolds; Andrew S. Hoey; Justin R. Rizzari; Louisa Evans; Brigid Kerrigan; Geoffrey Muldoon; David J. Welch; et al. (Reviews in Fish Biology and Fisheries, 2016)

Intramuscular MAPK signaling following high volume and high intensity resistance exercise protocols in trained men - Adam M. Gonzalez; Jay R. Hoffman; Jeremy R. Townsend; Adam R. Jajtner; Carleigh H. Boone; Kyle S. Beyer; Kayla M. Baker; Adam J. Wells; Gerald T. Mangine; Edward H. Robinson; David D. Church; Leonardo P. Oliveira; et al. (European Journal of Applied Physiology, 2016)

Genetics of aging bone - Douglas J. Adams; David W. Rowe; Cheryl L. Ackert-Bicknell (Mammalian Genome, 2016)

Siderastrea siderea spawning and oocyte resorption at high latitude - Adam T. St.Gelais; Andia Chaves-Fonnegra; Alison L. Moulding; Vladimir N. Kosmynin; David S. Gilliam (Invertebrate Reproduction & Development, 2016)

Dactylogyrus olfactorius n. sp. (Monogenea, Dactylogyridae) from the olfactory chamber of the fathead minnow, Pimephales promelas Rafinesque (Cyprinidae) - Ebrahim Lari; Rachael V. Adams; David K. Cone; Cameron P. Goater; Greg G. Pyle (Systematic Parasitology, 2016)

Biodiversity responses to vegetation structure in a fragmented landscape: ant communities in a peri-urban coastal dune system - Sophie L. Cross; Adam T. Cross; David J. Merritt; Kingsley W. Dixon; Alan N. Andersen (Journal of Insect Conservation, 2016)

Metallothionein modulation in relation to cadmium bioaccumulation and age-dependent sensitivity of Chironomus riparius larvae - Zuzana Toušová; Jan Kuta; David Hynek; Vojtěch Adam; René Kizek; Luděk Bláha; Klára Hilscherová (Environmental Science and Pollution Research, 2016)

Testosterone enables growth and hypertrophy in fusion impaired myoblasts that display myotube atrophy: deciphering the role of androgen and IGF-I receptors - David C. Hughes; Claire E. Stewart; Nicholas Sculthorpe; Hannah F. Dugdale; Farzad Yousefian; Mark P. Lewis; Adam P. Sharples (Biogerontology, 2016)

Skeletal muscle cells possess a ‘memory’ of acute early life TNF-α exposure: role of epigenetic adaptation - Adam P. Sharples; Ioanna Polydorou; David C. Hughes; Daniel J. Owens; Thomas M. Hughes; Claire E. Stewart (Biogerontology, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Effects of Best Management Practice on Ecological Condition: Does Location Matter? - Roger Holmes; David G. Armanini; Adam G. Yates (Environmental Management, 2016)

The impact of tropical forest logging and oil palm agriculture on the soil microbiome - Binu M. Tripathi; David P. Edwards; Lucas William Mendes; Mincheol Kim; Ke Dong; Hyoki Kim; Jonathan M. Adams (Molecular Ecology, 2016)
Selective logging and forest conversion to oil palm agriculture are rapidly altering tropical forests. However, functional responses of the soil microbiome to these land‐use changes are poorly understood. Using 16S rRNA gene and shotgun metagenomic sequencing, we compared composition and functional attributes of soil biota between unlogged, once‐logged and twice‐logged rainforest, and areas converted to oil palm plantations in Sabah, Borneo. Although there was no significant effect of logging history, we found a significant difference between the taxonomic and functional composition of both primary and logged forests and oil palm. Oil palm had greater abundances of genes associated with DNA , RNA , protein metabolism and other core metabolic functions, but conversely, lower abundance of genes associated with secondary metabolism and cell–cell interactions, indicating less importance of antagonism or mutualism in the more oligotrophic oil palm environment. Overall, these results show a striking difference in taxonomic composition and functional gene diversity of soil microorganisms between oil palm and forest, but no significant difference between primary forest and forest areas with differing logging history. This reinforces the view that logged forest retains most features and functions of the original soil community. However, networks based on strong correlations between taxonomy and functions showed that network complexity is unexpectedly increased due to both logging and oil palm agriculture, which suggests a pervasive effect of both land‐use changes on the interaction of soil microbes.

Adaptive divergence despite strong genetic drift: genomic analysis of the evolutionary mechanisms causing genetic differentiation in the island fox ( Urocyon littoralis ) - W. Chris Funk; Robert E. Lovich; Paul A. Hohenlohe; Courtney A. Hofman; Scott A. Morrison; T. Scott Sillett; Cameron K. Ghalambor; Jesus E. Maldonado; Torben C. Rick; Mitch D. Day; Nicholas R. Polato; Sarah W. Fitzpatrick; et al. (Molecular Ecology, 2016)
The evolutionary mechanisms generating the tremendous biodiversity of islands have long fascinated evolutionary biologists. Genetic drift and divergent selection are predicted to be strong on islands and both could drive population divergence and speciation. Alternatively, strong genetic drift may preclude adaptation. We conducted a genomic analysis to test the roles of genetic drift and divergent selection in causing genetic differentiation among populations of the island fox ( Urocyon littoralis ). This species consists of six subspecies, each of which occupies a different California Channel Island. Analysis of 5293 SNP loci generated using Restriction‐site Associated DNA ( RAD ) sequencing found support for genetic drift as the dominant evolutionary mechanism driving population divergence among island fox populations. In particular, populations had exceptionally low genetic variation, small N e (range = 2.1–89.7; median = 19.4), and significant genetic signatures of bottlenecks. Moreover, islands with the lowest genetic variation (and, by inference, the strongest historical genetic drift) were most genetically differentiated from mainland grey foxes, and vice versa, indicating genetic drift drives genome‐wide divergence. Nonetheless, outlier tests identified 3.6–6.6% of loci as high F ST outliers, suggesting that despite strong genetic drift, divergent selection contributes to population divergence. Patterns of similarity among populations based on high F ST outliers mirrored patterns based on morphology, providing additional evidence that outliers reflect adaptive divergence. Extremely low genetic variation and small N e in some island fox populations, particularly on San Nicolas Island, suggest that they may be vulnerable to fixation of deleterious alleles, decreased fitness and reduced adaptive potential.

Patterns of Fraxinus angustifolia in an alluvial old-growth forest after declines in flooding events - David Janík; Dušan Adam; Libor Hort; Kamil Král; Pavel Šamonil; Pavel Unar; Tomáš Vrška (European Journal of Forest Research, 2016)

Ag nanoparticles generated using bio-reduction and -coating cause microbial killing without cell lysis - Aniket Gade; Joshua Adams; David W. Britt; Fen-Ann Shen; Joan E. McLean; Astrid Jacobson; Young-Cheol Kim; Anne J. Anderson (BioMetals, 2016)

Intentionally introduced terrestrial invertebrates: patterns, risks, and options for management - Sabrina Kumschick; Adam Devenish; Marc Kenis; Wolfgang Rabitsch; David M. Richardson; John R. U. Wilson (Biological Invasions, 2016)

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Reorganization and expansion of the nidoviral family Arteriviridae - Jens H. Kuhn; Michael Lauck; Adam L. Bailey; Alexey M. Shchetinin; Tatyana V. Vishnevskaya; Yīmíng Bào; Terry Fei Fan Ng; Matthew LeBreton; Bradley S. Schneider; Amethyst Gillis; Ubald Tamoufe; Joseph Le Doux Diffo; et al. (Archives of Virology, 2016)

Evaluation of economically feasible, natural plant extract-based microbiological media for producing biomass of the dry rot biocontrol strain Pseudomonas fluorescens P22Y05 in liquid culture - Sadia Khalil; Tasneem Adam Ali; Chris Skory; Patricia J. Slininger; David A. Schisler (World Journal of Microbiology and Biotechnology, 2016)

Pharmacokinetics of Morphine and Its Metabolites in Infants and Young Children After Congenital Heart Surgery - Mohammed H. Elkomy; David R. Drover; Kristi L. Glotzbach; Jeffery L. Galinkin; Adam Frymoyer; Felice Su; Gregory B. Hammer (The AAPS Journal, 2016)

Germline TERT promoter mutations are rare in familial melanoma - Mark Harland; Mia Petljak; Carla Daniela Robles-Espinoza; Zhihao Ding; Nelleke A. Gruis; Remco van Doorn; Karen A. Pooley; Alison M. Dunning; Lauren G. Aoude; Karin A. W. Wadt; Anne-Marie Gerdes; Kevin M. Brown; et al. (Familial Cancer, 2016)

Understanding public attitudes towards sharks at the Galapagos Islands - roadmap for a sustainable coexistence in a Marine World Heritage site - Acuna Marrero David; Smith Adam; Anderson Marti; Salinas De Leon Pelayo; De La Cruz Modino Raquel (Frontiers in Marine Science, 2016)

Drought and the rebound effect: a Murray–Darling Basin example - Adam Loch; David Adamson (Natural Hazards, 2015)

Dispersal in the desert: ephemeral water drives connectivity and phylogeography of an arid‐adapted fish - Krystina D. Mossop; Mark Adams; Peter J. Unmack; Katie L. Smith Date; Bob B. M. Wong; David G. Chapple (Journal of Biogeography, 2015)
Aim We examine landscape processes shaping the range‐wide phylogeography of a dispersal‐limited, desert‐dwelling fish (the desert goby, Chlamydogobius eremius ) in arid Australia. Location South‐western Lake Eyre Basin, central Australia. Methods We obtained sequence data for the mitochondrial cytochrome b gene ( n = 513 individuals) and nuclear genetic markers (51 allozyme loci; n ≥ 128 individuals) to investigate the phylogeographic relationships among 51 populations. Sampling spanned multiple habitat types (permanent desert springs, ephemeral rivers) and sub‐catchments, and the entire distribution of C. eremius and representatives of its sister species, Chlamydogobius japalpa . Phylogeographic analyses (genetic diversity, AMOVA , Tajima's D , W ST , mismatch distribution) were used to explore the distribution and partitioning of mt DNA variation; principal coordinates analysis and neighbour‐joining tree networks were used to explore allozyme variation. Results Three main genetic groups exist across C. eremius / C. japalpa populations. The geographical distributions of these groups reflected the historical and current confluence point of major rivers in the region. Surprisingly, permanent desert springs did not contain higher genetic diversity than ephemeral rivers. Main conclusions Genetic structuring of Chlamydogobius populations revealed unanticipated levels of connectivity, indicating that the ephemeral waters of Lake Eyre have allowed gene flow across drainage boundaries and large distances. Phylogeographic breaks reveal that connectivity relies on temporary surface water, while rapid temporal changes in diversity highlight flood‐driven dispersal as the main means of gene flow between localities and habitats. Dispersal pathways reveal that ecological context (life history and tolerance of extreme conditions) has played a key role in shaping observed patterns.

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Ischemic Stroke Patients with Active Malignancy or Extracardiac Shunts Are More Likely to Have a Right-to-Left Shunt Found by TCD Than Echocardiogram - Adam de Havenon; Anne Moore; Ali Sultan-Qurraie; Jennifer J. Majersik; Greg Stoddard; David Tirschwell (Translational Stroke Research, 2015)

The Mouse Genomes Project: a repository of inbred laboratory mouse strain genomes - David J. Adams; Anthony G. Doran; Jingtao Lilue; Thomas M. Keane (Mammalian Genome, 2015)

Recovery of African wild dogs suppresses prey but does not trigger a trophic cascade - Adam T. Ford; Jacob R. Goheen; David J. Augustine; Margaret F. Kinnaird; Timothy G. O'Brien; Todd M. Palmer; Robert M. Pringle; Rosie Woodroffe (Ecology, 2015)
Increasingly, the restoration of large carnivores is proposed as a means through which to restore community structure and ecosystem function via trophic cascades. After a decades‐long absence, African wild dogs ( Lycaon pictus ) recolonized the Laikipia Plateau in central Kenya, which we hypothesized would trigger a trophic cascade via suppression of their primary prey (dik‐dik, Madoqua guentheri ) and the subsequent relaxation of browsing pressure on trees. We tested the trophic‐cascade hypothesis using (1) a 14‐year time series of wild dog abundance; (2) surveys of dik‐dik population densities conducted before and after wild dog recovery; and (3) two separate, replicated, herbivore‐exclusion experiments initiated before and after wild dog recovery. The dik‐dik population declined by 33% following wild dog recovery, which is best explained by wild dog predation. Dik‐dik browsing suppressed tree abundance, but the strength of suppression did not differ between before and after wild dog recovery. Despite strong, top‐down limitation between adjacent trophic levels (carnivore–herbivore and herbivore–plant), a trophic cascade did not occur, possibly because of a time lag in indirect effects, variation in rainfall, and foraging by herbivores other than dik‐dik. Our ability to reject the trophic‐cascade hypothesis required two important approaches: (1) temporally replicated herbivore exclusions, separately established before and after wild dog recovery; and (2) evaluating multiple drivers of variation in the abundance of dik‐dik and trees. While the restoration of large carnivores is often a conservation priority, our results suggest that indirect effects are mediated by ecological context, and that trophic cascades are not a foregone conclusion of such recoveries.

Exploration of EEG features of Alzheimer’s disease using continuous wavelet transform - Parham Ghorbanian; David M. Devilbiss; Terry Hess; Allan Bernstein; Adam J. Simon; Hashem Ashrafiuon (Medical & Biological Engineering & Computing, 2015)

High-Throughput Prediction of Acacia and Eucalypt Lignin Syringyl/Guaiacyl Content Using FT-Raman Spectroscopy and Partial Least Squares Modeling - Jason S. Lupoi; Adam Healey; Seema Singh; Robert Sykes; Mark Davis; David J. Lee; Merv Shepherd; Blake A. Simmons; Robert J. Henry (BioEnergy Research, 2015)

Sensitivity of regional evapotranspiration partitioning to variation in woody plant cover: insights from experimental dryland tree mosaics - Juan Camilo Villegas; Francina Dominguez; Greg A. Barron‐Gafford; Henry D. Adams; Maite Guardiola‐Claramonte; Evan D. Sommer; Ashley Wiede Selvey; Javier F. Espeleta; Chris B. Zou; David D. Breshears; Travis E. Huxman (Global Ecology and Biogeography, 2015)
Aim Movement of water from the land surface to the atmosphere (evapotranspiration, ET ) is the dominant output flux in the global terrestrial surface water budget. The partitioning of ET between soil evaporation ( E ) and plant transpiration ( T ) couples important ecological, hydrological and atmospheric processes. ET partitioning has been hypothesized to vary as a function of woody plant cover, yet a relationship between ET partitioning and woody cover has not been quantified empirically. Land surface models assume unit increase in T per unit increase in vegetation cover (woody cover), following a proportional linear relationship. Recent assessments have questioned the validity of this assumption for heterogeneous canopies, but we lack experimental data across an explicitly defined gradient of woody cover to characterize this relationship. Location N orth A merican monsoon region. Methods In a controlled dryland environment experimental facility, we manipulated woody cover and documented the response of ET and its component fluxes. We incorporated the resulting functions into a widely used coupled land–atmosphere model ( WRF ‐ N oah) to document the implications of modifying specific model parameters that assume (1:1) proportionality. Results As total ET increased with woody cover, T/ET deviated below 1:1 proportionality. Using our experimentally determined relationship for ET partitioning and woody cover in the model, we observed reductions in ET of as much as 40% during the monsoon season and annual increases of almost 200% in regional E . Main conclusions Our results highlight a limitation of modelled ET that affects regional to global patterns of water flux, with implications for a number of earth surface processes. A better understanding of how changing woody cover influences patch‐scale ecohydrological processes is needed, particularly under current changes in woody cover associated with deforestation, afforestation and drought‐induced mortality. More specifically, improved representation of E and T fluxes will improve understanding and modelling of large‐scale ecological, hydrological and atmospheric processes.

On the controls of root lifespan: assessing the role of soluble phenolics - Thomas S. Adams; David M. Eissenstat (Plant and Soil, 2015)

Spatial convergent cross mapping to detect causal relationships from short time series - Adam Thomas Clark; Hao Ye; Forest Isbell; Ethan R. Deyle; Jane Cowles; G. David Tilman; George Sugihara (Ecology, 2015)
Recent developments in complex systems analysis have led to new techniques for detecting causal relationships using relatively short time series, on the order of 30 sequential observations. Although many ecological observation series are even shorter, perhaps fewer than ten sequential observations, these shorter time series are often highly replicated in space (i.e., plot replication). Here, we combine the existing techniques of convergent cross mapping (CCM) and dewdrop regression to build a novel test of causal relations that leverages spatial replication, which we call multispatial CCM. Using examples from simulated and real‐world ecological data, we test the ability of multispatial CCM to detect causal relationships between processes. We find that multispatial CCM successfully detects causal relationships with as few as five sequential observations, even in the presence of process noise and observation error. Our results suggest that this technique may constitute a useful test for causality in systems where experiments are difficult to perform and long time series are not available. This new technique is available in the multispatialCCM package for the R programming language.

Mating type and spore killing characterization of Fusarium verticillioides strains - Li Guo; Adam Z. Blatt; David M. Geiser; Maria del Mar Jiménez-Gasco; Gretchen A. Kuldau (Mycological Progress, 2015)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Massive Atenolol, Lisinopril, and Chlorthalidone Overdose Treated with Endoscopic Decontamination, Hemodialysis, Impella Percutaneous Left Ventricular Assist Device, and ECMO - C. William Heise; David Beutler; Adam Bosak; Geoffrey Orme; Akil Loli; Kimberlie Graeme (Journal of Medical Toxicology, 2015)

Long-term monitoring of arsenic, copper, selenium, and other elements in Great Salt Lake (Utah, USA) surface water, brine shrimp, and brine flies - William J. Adams; David K. DeForest; Lucinda M. Tear; Kelly Payne; Kevin V. Brix (Environmental Monitoring and Assessment, 2015)

Songbirds as sentinels of mercury in terrestrial habitats of eastern North America - Allyson K. Jackson; David C. Evers; Evan M. Adams; Daniel A. Cristol; Collin Eagles-Smith; Samuel T. Edmonds; Carrie E. Gray; Bart Hoskins; Oksana P. Lane; Amy Sauer; Timothy Tear (Ecotoxicology, 2015)

Ephemeral stream reaches preserve the evolutionary and distributional history of threespine stickleback in the Santa Clara and Ventura River watersheds of southern California - Jonathan Q. Richmond; David K. Jacobs; Adam R. Backlin; Camm C. Swift; Chris Dellith; Robert N. Fisher (Conservation Genetics, 2015)

Nonlinear thermal gradients shape broad‐scale patterns in geographic range size and can reverse R apoport's rule - Adam Tomašových; David Jablonski; Sarah K. Berke; Andrew Z. Krug; James W. Valentine (Global Ecology and Biogeography, 2015)
Aim Species living at latitudes that have greater annual temperature variations are expected to achieve broader geographic ranges than species living at latitudes that have smaller annual temperature variations, generating a positive relationship between range size and latitude ( R apoport's rule). However, this prediction fails to take into account the greater latitudinal extent of tropical temperatures relative to those at higher latitudes. Here we model the contributions of the broader latitudinal extent of equal‐temperature habitats at low latitudes and the greater annual temperature variation at high latitudes to the range size–latitude relationship, and test whether the latitudinal variation in geographic range size in marine bivalves can be explained by models that account for both annual temperature variation and the steepness of latitudinal thermal gradients. Location W estern P acific, eastern P acific and western A tlantic. Methods We use a null model where geographic ranges are placed on the ocean surface independently of thermal gradients, and a range‐expansion model where the minimum and maximum temperatures encompassed by the geographic range of a species (macroecological thermal ranges) are positively related to annual temperature minima and maxima at the location where the species originated. We compare results with a database containing 40,820 occurrences of 4760 marine bivalve species. Result Models incorporating temperature‐limited range expansion along realistic thermal gradients predict an inverse relationship between range size and latitude, in opposition to R apoport's rule. The distribution patterns of marine bivalves match this prediction. Main conclusions The poleward trend in latitudinal range size is determined by the nonlinearity of the latitudinal gradient of temperature minima and maxima and less by the latitudinal gradient of the local seasonal range in temperatures. Although tropical species do have narrower macroecological thermal ranges than high‐latitude species, the nearly constant temperatures over wide areas of the tropics allow tropical species to achieve broad latitudinal ranges.

Genetic Data Sharing and Privacy - Marco D. Sorani; John K. Yue; Sourabh Sharma; Geoffrey T. Manley; Adam R. Ferguson; Shelly R. Cooper; Kristen Dams-O’Connor; Wayne A. Gordon; Hester F. Lingsma; Andrew I. R. Maas; David K. Menon; Diane J. Morabito; et al. (Neuroinformatics, 2015)

Lithium carbonate in the management of cannabis withdrawal: a randomized placebo-controlled trial in an inpatient setting - Jennifer Johnston; Nicholas Lintzeris; David J. Allsop; Anastasia Suraev; Jessica Booth; Dean S. Carson; David Helliwell; Adam Winstock; Iain S. McGregor (Psychopharmacology, 2014)

Stable H–C–O isotope and trace element geochemistry of the Cummins Range Carbonatite Complex, Kimberley region, Western Australia: implications for hydrothermal REE mineralization, carbonatite evolution and mantle source regions - Peter J. Downes; Attila Demény; György Czuppon; A. Lynton Jaques; Michael Verrall; Marcus Sweetapple; David Adams; Neal J. McNaughton; Lalchand G. Gwalani; Brendan J. Griffin (Mineralium Deposita, 2014)

Population genetics of grotto sculpin (Cottus specus), a new cave-adapted fish species - Julie L. Day; David E. Starkey; Ginny Adams; Shawn Brummett; Devon Keeney (Environmental Biology of Fishes, 2014)

Plant–soil feedbacks of exotic plant species across life forms: a meta-analysis - Annelein Meisner; W. H. Gera Hol; Wietse de Boer; Jennifer Adams Krumins; David A. Wardle; Wim H. van der Putten (Biological Invasions, 2014)

Tree spatial patterns of Abies alba and Fagus sylvatica in the Western Carpathians over 30 years - David Janík; Dušan Adam; Libor Hort; Kamil Král; Pavel Šamonil; Pavel Unar; Tomáš Vrška (European Journal of Forest Research, 2014)

The energy‐conserving electron transfer system used by D esulfovibrio alaskensis strain G 20 during pyruvate fermentation involves reduction of endogenously formed fumarate and cytoplasmic and membrane‐bound complexes, Hdr‐Flox and Rnf - Birte Meyer; Jennifer V. Kuehl; Morgan N. Price; Jayashree Ray; Adam M. Deutschbauer; Adam P. Arkin; David A. Stahl (Environmental Microbiology, 2014)
Summary The adaptation capability of D esulfovibrio to natural fluctuations in electron acceptor availability was evaluated by studying D esulfovibrio alaskensis strain G 20 under varying respiratory, fermentative and methanogenic coculture conditions in chemostats. Transition from lactate to pyruvate in coculture resulted in a dramatic shift in the population structure and closer interspecies cell‐to‐cell interactions. Lower methane production rates in coculture than predicted from pyruvate input was attributed to redirection of electron flow to fumarate reduction. Without a methanogenic partner, accumulation of H 2 and formate resulted in greater succinate production. Comparative transcript and gene fitness analysis in concert with physiological data of G 20 wildtype and mutants demonstrated that pyruvate fermentation involves respiration of cytoplasmically formed fumarate using cytoplasmic and membrane‐bound energy‐conserving complexes, Rnf , Hdr‐Flox ‐1 and Hmc. At the low H 2 /formate levels maintained in coculture, Rnf likely functions as proton‐pumping ferredoxin (Fd) : type‐I cytochrome c oxidoreductase, which transitions to a proton‐pumping Fd red : nicotinamide adenine dinucleotide ( NAD + ) oxidoreductase at high H 2 /formate levels during fermentation in monoculture. Hdr‐Flox ‐1 is postulated to recycle Fd red via a flavin‐based electron bifurcation involving NADH , Fd ox and the thiol/disulphide‐containing DsrC . In a menaquinone ( MQ )‐based electron confurcation reaction, the high‐molecular‐weight cytochrome‐c 3 complex, Hmc , is proposed to then couple DsrC red and periplasmic H 2 /formate oxidation using the MQ pool to fuel a membrane‐bound fumarate reductase.

Primary alveolar macrophages exposed to diesel particulate matter increase RAGE expression and activate RAGE signaling - David B. Barton; Bryce C. Betteridge; Tyler D. Earley; Cameron S. Curtis; Adam B. Robinson; Paul R. Reynolds (Cell and Tissue Research, 2014)

Quantifying targets to manage invasion risk: light gradients dominate the early regeneration niche of naturalized and pre-commercial Miscanthus populations - Natalie M. West; David P. Matlaga; Adam S. Davis (Biological Invasions, 2014)

Beyond a warming fingerprint: individualistic biogeographic responses to heterogeneous climate change in California - Giovanni Rapacciuolo; Sean P. Maher; Adam C. Schneider; Talisin T. Hammond; Meredith D. Jabis; Rachel E. Walsh; Kelly J. Iknayan; Genevieve K. Walden; Meagan F. Oldfather; David D. Ackerly; Steven R. Beissinger (Global Change Biology, 2014)
Understanding recent biogeographic responses to climate change is fundamental for improving our predictions of likely future responses and guiding conservation planning at both local and global scales. Studies of observed biogeographic responses to 20th century climate change have principally examined effects related to ubiquitous increases in temperature – collectively termed a warming fingerprint. Although the importance of changes in other aspects of climate – particularly precipitation and water availability – is widely acknowledged from a theoretical standpoint and supported by paleontological evidence, we lack a practical understanding of how these changes interact with temperature to drive biogeographic responses. Further complicating matters, differences in life history and ecological attributes may lead species to respond differently to the same changes in climate. Here, we examine whether recent biogeographic patterns across California are consistent with a warming fingerprint. We describe how various components of climate have changed regionally in California during the 20th century and review empirical evidence of biogeographic responses to these changes, particularly elevational range shifts. Many responses to climate change do not appear to be consistent with a warming fingerprint, with downslope shifts in elevation being as common as upslope shifts across a number of taxa and many demographic and community responses being inconsistent with upslope shifts. We identify a number of potential direct and indirect mechanisms for these responses, including the influence of aspects of climate change other than temperature (e.g., the shifting seasonal balance of energy and water availability), differences in each taxon's sensitivity to climate change, trophic interactions, and land‐use change. Finally, we highlight the need to move beyond a warming fingerprint in studies of biogeographic responses by considering a more multifaceted view of climate, emphasizing local‐scale effects, and including a priori knowledge of relevant natural history for the taxa and regions under study.

Can tidal perturbations associated with sea level variations in the western Pacific Ocean be used to understand future effects of tidal evolution? - Adam T. Devlin; David A. Jay; Stefan A. Talke; Edward Zaron (Ocean Dynamics, 2014)

Variability in root production, phenology, and turnover rate among 12 temperate tree species - M. Luke McCormack; Thomas S. Adams; Erica A. H. Smithwick; David M. Eissenstat (Ecology, 2014)
The timing of fine root production and turnover strongly influences both the seasonal potential for soil resource acquisition among competing root systems and the plant fluxes of root carbon into soil pools. However, basic patterns and variability in the rates and timing or fine root production and turnover are generally unknown among perennial plants species. We address this shortfall using a heuristic model relating root phenology to turnover together with three years of minirhizotron observations of root dynamics in 12 temperate tree species grown in a common garden. We specifically investigated how the amount and the timing of root production differ among species and how they impact estimates of fine root turnover. Across the 12 species, there was wide variation in the timing of root production with some species producing a single root flush in early summer and others producing roots either more uniformly over the growing season or in multiple pulses. Additionally, the pattern and timing of root production appeared to be consistent across years for some species but varied in others. Root turnover rate was related to total root production ( P

Biogenic ethylene promotes seedling emergence from the sediment seed bank in an ephemeral tropical rock pool habitat - Adam T. Cross; Gregory R. Cawthray; David J. Merritt; Shane R. Turner; Michael Renton; Kingsley W. Dixon (Plant and Soil, 2014)

F 16915 prevents heart failure-induced atrial fibrillation: a promising new drug as upstream therapy - Bruno Le Grand; Robert Letienne; Elisabeth Dupont-Passelaigue; Frédérique Lantoine-Adam; Frédéric Longo; Monique David-Dufilho; Georghia Michael; Kunihiro Nishida; Daniel Catheline; Philippe Legrand; Stéphane Hatem; Stanley Nattel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Acute toxicity of copper, lead, cadmium, and zinc to early life stages of white sturgeon (Acipenser transmontanus) in laboratory and Columbia River water - David W. Vardy; Robert Santore; Adam Ryan; John P. Giesy; Markus Hecker (Environmental Science and Pollution Research, 2014)

Glucagon-like peptide 1 and peptide YY are in separate storage organelles in enteroendocrine cells - Hyun-Jung Cho; Eliza S. Robinson; Leni R. Rivera; Paul J. McMillan; Adam Testro; Mehrdad Nikfarjam; David M. Bravo; John B. Furness (Cell and Tissue Research, 2014)

How do various maize crop models vary in their responses to climate change factors? - Simona Bassu; Nadine Brisson; Jean‐Louis Durand; Kenneth Boote; Jon Lizaso; James W. Jones; Cynthia Rosenzweig; Alex C. Ruane; Myriam Adam; Christian Baron; Bruno Basso; Christian Biernath; et al. (Global Change Biology, 2014)
Potential consequences of climate change on crop production can be studied using mechanistic crop simulation models. While a broad variety of maize simulation models exist, it is not known whether different models diverge on grain yield responses to changes in climatic factors, or whether they agree in their general trends related to phenology, growth, and yield. With the goal of analyzing the sensitivity of simulated yields to changes in temperature and atmospheric carbon dioxide concentrations [ CO 2 ], we present the largest maize crop model intercomparison to date, including 23 different models. These models were evaluated for four locations representing a wide range of maize production conditions in the world: Lusignan (France), Ames ( USA ), Rio Verde (Brazil) and Morogoro (Tanzania). While individual models differed considerably in absolute yield simulation at the four sites, an ensemble of a minimum number of models was able to simulate absolute yields accurately at the four sites even with low data for calibration, thus suggesting that using an ensemble of models has merit. Temperature increase had strong negative influence on modeled yield response of roughly −0.5 Mg ha −1 per °C. Doubling [ CO 2 ] from 360 to 720 μmol mol −1 increased grain yield by 7.5% on average across models and the sites. That would therefore make temperature the main factor altering maize yields at the end of this century. Furthermore, there was a large uncertainty in the yield response to [ CO 2 ] among models. Model responses to temperature and [ CO 2 ] did not differ whether models were simulated with low calibration information or, simulated with high level of calibration information.

Assessing Risk to Birds from Industrial Wind Energy Development via Paired Resource Selection Models - TRICIA A. MILLER; ROBERT P. BROOKS; MICHAEL LANZONE; DAVID BRANDES; JEFF COOPER; KIERAN O'MALLEY; CHARLES MAISONNEUVE; JUNIOR TREMBLAY; ADAM DUERR; TODD KATZNER (Conservation Biology, 2014)
When wildlife habitat overlaps with industrial development animals may be harmed. Because wildlife and people select resources to maximize biological fitness and economic return, respectively, we estimated risk, the probability of eagles encountering and being affected by turbines, by overlaying models of resource selection for each entity. This conceptual framework can be applied across multiple spatial scales to understand and mitigate impacts of industry on wildlife. We estimated risk to Golden Eagles (Aquila chrysaetos) from wind energy development in 3 topographically distinct regions of the central Appalachian Mountains of Pennsylvania (United States) based on models of resource selection of wind facilities (n = 43) and of northbound migrating eagles (n = 30). Risk to eagles from wind energy was greatest in the Ridge and Valley region; all 24 eagles that passed through that region used the highest risk landscapes at least once during low altitude flight. In contrast, only half of the birds that entered the Allegheny Plateau region used highest risk landscapes and none did in the Allegheny Mountains. Likewise, in the Allegheny Mountains, the majority of wind turbines (56%) were situated in poor eagle habitat; thus, risk to eagles is lower there than in the Ridge and Valley, where only 1% of turbines are in poor eagle habitat. Risk within individual facilities was extremely variable; on average, facilities had 11% (SD 23; range = 0–100%) of turbines in highest risk landscapes and 26% (SD 30; range = 0–85%) of turbines in the lowest risk landscapes. Our results provide a mechanism for relocating high‐risk turbines, and they show the feasibility of this novel and highly adaptable framework for managing risk of harm to wildlife from industrial development. Evaluación del Riesgo para las Aves por el Desarrollo de Energía Eólica Industrial Mediante Modelos de Selección de Recursos Pareados.

Transcriptome population genomics reveals severe bottleneck and domestication cost in the A frican rice ( O ryza glaberrima ) - Benoit Nabholz; Gautier Sarah; François Sabot; Manuel Ruiz; Hélène Adam; Sabine Nidelet; Alain Ghesquière; Sylvain Santoni; Jacques David; Sylvain Glémin (Molecular Ecology, 2014)
The African cultivated rice ( Oryza glaberrima ) was domesticated in West Africa 3000 years ago. Although less cultivated than the Asian rice ( O. sativa ), O. glaberrima landraces often display interesting adaptation to rustic environment (e.g. drought). Here, using RNA ‐seq technology, we were able to compare more than 12 000 transcripts between 9 O. glaberrima, 10 wild O. barthii and one O. meridionalis individuals. With a synonymous nucleotide diversity π s = 0.0006 per site, O. glaberrima appears as the least genetically diverse crop grass ever documented. Using approximate Bayesian computation, we estimated that O. glaberrima experienced a severe bottleneck during domestication. This demographic scenario almost fully accounts for the pattern of genetic diversity across O. glaberrima genome as we detected very few outliers regions where positive selection may have further impacted genetic diversity. Moreover, the large excess of derived nonsynonymous substitution that we detected suggests that the O. glaberrima population suffered from the ‘cost of domestication’. In addition, we used this genome‐scale data set to demonstrate that (i) O. barthii genetic diversity is positively correlated with recombination rate and negatively with gene density, (ii) expression level is negatively correlated with evolutionary constraint, and (iii) one region on chromosome 5 (position 4–6 Mb) exhibits a clear signature of introgression with a yet unidentified Oryza species. This work represents the first genome‐wide survey of the African rice genetic diversity and paves the way for further comparison between the African and the Asian rice, notably regarding the genetics underlying domestication traits.

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

The Tendon Injury Response is Influenced by Decorin and Biglycan - Andrew A. Dunkman; Mark R. Buckley; Michael J. Mienaltowski; Sheila M. Adams; Stephen J. Thomas; Lauren Satchell; Akash Kumar; Lydia Pathmanathan; David P. Beason; Renato V. Iozzo; David E. Birk; Louis J. Soslowsky (Annals of Biomedical Engineering, 2014)

The Hypoglycemic Effect of Pumpkin Seeds, Trigonelline (TRG), Nicotinic Acid (NA), and D-Chiro-inositol (DCI) in Controlling Glycemic Levels in Diabetes Mellitus - Gary G. Adams; Shahwar Imran; Sheng Wang; Abubaker Mohammad; M. Samil Kok; David A. Gray; Guy A. Channell; Stephen E. Harding (Critical Reviews in Food Science and Nutrition, 2014)

Mercury in bats from the northeastern United States - David E. Yates; Evan M. Adams; Sofia E. Angelo; David C. Evers; John Schmerfeld; Marianne S. Moore; Thomas H. Kunz; Timothy Divoll; Samuel T. Edmonds; Christopher Perkins; Robert Taylor; Nelson J. O’Driscoll (Ecotoxicology, 2014)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Roles of Patch Characteristics, Drought Frequency, and Restoration in Long‐Term Trends of a Widespread Amphibian - BLAKE R. HOSSACK; MICHAEL J. ADAMS; CHRISTOPHER A. PEARL; KRISTINE W. WILSON; EVELYN L. BULL; KRISTIN LOHR; DEBRA PATLA; DAVID S. PILLIOD; JASON M. JONES; KEVIN K. WHEELER; SAMUEL P. MCKAY; PAUL STEPHEN CORN (Conservation Biology, 2013)
Despite the high profile of amphibian declines and the increasing threat of drought and fragmentation to aquatic ecosystems, few studies have examined long‐term rates of change for a single species across a large geographic area. We analyzed growth in annual egg‐mass counts of the Columbia spotted frog ( Rana luteiventris ) across the northwestern United States, an area encompassing 3 genetic clades. On the basis of data collected by multiple partners from 98 water bodies between 1991 and 2011, we used state‐space and linear‐regression models to measure effects of patch characteristics, frequency of summer drought, and wetland restoration on population growth. Abundance increased in the 2 clades with greatest decline history, but declined where populations are considered most secure. Population growth was negatively associated with temporary hydroperiods and landscape modification (measured by the human footprint index), but was similar in modified and natural water bodies. The effect of drought was mediated by the size of the water body: populations in large water bodies maintained positive growth despite drought, whereas drought magnified declines in small water bodies. Rapid growth in restored wetlands in areas of historical population declines provided strong evidence of successful management. Our results highlight the importance of maintaining large areas of habitat and underscore the greater vulnerability of small areas of habitat to environmental stochasticity. Similar long‐term growth rates in modified and natural water bodies and rapid, positive responses to restoration suggest pond construction and other forms of management can effectively increase population growth. These tools are likely to become increasingly important to mitigate effects of increased drought expected from global climate change . Papeles de las Características del Fragmento, Frecuencia de Sequía y Restauración en las Tendencias a Largo Plazo de un Anfibio Ampliamente Distribuido

Foraging ants trade off further for faster: use of natural bridges and trunk trail permanency in carpenter ants - Raquel G. Loreto; Adam G. Hart; Thairine M. Pereira; Mayara L. R. Freitas; David P. Hughes; Simon L. Elliot (The Science of Nature, 2013)

Magnetic Nanoparticles for Tumor Imaging and Therapy: A So-Called Theranostic System - Huining He; Allan David; Beata Chertok; Adam Cole; Kyuri Lee; Jian Zhang; Jianxin Wang; Yongzhuo Huang; Victor C. Yang (Pharmaceutical Research, 2013)

A survey of DNA methylation across social insect species, life stages, and castes reveals abundant and caste-associated methylation in a primitively social wasp - Susan A. Weiner; David A. Galbraith; Dean C. Adams; Nicole Valenzuela; Fernando B. Noll; Christina M. Grozinger; Amy L. Toth (The Science of Nature, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Protective Effect of Alpha-Melanocyte-Stimulating Hormone (α-MSH) on the Recovery of Ischemia/Reperfusion (I/R)-Induced Retinal Damage in A Rat Model - Balazs Varga; Rudolf Gesztelyi; Mariann Bombicz; David Haines; Adrienn Monika Szabo; Adam Kemeny-Beke; Miklos Antal; Miklos Vecsernyes; Bela Juhasz; Arpad Tosaki (Journal of Molecular Neuroscience, 2013)

The effects of BMY-14802 against l-DOPA- and dopamine agonist-induced dyskinesia in the hemiparkinsonian rat - Nirmal Bhide; David Lindenbach; Margaret A. Surrena; Adam A. Goldenberg; Christopher Bishop; S. Paul Berger; Melanie A. Paquette (Psychopharmacology, 2013)

The Evolution of Wing Shape in Ornamented-Winged Damselflies (Calopterygidae, Odonata) - David Outomuro; Dean C. Adams; Frank Johansson (Evolutionary Biology, 2013)

Identification of Resting and Active State EEG Features of Alzheimer’s Disease using Discrete Wavelet Transform - Parham Ghorbanian; David M. Devilbiss; Ajay Verma; Allan Bernstein; Terry Hess; Adam J. Simon; Hashem Ashrafiuon (Annals of Biomedical Engineering, 2013)

Exercise-induced endocannabinoid signaling is modulated by intensity - David A. Raichlen; Adam D. Foster; Alexandre Seillier; Andrea Giuffrida; Gregory L. Gerdeman (European Journal of Applied Physiology, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Macroecological patterns of marine bacteria on a global scale - Anthony S. Amend; Tom A. Oliver; Linda A. Amaral‐Zettler; Antje Boetius; Jed A. Fuhrman; M. Claire Horner‐Devine; Susan M. Huse; David B. Mark Welch; Adam C. Martiny; Alban Ramette; Lucie Zinger; Mitchell L. Sogin; et al. (Journal of Biogeography, 2013)
Aim To test whether within‐species and among‐species patterns of abundance and latitudinal range in marine bacteria resemble those found for macro‐organisms, and whether these patterns differ along latitudinal clines. Location Global pelagic marine environments. Methods Taxon‐specific sequence abundance and location were retrieved from the open‐access V6‐ rRNA pyrotag sequence data base VAMPS ( http://vamps.mbl.edu/ ), which holds a massive collection of marine bacterial community data sets from the I nternational C ensus of M arine M icrobes sampling effort of global ocean water masses. Data were randomly subsampled to correct for spatial bias and for differences in sampling effort. Results We show that bacterial latitudinal ranges are narrower than expected by chance. When present in both N orthern and S outhern hemispheres, taxa occupy restricted ranges at similar latitudes on both sides of the equator. A significant and positive relationship exists between sequence abundance and latitudinal range, although this pattern contains a large amount of variance. Abundant taxa in the tropics and in the N orthern H emisphere generally have smaller ranges than those in the S outhern H emisphere. We show that the mean latitudinal range of bacterial taxa increases with latitude, supporting the existence of a R apoport effect in marine bacterioplankton. Finally, we show that bacterioplankton communities contain a higher proportion of abundant taxa as they approach the poles. Main conclusions Macroecological patterns such as the abundance–range relationship, in general, extend to marine bacteria. However, differences in the shape of these relationships between bacteria and macro‐organisms call into question whether the processes and their relative importance in shaping global marine bacteria and macro‐organism distributions are the same.

A Comparison of the Prevalence of Lead-Contaminated Imported Chinese Ceramic Dinnerware Purchased Inside Versus Outside Philadelphia's Chinatown - Thomas Gilmore; Gerald F. O’Malley; Wayne Bond Lau; David R. Vann; Adam Bromberg; Aaron Martin; Andrea Gibbons; Evan Rimmer (Journal of Medical Toxicology, 2013)

On the canopy structure manipulation to buffer climate change effects on insect herbivore development - Marc Saudreau; Sylvain Pincebourde; Mathieu Dassot; Boris Adam; Hugh D. Loxdale; David G. Biron (Trees, 2013)

Toxicological Status of Children with Autism vs. Neurotypical Children and the Association with Autism Severity - James B. Adams; Tapan Audhya; Sharon McDonough-Means; Robert A. Rubin; David Quig; Elizabeth Geis; Eva Gehn; Melissa Loresto; Jessica Mitchell; Sharon Atwood; Suzanne Barnhouse; Wondra Lee (Biological Trace Element Research, 2013)

Symbiosis between the cyanobacterium Nostoc and the liverwort Blasia requires a CheR-type MCP methyltransferase - Paula S. Duggan; Teresa Thiel; David G. Adams (Symbiosis, 2013)

Beyond Bergmann's rule: size–latitude relationships in marine Bivalvia world‐wide - Sarah K. Berke; David Jablonski; Andrew Z. Krug; Kaustuv Roy; Adam Tomasovych (Global Ecology and Biogeography, 2013)
Aim Variations in body size are well established for many taxa of endotherms and ectotherms, but remain poorly documented for marine invertebrates. Here we explore how body size varies with latitude, temperature and productivity for a major marine invertebrate class, the Bivalvia. Location Continental shelves world‐wide. Methods We used regression models to assess univariate relationships between size and latitude as well as multivariate relationships between size, latitude and environmental parameters (mean and seasonality in temperature and mean productivity). The dataset consisted of 4845 species in 59 families from shelf depths at all latitudes in the Pacific and Atlantic oceans. We also used Blomberg's K to assess whether size–latitude relationships show phylogenetic signal, and test whether functional groups based on feeding mode, substrate relationships, mobility and fixation can account for observed size–latitude trends. Results Size–latitude trends are taxonomically and geographically common in bivalves, but vary widely in sign and strength – no simple explanations based on environmental parameters, phylogeny or functional group hold across all families. Perhaps most importantly, we found that the observed trends vary considerably between hemispheres and among coastlines. Main conclusions Broadly generalizable macroecological patterns in inter‐specific body size may not exist for marine invertebrates. Although size–latitude trends occur in many bivalve lineages, the underlying mechanisms evidently differ among regions and/or lineages. Fully understanding macroecological patterns requires truly global datasets as well as information about the evolutionary history of specific lineages and regions.

Comparative mapping in watermelon [Citrullus lanatus (Thunb.) Matsum. et Nakai] - Katherine Sandlin; Jason Prothro; Adam Heesacker; Nelly Khalilian; Rebecca Okashah; Wenwen Xiang; Eleni Bachlava; David G. Caldwell; Chris A. Taylor; Danelle K. Seymour; Victoria White; Eva Chan; et al. (Theoretical and Applied Genetics, 2012)

Generation of the Sotos syndrome deletion in mice - Anna M. Migdalska; Louise van der Weyden; Ozama Ismail; Alistair G. Rust; Mamunur Rashid; Jacqueline K. White; Gabriela Sánchez-Andrade; James R. Lupski; Darren W. Logan; Mark J. Arends; David J. Adams (Mammalian Genome, 2012)

Endosis and Exosis: New Names for Fusion and Budding - David D. Busath; Dixon J. Woodbury; Adam Frost (The Journal of Membrane Biology, 2012)

Mouse large-scale phenotyping initiatives: overview of the European Mouse Disease Clinic (EUMODIC) and of the Wellcome Trust Sanger Institute Mouse Genetics Project - Abdel Ayadi; Marie-Christine Birling; Joanna Bottomley; James Bussell; Helmut Fuchs; Martin Fray; Valérie Gailus-Durner; Simon Greenaway; Richard Houghton; Natasha Karp; Sophie Leblanc; Christoph Lengger; et al. (Mammalian Genome, 2012)

Next-generation sequencing of experimental mouse strains - Binnaz Yalcin; David J. Adams; Jonathan Flint; Thomas M. Keane (Mammalian Genome, 2012)

Anaerobic methane oxidation in metalliferous hydrothermal sediments: influence on carbon flux and decoupling from sulfate reduction - Scott D. Wankel; Melissa M. Adams; David T. Johnston; Colleen M. Hansel; Samantha B. Joye; Peter R. Girguis (Environmental Microbiology, 2012)
Summary The anaerobic oxidation of methane (AOM) is a globally significant sink that regulates methane flux from sediments into the oceans and atmosphere. Here we examine mesophilic to thermophilic AOM in hydrothermal sediments recovered from the Middle Valley vent field, on the Juan de Fuca Ridge. Using continuous‐flow sediment bioreactors and batch incubations, we characterized (i) the degree to which AOM contributes to net dissolved inorganic carbon flux, (ii) AOM and sulfate reduction (SR) rates as a function of temperature and (iii) the distribution and density of known anaerobic methanotrophs (ANMEs). In sediment bioreactors, inorganic carbon stable isotope mass balances results indicated that AOM accounted for between 16% and 86% of the inorganic carbon produced, underscoring the role of AOM in governing inorganic carbon flux from these sediments. At 90°C, AOM occurred in the absence of SR, demonstrating a striking decoupling of AOM from SR. An abundance of Fe(III)‐bearing minerals resembling mixed valent Fe oxides, such as green rust, suggests the potential for a coupling of AOM to Fe(III) reduction in these metalliferous sediments. While SR bacteria were only observed in cooler temperature sediments, ANMEs allied to ANME‐1 ribotypes, including a putative ANME‐1c group, were found across all temperature regimes and represented a substantial proportion of the archaeal community. In concert, these results extend and reshape our understanding of the nature of high temperature methane biogeochemistry, providing insight into the physiology and ecology of thermophilic anaerobic methanotrophy and suggesting that AOM may play a central role in regulating biological dissolved inorganic carbon fluxes to the deep ocean from the organic‐poor, metalliferous sediments of the global mid‐ocean ridge hydrothermal vent system.

Effect of salt on the interaction of Hal18 with lipid membranes - Sarah R. Dennison; Adam J. Phoenix; David A. Phoenix (European Biophysics Journal, 2012)

Timing of disturbance alters competitive outcomes and mechanisms of coexistence in an annual plant model - Adam David Miller; Stephen H. Roxburgh; Katriona Shea (Theoretical Ecology, 2012)

High anxiety is a predisposing endophenotype for loss of control over cocaine, but not heroin, self-administration in rats - Ruth Dilleen; Yann Pelloux; Adam C. Mar; Anna Molander; Trevor W. Robbins; Barry J. Everitt; Jeffrey W. Dalley; David Belin (Psychopharmacology, 2012)

Behavioral effects of α,α,β,β-tetradeutero-5-MeO-DMT in rats: comparison with 5-MeO-DMT administered in combination with a monoamine oxidase inhibitor - Adam L. Halberstadt; David E. Nichols; Mark A. Geyer (Psychopharmacology, 2012)

Analysis of climate policy targets under uncertainty - Mort Webster; Andrei P. Sokolov; John M. Reilly; Chris E. Forest; Sergey Paltsev; Adam Schlosser; Chien Wang; David Kicklighter; Marcus Sarofim; Jerry Melillo; Ronald G. Prinn; Henry D. Jacoby (Climatic Change, 2012)

Biodiversity and conservation genetics research in Central Africa: new approaches and avenues for international collaboration - Nicola M. Anthony; Patrick Mickala; Katharine A. Abernethy; Christiane Atteke; Pulchérie Bissiengou; Michael W. Bruford; Francisco Dallmeier; Thibaud Decaëns; Akaibe Dudu; Adam Freedman; Mary Katherine Gonder; Olivier Hardy; et al. (Conservation Genetics Resources, 2012)

Conservation status of eulachon in the California Current - Richard G Gustafson; Michael J Ford; Peter B Adams; Jonathan S Drake; Robert L Emmett; Kurt L Fresh; Mindy Rowse; Elizabeth A K Spangler; Robert E Spangler; David J Teel; Matthew T Wilson (Fish and Fisheries, 2012)
Eulachon ( Thaleichthys pacificus ), an anadromous smelt in the Northeast Pacific Ocean was examined for listing under the USA’s Endangered Species Act (ESA). A southern Distinct Population Segment (DPS) of eulachon – that occurs in the California Current and is composed of numerous subpopulations that spawn in rivers from northern California to northern British Columbia – was identified on the basis of ecological and environmental characteristics, and to a lesser extent, genetic and life history variation. Although the northern terrestrial boundary of this DPS remains uncertain, our consensus opinion was that this northern boundary occurs south of the Nass River and that the DPS was discrete from more northern eulachon, as well as significant to the biological species as a whole and thus is a ‘species’ under the ESA. Eulachon have been nearly absent in northern California for over two decades, have declined in the Fraser River by over 97% in the past 10 years, and are at historically low levels in other British Columbia rivers in the DPS, and nearly so in the Columbia River. Major threats to southern eulachon include climate change impacts on ocean and freshwater habitat, by‐catch in offshore shrimp trawl fisheries, changes in downstream flow timing and intensity owing to dams and water diversions, and predation. These threats, together with large declines in abundance, indicate that the southern DPS of eulachon is at moderate risk of extinction throughout all of its range. The southern DPS was listed as threatened under the ESA in May 2010 – the first marine forage fish to be afforded these statutory protections, which apply only to waters under U.S. jurisdiction.

A cable theory based biophysical model of resistance change in crab peripheral nerve and human cerebral cortex during neuronal depolarisation: implications for electrical impedance tomography of fast neural activity in the brain - Adam Liston; Richard Bayford; David Holder (Medical & Biological Engineering & Computing, 2012)

Climate change projections and stratosphere–troposphere interaction - Adam A. Scaife; Thomas Spangehl; David R. Fereday; Ulrich Cubasch; Ulrike Langematz; Hideharu Akiyoshi; Slimane Bekki; Peter Braesicke; Neal Butchart; Martyn P. Chipperfield; Andrew Gettelman; Steven C. Hardiman; et al. (Climate Dynamics, 2012)

Priorities in policy and management when existing biodiversity stressors interact with climate-change - Don A. Driscoll; Adam Felton; Philip Gibbons; Annika M. Felton; Nicola T. Munro; David B. Lindenmayer (Climatic Change, 2012)

Levels of novel hybridization in the saltcedar invasion compared over seven decades - John F. Gaskin; Adam S. Birken; David J. Cooper (Biological Invasions, 2012)

Volcanic Eruptions in the Deep Sea - Kenneth Rubin; S. Adam Soule; William Chadwick; Daniel Fornari; David Clague; Robert Embley; Edward Baker; Michael Perfit; David Caress; Robert Dziak (Oceanography, 2012)

Sequencing wheat chromosome arm 7BS delimits the 7BS/4AL translocation and reveals homoeologous gene conservation - Paul J. Berkman; Adam Skarshewski; Sahana Manoli; Michał T. Lorenc; Jiri Stiller; Lars Smits; Kaitao Lai; Emma Campbell; Marie Kubaláková; Hana Šimková; Jacqueline Batley; Jaroslav Doležel; et al. (Theoretical and Applied Genetics, 2012)

Characterization of land-based sources of pollution in Jobos Bay, Puerto Rico: status of heavy metal concentration in bed sediment - Dennis A. Apeti; David R. Whitall; Anthony S. Pait; Angel Dieppa; Adam G. Zitello; Gunnar G. Lauenstein (Environmental Monitoring and Assessment, 2012)

Effects of elevated atmospheric [ CO 2 ] on instantaneous transpiration efficiency at leaf and canopy scales in E ucalyptus saligna - Craig V.M. Barton; Remko A. Duursma; Belinda E. Medlyn; David S. Ellsworth; Derek Eamus; David T. Tissue; Mark A. Adams; Jann Conroy; Kristine Y. Crous; Marion Liberloo; Markus Löw; Sune Linder; et al. (Global Change Biology, 2012)
Rising atmospheric concentrations of CO 2 ( C a ) can reduce stomatal conductance and transpiration rate in trees, but the magnitude of this effect varies considerably among experiments. The theory of optimal stomatal behaviour predicts that the ratio of photosynthesis to transpiration (instantaneous transpiration efficiency, ITE ) should increase in proportion to C a . We hypothesized that plants regulate stomatal conductance optimally in response to rising C a . We tested this hypothesis with data from young Eucalyptus saligna Sm. trees grown in 12 climate‐controlled whole‐tree chambers for 2 years at ambient and elevated C a . Elevated C a was ambient + 240 ppm, 60% higher than ambient C a . Leaf‐scale gas exchange was measured throughout the second year of the study and leaf‐scale ITE increased by 60% under elevated C a , as predicted. Values of leaf‐scale ITE depended strongly on vapour pressure deficit ( D ) in both CO 2 treatments. Whole‐canopy CO 2 and H 2 O fluxes were also monitored continuously for each chamber throughout the second year. There were small differences in D between C a treatments, which had important effects on values of canopy‐scale ITE . However, when C a treatments were compared at the same D , canopy‐scale ITE was consistently increased by 60%, again as predicted. Importantly, leaf and canopy‐scale ITE were not significantly different, indicating that ITE was not scale‐dependent. Observed changes in transpiration rate could be explained on the basis that ITE increased in proportion to C a . The effect of elevated C a on photosynthesis increased with rising D . At high D , C a had a large effect on photosynthesis and a small effect on transpiration rate. At low D , in contrast, there was a small effect of C a on photosynthesis, but a much larger effect on transpiration rate. If shown to be a general response, the proportionality of ITE with C a will allow us to predict the effects of C a on transpiration rate.

Impulsive behaviour induced by both NMDA receptor antagonism and GABAA receptor activation in rat ventromedial prefrontal cortex - Emily R. Murphy; Anushka B. P. Fernando; Gonzalo P. Urcelay; Emma S. J. Robinson; Adam C. Mar; David E. H. Theobald; Jeffrey W. Dalley; Trevor W. Robbins (Psychopharmacology, 2012)

Foraging segregation and genetic divergence between geographically proximate colonies of a highly mobile seabird - Anne E. Wiley; Andreanna J. Welch; Peggy H. Ostrom; Helen F. James; Craig A. Stricker; Robert C. Fleischer; Hasand Gandhi; Josh Adams; David G. Ainley; Fern Duvall; Nick Holmes; Darcy Hu; et al. (Oecologia, 2012)

Female preference for male lateral projection area in Poecilia reticulata - Ronald David MacLaren; Adam Fontaine (Environmental Biology of Fishes, 2012)

Presence of Arundinaria gigantea (river cane) on numerous non-wetland sites suggests improper ecological classification of the species - Benjamin R. Tanner; David A. Kinner; Adam D. Griffith; Robert S. Young; Lee M. Sorrell (Wetlands Ecology and Management, 2011)

Investigation of amygdala volume in men with the fragile X premutation - Diana Selmeczy; Kami Koldewyn; John M. Wang; Aaron Lee; Danielle Harvey; David R. Hessl; Flora Tassone; Patrick Adams; Randi J. Hagerman; Paul J. Hagerman; Susan M. Rivera (Brain Imaging and Behavior, 2011)

Forest Management, Engineering, and Operations / Global Competency and Issues in Contemporary Education - Finto Antony; Lewis Jordan; Laurie Schimleck; Richard Daniels; Rapeepan Kantavichai; Lara Hansen; Jessica Hitt; William Hubbard; Gwendolyn Boyd; Ryan Boyles; Heather Dinon; Joshua Idassi; et al. (Journal of Forestry, 2011)
31Maps depicting spatial variation in wood properties are important for forest product industries as they aid decision making regarding raw material procurement, can assist in product categorization and help improve utilization. Loblolly pine is an important commercial species grown throughout the southern Unites States of America (USA). Wood Quality Consortium (WQC)—a joint collaboration between the University of Georgia, USDA Forest Service and industries—was established in 1999 with the objective of characterizing wood property variation of plantation grown loblolly pine. Data on wood specific gravity (SG), modulus of elasticity (MOE) and modulus of rupture (MOR) collected by the WQC was utilized in this study. Maps showing spatial variation in SG at different stand ages and SG, MOE and MOR at different heights within a tree were developed using appropriate spatial prediction methods (kriging). The geographical variation of these wood properties across southeastern USA was demonstrated here.

Human Dimensions - Bob Tjaden; Marissa Jo Daniel; Francisco Aguilar; Hank Stelzer; Timothy Gallaher; John Kushla; James Henderson; Andrew Londo; Melissa Kreye; Damian Adams; Tatiana Borisova; Francisco Escobedo; et al. (Journal of Forestry, 2011)
12The University of MD Extension (UME) has been very effective in teaching forest landowners concepts and principles of forest management through seminars, workshops and field days. After evaluating these techniques and recognizing people learn differently, new delivery methods were developed. UME developed a landowner based forestry correspondence course in two formats, first a traditional paper then a web based version. These were developed to support the range of ages, learning styles, high-speed internet availability and computer knowledge. Both versions lead the learner through the components of a forest stewardship plan. Upon course completion, the student has the framework of a forest stewardship plan in a format acceptable for State Forester approval. This has helped the State Forester meet forest stewardship plan goals during a significant decline of personnel who normally assist forest landowners. The courses have also helped forest landowners meet the NRCS requirements of having a plan in order to qualify for certain federal cost share programs. We are constantly adapting the courses based on course evaluations, new issues and programs, and innovative forest management techniques. Evaluations are performed upon the completion of the course to assist in measuring overall course effectiveness, student success, plan objectives and any enhancements necessary to improve the course. There is also a follow-up evaluation performed five years after completion to evaluate plan implementation, behavioral changes, knowledge maintained, acres impacted, financial impacts, and direct contacts of the students. Data from all evaluations will be presented in the poster as well as lesson learned.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Salmonid biomass and habitat relationships for small lakes - David Cote; Blair K. Adams; Keith D. Clarke; Mervin Langdon (Environmental Biology of Fishes, 2011)

Maintenance of C sinks sustains enhanced C assimilation during long-term exposure to elevated [CO2] in Mojave Desert shrubs - Iker Aranjuelo; Allison L. Ebbets; R. Dave Evans; David T. Tissue; Salvador Nogués; Natasja van Gestel; Paxton Payton; Volker Ebbert; Williams W. Adams III; Robert S. Nowak; Stanley D. Smith (Oecologia, 2011)

Pre-clinical characterization of CX-4945, a potent and selective small molecule inhibitor of CK2 for the treatment of cancer - Fabrice Pierre; Peter C. Chua; Sean E. O’Brien; Adam Siddiqui-Jain; Pauline Bourbon; Mustapha Haddach; Jerome Michaux; Johnny Nagasawa; Michael K. Schwaebe; Eric Stefan; Anne Vialettes; Jeffrey P. Whitten; et al. (Molecular and Cellular Biochemistry, 2011)

Sex-specific effect of aging on submaximal leg exercise hemodynamics in middle-aged and older adults - Beth Parker; Jeffrey Capizzi; Amanda Augeri; Adam Grimaldi; David Proctor; Paul Thompson (European Journal of Applied Physiology, 2011)

Mechanical, Compositional, and Structural Properties of the Post-natal Mouse Achilles Tendon - Heather L. Ansorge; Sheila Adams; David E. Birk; Louis J. Soslowsky (Annals of Biomedical Engineering, 2011)

High impulsivity predicting vulnerability to cocaine addiction in rats: some relationship with novelty preference but not novelty reactivity, anxiety or stress - Anna C. Molander; Adam Mar; Agnes Norbury; Sarah Steventon; Margarita Moreno; Daniele Caprioli; David E. H. Theobald; David Belin; Barry J. Everitt; Trevor W. Robbins; Jeffrey W. Dalley (Psychopharmacology, 2011)

A structurally diversified linker enhances the immune response to a small carbohydrate hapten - Tomasz Lipinski; Thanh Luu; Pavel I. Kitov; Adam Szpacenko; David R. Bundle (Glycoconjugate Journal, 2011)

An improved curvilinear gradient method for parameter optimization in complex biological models - David Szekely; Jamie I. Vandenberg; Socrates Dokos; Adam P. Hill (Medical & Biological Engineering & Computing, 2011)

Field maple and hornbeam populations along a 4-m elevation gradient in an alluvial forest - David Janik; Dušan Adam; Tomáš Vrška; Libor Hort; Pavel Unar; Kamil Král; Pavel Šamonil; David Horal (European Journal of Forest Research, 2011)

Bioenergetic Constraints on Primate Abundance - David A. Raichlen; Adam D. Gordon; Wes Sechrest (International Journal of Primatology, 2011)

Development of co-selected single nucleotide polymorphisms in the viral promoter precedes the onset of human immunodeficiency virus type 1-associated neurocognitive impairment - Luna Li; Benjamas Aiamkitsumrit; Vanessa Pirrone; Michael R. Nonnemacher; Adam Wojno; Shendra Passic; Katherine Flaig; Evelyn Kilareski; Brandon Blakey; Jade Ku; Nirzari Parikh; Rushabh Shah; et al. (Journal of NeuroVirology, 2011)

A biomarker of mercury body-burden correlated with diagnostic domain specific clinical symptoms of autism spectrum disorder - Janet K. Kern; David A. Geier; James B. Adams; Mark R. Geier (BioMetals, 2010)

Estimating the Value of Non‐Use Benefits from Small Changes in the Provision of Ecosystem Services - ADAM DUTTON; GARETH EDWARDS‐JONES; DAVID W. MACDONALD (Conservation Biology, 2010)
The unit of trade in ecosystem services is usually the use of a proportion of the parcels of land associated with a given service. Valuing small changes in the provision of an ecosystem service presents obstacles, particularly when the service provides non‐use benefits, as is the case with conservation of most plants and animals. Quantifying non‐use values requires stated‐preference valuations. Stated‐preference valuations can provide estimates of the public's willingness to pay for a broad conservation goal. Nevertheless, stated‐preference valuations can be expensive and do not produce consistent measures for varying levels of provision of a service. Additionally, the unit of trade, land use, is not always linearly related to the level of ecosystem services the land might provide. To overcome these obstacles, we developed a method to estimate the value of a marginal change in the provision of a non‐use ecosystem service—in this case conservation of plants or animals associated with a given land‐cover type. Our method serves as a tool for calculating transferable valuations of small changes in the provision of ecosystem services relative to the existing provision. Valuation is achieved through stated‐preference investigations, calculation of a unit value for a parcel of land, and the weighting of this parcel by its ability to provide the desired ecosystem service and its effect on the ability of the surrounding land parcels to provide the desired service. We used the water vole ( Arvicola terrestris ) as a case study to illustrate the method. The average present value of a meter of water vole habitat was estimated at UK£12, but the marginal value of a meter (based on our methods) could range between £0 and £40 or more .

Role of a cdk5-associated protein, p35, in herpes simplex virus type 1 replication in vivo - Steve D Haenchen; Jeff A Utter; Adam M Bayless; Rick T Dobrowsky; David J Davido (Journal of NeuroVirology, 2010)

Hydrogen peroxide‐induced oxidative stress responses in Desulfovibrio vulgaris Hildenborough - Aifen Zhou; Zhili He; Alyssa M. Redding‐Johanson; Aindrila Mukhopadhyay; Christopher L. Hemme; Marcin P. Joachimiak; Feng Luo; Ye Deng; Kelly S. Bender; Qiang He; Jay D. Keasling; David A. Stahl; et al. (Environmental Microbiology, 2010)
Summary To understand how sulphate‐reducing bacteria respond to oxidative stresses, the responses of Desulfovibrio vulgaris Hildenborough to H 2 O 2 ‐induced stresses were investigated with transcriptomic, proteomic and genetic approaches. H 2 O 2 and induced chemical species (e.g. polysulfide, ROS) and redox potential shift increased the expressions of the genes involved in detoxification, thioredoxin‐dependent reduction system, protein and DNA repair, and decreased those involved in sulfate reduction, lactate oxidation and protein synthesis. A gene coexpression network analysis revealed complicated network interactions among differentially expressed genes, and suggested possible importance of several hypothetical genes in H 2 O 2 stress. Also, most of the genes in PerR and Fur regulons were highly induced, and the abundance of a Fur regulon protein increased. Mutant analysis suggested that PerR and Fur are functionally overlapped in response to stresses induced by H 2 O 2 and reaction products, and the upregulation of thioredoxin‐dependent reduction genes was independent of PerR or Fur. It appears that induction of those stress response genes could contribute to the increased resistance of deletion mutants to H 2 O 2 ‐induced stresses. In addition, a conceptual cellular model of D. vulgaris responses to H 2 O 2 stress was constructed to illustrate that this bacterium may employ a complicated molecular mechanism to defend against the H 2 O 2 ‐induced stresses.

The Effectiveness of Surrogate Taxa for the Representation of Biodiversity - ADAM S. LEWANDOWSKI; REED F. NOSS; DAVID R. PARSONS (Conservation Biology, 2010)
Biodiversity is too complex to measure directly, so conservation planning must rely on surrogates to estimate the biodiversity of sites. The species richness of selected taxa is often used as a surrogate for the richness of other taxa. Surrogacy values of taxa have been evaluated in diverse contexts, yet broad trends in their effectiveness remain unclear. We reviewed published studies testing the ability of species richness of surrogate taxa to capture the richness of other (target) taxa. We stratified studies into two groups based on whether a complementarity approach (surrogates used to select a combination of sites that together maximize total species richness for the taxon) or a richness‐hotspot approach (surrogates used to select sites containing the highest species richness for the taxon) was used. For each comparison of one surrogate taxon with one target, we used the following predictor variables: biome, spatial extent of study area, surrogate taxon, and target taxon. We developed a binary response variable based on whether the surrogate taxon provided better than random representation of the target taxon. For studies that used an evaluation approach that was not based on better than random representation of target taxa, we based the response variable on the interpretation of results in the original study. We performed a categorical regression to elucidate trends in the effectiveness of surrogate taxa with regard to each of the predictor variables. A surrogate was 25% more likely to be effective with a complementarity approach than with a hotspot approach. For hotspot‐based approaches, biome, extent of study, surrogate taxon, and target taxon significantly influenced effectiveness of the surrogate. For complementarity‐based approaches, biome, extent, and surrogate taxon significantly influenced effectiveness of the surrogate. For all surrogate evaluations, biome explained the greatest amount of variation in surrogate effectiveness. From most to least, extent, surrogate taxon, and target taxon explained the most variation after biome. Surrogate taxa were most effective in grasslands and in some cases boreal zones, deserts, and tropical forests; surrogate taxa also were more effective in studies examining larger areas. Herpetofauna were the most effective taxon as both surrogate and target when a richness‐hotspot approach was used; however, herpetofauna were analyzed in fewer studies, so this result is tentative. For complementarity approaches, taxa that are easy to measure and tend to have a large number of habitat specialists distributed collectively across broad environmental gradients (e.g., plants, birds, and mammals) were the most effective surrogates.

A Metabolomic Approach to Identifying Chemical Mediators of Mammal–Plant Interactions - David J. Tucker; Ian Robert Wallis; Jessica M. Bolton; Karen J. Marsh; Adam A. Rosser; Ian M. Brereton; Dean Nicolle; William J. Foley (Journal of Chemical Ecology, 2010)

Baseline, diurnal variations, and stress-induced changes of stress hormones in three captive beluga, Delphinapterus leucas - Todd L. Schmitt; David J. St. Aubin; Adam M. Schaefer; J. Lawrence Dunn (Marine Mammal Science, 2010)

Cryptic diversity within the invasive virile crayfish Orconectes virilis (Hagen, 1870) species complex: new lineages recorded in both native and introduced ranges - Lenka Filipová; David M. Holdich; Jérôme Lesobre; Frédéric Grandjean; Adam Petrusek (Biological Invasions, 2010)

The distribution and host range of the pandemic disease chytridiomycosis in Australia, spanning surveys from 1956–2007 - Kris Murray; Richard Retallick; Keith R. McDonald; Diana Mendez; Ken Aplin; Peter Kirkpatrick; Lee Berger; David Hunter; Harry B. Hines; R. Campbell; Matthew Pauza; Michael Driessen; et al. (Ecology, 2010)
Chytridiomycosis is the worst disease to affect vertebrate biodiversity on record. In Australia, it is thought to have caused the extinction of four frog species, and it threatens the survival of at least 10 more. We report the current distribution and host range of this invasive disease in Australia, which is essential knowledge for conservation management. We envisage that the data be used in a global and national context for predictive modeling, meta‐analyses, and risk assessment. Our continent‐wide data set comprises 821 sites in Australia and includes 10 183 records from >80 contributors spanning collection dates from 1956 to 2007. Sick and dead frogs from the field and apparently healthy frogs from museum collections were tested opportunistically for the presence of Batrachochytrium dendrobatidis , the fungal pathogen causing chytridiomycosis, and apparently healthy frogs and tadpoles found during surveys were tested purposively. The diagnostic tests used were histology of skin samples and quantitative PCR of skin swabs. Chytridiomycosis was found in all Australian states and the Australian Capital Territory, but not in the Northern Territory. Currently it appears to be confined to the relatively cool and wet areas of Australia, such as along the Great Dividing Range and adjacent coastal areas in the eastern mainland states of Queensland, New South Wales, and Victoria, eastern and central Tasmania, southern South Australia, and southwestern Western Australia. Batrachochytrium dendrobatidis may have been introduced into Australia via the port of Brisbane around 1978 and spread northward and southward. It did not appear to arrive in Western Australia until 1985. The earliest records from South Australia and Tasmania are from 1995 and 2004, respectively, although archival studies from these states are lacking. We also report negative findings showing that the disease does not currently occur in some areas that appear to be environmentally suitable, including Cape York Peninsula in Queensland and most of the World Heritage Area in western Tasmania. Infection with B. dendrobatidis has been recorded from 63 frog species in Australia to date, all belonging to the Hylidae, Limnodynastidae, and Myobatrachidae, with the exception of one individual of a species from the Microhylidae and the introduced cane toad of the family Bufonidae. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Population synchrony of a native fish across three Laurentian Great Lakes: evaluating the effects of dispersal and climate - David B. Bunnell; Jean V. Adams; Owen T. Gorman; Charles P. Madenjian; Stephen C. Riley; Edward F. Roseman; Jeffrey S. Schaeffer (Oecologia, 2010)

Modeling and monitoring of mine water rebound in an abandoned coal mine complex: Siersza Mine, Upper Silesian Coal Basin, Poland - David Banks; Adam Frolik; Grzegorz Gzyl; Marek Rogoż (Hydrogeology Journal, 2010)

Causes and significance of variation in mammalian basal metabolism - David A. Raichlen; Adam D. Gordon; Magdalena N. Muchlinski; J. Josh Snodgrass (Journal of Comparative Physiology B, 2010)

Nutrition and interference competition have interactive effects on the behavior and performance of Argentine ants - Adam D. Kay; Taylor Zumbusch; Justa L. Heinen; Tom C. Marsh; David A. Holway (Ecology, 2010)
Food availability often influences competitive outcomes through effects on consumer growth. Although it has received less attention, food availability may also affect competition through nutritional effects on behavior. One hypothesis linking nutrition and competition in ants posits that increased access to carbohydrates favors greater investment in worker traits that underlie behavioral dominance. We tested this hypothesis by varying dietary protein : carbohydrate (P:C) ratios and levels of interspecific interference for Argentine ants ( Linepithema humile ), a widespread invasive species. As predicted, colonies facing interference increased patrolling more when reared on low P:C diets; this result is the first demonstration of an interactive effect of nutrition and interference on ant colonies. Several results suggest that this dietary effect on patrolling was due primarily to changes in colony size rather than worker behavior. Colonies on lower P:C diets had lower worker mortality and larger final colony sizes. Diet had little effect on per capita patrolling, and worker behavior in performance assays depended more on previous exposure to interference than on diet. Our findings indicate that dietary P:C ratios can influence Argentine ant performance in a competitive environment and suggest a mechanism by which monopolization of carbohydrate‐rich resources can help invasive ants displace native ant competitors.

Gum Arabic-Coated Magnetic Nanoparticles for Potential Application in Simultaneous Magnetic Targeting and Tumor Imaging - Lei Zhang; Faquan Yu; Adam J. Cole; Beata Chertok; Allan E. David; Jingkang Wang; Victor C. Yang (The AAPS Journal, 2009)

Role of epithelial-to-mesenchymal transition (EMT) in drug sensitivity and metastasis in bladder cancer - David J. McConkey; Woonyoung Choi; Lauren Marquis; Frances Martin; Michael B. Williams; Jay Shah; Robert Svatek; Aditi Das; Liana Adam; Ashish Kamat; Arlene Siefker-Radtke; Colin Dinney (Cancer and Metastasis Reviews, 2009)

Nutritional Ecology of Ateles chamek in lowland Bolivia: How Macronutrient Balancing Influences Food Choices - Annika M. Felton; Adam Felton; Jeff T. Wood; William J. Foley; David Raubenheimer; Ian R. Wallis; David B. Lindenmayer (International Journal of Primatology, 2009)

Contribution of mobile genetic elements to Desulfovibrio vulgaris genome plasticity - Christopher B. Walker; Sergey Stolyar; Dylan Chivian; Nicolas Pinel; Jeffrey A. Gabster; Paramvir S. Dehal; Zhili He; Zamin Koo Yang; Huei‐Che B. Yen; Jizhong Zhou; Judy D. Wall; Terry C. Hazen; et al. (Environmental Microbiology, 2009)
Summary The genome of Desulfovibrio vulgaris strain DePue, a sulfate‐reducing Deltaproteobacterium isolated from heavy metal‐impacted lake sediment, was completely sequenced and compared with the type strain D. vulgaris Hildenborough. The two genomes share a high degree of relatedness and synteny, but harbour distinct prophage and signatures of past phage encounters. In addition to a highly variable phage contribution, the genome of strain DePue contains a cluster of open‐reading frames not found in strain Hildenborough coding for the production and export of a capsule exopolysaccharide, possibly of relevance to heavy metal resistance. Comparative whole‐genome microarray analysis on four additional D. vulgaris strains established greater interstrain variation within regions associated with phage insertion and exopolysaccharide biosynthesis.

Re‐examination of a proposed case of stasipatric speciation: phylogeography of the Australian morabine grasshoppers ( Vandiemenella viatica species group) - TAKESHI KAWAKAMI; ROGER K. BUTLIN; MARK ADAMS; KATHLEEN M. SAINT; DAVID J. PAULL; STEVEN J. B. COOPER (Molecular Ecology, 2009)
Karyotypic differences have been used for delimiting populations or species, although whether these mutations provide strong barriers to gene flow between populations and promote speciation remains contentious. In this study, we assessed whether 11 chromosomal races of Australian morabine grasshoppers ( Vandiemenella viatica species group) represent genetically distinct populations by analyses of cytological and allozyme (35 loci) data and DNA sequences of the elongation factor‐1 alpha ( EF ‐1α), anonymous Mvia11 , and mitochondrial cytochrome c oxidase subunit I ( COI ) loci. While the Vandiemenella chromosomal taxa generally represent genetically distinct units, a substantial portion of the total genetic variation in our samples was not explained by the chromosomal variation. Mantel tests indicated that Vandiemenella populations were spatially structured and have maintained gene flow at a local scale within each of the taxa. The group was subdivided into 13 genetic clusters; four chromosomal taxa comprised single exclusive clusters, while others comprised more than one cluster or clusters shared with other taxa. Boundaries of these cryptic population subdivisions correspond with several biogeographical barriers, such as straits, gulfs, the Murray River, and an ancient mega‐lake, Lake Bungunnia. The viatica species group was previously proposed to have diversified without major geographical separation based on the stasipatric speciation model; however, the present study suggests the involvement of allopatric fragmentation. Given extensive nonmonophyly of chromosomal taxa and incomplete barriers to gene flow among taxa, all Vandiemenella chromosomal taxa and genetically distinct populations within chromosomal taxa, except Vandiemenella pichirichi , should be regarded as populations of one species: Vandiemenella viatica .

Biodiversity scales from plots to biomes with a universal species–area curve - John Harte; Adam B. Smith; David Storch (Ecology Letters, 2009)
Classic theory predicts species richness scales as the quarter‐power of area, yet species–area relationships (SAR) vary widely depending on habitat, taxa, and scale range. Because power‐law SAR are used to predict species loss under habitat loss, and to scale species richness from plots to biomes, insight into the wide variety of observed SAR and the conditions under which power‐law behavior should be observed is needed. Here we derive from the maximum entropy principle, a new procedure for upscaling species richness data from small census plots to larger areas, and test empirically, using multiple data sets, the prediction that up to an overall scale displacement, nested SAR lie along a universal curve, with average abundance per species at each scale determining the local slope of the curve. Power‐law behaviour only arises in the limit of increasing average abundance, and in that limit, the slope approaches zero, not ¼. An extrapolation of tree species richness in the Western Ghats to biome scale (60 000 km 2 ) using only census data at plot scale (¼ ha) is presented to illustrate the potential for applications of our theory.

Plant water parameters and the remote sensing R 1300/R 1450 leaf water index: controlled condition dynamics during the development of water deficit stress - Hans-Dieter Seelig; Alexander Hoehn; Louis S. Stodieck; David M. Klaus; William W. Adams; William J. Emery (Irrigation Science, 2009)

Climate change, conservation and management: an assessment of the peer-reviewed scientific journal literature - Adam Felton; Joern Fischer; David B. Lindenmayer; Rebecca Montague-Drake; Arianne R. Lowe; Debbie Saunders; Annika M. Felton; Will Steffen; Nicola T. Munro; Kara Youngentob; Jake Gillen; Phil Gibbons; et al. (Biodiversity and Conservation, 2009)

Invasive species cause large-scale loss of native California oyster habitat by disrupting trophic cascades - David L. Kimbro; Edwin D. Grosholz; Adam J. Baukus; Nicholas J. Nesbitt; Nicole M. Travis; Sarikka Attoe; Caitlin Coleman-Hulbert (Oecologia, 2009)

Next-generation sequencing of vertebrate experimental organisms - Daniel J. Turner; Thomas M. Keane; Ian Sudbery; David J. Adams (Mammalian Genome, 2009)

Indoor/ambient residential air toxics results in rural western Montana - Tony J. Ward; Heidi Underberg; David Jones; Raymond F. Hamilton; Earle Adams (Environmental Monitoring and Assessment, 2009)

Accumulation of an organic anticancer selenium compound in a transgenic Solanaceous species shows wider applicability of the selenocysteine methyltransferase transgene from selenium hyperaccumulators - Marian J. McKenzie; Donald A. Hunter; Ranjith Pathirana; Lyn M. Watson; Nigel I. Joyce; Adam J. Matich; Daryl D. Rowan; David A. Brummell (Transgenic Research, 2009)

Historical trends affecting accumulation of sediment and phosphorus in Lake Pepin, upper Mississippi River, USA - David J. Mulla; Adam C. Sekely (Journal of Paleolimnology, 2009)

Soil aggregation and carbon sequestration are tightly correlated with the abundance of arbuscular mycorrhizal fungi: results from long‐term field experiments - Gail W. T. Wilson; Charles W. Rice; Matthias C. Rillig; Adam Springer; David C. Hartnett (Ecology Letters, 2009)
We examined the role of arbuscular mycorrhizal fungi (AMF) in ecosystems using soil aggregate stability and C and N storage as representative ecosystem processes. We utilized a wide gradient in AMF abundance, obtained through long‐term (17 and 6 years) large‐scale field manipulations. Burning and N‐fertilization increased soil AMF hyphae, glomalin‐related soil protein (GRSP) pools and water‐stable macroaggregates while fungicide applications reduced AMF hyphae, GRSP and water‐stable macroaggregates. We found that AMF abundance was a surprisingly dominant factor explaining the vast majority of variability in soil aggregation. This experimental field study, involving long‐term diverse management practices of native multispecies prairie communities, invariably showed a close positive correlation between AMF hyphal abundance and soil aggregation, and C and N sequestration. This highly significant linear correlation suggests there are serious consequences to the loss of AMF from ecosystems.

Growth and reproduction in the Antarctic brooding bivalve Adacnarca nitens (Philobryidae) from the Ross Sea - Nicholas D. Higgs; Adam J. Reed; Rachel Hooke; David J. Honey; Olaf Heilmayer; Sven Thatje (Marine Biology, 2009)

Evolution of the Metazoan-Specific Importin α Gene Family - D. Adam Mason; Deborah E. Stage; David S. Goldfarb (Journal of Molecular Evolution, 2009)

Historic magmatism on the Reykjanes Peninsula, Iceland: a snap-shot of melt generation at a ridge segment - David W. Peate; Joel A. Baker; Sveinn P. Jakobsson; Tod E. Waight; Adam J. R. Kent; Nathalie V. Grassineau; Anna Cecile Skovgaard (Contributions to Mineralogy and Petrology, 2009)

Rejoinder to: Influence of river discharge in the tropical and subtropical North Atlantic Ocean - Antonio Tovar-Sanchez; Carlos M. Duarte; Adam B. Kustka; Susana Agustí; Jordi Dachs; David A. Hutchins; Douglas G. Capone; Sergio A. Sañudo-Wilhelmy (Limnology and Oceanography, 2009)

Landscape fluidity – a unifying perspective for understanding and adapting to global change - Adrian D. Manning; Joern Fischer; Adam Felton; Barry Newell; Will Steffen; David B. Lindenmayer (Journal of Biogeography, 2009)
Rapid, human‐induced global change presents major challenges to researchers, policy‐makers and land managers. Addressing these challenges requires an appreciation of the dynamics of ecological systems. Here, we propose ‘landscape fluidity’ as a perspective and research agenda from which to consider landscapes in the process of changing rapidly through both time and space. We define landscape fluidity as the ebb and flow of different organisms within a landscape through time. A range of existing ideas, themes and practical approaches are relevant to landscape fluidity, and we use a case study of scattered tree landscapes in south‐eastern Australia to illustrate the benefits of a landscape fluidity perspective. We suggest that a focus on landscape fluidity can bring a renewed emphasis on change in landscapes and so help unify a range of currently separate research themes in biogeography, ecology, palaeoecology and conservation biology.

A Mass Balance Mercury Budget for a Mine-Dominated Lake: Clear Lake, California - Thomas H. Suchanek; Janis Cooke; Kaylene Keller; Salvador Jorgensen; Peter J. Richerson; Collin A. Eagles-Smith; E. James Harner; David P. Adam (Water, Air, & Soil Pollution, 2009)

Directed dispersal of mistletoe (Plicosepalus acaciae) by Yellow-vented Bulbuls (Pycnonotus xanthopygos) - Adam K. Green; David Ward; Megan E. Griffiths (Journal of Ornithology, 2009)

Evolutionary constraints on regional faunas: whom, but not how many - Adam C. Algar; Jeremy T. Kerr; David J. Currie (Ecology Letters, 2009)
The latitudinal diversity gradient has been hypothesized to reflect past evolutionary dynamics driven by climatic niche conservation during cladogenesis, i.e. the tropical conservatism hypothesis. Here we show that the species diversity of treefrogs (Hylidae) across the western hemisphere is actually independent of evolutionary niche dynamics. We evaluated three key predictions of the tropical conservatism hypothesis that relate to the relationships between climate, species richness and the phylogenetic structure of regional treefrog faunas across the continental Americas. Species composition was dependent on the inability of some lineages to evolve cold tolerance, but the actual number of species in a region was strongly predicted by precipitation, not temperature. Moreover, phylogenetic structure was independent of precipitation. Thus, species in low‐richness areas were no more closely related than species in highly diverse regions. These results provide no support for the tropical conservatism hypothesis. Instead, they show that regional species composition and richness are constrained by different climatic components, demonstrating that global biodiversity gradients can be independent of niche stasis during cladogenesis.

Ataxia and pancytopenia caused by a mutation in TINF2 - Elena Tsangaris; Sally-Lin Adams; Grace Yoon; David Chitayat; Peter Lansdorp; Inderjeet Dokal; Yigal Dror (Human Genetics, 2008)

Divergence and Polymorphism Under the Nearly Neutral Theory of Molecular Evolution - John J. Welch; Adam Eyre-Walker; David Waxman (Journal of Molecular Evolution, 2008)

Integration of Wireless Sensor Networks into Cyberinfrastructure for Monitoring Hawaiian “Mountain-to-Sea” Environments - Michael H. Kido; Carsten W. Mundt; Kevin N. Montgomery; Adam Asquith; David W. Goodale; Kenneth Y. Kaneshiro (Environmental Management, 2008)

Regional White Matter Signal Abnormalities and Cognitive Correlates Among Geriatric Patients with Treated Cardiovascular Disease - David F. Tate; Angela L. Jefferson; Adam M. Brickman; Karin F. Hoth; John Gunstad; Kathryn Bramley; Robert H. Paul; Athena Poppas; Ronald A. Cohen (Brain Imaging and Behavior, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Extraneous variables and their influence on reflectance-based measurements of leaf water content - Hans-Dieter Seelig; William W. Adams; Alexander Hoehn; Louis S. Stodieck; David M. Klaus; William J. Emery (Irrigation Science, 2008)

Tree layer dynamics of the Cahnov–Soutok near-natural floodplain forest after 33 years (1973–2006) - David Janik; Dusan Adam; Tomas Vrska; Libor Hort; Pavel Unar; Kamil Kral; Pavel Samonil; David Horal (European Journal of Forest Research, 2008)

Reduced Hippocampal Activation During Recall is Associated with Elevated FMR1 mRNA and Psychiatric Symptoms in Men with the Fragile X Premutation - Kami Koldewyn; David Hessl; John Adams; Flora Tassone; Paul J. Hagerman; Randi J. Hagerman; Susan M. Rivera (Brain Imaging and Behavior, 2008)

Diet and Feeding Ecology of Ateles chamek in a Bolivian Semihumid Forest: The Importance of Ficus as a Staple Food Resource - Annika M. Felton; Adam Felton; Jeff T. Wood; David B. Lindenmayer (International Journal of Primatology, 2008)

Effects of acute tyrosine/phenylalanine depletion on the selective processing of smoking-related cues and the relative value of cigarettes in smokers - Brian Hitsman; James MacKillop; Anne Lingford-Hughes; Tim M. Williams; Faheem Ahmad; Sally Adams; David J. Nutt; Marcus R. Munafò (Psychopharmacology, 2008)

Integration of Mouse Phenome Data Resources - John M. Hancock; Niels C. Adams; Vassilis Aidinis; Andrew Blake; Judith A. Blake; Molly Bogue; Steve D. M. Brown; Elissa J. Chesler; Duncan Davidson; Christopher Duran; Janan T. Eppig; Valérie Gailus-Durner; et al. (Mammalian Genome, 2008)

The CXCR4-SDF1α axis is a critical mediator of rhabdomyosarcoma metastatic signaling induced by bone marrow stroma - Brigitte Strahm; Adam D. Durbin; Elizabeth Sexsmith; David Malkin (Clinical & Experimental Metastasis, 2008)

Effect of a Rugulosin-producing Endophyte in Picea glauca on Choristoneura fumiferana - J. David Miller; Mark W. Sumarah; Gregory W. Adams (Journal of Chemical Ecology, 2008)

Surface plasmon resonance imaging for real-time, label-free analysis of protein interactions with carbohydrate microarrays - Rositsa Karamanska; Jonathan Clarke; Ola Blixt; James I. MacRae; Jiquan Q. Zhang; Paul R. Crocker; Nicolas Laurent; Adam Wright; Sabine L. Flitsch; David A. Russell; Robert A. Field (Glycoconjugate Journal, 2008)

Marine invasive species: validation of citizen science and implications for national monitoring networks - David G. Delaney; Corinne D. Sperling; Christiaan S. Adams; Brian Leung (Biological Invasions, 2008)

Product quality research institute evaluation of cascade impactor profiles of pharmaceutical aerosols, part 3: Final report on a statistical procedure for determining equivalence - David Christopher; Wallace Adams; Anthony Amann; Craig Bertha; Peter R. Byron; William Doub; Craig Dunbar; Walter Hauck; Svetlana Lyapustina; Jolyon Mitchell; Beth Morgan; Steve Nichols; et al. (AAPS PharmSciTech, 2007)

The polymorphism architecture of mouse genetic resources elucidated using genome-wide resequencing data: implications for QTL discovery and systems genetics - Adam Roberts; Fernando Pardo-Manuel de Villena; Wei Wang; Leonard McMillan; David W. Threadgill (Mammalian Genome, 2007)

Vascularized composite islet-kidney transplantation in a miniature swine model - Prashanth Vallabhajosyula; Adam Griesemer; Kazuhiko Yamada; David H. Sachs (Cell Biochemistry and Biophysics, 2007)

Effect of surfactants on plasticizer biodegradation by Bacillus subtilis ATCC 6633 - Adam R. Grochowalski; David G. Cooper; Jim A. Nicell (Biodegradation, 2007)

Recombinant protein production by large-scale transient gene expression in mammalian cells: state of the art and future perspectives - Lucia Baldi; David L. Hacker; Myriam Adam; Florian M. Wurm (Biotechnology Letters, 2007)

Investigating the Potential for Ongoing Pollution from an Abandoned Pyrite Mine - Russell Adams; David Ahlfeld; Ashmita Sengupta (Mine Water and the Environment, 2007)

Identification of the human liver UDP-glucuronosyltransferase involved in the metabolism of p-ethoxyphenylurea (dulcin) - Yoshihiro Uesawa; Adam G. Staines; David Lockley; Kiminori Mohri; Brian Burchell (Archives of Toxicology, 2007)

Product Quality Research Institute evaluation of cascade impactor profiles of pharmaceutical aerosols: Part 2—Evaluation of a method for determining equivalence - David Christopher; Wallace P. Adams; Douglas S. Lee; Beth Morgan; Ziqing Pan; Gur Jai Pal Singh; Yi Tsong; Svetlana Lyapustina (AAPS PharmSciTech, 2007)

Product Quality Research Institute evaluation of cascade impactor profiles of pharmaceutical aerosols, part 1: Background for a statistical method - Wallace P. Adams; David Christopher; Douglas S. Lee; Beth Morgan; Ziqing Pan; Gur Jai Pal Singh; Yi Tsong; Svetlana Lyapustina (AAPS PharmSciTech, 2007)

A test of Metabolic Theory as the mechanism underlying broad‐scale species‐richness gradients - Adam C. Algar; Jeremy T. Kerr; David J. Currie (Global Ecology and Biogeography, 2007)
Aim To test whether the temperature dependence of individuals’ metabolic rates is the mechanism shaping broad‐scale species‐richness gradients as proposed in the Metabolic Theory of Ecology recently proposed by Allen, Gillooly and Brown. Location North America, north of Mexico. Methods Metabolic Theory predicts that the natural logarithm of species richness will be a linear function of environmental temperature (( kT ) −1 , where k is Boltzmann's constant and T is temperature in K) with a slope of −0.78. We tested these predictions using the broad‐scale variation in richness of amphibians, reptiles, trees, tiger beetles, butterflies and blister beetles. We tested whether the temperature–richness relationship was linear or curvilinear, and determined the range of temperature values (and geographical area) where the instantaneous slope of the curvilinear temperature–richness relationship was statistically indistinguishable from −0.78, after correcting for spatial autocorrelation. Results We found that for all taxa, temperature–richness relationships were curvilinear. Moreover, for five of six taxa, the slope of this relationship was close to the predicted value for only a narrow range of temperatures. Blister beetles displayed the widest temperature range that is consistent with the Metabolic Theory, covering 45% of the study's geographical area. For the remaining taxa, the geographical range in which the slope is consistent with the predicted value amounts to only 10–20% of North America. Main conclusions For a wide array of taxa in North America, temperature–richness relationships deviate from the pattern predicted by Metabolic Theory. These results demonstrate that the temperature dependence of individuals’ metabolic rates is not the sole cause of broad‐scale diversity gradients. Even in areas where factors other than temperature do not influence productivity, the data do not suggest that richness patterns are determined by the temperature dependence of metabolic rate.

Determining biological tissue turnover using stable isotopes: the reaction progress variable - Thure E. Cerling; Linda K. Ayliffe; M. Denise Dearing; James R. Ehleringer; Benjamin H. Passey; David W. Podlesak; Ann-Marie Torregrossa; Adam G. West (Oecologia, 2007)

Head control strategies during whole-body turns - David Solomon; Vijay Kumar; R. Adam Jenkins; John Jewell (Experimental Brain Research, 2006)

Effects of dust deposition and river discharges on trace metal composition of Trichodesmium spp. in the tropical and subtropical North Atlantic Ocean - Antonio Tovar-Sanchez; Sergio A. Sañudo-Wilhelmy; Adam B. Kustka; Susana Agustí; Jordi Dachs; David A. Hutchins; Douglas G. Capone; Carlos M. Duarte (Limnology and Oceanography, 2006)
We present the elemental composition (Al, Cd, Co, Cu, Fe, Mn, Mo, Ni, V, Zn, and P) of field‐collected Trichodesmium populations. To distinguish the effects of river discharges (Amazon and Niger Rivers) and Saharan dust deposition on metal concentrations in the colonies, samples were collected both in the western (February 2001, July‐August 2001, and April‐May 2003) and eastern (May‐June 2003) basins of the North Atlantic. Metal composition (medians normalized to P) in Trichodesmium ranged from 0.011 mmol mol −1 for Co to 39 mmol mol −1 for Fe and varied over an order of magnitude among different locations. A comparison of metal ratios measured in the Trichodesmium colonies with ratios reported for the potential sources suggests that the most important sources of trace metals to the tropical and subtropical Atlantic during our sampling were the Amazon and Niger Rivers, rather than dust deposition from the Sahara.

Elicitation of Expert Judgments of Aerosol Forcing - M. Granger Morgan; Peter J. Adams; David W. Keith (Climatic Change, 2006)

Is alpha-Pinene a Substrate for Permeability-Glycoprotein in Wood Rats? - Adam K. Green; Shannon L. Haley; David M. Barnes; M. Denise Dearing; William H. Karasov (Journal of Chemical Ecology, 2006)

Microsatellite analysis of the phylogeography, Pleistocene history and secondary contact hypotheses for the killifish, Fundulus heteroclitus - STEPHANIE M. ADAMS; JAMES B. LINDMEIER; DAVID D. DUVERNELL (Molecular Ecology, 2006)
The mummichog, Fundulus heteroclitus , exhibits extensive latitudinal clinal variation in a number of physiological and biochemical traits, coupled with phylogeographical patterns at mitochondrial and nuclear DNA loci that suggest a complicated history of spatially variable selection and secondary intergradation. This species continues to serve as a model for understanding local and regional adaptation to variable environments. Resolving the influences of historical processes on the distribution of genetic variation within and among extant populations of F. heteroclitus is crucial to a better understanding of how populations evolve in the context of contemporary environments. In this study, we analysed geographical patterns of genetic variation at eight microsatellite loci among 15 populations of F. heteroclitus distributed throughout the North American range of the species from Nova Scotia to Georgia. Genetic variation in Northern populations was lower than in Southern populations and was strongly correlated with latitude throughout the species range. The most common Northern alleles at all eight loci exhibited concordant latitudinal clinal patterns, and the existence of an abrupt transition zone in allele frequencies between Northern and Southern populations was similar to that observed for mitochondrial DNA and allozyme loci. A significant pattern of isolation by distance was observed both within and between northern and southern regions. This pattern was unexpected, particularly for northern populations, given the recent colonization history of post‐Pleistocene habitats, and was inconsistent with either a recent northward population expansion or a geographically restricted northern Pleistocene refugium. The data provided no evidence for recent population bottlenecks, and estimates of historical effective population sizes suggest that post‐Pleistocene populations have been large throughout the species distribution. These results suggest that F. heteroclitus was broadly distributed throughout most of its current range during the last glacial event and that the abrupt transition in allele frequencies that separate Northern and Southern populations may reflect regional disequilibrium conditions associated with the post‐Pleistocene colonization history of habitats in that region.

The Effects of Small Dam Removal on the Distribution of Sedimentary Contaminants - Jeffrey T. F. Ashley; Karen Bushaw-Newton; Matt Wilhelm; Adam Boettner; Gregg Drames; David J. Velinsky (Environmental Monitoring and Assessment, 2006)

Incorporating patterns of disperser behaviour into models of seed dispersal and its effects on estimated dispersal curves - David A. Westcott; Joan Bentrupperbäumer; Matt G. Bradford; Adam McKeown (Oecologia, 2006)

The dual functions of sea urchin gonads are reflected in the temporal variations of their biochemistry - Adam D. Hughes; Maeve S. Kelly; David K. A. Barnes; Ana I. Catarino; Kenneth D. Black (Marine Biology, 2006)

Is Radix peregra a new intermediate host of Fascioloides magna (Trematoda) in Europe? Field and experimental evidence - Anna Faltýnková; Eva Horáčková; Lenka Hirtová; Adam Novobilský; David Modrý; Tomáš Scholz (Acta Parasitologica, 2006)
Rediae and immature cercariae of the giant liver fluke, Fascioloides magna, a pathogenic and important parasite of game animals, were found in 6 out of 7,277 Radix peregra (Gastropoda, Lymnaeidae) from two localities in Western and Central Bohemia, Czech Republic. In one of these localities a relatively high infection of Galba truncatula (26 out of 76) with mature cercariae of F. magna was detected. R. peregra, which is dominant over Galba truncatula, has never been reported as the natural intermediate host of F. magna. Its potential susceptibility to F. magna infection was confirmed experimentally with 67 snails of R. peregra (out of 371) infected. The present data indicate the capability of F. magna to expand the spectrum of its intermediate hosts and demonstrate the potential epizootiological importance of lymnaeid snails, other than G. truncatula, for transmission of the parasite in Europe.

A catalog of nonsynonymous polymorphism on mouse Chromosome 16 - Jeffrey M. Kidd; Karrie C. Trevarthen; David L. Tefft; Ze Cheng; Michaele Mooney; Mark D. Adams (Mammalian Genome, 2005)

Thermodynamic efficiencies of an idealized global climate model - David K. Adams; Nilton O. Rennó (Climate Dynamics, 2005)

Differential expression and extent of fungal/plant and fungal/bacterial chitinases of Aspergillus fumigatus - Mariam Taib; John W. Pinney; David R. Westhead; Kenneth J. McDowall; David J. Adams (Archives of Microbiology, 2005)

Flower proteome: changes in protein spectrum during the advanced stages of rose petal development - Mery Dafny-Yelin; Inna Guterman; Naama Menda; Mariana Ovadis; Moshe Shalit; Eran Pichersky; Dani Zamir; Efraim Lewinsohn; Zach Adam; David Weiss; Alexander Vainstein (Planta, 2005)

Maintenance of stimulus-secretion coupling and single beta-cell function in cryopreserved-thawed human islets of Langerhans - Stanley Misler; Adam Dickey; David W. Barnett (Pflügers Archiv - European Journal of Physiology, 2005)

Estimated Ultraviolet Radiation Doses in Wetlands in Six National Parks - Stephen A. Diamond; Peter C. Trenham; Michael J. Adams; Blake R. Hossack; Roland A. Knapp; Stacey L. Stark; David Bradford; P. Stephen Corn; Ken Czarnowski; Paul D. Brooks; Dan Fagre; Bob Breen; et al. (Ecosystems, 2005)

A new method to measure intestinal activity of P-glycoprotein in avian and mammalian species - Adam K. Green; David M. Barnes; William H. Karasov (Journal of Comparative Physiology B, 2005)

Apparent Selection Intensity for the Cytochrome Oxidase Subunit I Gene Varies with Mode of Reproduction in Echinoderms - David W. Foltz; Adam W. Hrincevich; Axayácatl Rocha-Olivares (Genetica, 2004)

Induced defences in an endangered amphibian in response to an introduced snake predator - Robin D. Moore; Richard A. Griffiths; Cliona M. O’Brien; Adam Murphy; David Jay (Oecologia, 2004)

Teleost Fish Genomes Contain a Diverse Array of L1 RetrotransposonLineages That Exhibit a Low Copy Number and High Rate of Turnover - David D. Duvernell; Shelley R. Pryor; Stephanie M. Adams (Journal of Molecular Evolution, 2004)

Low Levels of Nucleotide Diversity in Crocodylus moreletii and Evidence of Hybridization with C. acutus - David A. Ray; Jennifer A. Dever; Steven G. Platt; Thomas R. Rainwater; Adam G. Finger; Scott T. McMurry; Mark A. Batzer; Brady Barr; Peter J. Stafford; Jenna McKnight; Llewellyn D. Densmore (Conservation Genetics, 2004)

Effects of Silvicultural Practices on Soil Carbon and Nitrogen in a Nitrogen Saturated Central Appalachian (USA) Hardwood Forest Ecosystem - Frank S. Gilliam; David A. Dick; Michelle L. Kerr; Mary Beth Adams (Environmental Management, 2004)

Human BAC-mediated rescue of the Friedreich ataxia knockout mutation in transgenic mice - Joseph P. Sarsero; Lingli Li; Timothy P. Holloway; Lucille Voullaire; Sophie Gazeas; Kerry J. Fowler; Denise M. Kirby; David R. Thorburn; Adam Galle; Surindar Cheema; Michel Koenig; Robert Williamson; et al. (Mammalian Genome, 2004)

Genes controlling seed dormancy and pre-harvest sprouting in a rice-wheat-barley comparison - Chengdao Li; Peixiang Ni; Michael Francki; Adam Hunter; Yong Zhang; David Schibeci; Heng Li; Allen Tarr; Jun Wang; Mehmet Cakir; Jun Yu; Matthew Bellgard; et al. (Functional & Integrative Genomics, 2004)

Reciptrocal regulation of beta-adrenergic receptor mRNA stability by mitogen activated protein kinase activation and inhibition - Violetta V. Headley; Rasheeda Tanveer; Scott M. Greene; Adam Zweifach; J. David Port (Molecular and Cellular Biochemistry, 2004)

The re-stocking of captive-bred ruffed lemurs (Varecia variegata variegata) into the Betampona Reserve, Madagascar: methodology and recommendations - Adam Britt; Charles Welch; Andrea Katz; Bernard Iambana; Ingrid Porton; Randall Junge; Graham Crawford; Cathy Williams; David Haring (Biodiversity and Conservation, 2004)

Late Pleistocene Vegetation and Climate in the Southern Cascade Range and the Modoc Plateau Region - Katharine J. Hakala; David P. Adam (Journal of Paleolimnology, 2004)

Record of Late Pleistocene Glaciation and Deglaciation in the Southern Cascade Range. I. Petrological Evidence from Lacustrine Sediment in Upper Klamath Lake, Southern Oregon - Richard L. Reynolds; Joseph G. Rosenbaum; Josh Rapp; Michael W. Kerwin; J. Platt Bradbury; Steven Colman; David Adam (Journal of Paleolimnology, 2004)

An evaluation of the role played by remote sensing technology following the World Trade Center attack - Charles K. Huyck; Beverley J. Adams; David I. Kehrlein (Earthquake Engineering and Engineering Vibration, 2003)

Distribution and abundance of the Louisiana red swamp crayfish Procambarus clarkii Girard at Lake Naivasha, Kenya between 1987 and 1999 - David M. Harper; Andrew C. Smart; Stephanie Coley; Sophie Schmitz; Anne-Christine Gouder de Beauregard; Rick North; Chris Adams; Paul Obade; Mbogo Kamau (Hydrobiologia, 2002)

Differential selection of baculovirus genotypes mediated by different species of host food plant - David J. Hodgson; Adam J. Vanbergen; Susan E. Hartley; Rosie S. Hails; Jenny S. Cory (Ecology Letters, 2002)
Recent studies have demonstrated high levels of genotypic and phenotypic variation in populations of parasites, even within individual hosts. Several genetic, immunological and epidemiological mechanisms have been postulated as promoters of such variation, but little empirical work has addressed the role of host ecology. A nucleopolyhedrovirus that attacks larvae of the pine beauty moth, Panolis flammea , exists as a complex mixture of genotypes within individual host larvae. We demonstrate that the food plant species eaten by the host (Scots pine vs. lodgepole pine) differentially affects the pathogenicity and productivity of two virus genotypes originally purified from a single host individual. We hypothesize that such food plant‐mediated differential selection will promote genotypic variation between baculovirus populations, and that subsequent remixing of virus genotypes could maintain genotypic variation within individual hosts. Our results provide a tritrophic explanation for the genotypic and phenotypic complexity of host–parasite interactions with complex ecologies.

Association of a functional inducible nitric oxide synthase promoter variant with complications in type 2 diabetes - Brian J. Morris; Andrea M. Markus; Cheryl L. Glenn; David J. Adams; S. Colagiuri; Xing Wang (Journal of Molecular Medicine, 2002)

Invasions on Large and Small Scales: Management of a Well-established Crop Pest, the Colorado Potato Beetle - Mitchell B. Baker; David N. Ferro; Adam H. Porter (Biological Invasions, 2001)

Gene structure, alternative splicing, and chromosomal localization of pro-apoptotic Bcl-2 relative Bim - Philippe Bouillet; Li Chen Zhang; David C.S. Huang; Graham C. Webb; Cynthia D.K. Bottema; Paul Shore; Helen J. Eyre; Grant R. Sutherland; Jerry M. Adams (Mammalian Genome, 2001)

Variation in isomeric products of a phosphodiesterase from the chloroplasts of Phaseolus vulgaris in response to cations - Penny E. Diffley; Alan Geisbrecht; Russell P. Newton; Michael Oliver; Christopher J. Smith; Judith Vaughan; Jan van Cleef; Jan van Geyschem; Terence J. Walton; Mark Bayliss; A. Gareth Brenton; Frank M. Harris; et al. (Plant Biosystems, 2001)

The effect of illusory size on force production when grasping objects - David A. Westwood; Adam Dubrowski; Heather Carnahan; Eric A. Roy (Experimental Brain Research, 2000)

Pharmacological characterisation of the P2Y11 receptor in stably transfected haematological cell lines - Louise van der Weyden; David J. Adams; Brian M. Luttrell; Arthur D. Conigrave; Michael B. Morris (Molecular and Cellular Biochemistry, 2000)

Seasonal soil‐surface carbon fluxes from the root systems of young Pinus radiata trees growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; Freeman J. Cook; David Whitehead; John A. Adams (Global Change Biology, 2000)
Summary Elevated atmospheric CO 2 concentration may result in increased below‐ground carbon allocation by trees, thereby altering soil carbon cycling. Seasonal estimates of soil surface carbon flux were made to determine whether carbon losses from Pinus radiata trees growing at elevated CO 2 concentration were higher than those at ambient CO 2 concentration, and whether this was related to increased fine root growth. Monthly soil surface carbon flux density ( f ) measurements were made on plots with trees growing at ambient (350) and elevated (650 μmol mol −1 ) CO 2 concentration in large open‐top chambers. Prior to planting the soil carbon concentration (0.1%) and f (0.28 μmol m −2 s −1 at 15 °C) were low. A function describing the radial pattern of f with distance from tree stems was used to estimate the annual carbon flux from tree plots. Seasonal estimates of fine root production were made from minirhizotrons and the radial distribution of roots compared with radial measurements of f . A one‐dimensional gas diffusion model was used to estimate f from soil CO 2 concentrations at four depths. For the second year of growth, the annual carbon flux from the plots was 1671 g y −1 and 1895 g y −1 at ambient and elevated CO 2 concentrations, respectively, although this was not a significant difference. Higher f at elevated CO 2 concentration was largely explained by increased fine root biomass. Fine root biomass and stem production were both positively related to f. Both root length density and f declined exponentially with distance from the stem, and had similar length scales. Diurnal changes in f were largely explained by changes in soil temperature at a depth of 0.05 m. Ignoring the change of f with increasing distance from tree stems when scaling to a unit ground area basis from measurements with individual trees could result in under‐ or overestimates of soil‐surface carbon fluxes, especially in young stands when fine roots are unevenly distributed.

Renal effects of cyclooxygenase inhibitors in volume-depleted dogs - David P. Brooks; Jerry Adams; P. Dennis DePalma; Edward F. Webb; Robert H. Palmer; Don E. Griswold (Inflammopharmacology, 2000)

A deletion on Chromosome 4 cosegregates with the whirler deafness mutation: exclusion of Orm1 as a candidate - Adam J.W. Paige; Brent W. Kiernan; Anabel Varela; Michael J.C. Rogers; David Hughes; Karen P. Steel; Steve D.M. Brown (Mammalian Genome, 2000)

A 500-kb region on chromosome 16p13.1 contains the pseudoxanthoma elasticum locus: high-resolution mapping and genomic structure - Li Cai; Berthold Struk; Mark D. Adams; Wan Ji; Thomas Haaf; Hyung-Lyun Kang; So Hee Dho; Xuequn Xu; Franziska Ringpfeil; Julie Nancarrow; Stéphanie Zäch; Lori Schaen; et al. (Journal of Molecular Medicine, 2000)

Threatened Fishes of the World: Carcharias taurus (Rafinesque, 1810) (Odontaspididae) - Adam K. Smith; David A. Pollard (Environmental Biology of Fishes, 1999)

Growth, loss, and vertical distribution of Pinus radiata fine roots growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; David Whitehead; JefF. B. Reid; Freeman J. Cook; JohN. A. Adams; AlaN. C. Leckie (Global Change Biology, 1999)
Increased below‐ground carbon allocation in forest ecosystems is a likely consequence of rising atmospheric CO 2 concentration. If this results in changes to fine root growth, turnover and distribution long‐term soil carbon cycling and storage could be altered. Bi‐weekly measurements were made to determine the dynamics and distribution of fine roots ( Pinus radiata trees growing at ambient (350 μmol mol –1 ) and elevated (650 μmol mol –1 ) CO 2 concentration in large open‐top chambers. Measurements were made using minirhizotrons installed horizontally at depths of 0.1, 0.3, 0.5 and 0.9 m. During the first year, at a depth of 0.3 m, the increase in relative growth rate of roots occurred 6 weeks earlier in the elevated CO 2 treatment and the maximum rate was reached 10 weeks earlier than for trees in the ambient treatment. After 2 years, cumulative fine root growth ( P t ) was 36% greater for trees growing at elevated CO 2 than at ambient CO 2 concentration, although this difference was not significant. A model of root growth driven by daily soil temperature accounted for between 43 and 99% of root growth variability. Total root loss ( L t ) was 9% in the ambient and 14% in the elevated CO 2 treatment, although this difference was not significant. Root loss was greatest at 0.3 m. In the first year, 62% of fine roots grown between mid‐summer and late‐autumn disappeared within a year in the elevated CO 2 treatment, but only 18% in the ambient CO 2 treatment ( P L t to time accounted for between 74 and 99% of the variability. Root cohort half‐lives were 951 d for the ambient and 333 d for the elevated treatment. Root length density decreased exponentially with depth in both treatments, but relatively more fine roots grown in the elevated CO 2 treatment tended to occur deeper in the soil profile.

Spatial and temporal variations in phloem sap composition of plantation-grown Eucalyptus globulus - John Pate; Erica Shedley; David Arthur; Mark Adams (Oecologia, 1998)

The Value of Improved ENSO Prediction to U.S. Agriculture - Andrew R. Solow; Richard F. Adams; Kelly J. Bryant; David M. Legler; James J. O'Brien; Bruce A. McCarl; William Nayda; Rodney Weiher (Climatic Change, 1998)

Habitat and Avifaunal Recovery from Livestock Grazing in a Riparian Meadow System of the Northwestern Great Basin - David S. Dobkin; Adam C. Rich; William H. Pyle (Conservation Biology, 1998)

Habitat and Avifaunal Recovery from Livestock Grazing in a Riparian Meadow System of the Northwestern Great Basin - David S. Dobkin; Adam C. Rich; William H. Pyle (Conservation Biology, 1998)
Riparian habitats are centers of biological diversity in arid and semiarid portions of western North America, but despite widespread loss and degradation of these habitats there is little quantitative information concerning restoration of native riparian biota. We examined the recovery of a riparian meadow system in the context of long‐term versus short‐term release from livestock grazing. We compared the structure and dynamics of plant and avian communities on 1.5‐ha plots inside a long‐term (>30 years) livestock exclosure (“exclosure plots”), with adjacent plots outside the exclosure (“open plots”) for 4 years following removal of livestock from open plots. Throughout the study, sedge cover, forb cover, and foliage height diversity of herbs were greater on exclosure plots; bare ground, litter cover, shrub cover, and shrub foliage height diversity were greater on open plots. Forb, rush, and cryptogamic cover increased on open plots but not on exclosure plots. Grass cover increased, whereas litter and bare ground decreased on all plots in conjunction with increased availability of moisture. Sedge cover did not change. Avian species richness and relative abundances were greater on exclosure plots; species composition differed markedly between exclosure and open plots ( Jaccard Coefficient = 0.23–0.46), with exclosure plots dominated by wetland and riparian birds and open plots dominated by upland species. The appearance of key species of wet‐meadow birds on open plots in the third and fourth years following livestock removal signaled the beginning of restoration of the riparian avifauna. We interpret the recovery of riparian vegetation and avifaunal composition inside the exclosure as a consequence of livestock removal, which led to a rise in the water table and an expansion of the hyporheic zone laterally from the stream channel. The lack of change in sedge and shrub cover on open plots suggests that restoration to a sedge‐dominated meadow will not happen quickly. Hábitat y Recuperación de la Avifauna de Actividades de Pastoreo en un Sistema de Pradera Riparia en el Noroeste de Great Basin Los hábitats riparios son centros de diversidad ecológica en porciones áridas y semiáridas del Oeste de Norte América, sin embargo, a pesar de la ampia pérdida y degradación de estos hábitats, existe muy poca información cuantitativa referente al restablecimiento de la biota riparia nativa. Examinamos la recuperación de un sistema de pradera riperia en el contexto de su liberación de actividades de pastoreo a largo plazo contra uno a corto plazo. Comparamos la estructura y dinámica de comunidades de plantas y aves en lotes de 1.5 ha. dentro de una zona exluyente de ganado por largo plazo (30 años) “lotes excluyentes” con lotes adyacentes fuera de la zona de exclusión “lotes abiertos” durante cuatro años después de que el ganado fuera removido de los lotes abiertos. A lo largo del estudio, la cobertura de ciperáceas, cobertura de hierbas forrajeras (diferentes a pasto) y la diversidad de la altura del follage de las hierbas fue mayor en los lotes excluyentes; suelo descubierto, cobertura de hojarasca, cobertura arbustiva y diversidad de la altura de arbustos fue mayor en los lotes abiertos. La cobertura de hierbas diferentes al pasto, juncáceas y criptógamas incrementó en los lotes abiertos, pero no en los lotes excluyentes. La cobertura de pasto incrementó, mientras que la hojaraca y suelo descubierto disminuyó en todos los lotes en conjunctión con el incremento en la disponibilidad de humedad. La cobertura de ciperáceas no cambió. La riqueza y abundancia relativa de especies de aves fue mayor en lotes excluyentes; la composición de especies difirió marcadamente entre lotes excluyentes y abiertos (coeficiente Jaccard = 0.23–0.46), con lotes excluyentes dominados por especies de tierras altas. La aparición de especies clave de aves de praderas húmedas en el tercero y cuarto año posteriores a la remoción de ganado señala el inicio de la restauración y avifauna riparina. Nosotros interpretamos la recuperación de la composición de vegetación y avifauna riparina dentro de las zonas de exclusión como una consecuencia de la remoción del ganado, lo cual conduce a un incremento en el manto acuífero y una expansión de la zona hiporréica lateral al canal del arroyo. La carencia de cambios en la cobertura de ciperáceas y arbustos en lotes abiertos sugiere que la restauración de una pradera dominada por ciperáceas no sucederá rápidamente.

Impacts of ocean CO2 disposal on marine life: II. Probabilistic plume exposure model used with a time‐varying dose‐response analysis - Jennifer A. Caulfield; E. Eric Adams; David I. Auerbach; Howard J. Herzog (Environmental Modeling & Assessment, 1997)

Impacts of ocean CO2 disposal on marine life: I. A toxicological assessment integrating constant‐concentration laboratory assay data with variable‐concentration field exposure - David I. Auerbach; Jennifer A. Caulfield; E. Eric Adams; Howard J. Herzog (Environmental Modeling & Assessment, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Growth and phage resistance of Anabaena sp. strain PCC 7120 in the presence of cyanophage AN-15 - Richard Mole; David Meredith; David G. Adams (Journal of Applied Phycology, 1997)

Nitrogen regulation in fungi - Mark X. Caddick; David Peters; Adam Platt (Antonie van Leeuwenhoek, 1994)

Natural etching rates of feldspar and hornblende - Susan L. Brantley; Adam C. Blai; David L. Cremeens; Ian MacInnis; Robert G. Darmody (Aquatic Sciences, 1993)

Artificial neural network classification of Drosophila courtship song mutants - Eric K. Neumann; David A. Wheeler; Adam S. Bernstein; Jamie W. Burnside; Jeffrey C. Hall (Biological Cybernetics, 1992)

Promoter function and in situ protein/DNA interactions upstream of the yeast HSP90 heat shock genes - David S. Gross; Christopher C. Adams; Karen E. English; Kerry W. Collins; Seewoo Lee (Antonie van Leeuwenhoek, 1990)

Polychlorinated biphenyls and organochlorine pesticides in milk and blood of Canadian women during lactation - Jos Mes; John A. Doyle; Barrett R. Adams; David J. Davies; Davida Turton (Archives of Environmental Contamination and Toxicology, 1984)

An improved method for water vapor detection - Thomas Adams; Michael A. Steinmetz; David B. Manner; Duane M. Baldwin; S. Richard Heisey (Annals of Biomedical Engineering, 1983)

Effect of canavanine and other amino acid analogues on akinete formation in the cyanobacterium Anabaena cylindrica - Josie M. Nichols; David G. Adams; Noel G. Carr (Archives of Microbiology, 1980)